Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Boerwinkle, Eric; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.

Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

Association of Genetic Variation With Cirrhosis: A Multi-Trait Genome-Wide Association and Gene-Environment Interaction Study. - Emdin, Connor A; Haas, Mary; Ajmera, Veeral; Simon, Tracey G; Homburger, Julian; Neben, Cynthia; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Zhou, Alicia; Denny, Joshua; Corey, Kathleen; et al. (Gastroenterology, 2021)
BACKGROUND & AIMS: In contrast to most other common diseases, few genetic variants have been identified that impact risk of cirrhosis. We aimed to identify new genetic variants that predispose to cirrhosis, to test whether such variants, aggregated into a polygenic score, enable genomic risk stratification, and to test whether alcohol intake or body mass index interacts with polygenic predisposition. METHODS: We conducted a multi-trait genome-wide association study combining cirrhosis and alanine aminotransferase levels performed in 5 discovery studies (UK Biobank, Vanderbilt BioVU, Atherosclerosis Risk in Communities study, and 2 case-control studies including 4829 individuals with cirrhosis and 72,705 controls and 362,539 individuals with alanine aminotransferase levels). Identified variants were replicated in 3 studies (Partners HealthCare Biobank, FinnGen, and Biobank Japan including 3554 individuals with cirrhosis and 343,826 controls). A polygenic score was tested in Partners HealthCare Biobank. RESULTS: Five previously reported and 7 newly identified genetic variants were associated with cirrhosis in both the discovery studies multi-trait genome-wide association study (P < 5 × 10) and the replication studies (P < .05), including a missense variant in the APOE gene and a noncoding variant near EFN1A. These 12 variants were used to generate a polygenic score. Among Partners HealthCare Biobank individuals, high polygenic score-defined as the top quintile of the distribution-was associated with significantly increased risk of cirrhosis (odds ratio, 2.26; P < .001) and related comorbidities compared with the lowest quintile. Risk was even more pronounced among those with extreme polygenic risk (top 1% of the distribution, odds ratio, 3.16; P < .001). The impact of extreme polygenic risk was substantially more pronounced in those with elevated alcohol consumption or body mass index. Modeled as risk by age 75 years, probability of cirrhosis with extreme polygenic risk was 13.7%, 20.1%, and 48.2% among individuals with no or modest, moderate, and increased alcohol consumption, respectively (P < .001). Similarly, probability among those with extreme polygenic risk was 6.5%, 10.3%, and 19.5% among individuals with normal weight, overweight, and obesity, respectively (P < .001). CONCLUSIONS: Twelve independent genetic variants, 7 of which are newly identified in this study, conferred risk for cirrhosis. Aggregated into a polygenic score, these variants identified a subset of the population at substantially increased risk who are most susceptible to the hepatotoxic effects of excess alcohol consumption or obesity.

Association of structural variation with cardiometabolic traits in Finns. - Chen, Lei; Abel, Haley J; Das, Indraniel; Larson, David E; Ganel, Liron; Kanchi, Krishna L; Regier, Allison A; Young, Erica P; Kang, Chul Joo; Scott, Alexandra J; Chiang, Colby; Wang, Xinxin; et al. (Am J Hum Genet, 2021)
The contribution of genome structural variation (SV) to quantitative traits associated with cardiometabolic diseases remains largely unknown. Here, we present the results of a study examining genetic association between SVs and cardiometabolic traits in the Finnish population. We used sensitive methods to identify and genotype 129,166 high-confidence SVs from deep whole-genome sequencing (WGS) data of 4,848 individuals. We tested the 64,572 common and low-frequency SVs for association with 116 quantitative traits and tested candidate associations using exome sequencing and array genotype data from an additional 15,205 individuals. We discovered 31 genome-wide significant associations at 15 loci, including 2 loci at which SVs have strong phenotypic effects: (1) a deletion of the ALB promoter that is greatly enriched in the Finnish population and causes decreased serum albumin level in carriers (p = 1.47 × 10) and is also associated with increased levels of total cholesterol (p = 1.22 × 10) and 14 additional cholesterol-related traits, and (2) a multi-allelic copy number variant (CNV) at PDPR that is strongly associated with pyruvate (p = 4.81 × 10) and alanine (p = 6.14 × 10) levels and resides within a structurally complex genomic region that has accumulated many rearrangements over evolutionary time. We also confirmed six previously reported associations, including five led by stronger signals in single nucleotide variants (SNVs) and one linking recurrent HP gene deletion and cholesterol levels (p = 6.24 × 10), which was also found to be strongly associated with increased glycoprotein level (p = 3.53 × 10). Our study confirms that integrating SVs in trait-mapping studies will expand our knowledge of genetic factors underlying disease risk.
Keywords: Alleles; Cardiovascular Diseases; Cholesterol; DNA Copy Number Variations; Female; Finland; Genome, Human; Genomic Structural Variation; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Promoter Regions, Genetic; Pyruvate Dehydrogenase (Lipoamide)-Phosphatase; Pyruvic Acid; Serum Albumin, Human

Biallelic variants in HPDL, encoding 4-hydroxyphenylpyruvate dioxygenase-like protein, lead to an infantile neurodegenerative condition. - Ghosh, Shereen G; Lee, Sangmoon; Fabunan, Rudy; Chai, Guoliang; Zaki, MAH S; Abdel-Salam, Ghada; Sultan, Tipu; Ben-Omran, Tawfeg; Alvi, Javeria Raza; McEvoy-Venneri, Jennifer; Stanley, Valentina; Patel, Aakash; et al. (Genet Med, 2021)
PURPOSE: Dioxygenases are oxidoreductase enzymes with roles in metabolic pathways necessary for aerobic life. 4-hydroxyphenylpyruvate dioxygenase-like protein (HPDL), encoded by HPDL, is an orphan paralogue of 4-hydroxyphenylpyruvate dioxygenase (HPD), an iron-dependent dioxygenase involved in tyrosine catabolism. The function and association of HPDL with human diseases remain unknown. METHODS: We applied exome sequencing in a cohort of over 10,000 individuals with neurodevelopmental diseases. Effects of HPDL loss were investigated in vitro and in vivo, and through mass spectrometry analysis. Evolutionary analysis was performed to investigate the potential functional separation of HPDL from HPD. RESULTS: We identified biallelic variants in HPDL in eight families displaying recessive inheritance. Knockout mice closely phenocopied humans and showed evidence of apoptosis in multiple cellular lineages within the cerebral cortex. HPDL is a single-exonic gene that likely arose from a retrotransposition event at the base of the tetrapod lineage, and unlike HPD, HPDL is mitochondria-localized. Metabolic profiling of HPDL mutant cells and mice showed no evidence of altered tyrosine metabolites, but rather notable accumulations in other metabolic pathways. CONCLUSION: The mitochondrial localization, along with its disrupted metabolic profile, suggests HPDL loss in humans links to a unique neurometabolic mitochondrial infantile neurodegenerative condition.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Animals; Dioxygenases; Exons; Mice; Mice, Knockout; Phenotype

Constrained chromatin accessibility in PU.1-mutated agammaglobulinemia patients. - Le Coz, Carole; Nguyen, David N; Su, Chun; Nolan, Brian E; Albrecht, Amanda V; Xhani, Suela; Sun, Di; Demaree, Benjamin; Pillarisetti, Piyush; Khanna, Caroline; Wright, Francis; Chen, Peixin Amy; et al. (J Exp Med, 2021)
The pioneer transcription factor (TF) PU.1 controls hematopoietic cell fate by decompacting stem cell heterochromatin and allowing nonpioneer TFs to enter otherwise inaccessible genomic sites. PU.1 deficiency fatally arrests lymphopoiesis and myelopoiesis in mice, but human congenital PU.1 disorders have not previously been described. We studied six unrelated agammaglobulinemic patients, each harboring a heterozygous mutation (four de novo, two unphased) of SPI1, the gene encoding PU.1. Affected patients lacked circulating B cells and possessed few conventional dendritic cells. Introducing disease-similar SPI1 mutations into human hematopoietic stem and progenitor cells impaired early in vitro B cell and myeloid cell differentiation. Patient SPI1 mutations encoded destabilized PU.1 proteins unable to nuclear localize or bind target DNA. In PU.1-haploinsufficient pro-B cell lines, euchromatin was less accessible to nonpioneer TFs critical for B cell development, and gene expression patterns associated with the pro- to pre-B cell transition were undermined. Our findings molecularly describe a novel form of agammaglobulinemia and underscore PU.1's critical, dose-dependent role as a hematopoietic euchromatin gatekeeper.

CSNK2B: A broad spectrum of neurodevelopmental disability and epilepsy severity. - Ernst, Michelle E; Baugh, Evan H; Thomas, Amanda; Bier, Louise; Lippa, Natalie; Stong, Nicholas; Mulhern, Maureen S; Kushary, Sulagna; Akman, Cigdem I; Heinzen, Erin L; Yeh, Raymond; Bi, Weimin; et al. (Epilepsia, 2021)
CSNK2B has recently been implicated as a disease gene for neurodevelopmental disability (NDD) and epilepsy. Information about developmental outcomes has been limited by the young age and short follow-up for many of the previously reported cases, and further delineation of the spectrum of associated phenotypes is needed. We present 25 new patients with variants in CSNK2B and refine the associated NDD and epilepsy phenotypes. CSNK2B variants were identified by research or clinical exome sequencing, and investigators from different centers were connected via GeneMatcher. Most individuals had developmental delay and generalized epilepsy with onset in the first 2 years. However, we found a broad spectrum of phenotypic severity, ranging from early normal development with pharmacoresponsive seizures to profound intellectual disability with intractable epilepsy and recurrent refractory status epilepticus. These findings suggest that CSNK2B should be considered in the diagnostic evaluation of patients with a broad range of NDD with treatable or intractable seizures.

De novo TRIM8 variants impair its protein localization to nuclear bodies and cause developmental delay, epilepsy, and focal segmental glomerulosclerosis. - Weng, Patricia L; Majmundar, Amar J; Khan, Kamal; Lim, Tze Y; Shril, Shirlee; Jin, Gina; Musgrove, John; Wang, Minxian; Ahram, Dina F; Aggarwal, Vimla S; Bier, Louise E; Heinzen, Erin L; et al. (Am J Hum Genet, 2021)
Focal segmental glomerulosclerosis (FSGS) is the main pathology underlying steroid-resistant nephrotic syndrome (SRNS) and a leading cause of chronic kidney disease. Monogenic forms of pediatric SRNS are predominantly caused by recessive mutations, while the contribution of de novo variants (DNVs) to this trait is poorly understood. Using exome sequencing (ES) in a proband with FSGS/SRNS, developmental delay, and epilepsy, we discovered a nonsense DNV in TRIM8, which encodes the E3 ubiquitin ligase tripartite motif containing 8. To establish whether TRIM8 variants represent a cause of FSGS, we aggregated exome/genome-sequencing data for 2,501 pediatric FSGS/SRNS-affected individuals and 48,556 control subjects, detecting eight heterozygous TRIM8 truncating variants in affected subjects but none in control subjects (p = 3.28 × 10). In all six cases with available parental DNA, we demonstrated de novo inheritance (p = 2.21 × 10). Reverse phenotyping revealed neurodevelopmental disease in all eight families. We next analyzed ES from 9,067 individuals with epilepsy, yielding three additional families with truncating TRIM8 variants. Clinical review revealed FSGS in all. All TRIM8 variants cause protein truncation clustering within the last exon between residues 390 and 487 of the 551 amino acid protein, indicating a correlation between this syndrome and loss of the TRIM8 C-terminal region. Wild-type TRIM8 overexpressed in immortalized human podocytes and neuronal cells localized to nuclear bodies, while constructs harboring patient-specific variants mislocalized diffusely to the nucleoplasm. Co-localization studies demonstrated that Gemini and Cajal bodies frequently abut a TRIM8 nuclear body. Truncating TRIM8 DNVs cause a neuro-renal syndrome via aberrant TRIM8 localization, implicating nuclear bodies in FSGS and developmental brain disease.
Keywords: Adult; Animals; Carrier Proteins; Cell Line; Child; Child, Preschool; Codon, Nonsense; Developmental Disabilities; Epilepsy; Female; Glomerulosclerosis, Focal Segmental; Humans; Intranuclear Space; Kidney; Male; Mice; Mutation; Nephrotic Syndrome; Nerve Tissue Proteins; Phenotype; Podocytes; Whole Exome Sequencing

De novo variants in SNAP25 cause an early-onset developmental and epileptic encephalopathy. - Klöckner, Chiara; Sticht, Heinrich; Zacher, Pia; Popp, Bernt; Babcock, Holly E; Bakker, Dewi P; Barwick, Katy; Bonfert, Michaela V; Bönnemann, Carsten G; Brilstra, Eva H; Chung, Wendy K; Clarke, Angus J; et al. (Genet Med, 2021)
PURPOSE: This study aims to provide a comprehensive description of the phenotypic and genotypic spectrum of SNAP25 developmental and epileptic encephalopathy (SNAP25-DEE) by reviewing newly identified and previously reported individuals. METHODS: Individuals harboring heterozygous missense or loss-of-function variants in SNAP25 were assembled through collaboration with international colleagues, matchmaking platforms, and literature review. For each individual, detailed phenotyping, classification, and structural modeling of the identified variant were performed. RESULTS: The cohort comprises 23 individuals with pathogenic or likely pathogenic de novo variants in SNAP25. Intellectual disability and early-onset epilepsy were identified as the core symptoms of SNAP25-DEE, with recurrent findings of movement disorders, cerebral visual impairment, and brain atrophy. Structural modeling for all variants predicted possible functional defects concerning SNAP25 or impaired interaction with other components of the SNARE complex. CONCLUSION: We provide a comprehensive description of SNAP25-DEE with intellectual disability and early-onset epilepsy mostly occurring before the age of two years. These core symptoms and additional recurrent phenotypes show an overlap to genes encoding other components or associated proteins of the SNARE complex such as STX1B, STXBP1, or VAMP2. Thus, these findings advance the concept of a group of neurodevelopmental disorders that may be termed "SNAREopathies."
Keywords: Brain Diseases; Child, Preschool; Epilepsy; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype; Synaptosomal-Associated Protein 25

De novo variants in TCF7L2 are associated with a syndromic neurodevelopmental disorder. - Dias, Caroline; Pfundt, Rolph; Kleefstra, Tjitske; Shuurs-Hoeijmakers, Janneke; Boon, Elles M J; van Hagen, Johanna M; Zwijnenburg, Petra; Weiss, Marjan M; Keren, Boris; Mignot, Cyril; Isapof, Arnaud; Weiss, Karin; et al. (Am J Med Genet A, 2021)
TCF7L2 encodes transcription factor 7-like 2 (OMIM 602228), a key mediator of the evolutionary conserved canonical Wnt signaling pathway. Although several large-scale sequencing studies have implicated TCF7L2 in intellectual disability and autism, both the genetic mechanism and clinical phenotype have remained incompletely characterized. We present here a comprehensive genetic and phenotypic description of 11 individuals who have been identified to carry de novo variants in TCF7L2, both truncating and missense. Missense variation is clustered in or near a high mobility group box domain, involving this region in these variants' pathogenicity. All affected individuals present with developmental delays in childhood, but most ultimately achieved normal intelligence or had only mild intellectual disability. Myopia was present in approximately half of the individuals, and some individuals also possessed dysmorphic craniofacial features, orthopedic abnormalities, or neuropsychiatric comorbidities including autism and attention-deficit/hyperactivity disorder (ADHD). We thus present an initial clinical and genotypic spectrum associated with variation in TCF7L2, which will be important in informing both medical management and future research.

Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.

DLG4-related synaptopathy: a new rare brain disorder. - Rodríguez-Palmero, Agustí; Boerrigter, Melissa Maria; Gómez-Andrés, David; Aldinger, Kimberly A; Marcos-Alcalde, Íñigo; Popp, Bernt; Everman, David B; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genet Med, 2021)
PURPOSE: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. METHODS: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. RESULTS: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit-hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. CONCLUSION: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy.
Keywords: Autism Spectrum Disorder; Brain; Brain Diseases; Disks Large Homolog 4 Protein; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype

A DNA repair disorder caused by de novo monoallelic DDB1 variants is associated with a neurodevelopmental syndrome. - White, Susan M; Bhoj, Elizabeth; Nellaker, Christoffer; Lachmeijer, Augusta M A; Marshall, Aren E; Boycott, Kym M; Li, Dong; Smith, Wendy; Hartley, Taila; McBride, Arran; Ernst, Michelle E; May, Alison S; et al. (Am J Hum Genet, 2021)
The DNA damage-binding protein 1 (DDB1) is part of the CUL4-DDB1 ubiquitin E3 ligase complex (CRL4), which is essential for DNA repair, chromatin remodeling, DNA replication, and signal transduction. Loss-of-function variants in genes encoding the complex components CUL4 and PHIP have been reported to cause syndromic intellectual disability with hypotonia and obesity, but no phenotype has been reported in association with DDB1 variants. Here, we report eight unrelated individuals, identified through Matchmaker Exchange, with de novo monoallelic variants in DDB1, including one recurrent variant in four individuals. The affected individuals have a consistent phenotype of hypotonia, mild to moderate intellectual disability, and similar facies, including horizontal or slightly bowed eyebrows, deep-set eyes, full cheeks, a short nose, and large, fleshy and forward-facing earlobes, demonstrated in the composite face generated from the cohort. Digital anomalies, including brachydactyly and syndactyly, were common. Three older individuals have obesity. We show that cells derived from affected individuals have altered DDB1 function resulting in abnormal DNA damage signatures and histone methylation following UV-induced DNA damage. Overall, our study adds to the growing family of neurodevelopmental phenotypes mediated by disruption of the CRL4 ubiquitin ligase pathway and begins to delineate the phenotypic and molecular effects of DDB1 misregulation.
Keywords: Adolescent; Alleles; Child; Child, Preschool; DNA Repair; DNA-Binding Proteins; Female; Humans; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Syndrome

Dominant variants in PRR12 result in unilateral or bilateral complex microphthalmia. - Reis, Linda M; Costakos, Deborah; Wheeler, Patricia G; Bardakjian, Tanya; Schneider, Adele; Fung, Simon S M; Semina, Elena V (Clin Genet, 2021)
Complex microphthalmia is characterized by small eyes with additional abnormalities that may include anterior segment dysgenesis. While many genes are known, a genetic cause is identified in only 4-30% of microphthalmia, with the lowest rate in unilateral cases. We identified four novel pathogenic loss-of-function alleles in PRR12 in families affected by complex microphthalmia and/or Peters anomaly, including two de novo, the first dominantly transmitted allele, as well as the first splicing variant. The ocular phenotypes were isolated with no additional systemic features observed in two unrelated families. Remarkably, ocular phenotypes were asymmetric in all individuals and unilateral (with structurally normal contralateral eye) in three. There are only three previously reported PRR12 variants identified in probands with intellectual disability, neuropsychiatric disorders, and iris anomalies. While some overlap with previously reported cases is seen, nonsyndromic developmental ocular anomalies are a novel phenotype for this gene. Additional phenotypic expansions included short stature and normal development/cognition, each noted in two individuals in this cohort, as well as absence of neuropsychiatric disorders in all. This study identifies new associations for PRR12 disruption in humans and presents a genetic diagnosis resulting in unilateral ocular phenotypes in a significant proportion of cases.

Exome sequencing identifies novel missense and deletion variants in RTN4IP1 associated with optic atrophy, global developmental delay, epilepsy, ataxia, and choreoathetosis. - D'Gama, Alissa M; England, Eleina; Madden, Jill A; Shi, JiAHi; Chao, Katherine R; Wojcik, Monica H; Torres, Alcy R; Tan, Wen-Hann; Berry, Gerard T; Prabhu, Sanjay P; Agrawal, Pankaj B (Am J Med Genet A, 2021)
Inherited optic neuropathies (IONs) are neurodegenerative disorders characterized by optic atrophy with or without extraocular manifestations. Optic atrophy-10 (OPA10) is an autosomal recessive ION recently reported to be caused by mutations in RTN4IP1, which encodes reticulon 4 interacting protein 1 (RTN4IP1), a mitochondrial ubiquinol oxydo-reductase. Here we report novel compound heterozygous mutations in RTN4IP1 in a male proband with developmental delay, epilepsy, optic atrophy, ataxia, and choreoathetosis. Workup was notable for transiently elevated lactate and lactate-to-pyruvate ratio, brain magnetic resonance imaging with optic atrophy and T2 signal abnormalities, and a nondiagnostic initial genetic workup, including chromosomal microarray and mitochondrial panel testing. Exome sequencing identified a paternally inherited missense variant (c.263T>G, p.Val88Gly) predicted to be deleterious and a maternally inherited deletion encompassing RTN4IP1. To our knowledge, this is the first report of a non-single nucleotide pathogenic variant associated with OPA10. This case highlights the expanding phenotypic spectrum of OPA10, the association between "syndromic" cases and severe RTN4IP1 mutations, and the importance of nonbiased genetic testing, such as ES, to analyze multiple genes and variants types, in patients suspected of having genetic disease.

Familial thrombocytopenia due to a complex structural variant resulting in a WAC-ANKRD26 fusion transcript. - Wahlster, Lara; Verboon, Jeffrey M; Ludwig, Leif S; Black, Susan C; Luo, Wendy; Garg, Kopal; Voit, Richard A; Collins, Ryan L; Garimella, Kiran; Costello, Maura; Chao, Katherine R; Goodrich, Julia K; et al. (J Exp Med, 2021)
Advances in genome sequencing have resulted in the identification of the causes for numerous rare diseases. However, many cases remain unsolved with standard molecular analyses. We describe a family presenting with a phenotype resembling inherited thrombocytopenia 2 (THC2). THC2 is generally caused by single nucleotide variants that prevent silencing of ANKRD26 expression during hematopoietic differentiation. Short-read whole-exome and genome sequencing approaches were unable to identify a causal variant in this family. Using long-read whole-genome sequencing, a large complex structural variant involving a paired-duplication inversion was identified. Through functional studies, we show that this structural variant results in a pathogenic gain-of-function WAC-ANKRD26 fusion transcript. Our findings illustrate how complex structural variants that may be missed by conventional genome sequencing approaches can cause human disease.

Further delineation of van den Ende-Gupta syndrome: Genetic heterogeneity and overlap with congenital heart defects and skeletal malformations syndrome. - Hildebrandt, Clara C; Patel, Nisha; GrAHm, John M; Bamshad, Michael; Nickerson, Deborah A; White, Janson J; Marvin, Colby T; Miller, Danny E; Grand, Katheryn L; Sanchez-Lara, Pedro A; Schweitzer, Daniela; Al-Zaidan, Hamad I; et al. (Am J Med Genet A, 2021)
Van den Ende-Gupta syndrome (VDEGS) is a rare autosomal recessive condition characterized by distinctive facial and skeletal features, and in most affected persons, by biallelic pathogenic variants in SCARF2. We review the type and frequency of the clinical features in 36 reported individuals with features of VDEGS, 15 (42%) of whom had known pathogenic variants in SCARF2, 6 (16%) with negative SCARF2 testing, and 15 (42%) not tested. We also report three new individuals with pathogenic variants in SCARF2 and clinical features of VDEGS. Of the six persons without known pathogenic variants in SCARF2, three remain unsolved despite extensive genetic testing. Three were found to have pathogenic ABL1 variants using whole exome sequencing (WES) or whole genome sequencing (WGS). Their phenotype was consistent with the congenital heart disease and skeletal malformations syndrome (CHDSKM), which has been associated with ABL1 variants. Of the three unsolved cases, two were brothers who underwent WGS and targeted long-range sequencing of both SCARF2 and ABL1, and the third person who underwent WES and RNA sequencing for SCARF2. Because these affected individuals with classical features of VDEGS lacked a detectable pathogenic SCARF2 variant, genetic heterogeneity is likely. Our study shows the importance of performing genetic testing on individuals with the VDEGS "phenotype," either as a targeted gene analysis (SCARF2, ABL1) or WES/WGS. Additionally, individuals with the combination of arachnodactyly and blepharophimosis should undergo echocardiography while awaiting results of molecular testing due to the overlapping physical features of VDEGS and CHDSKM.

Generation of Monogenic Candidate Genes for Human Nephrotic Syndrome Using 3 Independent Approaches. - Klämbt, Verena; Mao, Youying; Schneider, Ronen; Buerger, Florian; Shamseldin, Hanan; Onuchic-Whitford, Ana C; Deutsch, Konstantin; Kitzler, Thomas M; Nakayama, Makiko; Majmundar, Amar J; Mann, Nina; Hugo, Hannah; et al. (Kidney Int Rep, 2021)
Introduction: Steroid-resistant nephrotic syndrome (SRNS) is the second most common cause of chronic kidney disease during childhood. Identification of 63 monogenic human genes has delineated 12 distinct pathogenic pathways. Methods: Here, we generated 2 independent sets of nephrotic syndrome (NS) candidate genes to augment the discovery of additional monogenic causes based on whole-exome sequencing (WES) data from 1382 families with NS. Results: We first identified 63 known monogenic causes of NS in mice from public databases and scientific publications, and 12 of these genes overlapped with the 63 known human monogenic SRNS genes. Second, we used a set of 64 genes that are regulated by the transcription factor Wilms tumor 1 (WT1), which causes SRNS if mutated. Thirteen of these WT1-regulated genes overlapped with human or murine NS genes. Finally, we overlapped these lists of murine and WT1 candidate genes with our list of 120 candidate genes generated from WES in 1382 NS families, to identify novel candidate genes for monogenic human SRNS. Using this approach, we identified 7 overlapping genes, of which 3 genes were shared by all datasets, including . We show that loss-of-function of leads to decreased CDC42 activity and reduced podocyte migration rate, both of which are rescued by overexpression of wild-type complementary DNA (cDNA), but not by cDNA representing the patient mutation. Conclusion: Thus, we identified 3 novel candidate genes for human SRNS using 3 independent, nonoverlapping hypotheses, and generated functional evidence for as a novel potential monogenic cause of NS.

Genetic and non-genetic factors affecting the expression of COVID-19-relevant genes in the large airway epithelium. - Kasela, Silva; Ortega, Victor E; Martorella, Molly; Garudadri, Suresh; Nguyen, Jenna; Ampleford, Elizabeth; Pasanen, Anu; Nerella, Srilaxmi; Buschur, Kristina L; Barjaktarevic, Igor Z; Barr, R Graham; Bleecker, Eugene R; et al. (Genome Med, 2021)
BACKGROUND: The large airway epithelial barrier provides one of the first lines of defense against respiratory viruses, including SARS-CoV-2 that causes COVID-19. Substantial inter-individual variability in individual disease courses is hypothesized to be partially mediated by the differential regulation of the genes that interact with the SARS-CoV-2 virus or are involved in the subsequent host response. Here, we comprehensively investigated non-genetic and genetic factors influencing COVID-19-relevant bronchial epithelial gene expression. METHODS: We analyzed RNA-sequencing data from bronchial epithelial brushings obtained from uninfected individuals. We related ACE2 gene expression to host and environmental factors in the SPIROMICS cohort of smokers with and without chronic obstructive pulmonary disease (COPD) and replicated these associations in two asthma cohorts, SARP and MAST. To identify airway biology beyond ACE2 binding that may contribute to increased susceptibility, we used gene set enrichment analyses to determine if gene expression changes indicative of a suppressed airway immune response observed early in SARS-CoV-2 infection are also observed in association with host factors. To identify host genetic variants affecting COVID-19 susceptibility in SPIROMICS, we performed expression quantitative trait (eQTL) mapping and investigated the phenotypic associations of the eQTL variants. RESULTS: We found that ACE2 expression was higher in relation to active smoking, obesity, and hypertension that are known risk factors of COVID-19 severity, while an association with interferon-related inflammation was driven by the truncated, non-binding ACE2 isoform. We discovered that expression patterns of a suppressed airway immune response to early SARS-CoV-2 infection, compared to other viruses, are similar to patterns associated with obesity, hypertension, and cardiovascular disease, which may thus contribute to a COVID-19-susceptible airway environment. eQTL mapping identified regulatory variants for genes implicated in COVID-19, some of which had pheWAS evidence for their potential role in respiratory infections. CONCLUSIONS: These data provide evidence that clinically relevant variation in the expression of COVID-19-related genes is associated with host factors, environmental exposures, and likely host genetic variation.
Keywords: Adult; Aged; Aged, 80 and over; Angiotensin-Converting Enzyme 2; Asthma; Bronchi; Cardiovascular Diseases; COVID-19; Gene Expression; Genetic Variation; Humans; Middle Aged; Obesity; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; Respiratory Mucosa; Risk Factors; SARS-CoV-2; Smoking

Genetic Predictor to Identify Individuals With High Lipoprotein(a) Concentrations. - Dron, Jacqueline S; Wang, Minxian; Patel, Aniruddh P; Kartoun, Uri; Ng, Kenney; Hegele, Robert A; Khera, Amit V (Circ Genom Precis Med, 2021)

Genetic profiles of 103,106 individuals in the Taiwan Biobank provide insights into the health and history of Han Chinese. - Wei, Chun-Yu; Yang, Jenn-Hwai; Yeh, Erh-Chan; Tsai, Ming-Fang; Kao, Hsiao-Jung; Lo, Chen-Zen; Chang, Lung-Pao; Lin, Wan-Jia; Hsieh, Feng-Jen; Belsare, Saurabh; Bhaskar, Anand; Su, Ming-Wei; et al. (NPJ Genom Med, 2021)
Personalized medical care focuses on prediction of disease risk and response to medications. To build the risk models, access to both large-scale genomic resources and human genetic studies is required. The Taiwan Biobank (TWB) has generated high-coverage, whole-genome sequencing data from 1492 individuals and genome-wide SNP data from 103,106 individuals of Han Chinese ancestry using custom SNP arrays. Principal components analysis of the genotyping data showed that the full range of Han Chinese genetic variation was found in the cohort. The arrays also include thousands of known functional variants, allowing for simultaneous ascertainment of Mendelian disease-causing mutations and variants that affect drug metabolism. We found that 21.2% of the population are mutation carriers of autosomal recessive diseases, 3.1% have mutations in cancer-predisposing genes, and 87.3% carry variants that affect drug response. We highlight how TWB data provide insight into both population history and disease burden, while showing how widespread genetic testing can be used to improve clinical care.

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

Germline SAMD9L truncation variants trigger global translational repression. - Allenspach, Eric J; Soveg, Frank; Finn, Laura S; So, Lomon; Gorman, Jacquelyn A; Rosen, Aaron B I; Skoda-Smith, Suzanne; Wheeler, Marsha M; Barrow, Kaitlyn A; Rich, Lucille M; Debley, Jason S; Bamshad, Michael J; et al. (J Exp Med, 2021)
SAMD9L is an interferon-induced tumor suppressor implicated in a spectrum of multisystem disorders, including risk for myeloid malignancies and immune deficiency. We identified a heterozygous de novo frameshift variant in SAMD9L in an infant with B cell aplasia and clinical autoinflammatory features who died from respiratory failure with chronic rhinovirus infection. Autopsy demonstrated absent bone marrow and peripheral B cells as well as selective loss of Langerhans and Purkinje cells. The frameshift variant led to expression of a truncated protein with interferon treatment. This protein exhibited a gain-of-function phenotype, resulting in interference in global protein synthesis via inhibition of translational elongation. Using a mutational scan, we identified a region within SAMD9L where stop-gain variants trigger a similar translational arrest. SAMD9L variants that globally suppress translation had no effect or increased mRNA transcription. The complex-reported phenotype likely reflects lineage-dominant sensitivities to this translation block. Taken together, our findings indicate that interferon-triggered SAMD9L gain-of-function variants globally suppress translation.

Haplotype-resolved diverse human genomes and integrated analysis of structural variation. - Ebert, Peter; Audano, Peter A; Zhu, Qihui; Rodriguez-Martin, Bernardo; Porubsky, David; Bonder, Marc Jan; Sulovari, Arvis; Ebler, Jana; Zhou, Weichen; Serra Mari, Rebecca; Yilmaz, Feyza; Zhao, Xuefang; et al. (Science, 2021)
Long-read and strand-specific sequencing technologies together facilitate the de novo assembly of high-quality haplotype-resolved human genomes without parent-child trio data. We present 64 assembled haplotypes from 32 diverse human genomes. These highly contiguous haplotype assemblies (average minimum contig length needed to cover 50% of the genome: 26 million base pairs) integrate all forms of genetic variation, even across complex loci. We identified 107,590 structural variants (SVs), of which 68% were not discovered with short-read sequencing, and 278 SV hotspots (spanning megabases of gene-rich sequence). We characterized 130 of the most active mobile element source elements and found that 63% of all SVs arise through homology-mediated mechanisms. This resource enables reliable graph-based genotyping from short reads of up to 50,340 SVs, resulting in the identification of 1526 expression quantitative trait loci as well as SV candidates for adaptive selection within the human population.
Keywords: Female; Genetic Variation; Genome, Human; Genotype; Haplotypes; High-Throughput Nucleotide Sequencing; Humans; INDEL Mutation; Interspersed Repetitive Sequences; Male; Population Groups; Quantitative Trait Loci; Retroelements; Sequence Analysis, DNA; Sequence Inversion; Whole Genome Sequencing

Identification of Required Host Factors for SARS-CoV-2 Infection in Human Cells. - Daniloski, Zharko; Jordan, Tristan X; Wessels, Hans-Hermann; Hoagland, Daisy A; Kasela, Silva; Legut, Mateusz; Maniatis, Silas; Mimitou, Eleni P; Lu, Lu; Geller, Evan; Danziger, Oded; Rosenberg, Brad R; et al. (Cell, 2021)
To better understand host-virus genetic dependencies and find potential therapeutic targets for COVID-19, we performed a genome-scale CRISPR loss-of-function screen to identify host factors required for SARS-CoV-2 viral infection of human alveolar epithelial cells. Top-ranked genes cluster into distinct pathways, including the vacuolar ATPase proton pump, Retromer, and Commander complexes. We validate these gene targets using several orthogonal methods such as CRISPR knockout, RNA interference knockdown, and small-molecule inhibitors. Using single-cell RNA-sequencing, we identify shared transcriptional changes in cholesterol biosynthesis upon loss of top-ranked genes. In addition, given the key role of the ACE2 receptor in the early stages of viral entry, we show that loss of RAB7A reduces viral entry by sequestering the ACE2 receptor inside cells. Overall, this work provides a genome-scale, quantitative resource of the impact of the loss of each host gene on fitness/response to viral infection.
Keywords: A549 Cells; Alveolar Epithelial Cells; Angiotensin-Converting Enzyme 2; Biosynthetic Pathways; Cholesterol; Clustered Regularly Interspaced Short Palindromic Repeats; COVID-19; Endosomes; Gene Expression Profiling; Gene Knockdown Techniques; Gene Knockout Techniques; Genome-Wide Association Study; Host-Pathogen Interactions; Humans; rab GTP-Binding Proteins; RNA Interference; SARS-CoV-2; Single-Cell Analysis; Viral Load

Increased Burden of Rare Sequence Variants in GnRH-Associated Genes in Women With Hypothalamic Amenorrhea. - Delaney, Angela; Burkholder, Adam B; Lavender, Christopher A; Plummer, Lacey; Mericq, Veronica; Merino, Paulina M; Quinton, Richard; Lewis, Katie L; Meader, Brooke N; Albano, Alessandro; Shaw, Natalie D; Welt, Corrine K; et al. (J Clin Endocrinol Metab, 2021)
CONTEXT: Functional hypothalamic amenorrhea (HA) is a common, acquired form of hypogonadotropic hypogonadism that occurs in the setting of energy deficits and/or stress. Variability in individual susceptibility to these stressors, HA heritability, and previous identification of several rare sequence variants (RSVs) in genes associated with the rare disorder, isolated hypogonadotropic hypogonadism (IHH), in individuals with HA suggest a possible genetic contribution to HA susceptibility. OBJECTIVE: We sought to determine whether the burden of RSVs in IHH-related genes is greater in women with HA than controls. DESIGN: We compared patients with HA to control women. SETTING: The study was conducted at secondary referral centers. PATIENTS AND OTHER PARTICIPANTS: Women with HA (n = 106) and control women (ClinSeq study; n = 468). INTERVENTIONS: We performed exome sequencing in all patients and controls. MAIN OUTCOME MEASURE(S): The frequency of RSVs in 53 IHH-associated genes was determined using rare variant burden and association tests. RESULTS: RSVs were overrepresented in women with HA compared with controls (P = .007). Seventy-eight heterozygous RSVs in 33 genes were identified in 58 women with HA (36.8% of alleles) compared to 255 RSVs in 41 genes among 200 control women (27.2%). CONCLUSIONS: Women with HA are enriched for RSVs in genes that cause IHH, suggesting that variation in genes associated with gonadotropin-releasing hormone neuronal ontogeny and function may be a major determinant of individual susceptibility to developing HA in the face of diet, exercise, and/or stress.

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Longitudinal single-cell epitope and RNA-sequencing reveals the immunological impact of type 1 interferon autoantibodies in critical COVID-19. - van der Wijst, Monique G P; Vazquez, Sara E; Hartoularos, George C; Bastard, Paul; Grant, Tianna; Bueno, Raymund; Lee, David S; Greenland, John R; Sun, Yang; Perez, Richard; Ogorodnikov, Anton; Ward, Alyssa; et al. (bioRxiv, 2021)
Type I interferon (IFN-I) neutralizing autoantibodies have been found in some critical COVID-19 patients; however, their prevalence and longitudinal dynamics across the disease severity scale, and functional effects on circulating leukocytes remain unknown. Here, in 284 COVID-19 patients, we found IFN-I autoantibodies in 19% of critical, 6% of severe and none of the moderate cases. Longitudinal profiling of over 600,000 peripheral blood mononuclear cells using multiplexed single-cell epitope and transcriptome sequencing from 54 COVID-19 patients, 15 non-COVID-19 patients and 11 non-hospitalized healthy controls, revealed a lack of IFN-I stimulated gene (ISG-I) response in myeloid cells from critical cases, including those producing anti-IFN-I autoantibodies. Moreover, surface protein analysis showed an inverse correlation of the inhibitory receptor LAIR-1 with ISG-I expression response early in the disease course. This aberrant ISG-I response in critical patients with and without IFN-I autoantibodies, supports a unifying model for disease pathogenesis involving ISG-I suppression via convergent mechanisms.

Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder. - Kour, Sukhleen; Rajan, Deepa S; Fortuna, Tyler R; Anderson, Eric N; Ward, Caroline; Lee, Youngha; Lee, Sangmoon; Shin, Yong Beom; Chae, Jong-Hee; Choi, Murim; Siquier, Karine; Cantagrel, Vincent; et al. (Nat Commun, 2021)
GEMIN5, an RNA-binding protein is essential for assembly of the survival motor neuron (SMN) protein complex and facilitates the formation of small nuclear ribonucleoproteins (snRNPs), the building blocks of spliceosomes. Here, we have identified 30 affected individuals from 22 unrelated families presenting with developmental delay, hypotonia, and cerebellar ataxia harboring biallelic variants in the GEMIN5 gene. Mutations in GEMIN5 perturb the subcellular distribution, stability, and expression of GEMIN5 protein and its interacting partners in patient iPSC-derived neurons, suggesting a potential loss-of-function mechanism. GEMIN5 mutations result in disruption of snRNP complex assembly formation in patient iPSC neurons. Furthermore, knock down of rigor mortis, the fly homolog of human GEMIN5, leads to developmental defects, motor dysfunction, and a reduced lifespan. Interestingly, we observed that GEMIN5 variants disrupt a distinct set of transcripts and pathways as compared to SMA patient neurons, suggesting different molecular pathomechanisms. These findings collectively provide evidence that pathogenic variants in GEMIN5 perturb physiological functions and result in a neurodevelopmental delay and ataxia syndrome.
Keywords: Alleles; Amino Acid Sequence; Animals; Child, Preschool; Developmental Disabilities; Drosophila; Female; Gene Expression Regulation, Developmental; Gene Knockdown Techniques; Gene Ontology; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Loss of Function Mutation; Male; Muscle Hypotonia; Myoclonic Cerebellar Dyssynergia; Neurodevelopmental Disorders; Neurons; Pedigree; Polymorphism, Single Nucleotide; Ribonucleoproteins, Small Nuclear; Rigor Mortis; RNA-Seq; SMN Complex Proteins

MED27 Variants Cause Developmental Delay, Dystonia, and Cerebellar Hypoplasia. - Meng, Linyan; Isohanni, Pirjo; Shao, Yunru; GrAHm, Brett H; Hickey, Scott E; Brooks, Stephanie; Suomalainen, Anu; Joset, Pascal; Steindl, Katharina; Rauch, Anita; Hackenberg, Annette; High, Frances A; et al. (Ann Neurol, 2021)
The Mediator multiprotein complex functions as a regulator of RNA polymerase II-catalyzed gene transcription. In this study, exome sequencing detected biallelic putative disease-causing variants in MED27, encoding Mediator complex subunit 27, in 16 patients from 11 families with a novel neurodevelopmental syndrome. Patient phenotypes are highly homogeneous, including global developmental delay, intellectual disability, axial hypotonia with distal spasticity, dystonic movements, and cerebellar hypoplasia. Seizures and cataracts were noted in severely affected individuals. Identification of multiple patients with biallelic MED27 variants supports the critical role of MED27 in normal human neural development, particularly for the cerebellum. ANN NEUROL 2021;89:828-833.
Keywords: Adolescent; Adult; Amino Acid Sequence; Cataract; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Dystonia; Epilepsy; Genetic Variation; Humans; Infant; Mediator Complex; Nervous System Malformations; Phenotype; Whole Exome Sequencing

Multiomic analysis elucidates Complex I deficiency caused by a deep intronic variant in NDUFB10. - Helman, Guy; Compton, Alison G; Hock, Daniella H; Walkiewicz, Marzena; Brett, Gemma R; Pais, Lynn; Tan, Tiong Y; De Paoli-Iseppi, Ricardo; Clark, Michael B; Christodoulou, John; White, Susan M; Thorburn, David R; et al. (Hum Mutat, 2021)
The diagnosis of Mendelian disorders following uninformative exome and genome sequencing remains a challenging and often unmet need. Following uninformative exome and genome sequencing of a family quartet including two siblings with suspected mitochondrial disorder, RNA sequencing (RNAseq) was pursued in one sibling. Long-read amplicon sequencing was used to determine and quantify transcript structure. Immunoblotting studies and quantitative proteomics were performed to demonstrate functional impact. Differential expression analysis of RNAseq data identified significantly decreased expression of the mitochondrial OXPHOS Complex I subunit NDUFB10 associated with a cryptic exon in intron 1 of NDUFB10, that included an in-frame stop codon. The cryptic exon contained a rare intronic variant that was homozygous in both affected siblings. Immunoblot and quantitative proteomic analysis of fibroblasts revealed decreased abundance of Complex I subunits, providing evidence of isolated Complex I deficiency. Through multiomic analysis we present data implicating a deep intronic variant in NDUFB10 as the cause of mitochondrial disease in two individuals, providing further support of the gene-disease association. This study highlights the importance of transcriptomic and proteomic analyses as complementary diagnostic tools in patients undergoing genome-wide diagnostic evaluation.

Mutations in Spliceosomal Genes PPIL1 and PRP17 Cause Neurodegenerative Pontocerebellar Hypoplasia with Microcephaly. - Chai, Guoliang; Webb, Alice; Li, Chen; Antaki, Danny; Lee, Sangmoon; Breuss, Martin W; Lang, Nhi; Stanley, Valentina; Anzenberg, Paula; Yang, Xiaoxu; Marshall, Trevor; Gaffney, Patrick; et al. (Neuron, 2021)
Autosomal-recessive cerebellar hypoplasia and ataxia constitute a group of heterogeneous brain disorders caused by disruption of several fundamental cellular processes. Here, we identified 10 families showing a neurodegenerative condition involving pontocerebellar hypoplasia with microcephaly (PCHM). Patients harbored biallelic mutations in genes encoding the spliceosome components Peptidyl-Prolyl Isomerase Like-1 (PPIL1) or Pre-RNA Processing-17 (PRP17). Mouse knockouts of either gene were lethal in early embryogenesis, whereas PPIL1 patient mutation knockin mice showed neuron-specific apoptosis. Loss of either protein affected splicing integrity, predominantly affecting short and high GC-content introns and genes involved in brain disorders. PPIL1 and PRP17 form an active isomerase-substrate interaction, but we found that isomerase activity is not critical for function. Thus, we establish disrupted splicing integrity and "major spliceosome-opathies" as a new mechanism underlying PCHM and neurodegeneration and uncover a non-enzymatic function of a spliceosomal proline isomerase.
Keywords: Amino Acid Sequence; Animals; Cell Cycle Proteins; Cerebellar Diseases; Cohort Studies; Female; Gene Knockout Techniques; HEK293 Cells; Heredodegenerative Disorders, Nervous System; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microcephaly; Mutation; Pedigree; Peptidylprolyl Isomerase; Protein Structure, Secondary; Protein Structure, Tertiary; RNA Splicing Factors; Spliceosomes

Mutations in transcription factor CP2-like 1 may cause a novel syndrome with distal renal tubulopathy in humans. - Klämbt, Verena; Werth, Max; Onuchic-Whitford, Ana C; Getwan, Maike; Kitzler, Thomas M; Buerger, Florian; Mao, Youying; Deutsch, Konstantin; Mann, Nina; Majmundar, Amar J; Kaminski, Michael M; Shen, Tian; et al. (Nephrol Dial Transplant, 2021)
BACKGROUND: An underlying monogenic cause of early-onset chronic kidney disease (CKD) can be detected in ∼20% of individuals. For many etiologies of CKD manifesting before 25 years of age, >200 monogenic causative genes have been identified to date, leading to the elucidation of mechanisms of renal pathogenesis. METHODS: In 51 families with echogenic kidneys and CKD, we performed whole-exome sequencing to identify novel monogenic causes of CKD. RESULTS: We discovered a homozygous truncating mutation in the transcription factor gene transcription factor CP2-like 1 (TFCP2L1) in an Arabic patient of consanguineous descent. The patient developed CKD by the age of 2 months and had episodes of severe hypochloremic, hyponatremic and hypokalemic alkalosis, seizures, developmental delay and hypotonia together with cataracts. We found that TFCP2L1 was localized throughout kidney development particularly in the distal nephron. Interestingly, TFCP2L1 induced the growth and development of renal tubules from rat mesenchymal cells. Conversely, the deletion of TFCP2L1 in mice was previously shown to lead to reduced expression of renal cell markers including ion transporters and cell identity proteins expressed in different segments of the distal nephron. TFCP2L1 localized to the nucleus in HEK293T cells only upon coexpression with its paralog upstream-binding protein 1 (UBP1). A TFCP2L1 mutant complementary DNA (cDNA) clone that represented the patient's mutation failed to form homo- and heterodimers with UBP1, an essential step for its transcriptional activity. CONCLUSION: Here, we identified a loss-of-function TFCP2L1 mutation as a potential novel cause of CKD in childhood accompanied by a salt-losing tubulopathy.
Keywords: Animals; Child; DNA-Binding Proteins; Epithelial-Mesenchymal Transition; Female; HEK293 Cells; Humans; Kidney Diseases; Mice; Mice, Knockout; Mutation; Rats; Repressor Proteins; Single-Cell Analysis; Transcription Factors; Whole Exome Sequencing

NMIHBA results from hypomorphic PRUNE1 variants that lack short-chain exopolyphosphatase activity. - Nistala, Harikiran; Dronzek, John; Gonzaga-Jauregui, Claudia; Chim, Shek Man; Rajamani, Saathyaki; Nuwayhid, Samer; Delgado, Dennis; Burke, Elizabeth; Karaca, Ender; Franklin, Matthew C; Sarangapani, Prasad; Podgorski, Michael; et al. (Hum Mol Genet, 2021)
Neurodevelopmental disorder with microcephaly, hypotonia and variable brain anomalies (NMIHBA) is an autosomal recessive neurodevelopmental and neurodegenerative disorder characterized by global developmental delay and severe intellectual disability. Microcephaly, progressive cortical atrophy, cerebellar hypoplasia and delayed myelination are neurological hallmarks in affected individuals. NMIHBA is caused by biallelic variants in PRUNE1 encoding prune exopolyphosphatase 1. We provide in-depth clinical description of two affected siblings harboring compound heterozygous variant alleles, c.383G > A (p.Arg128Gln), c.520G > T (p.Gly174*) in PRUNE1. To gain insights into disease biology, we biochemically characterized missense variants within the conserved N-terminal aspartic acid-histidine-histidine (DHH) motif and provide evidence that they result in the destabilization of protein structure and/or loss of exopolyphosphatase activity. Genetic ablation of Prune1 results in midgestational lethality in mice, associated with perturbations to embryonic growth and vascular development. Our findings suggest that NMIHBA results from hypomorphic variant alleles in humans and underscore the potential key role of PRUNE1 exopolyphoshatase activity in neurodevelopment.

Novel variants in TUBA1A cause congenital fibrosis of the extraocular muscles with or without malformations of cortical brain development. - Jurgens, Julie A; Barry, Brenda J; Lemire, Gabrielle; Chan, Wai-Man; Whitman, Mary C; Shaaban, Sherin; Robson, Caroline D; MacKinnon, Sarah; England, Eleina M; McMillan, Hugh J; Kelly, Christopher; Pratt, Brandon M; et al. (Eur J Hum Genet, 2021)
Variants in multiple tubulin genes have been implicated in neurodevelopmental disorders, including malformations of cortical development (MCD) and congenital fibrosis of the extraocular muscles (CFEOM). Distinct missense variants in the beta-tubulin encoding genes TUBB3 and TUBB2B cause MCD, CFEOM, or both, suggesting substitution-specific mechanisms. Variants in the alpha tubulin-encoding gene TUBA1A have been associated with MCD, but not with CFEOM. Using exome sequencing (ES) and genome sequencing (GS), we identified 3 unrelated probands with CFEOM who harbored novel heterozygous TUBA1A missense variants c.1216C>G, p.(His406Asp); c.467G>A, p.(Arg156His); and c.1193T>G, p.(Met398Arg). MRI revealed small oculomotor-innervated muscles and asymmetrical caudate heads and lateral ventricles with or without corpus callosal thinning. Two of the three probands had MCD. Mutated amino acid residues localize either to the longitudinal interface at which α and β tubulins heterodimerize (Met398, His406) or to the lateral interface at which tubulin protofilaments interact (Arg156), and His406 interacts with the motor domain of kinesin-1. This series of individuals supports TUBA1A variants as a cause of CFEOM and expands our knowledge of tubulinopathies.

Pathogenic deep intronic MTM1 variant activates a pseudo-exon encoding a nonsense codon resulting in severe X-linked myotubular myopathy. - Bryen, Samantha J; Oates, Emily C; Evesson, Frances J; Lu, Jessica K; Waddell, Leigh B; Joshi, Himanshu; Ryan, Monique M; Cummings, Beryl B; McLean, Catriona A; MacArthur, Daniel G; Kornberg, Andrew J; Cooper, Sandra T (Eur J Hum Genet, 2021)
X-linked myotubular myopathy (XLMTM) is a severe congenital myopathy characterised by generalised weakness and respiratory insufficiency. XLMTM is associated with pathogenic variants in MTM1; a gene encoding the lipid phosphatase myotubularin. Whole genome sequencing (WGS) of an exome-negative male proband with severe hypotonia, respiratory insufficiency and centralised nuclei on muscle biopsy identified a deep intronic MTM1 variant NG_008199.1(NM_000252.2):c.1468-577A>G, which strengthened a cryptic 5' splice site (A>G substitution at the +5 position). Muscle RNA sequencing was non-diagnostic due to low read depth. Reverse transcription PCR (RT-PCR) of muscle RNA confirmed the c.1468-577A>G variant activates inclusion of a pseudo-exon encoding a premature stop codon into all detected MTM1 transcripts. Western blot analysis establishes deficiency of myotubularin protein, consistent with the severe XLMTM phenotype. We expand the genotypic spectrum of XLMTM and highlight benefits of screening non-coding regions of MTM1 in male probands with phenotypically concordant XLMTM who remain undiagnosed following exome sequencing.

Pathogenic variants in , a chromatin remodeler, cause a range of syndromic neurodevelopmental features. - Li, Dong; Wang, Qin; Gong, Naihua N; Kurolap, Alina; Feldman, Hagit Baris; Boy, Nikolas; Brugger, Melanie; Grand, Katheryn; McWalter, Kirsty; Guillen Sacoto, Maria J; Wakeling, Emma; Hurst, Jane; et al. (Sci Adv, 2021)
Intellectual disability encompasses a wide spectrum of neurodevelopmental disorders, with many linked genetic loci. However, the underlying molecular mechanism for more than 50% of the patients remains elusive. We describe pathogenic variants in , encoding the ATPase motor of the ISWI chromatin remodeler, as a cause of a previously unidentified neurodevelopmental disorder, identifying 12 individuals with de novo or dominantly segregating rare heterozygous variants. Accompanying phenotypes include mild developmental delay, frequent postnatal short stature and microcephaly, and recurrent dysmorphic features. Loss of function of the SMARCA5 ortholog led to smaller body size, reduced sensory dendrite complexity, and tiling defects in larvae. In adult flies, Iswi neural knockdown caused decreased brain size, aberrant mushroom body morphology, and abnormal locomotor function. loss of function was rescued by wild-type but not mutant SMARCA5. Our results demonstrate that pathogenic variants cause a neurodevelopmental syndrome with mild facial dysmorphia.

Perturbations of genes essential for Müllerian duct and Wölffian duct development in Mayer-Rokitansky-Küster-Hauser syndrome. - Chen, Na; Zhao, Sen; Jolly, Angad; Wang, Lianlei; Pan, Hongxin; Yuan, Jian; Chen, Shaoke; Koch, André; Ma, Congcong; Tian, Weijie; Jia, Ziqi; Kang, Jia; et al. (Am J Hum Genet, 2021)
Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS) is associated with congenital absence of the uterus, cervix, and the upper part of the vagina; it is a sex-limited trait. Disrupted development of the Müllerian ducts (MD)/Wölffian ducts (WD) through multifactorial mechanisms has been proposed to underlie MRKHS. In this study, exome sequencing (ES) was performed on a Chinese discovery cohort (442 affected subjects and 941 female control subjects) and a replication MRKHS cohort (150 affected subjects of mixed ethnicity from North America, South America, and Europe). Phenotypic follow-up of the female reproductive system was performed on an additional cohort of PAX8-associated congenital hypothyroidism (CH) (n = 5, Chinese). By analyzing 19 candidate genes essential for MD/WD development, we identified 12 likely gene-disrupting (LGD) variants in 7 genes: PAX8 (n = 4), BMP4 (n = 2), BMP7 (n = 2), TBX6 (n = 1), HOXA10 (n = 1), EMX2 (n = 1), and WNT9B (n = 1), while LGD variants in these genes were not detected in control samples (p = 1.27E-06). Interestingly, a sex-limited penetrance with paternal inheritance was observed in multiple families. One additional PAX8 LGD variant from the replication cohort and two missense variants from both cohorts were revealed to cause loss-of-function of the protein. From the PAX8-associated CH cohort, we identified one individual presenting a syndromic condition characterized by CH and MRKHS (CH-MRKHS). Our study demonstrates the comprehensive utilization of knowledge from developmental biology toward elucidating genetic perturbations, i.e., rare pathogenic alleles involving the same loci, contributing to human birth defects.
Keywords: 46, XX Disorders of Sex Development; Adult; Bone Morphogenetic Protein 4; Bone Morphogenetic Protein 7; Codon, Nonsense; Congenital Abnormalities; Female; Genetic Association Studies; Genetic Pleiotropy; Homeobox A10 Proteins; Homeodomain Proteins; Humans; Mullerian Ducts; Mutation; Paternal Inheritance; PAX8 Transcription Factor; Penetrance; T-Box Domain Proteins; Transcription Factors; Wnt Proteins; Wolffian Ducts

Phenotypic and protein localization heterogeneity associated with AHDC1 pathogenic protein-truncating alleles in Xia-Gibbs syndrome. - Khayat, Michael M; Li, He; Chander, Varuna; Hu, Jianhong; Hansen, Adam W; Li, Shoudong; Traynelis, Josh; Shen, Hua; Weissenberger, George; Stossi, Fabio; Johnson, Hannah L; Lupski, James R; et al. (Hum Mutat, 2021)
Xia-Gibbs syndrome (XGS) is a rare Mendelian disease typically caused by de novo stop-gain or frameshift mutations in the AT-hook DNA binding motif containing 1 (AHDC1) gene. Patients usually present in early infancy with hypotonia and developmental delay and later exhibit intellectual disability (ID). The overall presentation is variable, however, and the emerging clinical picture is still evolving. A detailed phenotypic analysis of 34 XGS individuals revealed five core phenotypes (delayed motor milestones, speech delay, low muscle tone, ID, and hypotonia) in more than 80% of individuals and an additional 12 features that occurred more variably. Seizures and scoliosis were more frequently associated with truncations that arise before the midpoint of the protein although the occurrence of most features could not be predicted by the mutation position. Transient expression of wild type and different patient truncated AHDC1 protein forms in human cell lines revealed abnormal patterns of nuclear localization including a diffuse distribution of a short truncated form and nucleolar aggregation in mid-protein truncated forms. Overall, both the occurrence of variable phenotypes and the different distribution of the expressed protein reflect the heterogeneity of this syndrome.

POLRMT mutations impair mitochondrial transcription causing neurological disease. - Oláhová, Monika; Peter, Bradley; Szilagyi, Zsolt; Diaz-Maldonado, Hector; Singh, Meenakshi; Sommerville, Ewen W; Blakely, Emma L; Collier, Jack J; Hoberg, Emily; Stránecký, Viktor; Hartmannová, Hana; Bleyer, Anthony J; et al. (Nat Commun, 2021)
While >300 disease-causing variants have been identified in the mitochondrial DNA (mtDNA) polymerase γ, no mitochondrial phenotypes have been associated with POLRMT, the RNA polymerase responsible for transcription of the mitochondrial genome. Here, we characterise the clinical and molecular nature of POLRMT variants in eight individuals from seven unrelated families. Patients present with global developmental delay, hypotonia, short stature, and speech/intellectual disability in childhood; one subject displayed an indolent progressive external ophthalmoplegia phenotype. Massive parallel sequencing of all subjects identifies recessive and dominant variants in the POLRMT gene. Patient fibroblasts have a defect in mitochondrial mRNA synthesis, but no mtDNA deletions or copy number abnormalities. The in vitro characterisation of the recombinant POLRMT mutants reveals variable, but deleterious effects on mitochondrial transcription. Together, our in vivo and in vitro functional studies of POLRMT variants establish defective mitochondrial transcription as an important disease mechanism.
Keywords: Adolescent; Adult; Child; DNA, Mitochondrial; DNA-Directed RNA Polymerases; Female; Fibroblasts; Humans; Infant; Male; Mitochondria; Mutation; Nervous System Diseases; Oxidative Phosphorylation; Pedigree; Protein Domains; Protein Subunits; RNA, Messenger; Transcription, Genetic; Young Adult

Rapid response to the alpha-1 adrenergic agent phenylephrine in the perioperative period is impacted by genomics and ancestry. - Wenric, Stephane; Jeff, Janina M; Joseph, Thomas; Yee, Muh-Ching; Belbin, Gillian M; Owusu Obeng, Aniwaa; Ellis, Stephen B; Bottinger, Erwin P; Gottesman, Omri; Levin, Matthew A; Kenny, Eimear E (Pharmacogenomics J, 2021)
The emergence of genomic data in biobanks and health systems offers new ways to derive medically important phenotypes, including acute phenotypes occurring during inpatient clinical care. Here we study the genetic underpinnings of the rapid response to phenylephrine, an α1-adrenergic receptor agonist commonly used to treat hypotension during anesthesia and surgery. We quantified this response by extracting blood pressure (BP) measurements 5 min before and after the administration of phenylephrine. Based on this derived phenotype, we show that systematic differences exist between self-reported ancestry groups: European-Americans (EA; n = 1387) have a significantly higher systolic response to phenylephrine than African-Americans (AA; n = 1217) and Hispanic/Latinos (HA; n = 1713) (31.3% increase, p value < 6e-08 and 22.9% increase, p value < 5e-05 respectively), after adjusting for genetic ancestry, demographics, and relevant clinical covariates. We performed a genome-wide association study to investigate genetic factors underlying individual differences in this derived phenotype. We discovered genome-wide significant association signals in loci and genes previously associated with BP measured in ambulatory settings, and a general enrichment of association in these genes. Finally, we discovered two low frequency variants, present at ~1% in EAs and AAs, respectively, where patients carrying one copy of these variants show no phenylephrine response. This work demonstrates our ability to derive a quantitative phenotype suited for comparative statistics and genome-wide association studies from dense clinical and physiological measures captured for managing patients during surgery. We identify genetic variants underlying non response to phenylephrine, with implications for preemptive pharmacogenomic screening to improve safety during surgery.

A relatively common homozygous TRAPPC4 splicing variant is associated with an early-infantile neurodegenerative syndrome. - Ghosh, Shereen G; Scala, Marcello; Beetz, Christian; Helman, Guy; Stanley, Valentina; Yang, Xiaoxu; Breuss, Martin W; Mazaheri, Neda; Selim, Laila; Hadipour, Fatemeh; Pais, Lynn; Stutterd, Chloe A; et al. (Eur J Hum Genet, 2021)
Trafficking protein particle (TRAPP) complexes, which include the TRAPPC4 protein, regulate membrane trafficking between lipid organelles in a process termed vesicular tethering. TRAPPC4 was recently implicated in a recessive neurodevelopmental condition in four unrelated families due to a shared c.454+3A>G splice variant. Here, we report 23 patients from 17 independent families with an early-infantile-onset neurodegenerative presentation, where we also identified the homozygous variant hg38:11:119020256 A>G (NM_016146.5:c.454+3A>G) in TRAPPC4 through exome or genome sequencing. No other clinically relevant TRAPPC4 variants were identified among any of over 10,000 patients with neurodevelopmental conditions. We found the carrier frequency of TRAPPC4 c.454+3A>G was 2.4-5.4 per 10,000 healthy individuals. Affected individuals with the homozygous TRAPPC4 c.454+3A>G variant showed profound psychomotor delay, developmental regression, early-onset epilepsy, microcephaly and progressive spastic tetraplegia. Based upon RNA sequencing, the variant resulted in partial exon 3 skipping and generation of an aberrant transcript owing to use of a downstream cryptic splice donor site, predicting a premature stop codon and nonsense mediated decay. These data confirm the pathogenicity of the TRAPPC4 c.454+3A>G variant, and refine the clinical presentation of TRAPPC4-related encephalopathy.

SPEN haploinsufficiency causes a neurodevelopmental disorder overlapping proximal 1p36 deletion syndrome with an episignature of X chromosomes in females. - Radio, Francesca Clementina; Pang, Kaifang; Ciolfi, Andrea; Levy, Michael A; Hernandez-Garcia, Andres; Pedace, Lucia; Pantaleoni, Francesca; Liu, Zhandong; de Boer, Elke; Jackson, Adam; Bruselles, Alessandro; McConkey, Haley; et al. (Am J Hum Genet, 2021)
Deletion 1p36 (del1p36) syndrome is the most common human disorder resulting from a terminal autosomal deletion. This condition is molecularly and clinically heterogeneous. Deletions involving two non-overlapping regions, known as the distal (telomeric) and proximal (centromeric) critical regions, are sufficient to cause the majority of the recurrent clinical features, although with different facial features and dysmorphisms. SPEN encodes a transcriptional repressor commonly deleted in proximal del1p36 syndrome and is located centromeric to the proximal 1p36 critical region. Here, we used clinical data from 34 individuals with truncating variants in SPEN to define a neurodevelopmental disorder presenting with features that overlap considerably with those of proximal del1p36 syndrome. The clinical profile of this disease includes developmental delay/intellectual disability, autism spectrum disorder, anxiety, aggressive behavior, attention deficit disorder, hypotonia, brain and spine anomalies, congenital heart defects, high/narrow palate, facial dysmorphisms, and obesity/increased BMI, especially in females. SPEN also emerges as a relevant gene for del1p36 syndrome by co-expression analyses. Finally, we show that haploinsufficiency of SPEN is associated with a distinctive DNA methylation episignature of the X chromosome in affected females, providing further evidence of a specific contribution of the protein to the epigenetic control of this chromosome, and a paradigm of an X chromosome-specific episignature that classifies syndromic traits. We conclude that SPEN is required for multiple developmental processes and SPEN haploinsufficiency is a major contributor to a disorder associated with deletions centromeric to the previously established 1p36 critical regions.
Keywords: Adolescent; Autism Spectrum Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosome Disorders; Chromosomes, Human, Pair 1; Chromosomes, Human, X; DNA Methylation; DNA-Binding Proteins; Epigenesis, Genetic; Female; Haploinsufficiency; Humans; Intellectual Disability; Male; Neurodevelopmental Disorders; Phenotype; RNA-Binding Proteins; Young Adult

TMEM218 dysfunction causes ciliopathies, including Joubert and Meckel syndromes. - Van De Weghe, Julie C; Giordano, Jessica L; Mathijssen, Inge B; Mojarrad, Majid; Lugtenberg, Dorien; Miller, Caitlin V; Dempsey, Jennifer C; Mohajeri, Mahsa Sadat Asl; van Leeuwen, Elizabeth; Pajkrt, Eva; Klaver, Caroline C W; Houlden, Henry; et al. (HGG Adv, 2021)
The Joubert-Meckel syndrome spectrum is a continuum of recessive ciliopathy conditions caused by primary cilium dysfunction. The primary cilium is a microtubule-based, antenna-like organelle that projects from the surface of most human cell types, allowing them to respond to extracellular signals. The cilium is partitioned from the cell body by the transition zone, a known hotspot for ciliopathy-related proteins. Despite years of Joubert syndrome (JBTS) gene discovery, the genetic cause cannot be identified in up to 30% of individuals with JBTS, depending on the cohort, sequencing method, and criteria for pathogenic variants. Using exome and targeted sequencing of 655 families with JBTS, we identified three individuals from two families harboring biallelic, rare, predicted-deleterious missense variants. Via MatchMaker Exchange, we identified biallelic variants in four additional families with ciliopathy phenotypes. Of note, four of the six families carry missense variants affecting the same highly conserved amino acid position 115. Clinical features included the molar tooth sign (N = 2), occipital encephalocele (N = 5, all fetuses), retinal dystrophy (N = 4, all living individuals), polycystic kidneys (N = 2), and polydactyly (N = 2), without liver involvement. Combined with existing functional data linking TMEM218 to ciliary transition zone function, our human genetic data make a strong case for TMEM218 dysfunction as a cause of ciliopathy phenotypes including JBTS with retinal dystrophy and Meckel syndrome. Identifying all genetic causes of the Joubert-Meckel spectrum enables diagnostic testing, prognostic and recurrence risk counseling, and medical monitoring, as well as work to delineate the underlying biological mechanisms and identify targets for future therapies.

Towards population-scale long-read sequencing. - De Coster, Wouter; Weissensteiner, Matthias H; Sedlazeck, Fritz J (Nat Rev Genet, 2021)
Long-read sequencing technologies have now reached a level of accuracy and yield that allows their application to variant detection at a scale of tens to thousands of samples. Concomitant with the development of new computational tools, the first population-scale studies involving long-read sequencing have emerged over the past 2 years and, given the continuous advancement of the field, many more are likely to follow. In this Review, we survey recent developments in population-scale long-read sequencing, highlight potential challenges of a scaled-up approach and provide guidance regarding experimental design. We provide an overview of current long-read sequencing platforms, variant calling methodologies and approaches for de novo assemblies and reference-based mapping approaches. Furthermore, we summarize strategies for variant validation, genotyping and predicting functional impact and emphasize challenges remaining in achieving long-read sequencing at a population scale.

Typical achondroplasia secondary to a unique insertional variant of FGFR3 with in vitro demonstration of its effect on FGFR3 function. - Meyer, April N; Modaff, Peggy; Wang, Clark G; Wohler, Elizabeth; Sobreira, Nara L; Donoghue, Daniel J; Pauli, Richard M (Am J Med Genet A, 2021)
We describe an individual in whom clinical and radiographic features are typical for achondroplasia, but in whom the common variants of FGFR3 that result in achondroplasia are absent. Whole exome sequencing demonstrated a novel, de novo 6 base pair tandem duplication in FGFR3 that results in the insertion of Ser-Phe after position Leu324. in vitro studies showed that this variant results in aberrant dimerization, excessive spontaneous phosphorylation of FGFR3 dimers and excessive, ligand-independent tyrosine kinase activity. Together, these data suggest that this variant leads to constitutive disulfide bond-mediated dimerization, and that this, surprisingly, occurs to an extent similar to the neonatal lethal thanatophoric dysplasia type I Ser249Cys variant.

Variants in GNAI1 cause a syndrome associated with variable features including developmental delay, seizures, and hypotonia. - Muir, Alison M; Gardner, Jennifer F; van Jaarsveld, Richard H; de Lange, Iris M; van der Smagt, Jasper J; Wilson, Golder N; Dubbs, Holly; Goldberg, Ethan M; Zitano, Lia; Bupp, Caleb; Martinez, Jose; Srour, Myriam; et al. (Genet Med, 2021)
PURPOSE: Neurodevelopmental disorders (NDDs) encompass a spectrum of genetically heterogeneous disorders with features that commonly include developmental delay, intellectual disability, and autism spectrum disorders. We sought to delineate the molecular and phenotypic spectrum of a novel neurodevelopmental disorder caused by variants in the GNAI1 gene. METHODS: Through large cohort trio-based exome sequencing and international data-sharing, we identified 24 unrelated individuals with NDD phenotypes and a variant in GNAI1, which encodes the inhibitory Gαi1 subunit of heterotrimeric G-proteins. We collected detailed genotype and phenotype information for each affected individual. RESULTS: We identified 16 unique variants in GNAI1 in 24 affected individuals; 23 occurred de novo and 1 was inherited from a mosaic parent. Most affected individuals have a severe neurodevelopmental disorder. Core features include global developmental delay, intellectual disability, hypotonia, and epilepsy. CONCLUSION: This collaboration establishes GNAI1 variants as a cause of NDDs. GNAI1-related NDD is most often characterized by severe to profound delays, hypotonia, epilepsy that ranges from self-limiting to intractable, behavior problems, and variable mild dysmorphic features.
Keywords: Child; Developmental Disabilities; Humans; Intellectual Disability; Muscle Hypotonia; Neurodevelopmental Disorders; Seizures; Whole Exome Sequencing

Whole-genome sequencing of African Americans implicates differential genetic architecture in inflammatory bowel disease. - Somineni, Hari K; Nagpal, Sini; Venkateswaran, Suresh; Cutler, David J; Okou, David T; Haritunians, Talin; Simpson, Claire L; Begum, Ferdouse; Datta, Lisa W; Quiros, Antonio J; Seminerio, Jenifer; Mengesha, Emebet; et al. (Am J Hum Genet, 2021)
Whether or not populations diverge with respect to the genetic contribution to risk of specific complex diseases is relevant to understanding the evolution of susceptibility and origins of health disparities. Here, we describe a large-scale whole-genome sequencing study of inflammatory bowel disease encompassing 1,774 affected individuals and 1,644 healthy control Americans with African ancestry (African Americans). Although no new loci for inflammatory bowel disease are discovered at genome-wide significance levels, we identify numerous instances of differential effect sizes in combination with divergent allele frequencies. For example, the major effect at PTGER4 fine maps to a single credible interval of 22 SNPs corresponding to one of four independent associations at the locus in European ancestry individuals but with an elevated odds ratio for Crohn disease in African Americans. A rare variant aggregate analysis implicates Ca-binding neuro-immunomodulator CALB2 in ulcerative colitis. Highly significant overall overlap of common variant risk for inflammatory bowel disease susceptibility between individuals with African and European ancestries was observed, with 41 of 241 previously known lead variants replicated and overall correlations in effect sizes of 0.68 for combined inflammatory bowel disease. Nevertheless, subtle differences influence the performance of polygenic risk scores, and we show that ancestry-appropriate weights significantly improve polygenic prediction in the highest percentiles of risk. The median amount of variance explained per locus remains the same in African and European cohorts, providing evidence for compensation of effect sizes as allele frequencies diverge, as expected under a highly polygenic model of disease.
Keywords: African Americans; Aged; Aged, 80 and over; Calbindin 2; Colitis, Ulcerative; Crohn Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammatory Bowel Diseases; Male; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Receptors, Prostaglandin E, EP4 Subtype; Whole Genome Sequencing

Analysis of cardiac magnetic resonance imaging in 36,000 individuals yields genetic insights into dilated cardiomyopathy. - Pirruccello, James P; Bick, Alexander; Wang, Minxian; Chaffin, Mark; Friedman, Samuel; Yao, Jie; Guo, Xiuqing; Venkatesh, Bharath Ambale; Taylor, Kent D; Post, Wendy S; Rich, Stephen; Lima, Joao A C; et al. (Nat Commun, 2020)
Dilated cardiomyopathy (DCM) is an important cause of heart failure and the leading indication for heart transplantation. Many rare genetic variants have been associated with DCM, but common variant studies of the disease have yielded few associated loci. As structural changes in the heart are a defining feature of DCM, we report a genome-wide association study of cardiac magnetic resonance imaging (MRI)-derived left ventricular measurements in 36,041 UK Biobank participants, with replication in 2184 participants from the Multi-Ethnic Study of Atherosclerosis. We identify 45 previously unreported loci associated with cardiac structure and function, many near well-established genes for Mendelian cardiomyopathies. A polygenic score of MRI-derived left ventricular end systolic volume strongly associates with incident DCM in the general population. Even among carriers of TTN truncating mutations, this polygenic score influences the size and function of the human heart. These results further implicate common genetic polymorphisms in the pathogenesis of DCM.
Keywords: Cardiomyopathy, Dilated; Genome-Wide Association Study; Heart; Humans; Magnetic Resonance Imaging; Myocardium; Polymorphism, Single Nucleotide

Association of Rare Pathogenic DNA Variants for Familial Hypercholesterolemia, Hereditary Breast and Ovarian Cancer Syndrome, and Lynch Syndrome With Disease Risk in Adults According to Family History. - Patel, Aniruddh P; Wang, Minxian; Fahed, Akl C; Mason-Suares, Heather; Brockman, Deanna; Pelletier, Renee; Amr, Sami; Machini, Kalotina; Hawley, Megan; Witkowski, Leora; Koch, Christopher; Philippakis, Anthony; et al. (JAMA Netw Open, 2020)
Importance: Pathogenic DNA variants associated with familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome are widely recognized as clinically important and actionable when identified, leading some clinicians to recommend population-wide genomic screening. Objectives: To assess the prevalence and clinical importance of pathogenic or likely pathogenic variants associated with each of 3 genomic conditions (familial hypercholesterolemia, hereditary breast and ovarian cancer syndrome, and Lynch syndrome) within the context of contemporary clinical care. Design, Setting, and Participants: This cohort study used gene-sequencing data from 49 738 participants in the UK Biobank who were recruited from 22 sites across the UK between March 21, 2006, and October 1, 2010. Inpatient hospital data date back to 1977; cancer registry data, to 1957; and death registry data, to 2006. Statistical analysis was performed from July 22, 2019, to November 15, 2019. Exposures: Pathogenic or likely pathogenic DNA variants classified by a clinical laboratory geneticist. Main Outcomes and Measures: Composite end point specific to each genomic condition based on atherosclerotic cardiovascular disease events for familial hypercholesterolemia, breast or ovarian cancer for hereditary breast and ovarian cancer syndrome, and colorectal or uterine cancer for Lynch syndrome. Results: Among 49 738 participants (mean [SD] age, 57 [8] years; 27 144 female [55%]), 441 (0.9%) harbored a pathogenic or likely pathogenic variant associated with any of 3 genomic conditions, including 131 (0.3%) for familial hypercholesterolemia, 235 (0.5%) for hereditary breast and ovarian cancer syndrome, and 76 (0.2%) for Lynch syndrome. Presence of these variants was associated with increased risk of disease: for familial hypercholesterolemia, 28 of 131 carriers (21.4%) vs 4663 of 49 607 noncarriers (9.4%) developed atherosclerotic cardiovascular disease; for hereditary breast and ovarian cancer syndrome, 32 of 116 female carriers (27.6%) vs 2080 of 27 028 female noncarriers (7.7%) developed associated cancers; and for Lynch syndrome, 17 of 76 carriers (22.4%) vs 929 of 49 662 noncarriers (1.9%) developed colorectal or uterine cancer. The predicted probability of disease at age 75 years despite contemporary clinical care was 45.3% for carriers of familial hypercholesterolemia, 41.1% for hereditary breast and ovarian cancer syndrome, and 38.3% for Lynch syndrome. Across the 3 conditions, 39.7% (175 of 441) of the carriers reported a family history of disease vs 23.2% (34 517 of 148 772) of noncarriers. Conclusions and Relevance: The findings suggest that approximately 1% of the middle-aged adult population in the UK Biobank harbored a pathogenic variant associated with any of 3 genomic conditions. These variants were associated with an increased risk of disease despite contemporary clinical care and were not reliably detected by family history.
Keywords: Aged; Cohort Studies; Colorectal Neoplasms, Hereditary Nonpolyposis; Female; Genetic Predisposition to Disease; Hereditary Breast and Ovarian Cancer Syndrome; Heterozygote; Humans; Hyperlipoproteinemia Type II; Male; Middle Aged; Pedigree; Proportional Hazards Models; United Kingdom; Whole Exome Sequencing

Bi-allelic ADARB1 Variants Associated with Microcephaly, Intellectual Disability, and Seizures. - Tan, Tiong Yang; Sedmík, Jiří; Fitzgerald, Mark P; Halevy, Rivka Sukenik; Keegan, Liam P; Helbig, Ingo; Basel-Salmon, Lina; Cohen, Lior; Straussberg, Rachel; Chung, Wendy K; Helal, Mayada; Maroofian, Reza; et al. (Am J Hum Genet, 2020)
The RNA editing enzyme ADAR2 is essential for the recoding of brain transcripts. Impaired ADAR2 editing leads to early-onset epilepsy and premature death in a mouse model. Here, we report bi-allelic variants in ADARB1, the gene encoding ADAR2, in four unrelated individuals with microcephaly, intellectual disability, and epilepsy. In one individual, a homozygous variant in one of the double-stranded RNA-binding domains (dsRBDs) was identified. In the others, variants were situated in or around the deaminase domain. To evaluate the effects of these variants on ADAR2 enzymatic activity, we performed in vitro assays with recombinant proteins in HEK293T cells and ex vivo assays with fibroblasts derived from one of the individuals. We demonstrate that these ADAR2 variants lead to reduced editing activity on a known ADAR2 substrate. We also demonstrate that one variant leads to changes in splicing of ADARB1 transcript isoforms. These findings reinforce the importance of RNA editing in brain development and introduce ADARB1 as a genetic etiology in individuals with intellectual disability, microcephaly, and epilepsy.
Keywords: Adenosine Deaminase; Alleles; Alternative Splicing; Child; Child, Preschool; Genetic Predisposition to Disease; Genetic Variation; HEK293 Cells; Humans; Intellectual Disability; Male; Microcephaly; RNA Splicing; RNA-Binding Proteins; Seizures

Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

Bi-allelic Variations of SMO in Humans Cause a Broad Spectrum of Developmental Anomalies Due to Abnormal Hedgehog Signaling. - Le, Thuy-Linh; Sribudiani, Yunia; Dong, Xiaomin; Huber, Celine; Kois, Chelsea; Baujat, Geneviève; Gordon, Christopher T; Mayne, Valerie; Galmiche, Louise; Serre, Valérie; Goudin, Nicolas; Zarhrate, Mohammed; et al. (Am J Hum Genet, 2020)
The evolutionarily conserved hedgehog (Hh) pathway is essential for organogenesis and plays critical roles in postnatal tissue maintenance and renewal. A unique feature of the vertebrate Hh pathway is that signal transduction requires the primary cilium (PC) where major pathway components are dynamically enriched. These factors include smoothened (SMO) and patched, which constitute the core reception system for sonic hedgehog (SHH) as well as GLI transcription factors, the key mediators of the pathway. Here, we report bi-allelic loss-of-function variations in SMO in seven individuals from five independent families; these variations cause a wide phenotypic spectrum of developmental anomalies affecting the brain (hypothalamic hamartoma and microcephaly), heart (atrioventricular septal defect), skeleton (postaxial polydactyly, narrow chest, and shortening of long bones), and enteric nervous system (aganglionosis). Cells derived from affected individuals showed normal ciliogenesis but severely altered Hh-signal transduction as a result of either altered PC trafficking or abnormal activation of the pathway downstream of SMO. In addition, Hh-independent GLI2 accumulation at the PC tip in cells from the affected individuals suggests a potential function of SMO in regulating basal ciliary trafficking of GLI2 when the pathway is off. Thus, loss of SMO function results in abnormal PC dynamics of key components of the Hh signaling pathway and leads to a large continuum of malformations in humans.
Keywords: Alleles; Base Sequence; Child; Child, Preschool; Cilia; Developmental Disabilities; Female; Hedgehog Proteins; Humans; Infant; Male; Models, Molecular; Neoplasms; Nerve Tissue Proteins; Nuclear Proteins; Pedigree; Signal Transduction; Smoothened Receptor; Zinc Finger Protein Gli2; Zinc Finger Protein Gli3

Cell type-specific genetic regulation of gene expression across human tissues. - Kim-Hellmuth, Sarah; Aguet, Francois; Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kasela, Silva; Wucher, Valentin; Castel, Stephane E; Hamel, Andrew R; Viñuela, Ana; Roberts, Amy L; Mangul, Serghei; Wen, Xiaoquan; et al. (Science, 2020)
The Genotype-Tissue Expression (GTEx) project has identified expression and splicing quantitative trait loci in cis (QTLs) for the majority of genes across a wide range of human tissues. However, the functional characterization of these QTLs has been limited by the heterogeneous cellular composition of GTEx tissue samples. We mapped interactions between computational estimates of cell type abundance and genotype to identify cell type-interaction QTLs for seven cell types and show that cell type-interaction expression QTLs (eQTLs) provide finer resolution to tissue specificity than bulk tissue cis-eQTLs. Analyses of genetic associations with 87 complex traits show a contribution from cell type-interaction QTLs and enables the discovery of hundreds of previously unidentified colocalized loci that are masked in bulk tissue.
Keywords: Cells; Gene Expression Regulation; Humans; Organ Specificity; Quantitative Trait Loci; RNA, Long Noncoding; Transcriptome

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Yuan, Bo; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exons; Humans; INDEL Mutation; Retrospective Studies; Whole Exome Sequencing

Collagen VI-related limb-girdle syndrome caused by frequent mutation in COL6A3 gene with conflicting reports of pathogenicity. - Stavusis, Janis; Micule, Ieva; Wright, Nathan T; Straub, Volker; Topf, Ana; Panadés-de Oliveira, Luísa; Domínguez-González, Cristina; Inashkina, Inna; Kidere, Dita; Chrestian, Nicolas; Lace, Baiba (Neuromuscul Disord, 2020)
Recently the scientific community has started to view Bethlem myopathy 1 and Ullrich congenital muscular dystrophy as two extremes of a collagen VI-related myopathy spectrum rather than two separate entities, as both are caused by mutations in one of the collagen VI genes. Here we report three individuals in two families who are homozygous for a COL6A3 mutation (c.7447A> G; p.Lys2483Glu), and compare their clinical features with seven previously published cases. Individuals carrying homozygous or compound heterozygous c.7447A> G, (p.Lys2483Glu) mutation exhibit mild phenotype without loss of ambulation, similar to the cases described previously as Collagen VI-related limb-girdle syndrome. The phenotype could arise due to an aberrant assembly of Von Willebrand factor A domains. Based on these data, we propose that c.7447A> G, (p.Lys2483Glu) is a common pathogenic mutation.

Combining Imaging and Genetics to Predict Recurrence of Anticoagulation-Associated Intracerebral Hemorrhage. - Biffi, Alessandro; Urday, Sebastian; Kubiszewski, Patryk; Gilkerson, Lee; Sekar, Padmini; Rodriguez-Torres, Axana; Bettin, Margaret; Charidimou, Andreas; Pasi, Marco; Kourkoulis, Christina; Schwab, Kristin; DiPucchio, Zora; et al. (Stroke, 2020)
BACKGROUND AND PURPOSE: For survivors of oral anticoagulation therapy (OAT)-associated intracerebral hemorrhage (OAT-ICH) who are at high risk for thromboembolism, the benefits of OAT resumption must be weighed against increased risk of recurrent hemorrhagic stroke. The ε2/ε4 alleles of the () gene, MRI-defined cortical superficial siderosis, and cerebral microbleeds are the most potent risk factors for recurrent ICH. We sought to determine whether combining MRI markers and genotype could have clinical impact by identifying ICH survivors in whom the risks of OAT resumption are highest. METHODS: Joint analysis of data from 2 longitudinal cohort studies of OAT-ICH survivors: (1) MGH-ICH study (Massachusetts General Hospital ICH) and (2) longitudinal component of the ERICH study (Ethnic/Racial Variations of Intracerebral Hemorrhage). We evaluated whether MRI markers and genotype predict ICH recurrence. We then developed and validated a combined -MRI classification scheme to predict ICH recurrence, using Classification and Regression Tree analysis. RESULTS: Cortical superficial siderosis, cerebral microbleed, and ε2/ε4 variants were independently associated with ICH recurrence after OAT-ICH (all <0.05). Combining genotype and MRI data resulted in improved prediction of ICH recurrence (Harrell C: 0.79 versus 0.55 for clinical data alone, =0.033). In the MGH (training) data set, CSS, cerebral microbleed, and ε2/ε4 stratified likelihood of ICH recurrence into high-, medium-, and low-risk categories. In the ERICH (validation) data set, yearly ICH recurrence rates for high-, medium-, and low-risk individuals were 6.6%, 2.5%, and 0.9%, respectively, with overall area under the curve of 0.91 for prediction of recurrent ICH. CONCLUSIONS: Combining MRI and genotype stratifies likelihood of ICH recurrence into high, medium, and low risk. If confirmed in prospective studies, this combined -MRI classification scheme may prove useful for selecting individuals for OAT resumption after ICH.
Keywords: Aged; Anticoagulants; Apolipoprotein E4; Cerebral Hemorrhage; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Recurrence

A common variant in PNPLA3 is associated with age at diagnosis of NAFLD in patients from a multi-ethnic biobank. - Walker, Ryan W; Belbin, Gillian M; Sorokin, Elena P; Van Vleck, Tielman; Wojcik, Genevieve L; Moscati, Arden; Gignoux, Christopher R; Cho, Judy; Abul-Husn, Noura S; Nadkarni, Girish; Kenny, Eimear E; Loos, Ruth J F (J Hepatol, 2020)
BACKGROUND & AIMS: The Ile138Met variant (rs738409) in the PNPLA3 gene has the largest effect on non-alcoholic fatty liver disease (NAFLD), increasing the risk of progression to severe forms of liver disease. It remains unknown if the variant plays a role in age of NAFLD onset. We aimed to determine if rs738409 impacts on the age of NAFLD diagnosis. METHODS: We applied a novel natural language processing (NLP) algorithm to a longitudinal electronic health records (EHR) dataset of >27,000 individuals with genetic data from a multi-ethnic biobank, defining NAFLD cases (n = 1,703) and confirming controls (n = 8,119). We conducted i) a survival analysis to determine if age at diagnosis differed by rs738409 genotype, ii) a receiver operating characteristics analysis to assess the utility of the rs738409 genotype in discriminating NAFLD cases from controls, and iii) a phenome-wide association study (PheWAS) between rs738409 and 10,095 EHR-derived disease diagnoses. RESULTS: The PNPLA3 G risk allele was associated with: i) earlier age of NAFLD diagnosis, with the strongest effect in Hispanics (hazard ratio 1.33; 95% CI 1.15-1.53; p <0.0001) among whom a NAFLD diagnosis was 15% more likely in risk allele carriers vs. non-carriers; ii) increased NAFLD risk (odds ratio 1.61; 95% CI 1.349-1.73; p <0.0001), with the strongest effect among Hispanics (odds ratio 1.43; 95% CI 1.28-1.59; p <0.0001); iii) additional liver diseases in a PheWAS (p <4.95 × 10) where the risk variant also associated with earlier age of diagnosis. CONCLUSION: Given the role of the rs738409 in NAFLD diagnosis age, our results suggest that stratifying risk within populations known to have an enhanced risk of liver disease, such as Hispanic carriers of the rs738409 variant, would be effective in earlier identification of those who would benefit most from early NAFLD prevention and treatment strategies. LAY SUMMARY: Despite clear associations between the PNPLA3 rs738409 variant and elevated risk of progression from non-alcoholic fatty liver disease (NAFLD) to more severe forms of liver disease, it remains unknown if PNPLA3 rs738409 plays a role in the age of NAFLD onset. Herein, we found that this risk variant is associated with an earlier age of NAFLD and other liver disease diagnoses; an observation most pronounced in Hispanic Americans. We conclude that PNPLA3 rs738409 could be used to better understand liver disease risk within vulnerable populations and identify patients that may benefit from early prevention strategies.

Congenital diaphragmatic hernia as a prominent feature of a SPECC1L-related syndrome. - Wild, K Taylor; Gordon, Tia; Bhoj, Elizabeth J; Du, Haowei; Jhangiani, Shalini N; Posey, Jennifer E; Lupski, James R; Scott, Daryl A; Zackai, Elaine H (Am J Med Genet A, 2020)
Congenital diaphragmatic hernias (CDH) confer substantial morbidity and mortality. Genetic defects, including chromosomal anomalies, copy number variants, and sequence variants are identified in ~30% of patients with CDH. A genetic etiology is not yet found in 70% of patients, however there is a growing number of genetic syndromes and single gene disorders associated with CDH. While there have been two reported individuals with X-linked Opitz G/BBB syndrome with MID1 mutations who have CDH as an associated feature, CDH appears to be a much more prominent feature of a SPECC1L-related autosomal dominant Opitz G/BBB syndrome. Features unique to autosomal dominant Opitz G/BBB syndrome include branchial fistulae, omphalocele, and a bicornuate uterus. Here we present one new individual and five previously reported individuals with CDH found to have SPECC1L mutations. These cases provide strong evidence that SPECC1L is a bona fide CDH gene. We conclude that a SPECC1L-related Opitz G/BBB syndrome should be considered in any patient with CDH who has additional features of hypertelorism, a prominent forehead, a broad nasal bridge, anteverted nares, cleft lip/palate, branchial fistulae, omphalocele, and/or bicornuate uterus.

DAAM2 Variants Cause Nephrotic Syndrome via Actin Dysregulation. - Schneider, Ronen; Deutsch, Konstantin; Hoeprich, Gregory J; Marquez, Jonathan; Hermle, Tobias; Braun, Daniela A; Seltzsam, Steve; Kitzler, Thomas M; Mao, Youying; Buerger, Florian; Majmundar, Amar J; Onuchic-Whitford, Ana C; et al. (Am J Hum Genet, 2020)
The discovery of >60 monogenic causes of nephrotic syndrome (NS) has revealed a central role for the actin regulators RhoA/Rac1/Cdc42 and their effectors, including the formin INF2. By whole-exome sequencing (WES), we here discovered bi-allelic variants in the formin DAAM2 in four unrelated families with steroid-resistant NS. We show that DAAM2 localizes to the cytoplasm in podocytes and in kidney sections. Further, the variants impair DAAM2-dependent actin remodeling processes: wild-type DAAM2 cDNA, but not cDNA representing missense variants found in individuals with NS, rescued reduced podocyte migration rate (PMR) and restored reduced filopodia formation in shRNA-induced DAAM2-knockdown podocytes. Filopodia restoration was also induced by the formin-activating molecule IMM-01. DAAM2 also co-localizes and co-immunoprecipitates with INF2, which is intriguing since variants in both formins cause NS. Using in vitro bulk and TIRF microscopy assays, we find that DAAM2 variants alter actin assembly activities of the formin. In a Xenopus daam2-CRISPR knockout model, we demonstrate actin dysregulation in vivo and glomerular maldevelopment that is rescued by WT-DAAM2 mRNA. We conclude that DAAM2 variants are a likely cause of monogenic human SRNS due to actin dysregulation in podocytes. Further, we provide evidence that DAAM2-associated SRNS may be amenable to treatment using actin regulating compounds.
Keywords: Actins; Alleles; Animals; Animals, Genetically Modified; Cell Movement; Cytoplasm; Formins; Genetic Variation; Humans; Kidney; Kidney Glomerulus; Microfilament Proteins; Mutation, Missense; Nephrotic Syndrome; Podocytes; Pseudopodia; rho GTP-Binding Proteins; RNA, Small Interfering; Whole Exome Sequencing; Xenopus

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Deciphering congenital anomalies for the next generation. - Wojcik, Monica H; Agrawal, Pankaj B (Cold Spring Harb Mol Case Stud, 2020)
Congenital anomalies are common, with 2%-3% of infants estimated to have at least one major congenital malformation and countless others with minor malformations of lesser cosmetic or medical importance. As congenital malformations are major drivers of morbidity and mortality, representing the leading cause of infant mortality in the United States, there is substantial interest in understanding the underlying etiologies-particularly if modifiable causes may be identified or pre- or postnatal treatments can be offered. Recent research has begun to reveal the spectrum of monogenic disorders that commonly result in birth defects, and newer approaches have revealed non-Mendelian genetic contributions including gene-environment interactions. Our experience suggests that increased efforts to sequence and analyze cases of perinatal death, as well as continued global collaboration, will be essential in understanding the genomic landscape of structural anomalies.
Keywords: Congenital Abnormalities; Family Characteristics; Female; Humans; Infant; Pregnancy

Defective glycosylation and multisystem abnormalities characterize the primary immunodeficiency XMEN disease. - Ravell, Juan C; Matsuda-Lennikov, Mami; Chauvin, Samuel D; Zou, Juan; Biancalana, Matthew; Deeb, Sally J; Price, Susan; Su, Helen C; Notarangelo, Giulia; Jiang, Ping; Morawski, Aaron; Kanellopoulou, Chrysi; et al. (J Clin Invest, 2020)
X-linked immunodeficiency with magnesium defect, EBV infection, and neoplasia (XMEN) disease are caused by deficiency of the magnesium transporter 1 (MAGT1) gene. We studied 23 patients with XMEN, 8 of whom were EBV naive. We observed lymphadenopathy (LAD), cytopenias, liver disease, cavum septum pellucidum (CSP), and increased CD4-CD8-B220-TCRαβ+ T cells (αβDNTs), in addition to the previously described features of an inverted CD4/CD8 ratio, CD4+ T lymphocytopenia, increased B cells, dysgammaglobulinemia, and decreased expression of the natural killer group 2, member D (NKG2D) receptor. EBV-associated B cell malignancies occurred frequently in EBV-infected patients. We studied patients with XMEN and patients with autoimmune lymphoproliferative syndrome (ALPS) by deep immunophenotyping (32 immune markers) using time-of-flight mass cytometry (CyTOF). Our analysis revealed that the abundance of 2 populations of naive B cells (CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4++CD10+CD38+ and CD20+CD27-CD22+IgM+HLA-DR+CXCR5+CXCR4+CD10-CD38-) could differentially classify XMEN, ALPS, and healthy individuals. We also performed glycoproteomics analysis on T lymphocytes and show that XMEN disease is a congenital disorder of glycosylation that affects a restricted subset of glycoproteins. Transfection of MAGT1 mRNA enabled us to rescue proteins with defective glycosylation. Together, these data provide new clinical and pathophysiological foundations with important ramifications for the diagnosis and treatment of XMEN disease.
Keywords: Antigens, CD; Autoimmune Lymphoproliferative Syndrome; Cation Transport Proteins; CD4-CD8 Ratio; Female; Glycosylation; Humans; Magnesium Deficiency; Male; X-Linked Combined Immunodeficiency Diseases

Deficiencies in vesicular transport mediated by TRAPPC4 are associated with severe syndromic intellectual disability. - Van Bergen, Nicole J; Guo, Yiran; Al-Deri, Noraldin; Lipatova, Zhanna; Stanga, Daniela; Zhao, Sarah; Murtazina, Rakhilya; Gyurkovska, Valeriya; Pehlivan, Davut; Mitani, Tadahiro; Gezdirici, Alper; Antony, Jayne; et al. (Brain, 2020)
The conserved transport protein particle (TRAPP) complexes regulate key trafficking events and are required for autophagy. TRAPPC4, like its yeast Trs23 orthologue, is a core component of the TRAPP complexes and one of the essential subunits for guanine nucleotide exchange factor activity for Rab1 GTPase. Pathogenic variants in specific TRAPP subunits are associated with neurological disorders. We undertook exome sequencing in three unrelated families of Caucasian, Turkish and French-Canadian ethnicities with seven affected children that showed features of early-onset seizures, developmental delay, microcephaly, sensorineural deafness, spastic quadriparesis and progressive cortical and cerebellar atrophy in an effort to determine the genetic aetiology underlying neurodevelopmental disorders. All seven affected subjects shared the same identical rare, homozygous, potentially pathogenic variant in a non-canonical, well-conserved splice site within TRAPPC4 (hg19:chr11:g.118890966A>G; TRAPPC4: NM_016146.5; c.454+3A>G). Single nucleotide polymorphism array analysis revealed there was no haplotype shared between the tested Turkish and Caucasian families suggestive of a variant hotspot region rather than a founder effect. In silico analysis predicted the variant to cause aberrant splicing. Consistent with this, experimental evidence showed both a reduction in full-length transcript levels and an increase in levels of a shorter transcript missing exon 3, suggestive of an incompletely penetrant splice defect. TRAPPC4 protein levels were significantly reduced whilst levels of other TRAPP complex subunits remained unaffected. Native polyacrylamide gel electrophoresis and size exclusion chromatography demonstrated a defect in TRAPP complex assembly and/or stability. Intracellular trafficking through the Golgi using the marker protein VSVG-GFP-ts045 demonstrated significantly delayed entry into and exit from the Golgi in fibroblasts derived from one of the affected subjects. Lentiviral expression of wild-type TRAPPC4 in these fibroblasts restored trafficking, suggesting that the trafficking defect was due to reduced TRAPPC4 levels. Consistent with the recent association of the TRAPP complex with autophagy, we found that the fibroblasts had a basal autophagy defect and a delay in autophagic flux, possibly due to unsealed autophagosomes. These results were validated using a yeast trs23 temperature sensitive variant that exhibits constitutive and stress-induced autophagic defects at permissive temperature and a secretory defect at restrictive temperature. In summary we provide strong evidence for pathogenicity of this variant in a member of the core TRAPP subunit, TRAPPC4 that associates with vesicular trafficking and autophagy defects. This is the first report of a TRAPPC4 variant, and our findings add to the growing number of TRAPP-associated neurological disorders.
Keywords: Atrophy; Autophagy; Cerebellum; Cerebral Cortex; Child; Child, Preschool; Craniofacial Abnormalities; Deafness; Developmental Disabilities; Epilepsy; Female; Fibroblasts; Hearing Loss, Sensorineural; Humans; Infant; Infant, Newborn; Intellectual Disability; Male; Microcephaly; Microscopy, Fluorescence; Muscle Spasticity; Nerve Tissue Proteins; Neurodevelopmental Disorders; Pedigree; Quadriplegia; RNA Splice Sites; Syndrome; Vesicular Transport Proteins

Discovery and population genomics of structural variation in a songbird genus. - Weissensteiner, Matthias H; Bunikis, Ignas; Catalán, Ana; Francoijs, Kees-Jan; Knief, Ulrich; Heim, Wieland; Peona, Valentina; Pophaly, Saurabh D; Sedlazeck, Fritz J; Suh, Alexander; Warmuth, Vera M; Wolf, Jochen B W (Nat Commun, 2020)
Structural variation (SV) constitutes an important type of genetic mutations providing the raw material for evolution. Here, we uncover the genome-wide spectrum of intra- and interspecific SV segregating in natural populations of seven songbird species in the genus Corvus. Combining short-read (N = 127) and long-read re-sequencing (N = 31), as well as optical mapping (N = 16), we apply both assembly- and read mapping approaches to detect SV and characterize a total of 220,452 insertions, deletions and inversions. We exploit sampling across wide phylogenetic timescales to validate SV genotypes and assess the contribution of SV to evolutionary processes in an avian model of incipient speciation. We reveal an evolutionary young (~530,000 years) cis-acting 2.25-kb LTR retrotransposon insertion reducing expression of the NDP gene with consequences for premating isolation. Our results attest to the wealth and evolutionary significance of SV segregating in natural populations and highlight the need for reliable SV genotyping.
Keywords: Animals; Chromosome Inversion; Gene Deletion; Genetic Variation; Genetics, Population; Genome; Genomic Structural Variation; Genotype; Phylogeny; Polymorphism, Single Nucleotide; Retroelements; Sequence Analysis, DNA; Songbirds

Distinct effects on mRNA export factor GANP underlie neurological disease phenotypes and alter gene expression depending on intron content. - Woldegebriel, Rosa; Kvist, Jouni; Andersson, Noora; Õunap, Katrin; Reinson, Karit; Wojcik, Monica H; Bijlsma, Emilia K; Hoffer, Mariette J V; Ryan, Monique M; Stark, Zornitza; Walsh, Maie; Cuppen, Inge; et al. (Hum Mol Genet, 2020)
Defects in the mRNA export scaffold protein GANP, encoded by the MCM3AP gene, cause autosomal recessive early-onset peripheral neuropathy with or without intellectual disability. We extend here the phenotypic range associated with MCM3AP variants, by describing a severely hypotonic child and a sibling pair with a progressive encephalopathic syndrome. In addition, our analysis of skin fibroblasts from affected individuals from seven unrelated families indicates that disease variants result in depletion of GANP except when they alter critical residues in the Sac3 mRNA binding domain. GANP depletion was associated with more severe phenotypes compared with the Sac3 variants. Patient fibroblasts showed transcriptome alterations that suggested intron content-dependent regulation of gene expression. For example, all differentially expressed intronless genes were downregulated, including ATXN7L3B, which couples mRNA export to transcription activation by association with the TREX-2 and SAGA complexes. Our results provide insight into the molecular basis behind genotype-phenotype correlations in MCM3AP-associated disease and suggest mechanisms by which GANP defects might alter RNA metabolism.

Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Evaluating systematic reanalysis of clinical genomic data in rare disease from single center experience and literature review. - Tan, Natalie B; Stapleton, Rachel; Stark, Zornitza; Delatycki, Martin B; Yeung, Alison; Hunter, Matthew F; Amor, David J; Brown, Natasha J; Stutterd, Chloe A; McGillivray, George; Yap, Patrick; Regan, Matthew; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Our primary aim was to evaluate the systematic reanalysis of singleton exome sequencing (ES) data for unsolved cases referred for any indication. A secondary objective was to undertake a literature review of studies examining the reanalysis of genomic data from unsolved cases. METHODS: We examined data from 58 unsolved cases referred between June 2016 and March 2017. First reanalysis at 4-13 months after the initial report considered genes newly associated with disease since the original analysis; second reanalysis at 9-18 months considered all disease-associated genes. At 25-34 months we reviewed all cases and the strategies which solved them. RESULTS: Reanalysis of existing ES data alone at two timepoints did not yield new diagnoses. Over the same timeframe, 10 new diagnoses were obtained (17%) from additional strategies, such as microarray detection of copy number variation, repeat sequencing to improve coverage, and trio sequencing. Twenty-seven peer-reviewed articles were identified on the literature review, with a median new diagnosis rate via reanalysis of 15% and median reanalysis timeframe of 22 months. CONCLUSION: Our findings suggest that an interval of greater than 18 months from the original report may be optimal for reanalysis. We also recommend a multi-faceted strategy for cases remaining unsolved after singleton ES.

Exome sequencing implicates genetic disruption of prenatal neuro-gliogenesis in sporadic congenital hydrocephalus. - Jin, Sheng Chih; Dong, Weilai; Kundishora, Adam J; Panchagnula, Shreyas; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca L; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra; et al. (Nat Med, 2020)
Congenital hydrocephalus (CH), characterized by enlarged brain ventricles, is considered a disease of excessive cerebrospinal fluid (CSF) accumulation and thereby treated with neurosurgical CSF diversion with high morbidity and failure rates. The poor neurodevelopmental outcomes and persistence of ventriculomegaly in some post-surgical patients highlight our limited knowledge of disease mechanisms. Through whole-exome sequencing of 381 patients (232 trios) with sporadic, neurosurgically treated CH, we found that damaging de novo mutations account for >17% of cases, with five different genes exhibiting a significant de novo mutation burden. In all, rare, damaging mutations with large effect contributed to ~22% of sporadic CH cases. Multiple CH genes are key regulators of neural stem cell biology and converge in human transcriptional networks and cell types pertinent for fetal neuro-gliogenesis. These data implicate genetic disruption of early brain development, not impaired CSF dynamics, as the primary pathomechanism of a significant number of patients with sporadic CH.
Keywords: Brain; Cerebral Ventricles; Exome; Female; Genetic Predisposition to Disease; Humans; Hydrocephalus; Male; Mutation; Neural Stem Cells; Neurogenesis; Neuroglia; Transcription Factors; Tripartite Motif Proteins; Ubiquitin-Protein Ligases; Whole Exome Sequencing

Exome Sequencing Implicates Impaired GABA Signaling and Neuronal Ion Transport in Trigeminal Neuralgia. - Dong, Weilai; Jin, Sheng Chih; Allocco, August; Zeng, Xue; Sheth, Amar H; Panchagnula, Shreyas; Castonguay, Annie; Lorenzo, Louis-Étienne; Islam, Barira; Brindle, Geneviève; Bachand, Karine; Hu, Jamie; et al. (iScience, 2020)
Trigeminal neuralgia (TN) is a common, debilitating neuropathic face pain syndrome often resistant to therapy. The familial clustering of TN cases suggests that genetic factors play a role in disease pathogenesis. However, no unbiased, large-scale genomic study of TN has been performed to date. Analysis of 290 whole exome-sequenced TN probands, including 20 multiplex kindreds and 70 parent-offspring trios, revealed enrichment of rare, damaging variants in GABA receptor-binding genes in cases. Mice engineered with a TN-associated mutation (p.Cys188Trp) in the GABA receptor Cl channel γ-1 subunit () exhibited trigeminal mechanical allodynia and face pain behavior. Other TN probands harbored rare damaging variants in Na and Ca channels, including a significant variant burden in the α-1H subunit of the voltage-gated Ca channel Ca3.2 (). These results provide exome-level insight into TN and implicate genetically encoded impairment of GABA signaling and neuronal ion transport in TN pathogenesis.

Exome sequencing in patients with microphthalmia, anophthalmia, and coloboma (MAC) from a consanguineous population. - Islam, Farrah; Htun, Stephanie; Lai, Li-Wen; Krall, Max; Poranki, Menitha; Martin, Pierre-Marie; Sobreira, Nara; Wohler, Elizabeth S; Yu, Jingwei; Moore, Anthony T; Slavotinek, Anne M (Clin Genet, 2020)
Next-generation sequencing strategies have resulted in mutation detection rates of 21% to 61% in small cohorts of patients with microphthalmia, anophthalmia and coloboma (MAC), but despite progress in identifying novel causative genes, many patients remain without a genetic diagnosis. We studied a cohort of 19 patients with MAC who were ascertained from a population with high rates of consanguinity. Using single nucleotide polymorphism (SNP) arrays and whole exome sequencing (WES), we identified one pathogenic variant in TENM3 in a patient with cataracts in addition to MAC. We also detected novel variants of unknown significance in genes that have previously been associated with MAC, including KIF26B, MICU1 and CDON, and identified variants in candidate genes for MAC from the Wnt signaling pathway, comprising LRP6, WNT2B and IQGAP1, but our findings do not prove causality. Plausible variants were not found for many of the cases, indicating that our current understanding of the pathogenesis of MAC, a highly heterogeneous group of ocular defects, remains incomplete.

Exome sequencing reveals a novel variant in causing intracranial aneurysm in a Chinese family. - Ding, Xinghuan; Zhao, Sen; Zhang, Qianqian; Yan, Zihui; Wang, Yang; Wu, Yong; Li, Xiaoxin; Liu, Jian; Niu, Yuchen; Zhang, Yisen; Zhang, Mingqi; Wang, Huizi; et al. (J Neurointerv Surg, 2020)
BACKGROUND: Genetic risk factors play an important role in the pathogenesis of familial intracranial aneurysms (FIAs); however, the molecular mechanisms remain largely unknown. OBJECTIVE: To investigate potential FIA-causing genetic variants by rare variant interrogation and a family-based genomics approach in a large family with an extensive multigenerational pedigree with FIAs. METHOD: Exome sequencing (ES) was performed in a dominant likely family with intracranial aneurysms (IAs). Variants were analyzed by an in-house developed pipeline and prioritized using various filtering strategies, including population frequency, variant type, and predicted variant pathogenicity. Sanger sequencing was also performed to evaluate the segregation of the variants with the phenotype. RESULTS: Based on the ES data obtained from five individuals from a family with 7/21 living members affected with IAs, a total of 14 variants were prioritized as candidate variants. Familial segregation analysis revealed that c.2519T>C (p.Leu840Pro) segregated in accordance with Mendelian expectations with the phenotype within the family-that is, present in all IA-affected cases and absent from all unaffected members of the second generation. This missense variant is absent from public databases (1000genome, ExAC, gnomAD, ESP5400), and has damaging predictions by bioinformatics tools (Gerp ++ score = 5.88, CADD score = 16.43, MutationTaster score = 1, LRT score = 0). In addition, 840Leu in NFX1 is robustly conserved in mammals and maps in a region before the RING-type zinc finger domain. CONCLUSION: c.2519T>C (p.Leu840Pro) may contribute to the pathogenetics of a subset of FIAs.
Keywords: Adult; Asian Continental Ancestry Group; Computational Biology; Exome; Female; Genetic Variation; Humans; Intracranial Aneurysm; Male; Middle Aged; Pedigree; Phenotype; Repressor Proteins

Expanding the phenotypic spectrum in RDH12-associated retinal disease. - Scott, Hilary A; Place, Emily M; Ferenchak, Kevin; Zampaglione, Erin; Wagner, Naomi E; Chao, Katherine R; DiTroia, Stephanie P; Navarro-Gomez, Daniel; Mukai, Shizuo; Huckfeldt, Rachel M; Pierce, Eric A; Bujakowska, Kinga M (Cold Spring Harb Mol Case Stud, 2020)
Retinol dehydrogenase 12, RDH12, plays a pivotal role in the visual cycle to ensure the maintenance of normal vision. Alterations in activity of this protein result in photoreceptor death and decreased vision beginning at an early age and progressing to substantial vision loss later in life. Here we describe 11 patients with retinal degeneration that underwent next-generation sequencing (NGS) with a targeted panel of all currently known inherited retinal degeneration (IRD) genes and whole-exome sequencing to identify the genetic causality of their retinal disease. These patients display a range of phenotypic severity prompting clinical diagnoses of macular dystrophy, cone-rod dystrophy, retinitis pigmentosa, and early-onset severe retinal dystrophy all attributed to biallelic recessive mutations in We report 15 causal alleles and expand the repertoire of known mutations with four novel variants: c.215A > G (p.Asp72Gly); c.362T > C (p.Ile121Thr); c.440A > C (p.Asn147Thr); and c.697G > A (p.Val233Ille). The broad phenotypic spectrum observed with biallelic mutations has been observed in other genetic forms of IRDs, but the diversity is particularly notable here given the prior association of primarily with severe early-onset disease. This breadth emphasizes the importance of broad genetic testing for inherited retinal disorders and extends the pool of individuals who may benefit from imminent gene-targeted therapies.
Keywords: Adolescent; Adult; Alcohol Oxidoreductases; Alleles; Amino Acid Substitution; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Humans; Male; Mutation; Optical Imaging; Pedigree; Phenotype; Retinal Diseases; Tomography, Optical Coherence; Whole Exome Sequencing; Young Adult

Forensic evaluation of the Asia Pacific ancestry-informative MAPlex assay. - Xavier, C; de la Puente, M; Phillips, C; Eduardoff, M; Heidegger, A; Mosquera-Miguel, A; Freire-Aradas, A; Lagace, R; Wootton, S; Power, D; Parson, W; Lareu, M V; et al. (Forensic Sci Int Genet, 2020)
DNA intelligence, and particularly the inference of biogeographical ancestry (BGA) is increasing in interest, and relevance within the forensic genetics community. The majority of current MPS-based forensic ancestry-informative assays focus on the differentiation of major global populations. The recently published MAPlex (Multiplex for the Asia Pacific) panel contains 144 SNPs and 20 microhaplotypes and aims to improve the differentiation of populations in the Asia Pacific region. This study reports the first forensic evaluation of the MAPlex panel using AmpliSeq technology and Ion S5 sequencing. This study reports on the overall performance of MAPlex including the assay's sequence coverage distribution and stability, baseline noise and description of problematic SNPs. Dilution series, artificially degraded and mixed DNA samples were also analysed to evaluate the sensitivity of the panel with challenging or compromised forensic samples. As the first panel to combine biallelic SNPs, multiple-allele SNPs and microhaplotypes, the MAPlex assay demonstrated an enhanced capacity for mixture detection, not easily performed with common binary SNPs. This performance evaluation indicates that MAPlex is a robust, stable and highly sensitive assay that is applicable to forensic casework for the prediction of BGA.

Functional biology of the Steel syndrome founder allele and evidence for clan genomics derivation of COL27A1 pathogenic alleles worldwide. - Gonzaga-Jauregui, Claudia; Yesil, Gözde; Nistala, Harikiran; Gezdirici, Alper; Bayram, Yavuz; Nannuru, Kalyan C; Pehlivan, Davut; Yuan, Bo; Jimenez, Johanna; Sahin, Yavuz; Paine, Ingrid S; Akdemir, Zeynep Coban; et al. (Eur J Hum Genet, 2020)
Previously we reported the identification of a homozygous COL27A1 (c.2089G>C; p.Gly697Arg) missense variant and proposed it as a founder allele in Puerto Rico segregating with Steel syndrome (STLS, MIM #615155); a rare osteochondrodysplasia characterized by short stature, congenital bilateral hip dysplasia, carpal coalitions, and scoliosis. We now report segregation of this variant in five probands from the initial clinical report defining the syndrome and an additional family of Puerto Rican descent with multiple affected adult individuals. We modeled the orthologous variant in murine Col27a1 and found it recapitulates some of the major Steel syndrome associated skeletal features including reduced body length, scoliosis, and a more rounded skull shape. Characterization of the in vivo murine model shows abnormal collagen deposition in the extracellular matrix and disorganization of the proliferative zone of the growth plate. We report additional COL27A1 pathogenic variant alleles identified in unrelated consanguineous Turkish kindreds suggesting Clan Genomics and identity-by-descent homozygosity contributing to disease in this population. The hypothesis that carrier states for this autosomal recessive osteochondrodysplasia may contribute to common complex traits is further explored in a large clinical population cohort. Our findings augment our understanding of COL27A1 biology and its role in skeletal development; and expand the functional allelic architecture in this gene underlying both rare and common disease phenotypes.
Keywords: Abnormalities, Multiple; Adolescent; Animals; Bone Development; Child; Child, Preschool; Consanguinity; Extracellular Matrix; Female; Fibrillar Collagens; Founder Effect; Gene Frequency; Hip Dislocation; Homozygote; Humans; Male; Mice; Mice, Inbred C57BL; Mutation; Pedigree; Scoliosis; Syndrome

Further delineation of the clinical spectrum of KAT6B disorders and allelic series of pathogenic variants. - Zhang, Li Xin; Lemire, Gabrielle; Gonzaga-Jauregui, Claudia; Molidperee, Sirinart; Galaz-Montoya, Carolina; Liu, David S; Verloes, Alain; Shillington, Amelle G; Izumi, Kosuke; Ritter, Alyssa L; Keena, Beth; Zackai, Elaine; et al. (Genet Med, 2020)
PURPOSE: Genitopatellar syndrome and Say-Barber-Biesecker-Young-Simpson syndrome are caused by variants in the KAT6B gene and are part of a broad clinical spectrum called KAT6B disorders, whose variable expressivity is increasingly being recognized. METHODS: We herein present the phenotypes of 32 previously unreported individuals with a molecularly confirmed diagnosis of a KAT6B disorder, report 24 new pathogenic KAT6B variants, and review phenotypic information available on all published individuals with this condition. We also suggest a classification of clinical subtypes within the KAT6B disorder spectrum. RESULTS: We demonstrate that cerebral anomalies, optic nerve hypoplasia, neurobehavioral difficulties, and distal limb anomalies other than long thumbs and great toes, such as polydactyly, are more frequently observed than initially reported. Intestinal malrotation and its serious consequences can be present in affected individuals. Additionally, we identified four children with Pierre Robin sequence, four individuals who had increased nuchal translucency/cystic hygroma prenatally, and two fetuses with severe renal anomalies leading to renal failure. We also report an individual in which a pathogenic variant was inherited from a mildly affected parent. CONCLUSION: Our work provides a comprehensive review and expansion of the genotypic and phenotypic spectrum of KAT6B disorders that will assist clinicians in the assessment, counseling, and management of affected individuals.
Keywords: Blepharophimosis; Exons; Histone Acetyltransferases; Humans; Intellectual Disability; Mutation

Gain-of-function variants identified in vigabatrin-hypersensitive epileptic encephalopathies. - Absalom, Nathan L; Liao, Vivian W Y; Kothur, Kavitha; Indurthi, Dinesh C; Bennetts, Bruce; Troedson, Christopher; Mohammad, Shekeeb S; Gupta, Sachin; McGregor, Iain S; Bowen, Michael T; Lederer, Damien; Mary, Sandrine; et al. (Brain Commun, 2020)
Variants in the gene encoding the β3-subunit of the γ-aminobutyric acid type A ( receptor are associated with various developmental and epileptic encephalopathies. Typically, these variants cause a loss-of-function molecular phenotype whereby γ-aminobutyric acid has reduced inhibitory effectiveness leading to seizures. Drugs that potentiate inhibitory GABAergic activity, such as nitrazepam, phenobarbital or vigabatrin, are expected to compensate for this and thereby reduce seizure frequency. However, vigabatrin, a drug that inhibits γ-aminobutyric acid transaminase to increase tonic γ-aminobutyric acid currents, has mixed success in treating seizures in patients with variants: some patients experience seizure cessation, but there is hypersensitivity in some patients associated with hypotonia, sedation and respiratory suppression. A variant that responds well to vigabatrin involves a truncation variant (p.Arg194*) resulting in a clear loss-of-function. We hypothesized that patients with a hypersensitive response to vigabatrin may exhibit a different γ-aminobutyric acid A receptor phenotype. To test this hypothesis, we evaluated the phenotype of variants in (p.Glu77Lys and p.Thr287Ile) associated with patients who are clinically hypersensitive to vigabatrin. We introduced the p.Glu77Lys and p.Thr287Ile variants into a concatenated synaptic and extrasynaptic γ-aminobutyric acid A receptor construct, to resemble the γ-aminobutyric acid A receptor expression by a patient heterozygous for the variant. The mRNA of these constructs was injected into oocytes and activation properties of each receptor measured by two-electrode voltage clamp electrophysiology. Results showed an atypical gain-of-function molecular phenotype in the p.Glu77Lys and p.Thr287Ile variants characterized by increased potency of γ-aminobutyric acid A without change to the estimated maximum open channel probability, deactivation kinetics or absolute currents. Modelling of the activation properties of the receptors indicated that either variant caused increased chloride flux in response to low concentrations of γ-aminobutyric acid that mediate tonic currents. We therefore propose that the hypersensitivity reaction to vigabatrin is a result of variants that exacerbate GABAergic tonic currents and caution is required when prescribing vigabatrin. In contrast, drug strategies increasing tonic currents in loss-of-function variants are likely to be a safe and effective therapy. This study demonstrates that functional genomics can explain beneficial and adverse anti-epileptic drug effects, and propose that vigabatrin should be considered in patients with clear loss-of-function variants.

Gain-of-Function Variants in Dilated Cardiomyopathy. - Cowan, Jason R; Salyer, Lorien; Wright, Nathan T; Kinnamon, Daniel D; Amaya, Pedro; Jordan, Elizabeth; Bamshad, Michael J; Nickerson, Deborah A; Hershberger, Ray E (Circ Genom Precis Med, 2020)
BACKGROUND: Dilated cardiomyopathy (DCM) is a genetically heterogeneous cardiac disease characterized by progressive ventricular enlargement and reduced systolic function. Here, we report genetic and functional analyses implicating the rat sarcoma signaling protein, SOS1 (Son of sevenless homolog 1), in DCM pathogenesis. METHODS: Exome sequencing was performed on 412 probands and family members from our DCM cohort, identifying several variants with potential disease involvement. As several lines of evidence have implicated dysregulated rat sarcoma signaling in the pathogenesis of DCM, we assessed functional impact of each variant on the activation of ERK (extracellular signal-regulated kinase), AKT (protein kinase B), and JNK (c-Jun N-terminal kinase) pathways. Relative expression levels were determined by Western blot in HEK293T cells transfected with variant or wild-type human expression constructs. RESULTS: A rare variant [c.571G>A, p.(Glu191Lys)] was found to segregate alongside an A-band truncating variant in a pedigree with aggressive, early-onset DCM. Reduced disease severity in the absence of the variant suggested its potential involvement as a genetic risk factor for DCM in this family. Exome sequencing identified 5 additional variants with potential disease involvement in 4 other families [c.1820T>C, p.(Ile607Thr); c.2156G>C, p.(Gly719Ala); c.2230A>G, p.(Arg744Gly); c.2728G>C, p.(Asp910His); c.3601C>T, p.(Arg1201Trp)]. Impacted amino acids occupied a number of functional domains relevant to SOS1 activity, including the N-terminal histone fold, as well as the C-terminal REM (rat sarcoma exchange motif), CDC25 (cell division cycle 25), and PR (proline-rich) tail domains. Increased phosphorylated ERK expression relative to wild-type levels was seen for all 6 variants, paralleling known disease-relevant signaling profiles. CONCLUSIONS: These data support gain-of-function variation in as a contributing factor to isolated DCM.

The genetic and clinical landscape of nanophthalmos and posterior microphthalmos in an Australian cohort. - Siggs, Owen M; Awadalla, Mona S; Souzeau, Emmanuelle; Staffieri, Sandra E; Kearns, Lisa S; Laurie, Kate; Kuot, AbrAHm; Qassim, Ayub; Edwards, Thomas L; Coote, Michael A; Mancel, Erica; Walland, Mark J; et al. (Clin Genet, 2020)
Nanophthalmos and posterior microphthalmos are ocular abnormalities in which both eyes are abnormally small, and typically associated with extreme hyperopia. We recruited 40 individuals from 13 kindreds with nanophthalmos or posterior microphthalmos, with 12 probands subjected to exome sequencing. Nine probands (69.2%) were assigned a genetic diagnosis, with variants in MYRF, TMEM98, MFRP, and PRSS56. Two of four PRSS56 families harbored the previously described c.1066dupC variant implicated in over half of all reported PRSS56 kindreds, with different surrounding haplotypes in each family suggesting a mutational hotspot. Individuals with a genetic diagnosis had shorter mean axial lengths and higher hyperopia than those without, with recessive forms associated with the most extreme phenotypes. These findings detail the genetic architecture of nanophthalmos and posterior microphthalmos in a cohort of predominantly European ancestry, their relative clinical phenotypes, and highlight the shared genetic architecture of rare and common disorders of refractive error.

Genetic and molecular mechanism for distinct clinical phenotypes conveyed by allelic truncating mutations implicated in FBN1. - Lin, Mao; Liu, Zhenlei; Liu, Gang; Zhao, Sen; Li, Chao; Chen, Weisheng; Coban Akdemir, Zeynep; Lin, Jiachen; Song, Xiaofei; Wang, Shengru; Xu, Qiming; Zhao, Yanxue; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: The molecular and genetic mechanisms by which different single nucleotide variant alleles in specific genes, or at the same genetic locus, cause distinct disease phenotypes often remain unclear. Allelic truncating mutations of FBN1 could cause either classical Marfan syndrome (MFS) or a more complicated phenotype associated with Marfanoid-progeroid-lipodystrophy syndrome (MPLS). METHODS: We investigated a small cohort, encompassing two classical MFS and one MPLS subjects from China, whose clinical presentation included scoliosis potentially requiring surgical intervention. Targeted next generation sequencing was performed on all the participants. We analyzed the molecular diagnosis, clinical features, and the potential molecular mechanism involved in the MPLS subject in our cohort. RESULTS: We report a novel de novo FBN1 mutation for the first Chinese subject with MPLS, a more complicated fibrillinopathy, and two subjects with more classical MFS. We further predict that the MPLS truncating mutation, and others previously reported, is prone to escape the nonsense-mediated decay (NMD), while MFS mutations are predicted to be subjected to NMD. Also, the MPLS mutation occurs within the glucogenic hormone asprosin domain of FBN1. In vitro experiments showed that the single MPLS mutation p.Glu2759Cysfs*9 appears to perturb proper FBN1 protein aggregation as compared with the classical MFS mutation p.Tyr2596Thrfs*86. Both mutations appear to upregulate SMAD2 phosphorylation in vitro. CONCLUSION: We provide direct evidence that a dominant-negative interaction of FBN1 potentially explains the complex MPLS phenotypes through genetic and functional analysis. Our study expands the mutation spectrum of FBN1 and highlights the potential molecular mechanism for MPLS.
Keywords: Adolescent; Adult; Child; Female; Fibrillin-1; HEK293 Cells; Humans; Lipodystrophy; Marfan Syndrome; Mutation; Phenotype; Progeria; Protein Domains; Smad2 Protein

Genetic diagnosis in the fetus. - Wojcik, Monica H; Reimers, Rebecca; Poorvu, Tabitha; Agrawal, Pankaj B (J Perinatol, 2020)
Many genetic disorders are detectable in the prenatal period, and the capacity to identify them has increased remarkably as molecular genetic testing techniques continue to improve and become incorporated into clinical practice. The indications for prenatal genetic testing vary widely, including follow-up of an anomaly found by routine ultrasound or maternal aneuploidy screening, a family history of genetic disease, advanced maternal or paternal age, or evaluation of a low-risk pregnancy due to parental concern. The interpretation of genetic variants identified in the prenatal period poses unique challenges due to the lack of ability for deep phenotyping as well as the option to make critical decisions regarding pregnancy continuation and perinatal management. In this review, we address the various modalities currently available and commonly used for genetic testing, including preimplantation genetic testing of embryos, cell-free DNA testing, and diagnostic procedures such as chorionic villous sampling, amniocentesis, or percutaneous umbilical blood sampling, from which samples may be sent for a wide variety of genetic tests. We discuss the difference between these modalities for the genetic diagnosis of a fetus, their strengths and weaknesses, and strategies for their optimal use in order to direct perinatal care.

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome sequencing identifies a homozygous inversion disrupting QDPR as a cause for dihydropteridine reductase deficiency. - Lilleväli, Hardo; Pajusalu, Sander; Wojcik, Monica H; Goodrich, Julia; Collins, Ryan L; Murumets, Ülle; Tammur, Pille; Blau, Nenad; Lilleväli, Kersti; Õunap, Katrin (Mol Genet Genomic Med, 2020)
BACKGROUND: Dihydropteridine reductase (DHPR) is one of the key enzymes for maintaining in the organism the supply of tetrahydrobiopterin (BH ), an essential cofactor for aromatic amino acid hydroxylases. Its dysfunction causes the condition of hyperphenylalaninemia together with the lack of neurotransmitters. METHODS: We report a patient with biochemically diagnosed DHPR deficiency, with extensive molecular investigations undertaken to detect variations in quinoid dihydropteridine reductase (QDPR) gene. Sanger sequencing of QDPR coding regions, exome sequencing, QDPR mRNA PCR, and karyotyping were followed by trio genome sequencing. RESULTS: Short-read genome sequencing revealed a homozygous 9-Mb inversion disrupting QDPR. Structural variant breakpoints in chromosome 4 were located to intron 2 of QDPR at Chr4(GRCh38):g.17505522 and in intron 8 of the ACOX3 gene, Chr4(GRCh38):g.8398067). Both nonrelated parents carried the variant in heterozygous state. The inversion was not present in gnomAD structural variant database. CONCLUSION: Identification of the exact breakpoints now allows further straightforward molecular genetic testing of potential carriers of the inversion. This study extends the pathogenic variant spectrum of DHPR deficiency and highlights the role of structural variants in recessive metabolic disorders. To our knowledge, this is the first report on a large, canonical (rather than complex) homozygous pathogenic inversion detected by genome sequencing.
Keywords: Acyl-CoA Oxidase; Child; Chromosome Breakpoints; Chromosome Inversion; Chromosomes, Human, Pair 4; Female; Genetic Testing; Homozygote; Humans; Phenylketonurias; Whole Exome Sequencing

Genome-wide association meta-analysis for early age-related macular degeneration highlights novel loci and insights for advanced disease. - Winkler, Thomas W; Grassmann, Felix; Brandl, Caroline; Kiel, Christina; Günther, Felix; Strunz, Tobias; Weidner, Lorraine; Zimmermann, Martina E; Korb, Christina A; Poplawski, Alicia; Schuster, Alexander K; Müller-Nurasyid, Martina; et al. (BMC Med Genomics, 2020)
BACKGROUND: Advanced age-related macular degeneration (AMD) is a leading cause of blindness. While around half of the genetic contribution to advanced AMD has been uncovered, little is known about the genetic architecture of early AMD. METHODS: To identify genetic factors for early AMD, we conducted a genome-wide association study (GWAS) meta-analysis (14,034 cases, 91,214 controls, 11 sources of data including the International AMD Genomics Consortium, IAMDGC, and UK Biobank, UKBB). We ascertained early AMD via color fundus photographs by manual grading for 10 sources and via an automated machine learning approach for > 170,000 photographs from UKBB. We searched for early AMD loci via GWAS and via a candidate approach based on 14 previously suggested early AMD variants. RESULTS: Altogether, we identified 10 independent loci with statistical significance for early AMD: (i) 8 from our GWAS with genome-wide significance (P < 5 × 10), (ii) one previously suggested locus with experiment-wise significance (P < 0.05/14) in our non-overlapping data and with genome-wide significance when combining the reported and our non-overlapping data (together 17,539 cases, 105,395 controls), and (iii) one further previously suggested locus with experiment-wise significance in our non-overlapping data. Of these 10 identified loci, 8 were novel and 2 known for early AMD. Most of the 10 loci overlapped with known advanced AMD loci (near ARMS2/HTRA1, CFH, C2, C3, CETP, TNFRSF10A, VEGFA, APOE), except two that have not yet been identified with statistical significance for any AMD. Among the 17 genes within these two loci, in-silico functional annotation suggested CD46 and TYR as the most likely responsible genes. Presence or absence of an early AMD effect distinguished the known pathways of advanced AMD genetics (complement/lipid pathways versus extracellular matrix metabolism). CONCLUSIONS: Our GWAS on early AMD identified novel loci, highlighted shared and distinct genetics between early and advanced AMD and provides insights into AMD etiology. Our data provide a resource comparable in size to the existing IAMDGC data on advanced AMD genetics enabling a joint view. The biological relevance of this joint view is underscored by the ability of early AMD effects to differentiate the major pathways for advanced AMD.
Keywords: Case-Control Studies; Genetic Loci; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Macular Degeneration; Polymorphism, Single Nucleotide

Genotypic diversity and phenotypic spectrum of infantile liver failure syndrome type 1 due to variants in LARS1. - Lenz, Dominic; Smith, Desirée E C; Crushell, Ellen; Husain, Ralf A; Salomons, Gajja S; Alhaddad, Bader; Bernstein, Jonathan A; Bianzano, Alyssa; Biskup, Saskia; Brennenstuhl, Heiko; Caldari, Dominique; Dikow, Nicola; et al. (Genet Med, 2020)
PURPOSE: Biallelic variants in LARS1, coding for the cytosolic leucyl-tRNA synthetase, cause infantile liver failure syndrome 1 (ILFS1). Since its description in 2012, there has been no systematic analysis of the clinical spectrum and genetic findings. METHODS: Individuals with biallelic variants in LARS1 were included through an international, multicenter collaboration including novel and previously published patients. Clinical variables were analyzed and functional studies were performed in patient-derived fibroblasts. RESULTS: Twenty-five individuals from 15 families were ascertained including 12 novel patients with eight previously unreported variants. The most prominent clinical findings are recurrent elevation of liver transaminases up to liver failure and encephalopathic episodes, both triggered by febrile illness. Magnetic resonance image (MRI) changes during an encephalopathic episode can be consistent with metabolic stroke. Furthermore, growth retardation, microcytic anemia, neurodevelopmental delay, muscular hypotonia, and infection-related seizures are prevalent. Aminoacylation activity is significantly decreased in all patient cells studied upon temperature elevation in vitro. CONCLUSION: ILFS1 is characterized by recurrent elevation of liver transaminases up to liver failure in conjunction with abnormalities of growth, blood, nervous system, and musculature. Encephalopathic episodes with seizures can occur independently from liver crises and may present with metabolic stroke.
Keywords: Humans; Liver Failure; Muscle Hypotonia; Mutation; Seizures

Heterozygous Gene Deficiency and Risk of Coronary Artery Disease. - Nomura, Akihiro; Emdin, Connor A; Won, Hong Hee; Peloso, Gina M; Natarajan, Pradeep; Ardissino, Diego; Danesh, John; Schunkert, Heribert; Correa, Adolfo; Bown, Matthew J; Samani, Nilesh J; Erdmann, Jeanette; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Familial sitosterolemia is a rare Mendelian disorder characterized by hyperabsorption and decreased biliary excretion of dietary sterols. Affected individuals typically have complete genetic deficiency-homozygous loss-of-function (LoF) variants-in the or genes and have substantially elevated plasma sitosterol and LDL (low-density lipoprotein) cholesterol (LDL-C) levels. The impact of partial genetic deficiency of or -as occurs in heterozygous carriers of LoF variants-on LDL-C and risk of coronary artery disease (CAD) has remained uncertain. METHODS: We first recruited 9 sitosterolemia families, identified causative LoF variants in or , and evaluated the associations of these or LoF variants with plasma phytosterols and lipid levels. We next assessed for LoF variants in or in CAD cases (n=29 321) versus controls (n=357 326). We tested the association of rare LoF variants in or with blood lipids and risk for CAD. Rare LoF variants were defined as protein-truncating variants with minor allele frequency <0.1% in or . RESULTS: In sitosterolemia families, 7 pedigrees harbored causative LoF variants in and 2 pedigrees in . Homozygous LoF variants in either or led to marked elevations in sitosterol and LDL-C. Of those sitosterolemia families, heterozygous carriers of LoF variants exhibited increased sitosterol and LDL-C levels compared with noncarriers. Within large-scale CAD case-control cohorts, prevalence of rare LoF variants in and in was ≈0.1% each. heterozygous LoF variant carriers had significantly elevated LDL-C levels (25 mg/dL [95% CI, 14-35]; =1.1×10) and were at 2-fold increased risk of CAD (odds ratio, 2.06 [95% CI, 1.27-3.35]; =0.004). By contrast, heterozygous LoF carrier status was not associated with increased LDL-C or risk of CAD. CONCLUSIONS: Although familial sitosterolemia is traditionally considered as a recessive disorder, we observed that heterozygous carriers of an LoF variant in had significantly increased sitosterol and LDL-C levels and a 2-fold increase in risk of CAD.

Heterozygous loss of WBP11 function causes multiple congenital defects in humans and mice. - Martin, Ella M M A; Enriquez, Annabelle; Sparrow, Duncan B; Humphreys, David T; McInerney-Leo, Aideen M; Leo, Paul J; Duncan, Emma L; Iyer, Kavitha R; Greasby, Joelene A; Ip, Eddie; Giannoulatou, Eleni; Sheng, Delicia; et al. (Hum Mol Genet, 2020)
The genetic causes of multiple congenital anomalies are incompletely understood. Here, we report novel heterozygous predicted loss-of-function (LoF) and predicted damaging missense variants in the WW domain binding protein 11 (WBP11) gene in seven unrelated families with a variety of overlapping congenital malformations, including cardiac, vertebral, tracheo-esophageal, renal and limb defects. WBP11 encodes a component of the spliceosome with the ability to activate pre-messenger RNA splicing. We generated a Wbp11 null allele in mouse using CRISPR-Cas9 targeting. Wbp11 homozygous null embryos die prior to E8.5, indicating that Wbp11 is essential for development. Fewer Wbp11 heterozygous null mice are found than expected due to embryonic and postnatal death. Importantly, Wbp11 heterozygous null mice are small and exhibit defects in axial skeleton, kidneys and esophagus, similar to the affected individuals, supporting the role of WBP11 haploinsufficiency in the development of congenital malformations in humans. LoF WBP11 variants should be considered as a possible cause of VACTERL association as well as isolated Klippel-Feil syndrome, renal agenesis or esophageal atresia.

Human and mouse studies establish TBX6 in Mendelian CAKUT and as a potential driver of kidney defects associated with the 16p11.2 microdeletion syndrome. - Yang, Nan; Wu, Nan; Dong, Shuangshuang; Zhang, Ling; Zhao, Yanxue; Chen, Weisheng; Du, Renqian; Song, Chengcheng; Ren, Xiaojun; Liu, Jiaqi; Pehlivan, Davut; Liu, Zhenlei; et al. (Kidney Int, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUTs) are the most common cause of chronic kidney disease in children. Human 16p11.2 deletions have been associated with CAKUT, but the responsible molecular mechanism remains to be illuminated. To explore this, we investigated 102 carriers of 16p11.2 deletion from multi-center cohorts, among which we retrospectively ascertained kidney morphologic and functional data from 37 individuals (12 Chinese and 25 Caucasian/Hispanic). Significantly higher CAKUT rates were observed in 16p11.2 deletion carriers (about 25% in Chinese and 16% in Caucasian/Hispanic) than those found in the non-clinically ascertained general populations (about 1/1000 found at autopsy). Furthermore, we identified seven additional individuals with heterozygous loss-of-function variants in TBX6, a gene that maps to the 16p11.2 region. Four of these seven cases showed obvious CAKUT. To further investigate the role of TBX6 in kidney development, we engineered mice with mutated Tbx6 alleles. The Tbx6 heterozygous null (i.e., loss-of-function) mutant (Tbx6) resulted in 13% solitary kidneys. Remarkably, this incidence increased to 29% in a compound heterozygous model (Tbx6) that reduced Tbx6 gene dosage to below haploinsufficiency, by combining the null allele with a novel mild hypomorphic allele (mh). Renal hypoplasia was also frequently observed in these Tbx6-mutated mouse models. Thus, our findings in patients and mice establish TBX6 as a novel gene involved in CAKUT and its gene dosage insufficiency as a potential driver for kidney defects observed in the 16p11.2 microdeletion syndrome.

Human CRY1 variants associate with attention deficit/hyperactivity disorder. - Onat, O Emre; Kars, M Ece; Gül, Şeref; Bilguvar, Kaya; Wu, Yiming; Özhan, Ayşe; Aydın, Cihan; Başak, A Nazlı; Trusso, M Allegra; Goracci, Arianna; Fallerini, Chiara; Renieri, Alessandra; et al. (J Clin Invest, 2020)
Attention deficit/hyperactivity disorder (ADHD) is a common and heritable phenotype frequently accompanied by insomnia, anxiety, and depression. Here, using a reverse phenotyping approach, we report heterozygous coding variations in the core circadian clock gene cryptochrome 1 in 15 unrelated multigenerational families with combined ADHD and insomnia. The variants led to functional alterations in the circadian molecular rhythms, providing a mechanistic link to the behavioral symptoms. One variant, CRY1Δ11 c.1657+3A>C, is present in approximately 1% of Europeans, therefore standing out as a diagnostic and therapeutic marker. We showed by exome sequencing in an independent cohort of patients with combined ADHD and insomnia that 8 of 62 patients and 0 of 369 controls carried CRY1Δ11. Also, we identified a variant, CRY1Δ6 c.825+1G>A, that shows reduced affinity for BMAL1/CLOCK and causes an arrhythmic phenotype. Genotype-phenotype correlation analysis revealed that this variant segregated with ADHD and delayed sleep phase disorder (DSPD) in the affected family. Finally, we found in a phenome-wide association study involving 9438 unrelated adult Europeans that CRY1Δ11 was associated with major depressive disorder, insomnia, and anxiety. These results defined a distinctive group of circadian psychiatric phenotypes that we propose to designate as "circiatric" disorders.
Keywords: Adult; ARNTL Transcription Factors; Attention Deficit Disorder with Hyperactivity; CLOCK Proteins; Cryptochromes; Female; Genetic Association Studies; HEK293 Cells; Humans; Male; Mutation; Sleep Disorders, Circadian Rhythm

The impact of sex on gene expression across human tissues. - Oliva, Meritxell; Muñoz-Aguirre, Manuel; Kim-Hellmuth, Sarah; Wucher, Valentin; Gewirtz, Ariel D H; Cotter, Daniel J; Parsana, Princy; Kasela, Silva; Balliu, Brunilda; Viñuela, Ana; Castel, Stephane E; Mohammadi, Pejman; et al. (Science, 2020)
Many complex human phenotypes exhibit sex-differentiated characteristics. However, the molecular mechanisms underlying these differences remain largely unknown. We generated a catalog of sex differences in gene expression and in the genetic regulation of gene expression across 44 human tissue sources surveyed by the Genotype-Tissue Expression project (GTEx, v8 release). We demonstrate that sex influences gene expression levels and cellular composition of tissue samples across the human body. A total of 37% of all genes exhibit sex-biased expression in at least one tissue. We identify cis expression quantitative trait loci (eQTLs) with sex-differentiated effects and characterize their cellular origin. By integrating sex-biased eQTLs with genome-wide association study data, we identify 58 gene-trait associations that are driven by genetic regulation of gene expression in a single sex. These findings provide an extensive characterization of sex differences in the human transcriptome and its genetic regulation.
Keywords: Chromosomes, Human, X; Disease; Epigenesis, Genetic; Female; Gene Expression; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; Male; Organ Specificity; Promoter Regions, Genetic; Quantitative Trait Loci; Sex Characteristics; Sex Factors

Increased gene dosages induce congenital cervical vertebral malformations in humans and mice. - Ren, Xiaojun; Yang, Nan; Wu, Nan; Xu, Ximing; Chen, Weisheng; Zhang, Ling; Li, Yingping; Du, Ren-Qian; Dong, Shuangshuang; Zhao, Sen; Chen, Shuxia; Jiang, Li-Ping; et al. (J Med Genet, 2020)
BACKGROUND: Congenital vertebral malformations (CVMs) manifest with abnormal vertebral morphology. Genetic factors have been implicated in CVM pathogenesis, but the underlying pathogenic mechanisms remain unclear in most subjects. We previously reported that the human 16p11.2 BP4-BP5 deletion and its associated dosage reduction caused CVMs. We aim to investigate the reciprocal 16p11.2 BP4-BP5 duplication and its potential genetic contributions to CVMs. METHODS AND RESULTS: Patients who were found to carry the 16p11.2 BP4-BP5 duplication by chromosomal microarray analysis were retrospectively analysed for their vertebral phenotypes. The spinal assessments in seven duplication carriers showed that four (57%) presented characteristics of CVMs, supporting the contention that increased dosage could induce CVMs. For further in vivo functional investigation in a model organism, we conducted genome editing of the upstream regulatory region of mouse using CRISPR-Cas9 and obtained three mouse mutant alleles ( to ) with elevated expression levels of . Luciferase reporter assays showed that the allele presented with the 160% expression level of that observed in the reference (+) allele. Therefore, the homozygous mice could functionally mimic the dosage of heterozygous carriers of 16p11.2 BP4-BP5 duplication (approximately 150%, ie, 3/2 gene dosage of the normal level). Remarkably, 60% of the mice manifested with CVMs. Consistent with our observations in humans, the CVMs induced by increased dosage in mice mainly affected the cervical vertebrae. CONCLUSION: Our findings in humans and mice consistently support that an increased dosage contributes to the risk of developing cervical CVMs.

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; African Continental Ancestry Group; Aged; Aged, 80 and over; alpha Karyopherins; Cell Self Renewal; Clonal Hematopoiesis; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

KIAA1217: A novel candidate gene associated with isolated and syndromic vertebral malformations. - Al Dhaheri, Noura; Wu, Nan; Zhao, Sen; Wu, Zhihong; Blank, Robert D; Zhang, Jianguo; Raggio, Cathy; Halanski, Matthew; Shen, Jianxiong; Noonan, Ken; Qiu, Guixing; Nemeth, Blaise; et al. (Am J Med Genet A, 2020)
Vertebral malformations (VMs) are caused by alterations in somitogenesis and may occur in association with other congenital anomalies. The genetic etiology of most VMs remains unknown and their identification may facilitate the development of novel therapeutic and prevention strategies. Exome sequencing was performed on both the discovery cohort of nine unrelated probands from the USA with VMs and the replication cohort from China (Deciphering Disorders Involving Scoliosis & COmorbidities study). The discovery cohort was analyzed using the PhenoDB analysis tool. Heterozygous and homozygous, rare and functional variants were selected and evaluated for their ClinVar, HGMD, OMIM, GWAS, mouse model phenotypes, and other annotations to identify the best candidates. Genes with candidate variants in three or more probands were selected. The replication cohort was analyzed by another in-house developed pipeline. We identified rare heterozygous variants in KIAA1217 in four out of nine probands in the discovery cohort and in five out of 35 probands in the replication cohort. Collectively, we identified 11 KIAA1217 rare variants in 10 probands, three of which have not been described in gnomAD and one of which is a nonsense variant. We propose that genetic variations of KIAA1217 may contribute to the etiology of VMs.
Keywords: Adolescent; Cervical Vertebrae; Child; Codon, Nonsense; Databases, Genetic; Female; Heterozygote; Homozygote; Humans; Male; Proteins; Spinal Diseases; Thoracic Vertebrae

KMT2B-related disorders: expansion of the phenotypic spectrum and long-term efficacy of deep brain stimulation. - Cif, Laura; Demailly, Diane; Lin, Jean-Pierre; Barwick, Katy E; Sa, Mario; Abela, Lucia; Malhotra, Sony; Chong, Wui K; Steel, Dora; Sanchis-Juan, Alba; Ngoh, Adeline; Trump, Natalie; et al. (Brain, 2020)
Heterozygous mutations in KMT2B are associated with an early-onset, progressive and often complex dystonia (DYT28). Key characteristics of typical disease include focal motor features at disease presentation, evolving through a caudocranial pattern into generalized dystonia, with prominent oromandibular, laryngeal and cervical involvement. Although KMT2B-related disease is emerging as one of the most common causes of early-onset genetic dystonia, much remains to be understood about the full spectrum of the disease. We describe a cohort of 53 patients with KMT2B mutations, with detailed delineation of their clinical phenotype and molecular genetic features. We report new disease presentations, including atypical patterns of dystonia evolution and a subgroup of patients with a non-dystonic neurodevelopmental phenotype. In addition to the previously reported systemic features, our study has identified co-morbidities, including the risk of status dystonicus, intrauterine growth retardation, and endocrinopathies. Analysis of this study cohort (n = 53) in tandem with published cases (n = 80) revealed that patients with chromosomal deletions and protein truncating variants had a significantly higher burden of systemic disease (with earlier onset of dystonia) than those with missense variants. Eighteen individuals had detailed longitudinal data available after insertion of deep brain stimulation for medically refractory dystonia. Median age at deep brain stimulation was 11.5 years (range: 4.5-37.0 years). Follow-up after deep brain stimulation ranged from 0.25 to 22 years. Significant improvement of motor function and disability (as assessed by the Burke Fahn Marsden's Dystonia Rating Scales, BFMDRS-M and BFMDRS-D) was evident at 6 months, 1 year and last follow-up (motor, P = 0.001, P = 0.004, and P = 0.012; disability, P = 0.009, P = 0.002 and P = 0.012). At 1 year post-deep brain stimulation, >50% of subjects showed BFMDRS-M and BFMDRS-D improvements of >30%. In the long-term deep brain stimulation cohort (deep brain stimulation inserted for >5 years, n = 8), improvement of >30% was maintained in 5/8 and 3/8 subjects for the BFMDRS-M and BFMDRS-D, respectively. The greatest BFMDRS-M improvements were observed for trunk (53.2%) and cervical (50.5%) dystonia, with less clinical impact on laryngeal dystonia. Improvements in gait dystonia decreased from 20.9% at 1 year to 16.2% at last assessment; no patient maintained a fully independent gait. Reduction of BFMDRS-D was maintained for swallowing (52.9%). Five patients developed mild parkinsonism following deep brain stimulation. KMT2B-related disease comprises an expanding continuum from infancy to adulthood, with early evidence of genotype-phenotype correlations. Except for laryngeal dysphonia, deep brain stimulation provides a significant improvement in quality of life and function with sustained clinical benefit depending on symptoms distribution.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Deletion; Cohort Studies; Computer Simulation; Deep Brain Stimulation; Disease Progression; Dystonic Disorders; Endocrine System Diseases; Female; Fetal Growth Retardation; Gait Disorders, Neurologic; Histone-Lysine N-Methyltransferase; Humans; Laryngeal Diseases; Male; Mutation; Mutation, Missense; Phenotype; Quality of Life; Treatment Outcome; Young Adult

Landscape of multi-nucleotide variants in 125,748 human exomes and 15,708 genomes. - Wang, Qingbo; Pierce-Hoffman, Emma; Cummings, Beryl B; Alföldi, Jessica; Francioli, Laurent C; Gauthier, Laura D; Hill, Andrew J; O'Donnell-Luria, Anne H; Karczewski, Konrad J; MacArthur, Daniel G (Nat Commun, 2020)
Multi-nucleotide variants (MNVs), defined as two or more nearby variants existing on the same haplotype in an individual, are a clinically and biologically important class of genetic variation. However, existing tools typically do not accurately classify MNVs, and understanding of their mutational origins remains limited. Here, we systematically survey MNVs in 125,748 whole exomes and 15,708 whole genomes from the Genome Aggregation Database (gnomAD). We identify 1,792,248 MNVs across the genome with constituent variants falling within 2 bp distance of one another, including 18,756 variants with a novel combined effect on protein sequence. Finally, we estimate the relative impact of known mutational mechanisms - CpG deamination, replication error by polymerase zeta, and polymerase slippage at repeat junctions - on the generation of MNVs. Our results demonstrate the value of haplotype-aware variant annotation, and refine our understanding of genome-wide mutational mechanisms of MNVs.
Keywords: CpG Islands; Databases, Genetic; DNA Mutational Analysis; Exome; Genetic Variation; Genome, Human; Humans; Mutation

Large-Scale Exome Sequencing Study Implicates Both Developmental and Functional Changes in the Neurobiology of Autism. - Satterstrom, F Kyle; Kosmicki, Jack A; Wang, Jiebiao; Breen, Michael S; De Rubeis, Silvia; An, Joon-Yong; Peng, Minshi; Collins, Ryan; Grove, Jakob; Klei, Lambertus; Stevens, Christine; Reichert, Jennifer; et al. (Cell, 2020)
We present the largest exome sequencing study of autism spectrum disorder (ASD) to date (n = 35,584 total samples, 11,986 with ASD). Using an enhanced analytical framework to integrate de novo and case-control rare variation, we identify 102 risk genes at a false discovery rate of 0.1 or less. Of these genes, 49 show higher frequencies of disruptive de novo variants in individuals ascertained to have severe neurodevelopmental delay, whereas 53 show higher frequencies in individuals ascertained to have ASD; comparing ASD cases with mutations in these groups reveals phenotypic differences. Expressed early in brain development, most risk genes have roles in regulation of gene expression or neuronal communication (i.e., mutations effect neurodevelopmental and neurophysiological changes), and 13 fall within loci recurrently hit by copy number variants. In cells from the human cortex, expression of risk genes is enriched in excitatory and inhibitory neuronal lineages, consistent with multiple paths to an excitatory-inhibitory imbalance underlying ASD.
Keywords: Autistic Disorder; Case-Control Studies; Cell Lineage; Cerebral Cortex; Cohort Studies; Exome; Female; Gene Expression Regulation, Developmental; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Mutation, Missense; Neurobiology; Neurons; Phenotype; Sex Factors; Single-Cell Analysis; Whole Exome Sequencing

Likely damaging de novo variants in congenital diaphragmatic hernia patients are associated with worse clinical outcomes. - Qiao, Lu; Wynn, Julia; Yu, Lan; Hernan, Rebecca; Zhou, Xueya; Duron, Vincent; Aspelund, Gudrun; Farkouh-Karoleski, Christiana; Zygumunt, Annette; Krishnan, Usha S; Nees, Shannon; Khlevner, Julie; et al. (Genet Med, 2020)
PURPOSE: Congenital diaphragmatic hernia (CDH) is associated with significant mortality and long-term morbidity in some but not all individuals. We hypothesize monogenic factors that cause CDH are likely to have pleiotropic effects and be associated with worse clinical outcomes. METHODS: We enrolled and prospectively followed 647 newborns with CDH and performed genomic sequencing on 462 trios to identify de novo variants. We grouped cases into those with and without likely damaging (LD) variants and systematically assessed CDH clinical outcomes between the genetic groups. RESULTS: Complex cases with additional congenital anomalies had higher mortality than isolated cases (P = 8 × 10). Isolated cases with LD variants had similar mortality to complex cases and much higher mortality than isolated cases without LD (P = 3 × 10). The trend was similar with pulmonary hypertension at 1 month. Cases with LD variants had an estimated 12-17 points lower scores on neurodevelopmental assessments at 2 years compared with cases without LD variants, and this difference is similar in isolated and complex cases. CONCLUSION: We found that the LD genetic variants are associated with higher mortality, worse pulmonary hypertension, and worse neurodevelopment outcomes compared with non-LD variants. Our results have important implications for prognosis, potential intervention and long-term follow up for children with CDH.
Keywords: Child; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Retrospective Studies

Loss of CBY1 results in a ciliopathy characterized by features of Joubert syndrome. - Epting, Daniel; Senaratne, Lokuliyange D S; Ott, Elisabeth; Holmgren, Asbjørn; Sumathipala, Dulika; Larsen, Selma M; Wallmeier, Julia; Bracht, Diana; Frikstad, Kari-Anne M; Crowley, Suzanne; Sikiric, Alma; Barøy, Tuva; et al. (Hum Mutat, 2020)
Ciliopathies are clinically and genetically heterogeneous diseases. We studied three patients from two independent families presenting with features of Joubert syndrome: abnormal breathing pattern during infancy, developmental delay/intellectual disability, cerebellar ataxia, molar tooth sign on magnetic resonance imaging scans, and polydactyly. We identified biallelic loss-of-function (LOF) variants in CBY1, segregating with the clinical features of Joubert syndrome in the families. CBY1 localizes to the distal end of the mother centriole, contributing to the formation and function of cilia. In accordance with the clinical and mutational findings in the affected individuals, we demonstrated that depletion of Cby1 in zebrafish causes ciliopathy-related phenotypes. Levels of CBY1 transcript were found reduced in the patients compared with controls, suggesting degradation of the mutated transcript through nonsense-mediated messenger RNA decay. Accordingly, we could detect CBY1 protein in fibroblasts from controls, but not from patients by immunofluorescence. Furthermore, we observed reduced ability to ciliate, increased ciliary length, and reduced levels of the ciliary proteins AHI1 and ARL13B in patient fibroblasts. Our data show that CBY1 LOF-variants cause a ciliopathy with features of Joubert syndrome.

Loss of NARS1 impairs progenitor proliferation in cortical brain organoids and leads to microcephaly. - Wang, Lu; Li, Zhen; Sievert, David; Smith, Desirée E C; Mendes, Marisa I; Chen, Dillon Y; Stanley, Valentina; Ghosh, Shereen; Wang, Yulu; Kara, Majdi; Aslanger, Ayca Dilruba; Rosti, Rasim O; et al. (Nat Commun, 2020)
Asparaginyl-tRNA synthetase1 (NARS1) is a member of the ubiquitously expressed cytoplasmic Class IIa family of tRNA synthetases required for protein translation. Here, we identify biallelic missense and frameshift mutations in NARS1 in seven patients from three unrelated families with microcephaly and neurodevelopmental delay. Patient cells show reduced NARS1 protein, impaired NARS1 activity and impaired global protein synthesis. Cortical brain organoid modeling shows reduced proliferation of radial glial cells (RGCs), leading to smaller organoids characteristic of microcephaly. Single-cell analysis reveals altered constituents of both astrocytic and RGC lineages, suggesting a requirement for NARS1 in RGC proliferation. Our findings demonstrate that NARS1 is required to meet protein synthetic needs and to support RGC proliferation in human brain development.
Keywords: Adolescent; Adult; Aspartate-tRNA Ligase; Base Sequence; Cell Differentiation; Cell Proliferation; Cell Size; Cell Survival; Cerebral Cortex; Child; Family; Female; Fibroblasts; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Ki-67 Antigen; Male; Microcephaly; Mutation; Neural Stem Cells; Neuroglia; Organoids; Pedigree; RNA, Transfer, Amino Acyl; Young Adult

Loss of the neural-specific BAF subunit ACTL6B relieves repression of early response genes and causes recessive autism. - Wenderski, Wendy; Wang, Lu; Krokhotin, Andrey; Walsh, Jessica J; Li, Hongjie; Shoji, Hirotaka; Ghosh, Shereen; George, Renee D; Miller, Erik L; Elias, Laura; Gillespie, Mark A; Son, Esther Y; et al. (Proc Natl Acad Sci U S A, 2020)
Synaptic activity in neurons leads to the rapid activation of genes involved in mammalian behavior. ATP-dependent chromatin remodelers such as the BAF complex contribute to these responses and are generally thought to activate transcription. However, the mechanisms keeping such "early activation" genes silent have been a mystery. In the course of investigating Mendelian recessive autism, we identified six families with segregating loss-of-function mutations in the neuronal BAF (nBAF) subunit (originally named ). Accordingly, was the most significantly mutated gene in the Simons Recessive Autism Cohort. At least 14 subunits of the nBAF complex are mutated in autism, collectively making it a major contributor to autism spectrum disorder (ASD). Patient mutations destabilized ACTL6B protein in neurons and rerouted dendrites to the wrong glomerulus in the fly olfactory system. Humans and mice lacking showed corpus callosum hypoplasia, indicating a conserved role for in facilitating neural connectivity. knockout mice on two genetic backgrounds exhibited ASD-related behaviors, including social and memory impairments, repetitive behaviors, and hyperactivity. Surprisingly, mutation of relieved repression of early response genes including AP1 transcription factors (, , , and ), increased chromatin accessibility at AP1 binding sites, and transcriptional changes in late response genes associated with early response transcription factor activity. loss is thus an important cause of recessive ASD, with impaired neuron-specific chromatin repression indicated as a potential mechanism.
Keywords: Actins; Adenosine Triphosphate; Animals; Autism Spectrum Disorder; Behavior, Animal; Chromatin; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; Chromosome Pairing; Corpus Callosum; Dendrites; Disease Models, Animal; DNA-Binding Proteins; Gene Expression Regulation; Hippocampus; Humans; Mice; Mice, Knockout; Mutation; Neurons; Transcription Factors

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

Lung Function in African American Children with Asthma Is Associated with Novel Regulatory Variants of the KIT Ligand and Gene-By-Air-Pollution Interaction. - Mak, Angel C Y; Sajuthi, Satria; Joo, Jaehyun; Xiao, Shujie; Sleiman, Patrick M; White, Marquitta J; Lee, Eunice Y; Saef, Benjamin; Hu, Donglei; Gui, Hongsheng; Keys, Kevin L; Lurmann, Fred; et al. (Genetics, 2020)
Baseline lung function, quantified as forced expiratory volume in the first second of exhalation (FEV), is a standard diagnostic criterion used by clinicians to identify and classify lung diseases. Using whole-genome sequencing data from the National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine project, we identified a novel genetic association with FEV on chromosome 12 in 867 African American children with asthma ( = 1.26 × 10, β = 0.302). Conditional analysis within 1 Mb of the tag signal (rs73429450) yielded one major and two other weaker independent signals within this peak. We explored statistical and functional evidence for all variants in linkage disequilibrium with the three independent signals and yielded nine variants as the most likely candidates responsible for the association with FEV Hi-C data and expression QTL analysis demonstrated that these variants physically interacted with (KIT ligand, also known as ), and their minor alleles were associated with increased expression of the gene in nasal epithelial cells. Gene-by-air-pollution interaction analysis found that the candidate variant rs58475486 interacted with past-year ambient sulfur dioxide exposure ( = 0.003, β = 0.32). This study identified a novel protective genetic association with FEV, possibly mediated through , in African American children with asthma. This is the first study that has identified a genetic association between lung function and , which has established a role in orchestrating allergic inflammation in asthma.

Major Impacts of Widespread Structural Variation on Gene Expression and Crop Improvement in Tomato. - Alonge, Michael; Wang, Xingang; Benoit, Matthias; Soyk, Sebastian; Pereira, Lara; Zhang, Lei; Suresh, Hamsini; Ramakrishnan, Srividya; Maumus, Florian; Ciren, Danielle; Levy, Yuval; Harel, Tom Hai; et al. (Cell, 2020)
Structural variants (SVs) underlie important crop improvement and domestication traits. However, resolving the extent, diversity, and quantitative impact of SVs has been challenging. We used long-read nanopore sequencing to capture 238,490 SVs in 100 diverse tomato lines. This panSV genome, along with 14 new reference assemblies, revealed large-scale intermixing of diverse genotypes, as well as thousands of SVs intersecting genes and cis-regulatory regions. Hundreds of SV-gene pairs exhibit subtle and significant expression changes, which could broadly influence quantitative trait variation. By combining quantitative genetics with genome editing, we show how multiple SVs that changed gene dosage and expression levels modified fruit flavor, size, and production. In the last example, higher order epistasis among four SVs affecting three related transcription factors allowed introduction of an important harvesting trait in modern tomato. Our findings highlight the underexplored role of SVs in genotype-to-phenotype relationships and their widespread importance and utility in crop improvement.
Keywords: Alleles; Crops, Agricultural; Cytochrome P-450 Enzyme System; Ecotype; Epistasis, Genetic; Fruit; Gene Duplication; Gene Expression Regulation, Plant; Genome, Plant; Genomic Structural Variation; Genotype; Inbreeding; Lycopersicon esculentum; Molecular Sequence Annotation; Phenotype; Plant Breeding; Quantitative Trait Loci

A missense mutation in the catalytic domain of O-GlcNAc transferase links perturbations in protein O-GlcNAcylation to X-linked intellectual disability. - Pravata, Veronica M; Gundogdu, Mehmet; Bartual, Sergio G; Ferenbach, Andrew T; Stavridis, Marios; Õunap, Katrin; Pajusalu, Sander; Žordania, Riina; Wojcik, Monica H; van Aalten, Daan M F (FEBS Lett, 2020)
X-linked intellectual disabilities (XLID) are common developmental disorders. The enzyme O-GlcNAc transferase encoded by OGT, a recently discovered XLID gene, attaches O-GlcNAc to nuclear and cytoplasmic proteins. As few missense mutations have been described, it is unclear what the aetiology of the patient phenotypes is. Here, we report the discovery of a missense mutation in the catalytic domain of OGT in an XLID patient. X-ray crystallography reveals that this variant leads to structural rearrangements in the catalytic domain. The mutation reduces in vitro OGT activity on substrate peptides/protein. Mouse embryonic stem cells carrying the mutation reveal reduced O-GlcNAcase (OGA) and global O-GlcNAc levels. These data suggest a direct link between changes in the O-GlcNAcome and intellectual disability observed in patients carrying OGT mutations.
Keywords: Animals; Catalytic Domain; Cell Line; Glycosylation; Humans; Intellectual Disability; Mice; Models, Molecular; Mutation, Missense; N-Acetylglucosaminyltransferases

Missense variant contribution to USP9X-female syndrome. - Jolly, Lachlan A; Parnell, Euan; Gardner, Alison E; Corbett, Mark A; Pérez-Jurado, Luis A; Shaw, Marie; Lesca, Gaetan; Keegan, Catherine; Schneider, Michael C; Griffin, Emily; Maier, Felicitas; Kiss, Courtney; et al. (NPJ Genom Med, 2020)
USP9X is an X-chromosome gene that escapes X-inactivation. Loss or compromised function of USP9X leads to neurodevelopmental disorders in males and females. While males are impacted primarily by hemizygous partial loss-of-function missense variants, in females de novo heterozygous complete loss-of-function mutations predominate, and give rise to the clinically recognisable USP9X-female syndrome. Here we provide evidence of the contribution of USP9X missense and small in-frame deletion variants in USP9X-female syndrome also. We scrutinise the pathogenicity of eleven such variants, ten of which were novel. Combined application of variant prediction algorithms, protein structure modelling, and assessment under clinically relevant guidelines universally support their pathogenicity. The core phenotype of this cohort overlapped with previous descriptions of USP9X-female syndrome, but exposed heightened variability. Aggregate phenotypic information of 35 currently known females with predicted pathogenic variation in USP9X reaffirms the clinically recognisable USP9X-female syndrome, and highlights major differences when compared to USP9X-male associated neurodevelopmental disorders.

A missense variant in Mitochondrial Amidoxime Reducing Component 1 gene and protection against liver disease. - Emdin, Connor A; Haas, Mary E; Khera, Amit V; Aragam, Krishna; Chaffin, Mark; Klarin, Derek; Hindy, George; Jiang, Lan; Wei, Wei-Qi; Feng, Qiping; Karjalainen, Juha; Havulinna, Aki; et al. (PLoS Genet, 2020)
Analyzing 12,361 all-cause cirrhosis cases and 790,095 controls from eight cohorts, we identify a common missense variant in the Mitochondrial Amidoxime Reducing Component 1 gene (MARC1 p.A165T) that associates with protection from all-cause cirrhosis (OR 0.91, p = 2.3*10-11). This same variant also associates with lower levels of hepatic fat on computed tomographic imaging and lower odds of physician-diagnosed fatty liver as well as lower blood levels of alanine transaminase (-0.025 SD, 3.7*10-43), alkaline phosphatase (-0.025 SD, 1.2*10-37), total cholesterol (-0.030 SD, p = 1.9*10-36) and LDL cholesterol (-0.027 SD, p = 5.1*10-30) levels. We identified a series of additional MARC1 alleles (low-frequency missense p.M187K and rare protein-truncating p.R200Ter) that also associated with lower cholesterol levels, liver enzyme levels and reduced risk of cirrhosis (0 cirrhosis cases for 238 R200Ter carriers versus 17,046 cases of cirrhosis among 759,027 non-carriers, p = 0.04) suggesting that deficiency of the MARC1 enzyme may lower blood cholesterol levels and protect against cirrhosis.
Keywords: Alleles; Cholesterol, LDL; Coronary Artery Disease; Datasets as Topic; Fatty Liver; Female; Genetic Predisposition to Disease; Homozygote; Humans; Liver; Liver Cirrhosis; Liver Cirrhosis, Alcoholic; Loss of Function Mutation; Male; Middle Aged; Mitochondrial Proteins; Mutation, Missense; Oxidoreductases

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Monogenic variants in dystonia: an exome-wide sequencing study. - Zech, Michael; Jech, Robert; Boesch, Sylvia; Škorvánek, Matej; Weber, Sandrina; Wagner, Matias; Zhao, Chen; Jochim, Angela; Necpál, Ján; Dincer, Yasemin; Vill, Katharina; Distelmaier, Felix; et al. (Lancet Neurol, 2020)
BACKGROUND: Dystonia is a clinically and genetically heterogeneous condition that occurs in isolation (isolated dystonia), in combination with other movement disorders (combined dystonia), or in the context of multisymptomatic phenotypes (isolated or combined dystonia with other neurological involvement). However, our understanding of its aetiology is still incomplete. We aimed to elucidate the monogenic causes for the major clinical categories of dystonia. METHODS: For this exome-wide sequencing study, study participants were identified at 33 movement-disorder and neuropaediatric specialty centres in Austria, Czech Republic, France, Germany, Poland, Slovakia, and Switzerland. Each individual with dystonia was diagnosed in accordance with the dystonia consensus definition. Index cases were eligible for this study if they had no previous genetic diagnosis and no indication of an acquired cause of their illness. The second criterion was not applied to a subset of participants with a working clinical diagnosis of dystonic cerebral palsy. Genomic DNA was extracted from blood of participants and whole-exome sequenced. To find causative variants in known disorder-associated genes, all variants were filtered, and unreported variants were classified according to American College of Medical Genetics and Genomics guidelines. All considered variants were reviewed in expert round-table sessions to validate their clinical significance. Variants that survived filtering and interpretation procedures were defined as diagnostic variants. In the cases that went undiagnosed, candidate dystonia-causing genes were prioritised in a stepwise workflow. FINDINGS: We sequenced the exomes of 764 individuals with dystonia and 346 healthy parents who were recruited between June 1, 2015, and July 31, 2019. We identified causative or probable causative variants in 135 (19%) of 728 families, involving 78 distinct monogenic disorders. We observed a larger proportion of individuals with diagnostic variants in those with dystonia (either isolated or combined) with coexisting non-movement disorder-related neurological symptoms (100 [45%] of 222; excepting cases with evidence of perinatal brain injury) than in those with combined (19 [19%] of 98) or isolated (16 [4%] of 388) dystonia. Across all categories of dystonia, 104 (65%) of the 160 detected variants affected genes which are associated with neurodevelopmental disorders. We found diagnostic variants in 11 genes not previously linked to dystonia, and propose a predictive clinical score that could guide the implementation of exome sequencing in routine diagnostics. In cases without perinatal sentinel events, genomic alterations contributed substantively to the diagnosis of dystonic cerebral palsy. In 15 families, we delineated 12 candidate genes. These include IMPDH2, encoding a key purine biosynthetic enzyme, for which robust evidence existed for its involvement in a neurodevelopmental disorder with dystonia. We identified six variants in IMPDH2, collected from four independent cohorts, that were predicted to be deleterious de-novo variants and expected to result in deregulation of purine metabolism. INTERPRETATION: In this study, we have determined the role of monogenic variants across the range of dystonic disorders, providing guidance for the introduction of personalised care strategies and fostering follow-up pathophysiological explorations. FUNDING: Else Kröner-Fresenius-Stiftung, Technische Universität München, Helmholtz Zentrum München, Medizinische Universität Innsbruck, Charles University in Prague, Czech Ministry of Education, the Slovak Grant and Development Agency, the Slovak Research and Grant Agency.
Keywords: Adolescent; Child; Child, Preschool; Dystonia; Exome; Female; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Pedigree; Whole Exome Sequencing; Young Adult

Multi-omic studies on missense PLG variants in families with otitis media. - Bootpetch, Tori C; Hafrén, Lena; Elling, Christina L; Baschal, Erin E; Manichaikul, Ani W; Pine, Harold S; Szeremeta, Wasyl; Scholes, Melissa A; Cass, Stephen P; Larson, Eric D; Chan, Kenny H; Ishaq, Rafaqat; et al. (Sci Rep, 2020)
Otitis media (OM), a very common disease in young children, can result in hearing loss. In order to potentially replicate previously reported associations between OM and PLG, exome and Sanger sequencing, RNA-sequencing of saliva and middle ear samples, 16S rRNA sequencing, molecular modeling, and statistical analyses including transmission disequilibrium tests (TDT) were performed in a multi-ethnic cohort of 718 families and simplex cases with OM. We identified four rare PLG variants c.112A > G (p.Lys38Glu), c.782G > A (p.Arg261His), c.1481C > T (p.Ala494Val) and c.2045 T > A (p.Ile682Asn), and one common variant c.1414G > A (p.Asp472Asn). However TDT analyses for these PLG variants did not demonstrate association with OM in 314 families. Additionally PLG expression is very low or absent in normal or diseased middle ear in mouse and human, and salivary expression and microbial α-diversity were non-significant in c.1414G > A (p.Asp472Asn) carriers. Based on molecular modeling, the novel rare variants particularly c.782G > A (p.Arg261His) and c.2045 T > A (p.Ile682Asn) were predicted to affect protein structure. Exploration of other potential disease mechanisms will help elucidate how PLG contributes to OM susceptibility in humans. Our results underline the importance of following up findings from genome-wide association through replication studies, preferably using multi-omic datasets.
Keywords: Animals; Ear, Middle; Female; Genomics; Humans; Male; Mice; Microbiota; Mutation, Missense; Otitis Media; Pedigree; Plasminogen; Polymorphism, Single Nucleotide; Saliva

The mutational constraint spectrum quantified from variation in 141,456 humans. - Karczewski, Konrad J; Francioli, Laurent C; Tiao, Grace; Cummings, Beryl B; Alföldi, Jessica; Wang, Qingbo; Collins, Ryan L; Laricchia, Kristen M; Ganna, Andrea; Birnbaum, Daniel P; Gauthier, Laura D; Brand, Harrison; et al. (Nature, 2020)
Genetic variants that inactivate protein-coding genes are a powerful source of information about the phenotypic consequences of gene disruption: genes that are crucial for the function of an organism will be depleted of such variants in natural populations, whereas non-essential genes will tolerate their accumulation. However, predicted loss-of-function variants are enriched for annotation errors, and tend to be found at extremely low frequencies, so their analysis requires careful variant annotation and very large sample sizes. Here we describe the aggregation of 125,748 exomes and 15,708 genomes from human sequencing studies into the Genome Aggregation Database (gnomAD). We identify 443,769 high-confidence predicted loss-of-function variants in this cohort after filtering for artefacts caused by sequencing and annotation errors. Using an improved model of human mutation rates, we classify human protein-coding genes along a spectrum that represents tolerance to inactivation, validate this classification using data from model organisms and engineered human cells, and show that it can be used to improve the power of gene discovery for both common and rare diseases.
Keywords: Adult; Brain; Cardiovascular Diseases; Cohort Studies; Databases, Genetic; Exome; Female; Genes, Essential; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Loss of Function Mutation; Male; Mutation Rate; Proprotein Convertase 9; Reproducibility of Results; RNA, Messenger; Whole Exome Sequencing; Whole Genome Sequencing

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in GET4 disrupt the transmembrane domain recognition complex pathway. - Tambe, Mitali A; Ng, Bobby G; Shimada, Shino; Wolfe, Lynne A; Adams, David R; Gahl, William A; Bamshad, Michael J; Nickerson, Deborah A; Malicdan, May C V; Freeze, Hudson H (J Inherit Metab Dis, 2020)
The transmembrane domain recognition complex (TRC) targets cytoplasmic C-terminal tail-anchored (TA) proteins to their respective membranes in the endoplasmic reticulum (ER), Golgi, and mitochondria. It is composed of three proteins, GET4, BAG6, and GET5. We identified an individual with compound heterozygous missense variants (p.Arg122His, p.Ile279Met) in GET4 that reduced all three TRC proteins by 70% to 90% in his fibroblasts, suggesting a possible defect in TA protein targeting. He presented with global developmental delay, intellectual disabilities, seizures, facial dysmorphism, and delayed bone age. We found the TA protein, syntaxin 5, is poorly targeted to Golgi membranes compared to normal controls. Since GET4 regulates ER to Golgi transport, we hypothesized that such transport would be disrupted in his fibroblasts, and discovered that retrograde (but not anterograde) transport was significantly reduced. Despite reduction in the three TRC proteins, their mRNA levels were unchanged, suggesting increased degradation in patient fibroblasts. Treating fibroblasts with the FDA-approved proteasome inhibitor, bortezomib (10 nM), restored syntaxin 5 localization and nearly normalized the levels of all three TRC proteins. Our study identifies the first individual with GET4 mutations.

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis. - Chong, Jessica X; Talbot, Jared C; Teets, Emily M; Previs, Samantha; Martin, Brit L; Shively, Kathryn M; Marvin, Colby T; Aylsworth, Arthur S; Saadeh-Haddad, Reem; Schatz, Ulrich A; Inzana, Francesca; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2020)
We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it to his son. In an eighth family comprised of seven individuals with dominantly inherited DA, a c.98C>T (p.Ala33Val) variant segregated in all four persons tested. Variants in MYLPF underlie both dominant and recessively inherited DA. Mylpf protein models suggest that the residues associated with dominant DA interact with myosin whereas the residues altered in families with recessive DA only indirectly impair this interaction. Pathological and histological exam of a foot amputated from an affected child revealed complete absence of skeletal muscle (i.e., segmental amyoplasia). To investigate the mechanism for this finding, we generated an animal model for partial MYLPF impairment by knocking out zebrafish mylpfa. The mylpfa mutant had reduced trunk contractile force and complete pectoral fin paralysis, demonstrating that mylpf impairment most severely affects limb movement. mylpfa mutant muscle weakness was most pronounced in an appendicular muscle and was explained by reduced myosin activity and fiber degeneration. Collectively, our findings demonstrate that partial loss of MYLPF function can lead to congenital contractures, likely as a result of degeneration of skeletal muscle in the distal limb.
Keywords: Adolescent; Amino Acid Sequence; Animals; Arthrogryposis; Child; Contracture; Extremities; Female; Humans; Male; Muscle, Skeletal; Musculoskeletal Abnormalities; Mutation; Myosin Light Chains; Myosins; Pedigree; Young Adult; Zebrafish

Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

A novel homozygous KY variant causing a complex neurological disorder. - Arif, Beenish; Rasheed, Arisha; Kumar, Kishore R; Fatima, Amara; Abbas, Ghazanfar; Wohler, Elizabeth; Sobriera, Nara; Lohmann, Katja; Naz, Sadaf (Eur J Med Genet, 2020)
Mutations in the gene kyphoscoliosis peptidase (KY) are known to cause myofibrillar myopathy-7 and hereditary spastic paraplegia. We investigated the genetic cause of a complex neurological phenotype in a consanguineous Pakistani family with four affected members, manifesting lower limb spasticity and weakness, toe walking, pes equinovarus, and a speech disorder. Genome-wide linkage analysis with microsatellite markers delineated chromosome 3q22.2-q24 harboring the disease gene. Whole exome sequencing was performed for two subjects, identifying a homozygous 14-bp frameshift deletion NM_178554.6:c.842_855del; p(Val281GlyfsTer18) in KY. The variant segregated with the phenotype and was absent from public databases and 100 ethnically matched controls. We confirm a novel homozygous KY variant causing a complex neurological phenotype in this family. A review of previously reported KY variants suggests that variants in this gene can cause a spectrum of neurological phenotypes.
Keywords: Child; Female; Frameshift Mutation; Gait; Homozygote; Humans; Male; Myopathies, Structural, Congenital; Pedigree; Peptide Hydrolases; Phenotype; Spastic Paraplegia, Hereditary; Speech

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Lindstrand, Anna; Lupski, James R; Sutton, V Reid; et al. (Am J Med Genet A, 2020)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.

A novel RFC1 repeat motif (ACAGG) in two Asia-Pacific CANVAS families. - Scriba, Carolin K; Beecroft, Sarah J; Clayton, Joshua S; Cortese, Andrea; Sullivan, Roisin; Yau, Wai Yan; Dominik, Natalia; Rodrigues, Miriam; Walker, Elizabeth; Dyer, Zoe; Wu, Teddy Y; Davis, Mark R; et al. (Brain, 2020)
Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) is a progressive late-onset, neurological disease. Recently, a pentanucleotide expansion in intron 2 of RFC1 was identified as the genetic cause of CANVAS. We screened an Asian-Pacific cohort for CANVAS and identified a novel RFC1 repeat expansion motif, (ACAGG)exp, in three affected individuals. This motif was associated with additional clinical features including fasciculations and elevated serum creatine kinase. These features have not previously been described in individuals with genetically-confirmed CANVAS. Haplotype analysis showed our patients shared the same core haplotype as previously published, supporting the possibility of a single origin of the RFC1 disease allele. We analysed data from >26 000 genetically diverse individuals in gnomAD to show enrichment of (ACAGG) in non-European populations.
Keywords: Aged; Asian Continental Ancestry Group; Bilateral Vestibulopathy; Cerebellar Ataxia; Cohort Studies; DNA Repeat Expansion; Female; Humans; Indonesia; Male; Middle Aged; Pedigree; Replication Protein C

Organic Solute Transporter Alpha Deficiency: A Disorder With Cholestasis, Liver Fibrosis, and Congenital Diarrhea. - Gao, Emily; Cheema, Huma; Waheed, Nadia; Mushtaq, Iqra; Erden, Nihan; Nelson-Williams, Carol; Jain, Dhanpat; Soroka, Carol J; Boyer, James L; Khalil, Youssef; Clayton, Peter T; Mistry, Pramod K; et al. (Hepatology, 2020)
Keywords: Child, Preschool; Cholestasis; Diarrhea; Humans; Liver; Liver Cirrhosis; Male; Mutation; Pedigree; Receptors, G-Protein-Coupled

The Parkinson's Disease Genome-Wide Association Study Locus Browser. - Grenn, Francis P; Kim, Jonggeol J; Makarious, Mary B; Iwaki, Hirotaka; Illarionova, Anastasia; Brolin, Kajsa; Kluss, Jillian H; Schumacher-Schuh, Artur F; Leonard, Hampton; Faghri, Faraz; Billingsley, Kimberley; Krohn, Lynne; et al. (Mov Disord, 2020)
BACKGROUND: Parkinson's disease (PD) is a neurodegenerative disease with an often complex component identifiable by genome-wide association studies. The most recent large-scale PD genome-wide association studies have identified more than 90 independent risk variants for PD risk and progression across more than 80 genomic regions. One major challenge in current genomics is the identification of the causal gene(s) and variant(s) at each genome-wide association study locus. The objective of the current study was to create a tool that would display data for relevant PD risk loci and provide guidance with the prioritization of causal genes and potential mechanisms at each locus. METHODS: We included all significant genome-wide signals from multiple recent PD genome-wide association studies including themost recent PD risk genome-wide association study, age-at-onset genome-wide association study, progression genome-wide association study, and Asian population PD risk genome-wide association study. We gathered data for all genes 1 Mb up and downstream of each variant to allow users to assess which gene(s) are most associated with the variant of interest based on a set of self-ranked criteria. Multiple databases were queried for each gene to collect additional causal data. RESULTS: We created a PD genome-wide association study browser tool (https://pdgenetics.shinyapps.io/GWASBrowser/) to assist the PD research community with the prioritization of genes for follow-up functional studies to identify potential therapeutic targets. CONCLUSIONS: Our PD genome-wide association study browser tool provides users with a useful method of identifying potential causal genes at all known PD risk loci from large-scale PD genome-wide association studies. We plan to update this tool with new relevant data as sample sizes increase and new PD risk loci are discovered. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. This article has been contributed to by US Government employees and their work is in the public domain in the USA.
Keywords: Age of Onset; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Neurodegenerative Diseases; Parkinson Disease; Risk Factors

Paternal mosaicism for a novel PBX1 mutation associated with recurrent perinatal death: Phenotypic expansion of the PBX1-related syndrome. - Arts, Peer; Garland, Jessica; Byrne, Alicia B; Hardy, Tristan S E; Babic, Milena; Feng, Jinghua; Wang, Paul; Ha, Thuong; King-Smith, Sarah L; Schreiber, Andreas W; Crawford, April; Manton, Nick; et al. (Am J Med Genet A, 2020)
Autosomal dominant (de novo) mutations in PBX1 are known to cause congenital abnormalities of the kidney and urinary tract (CAKUT), with or without extra-renal abnormalities. Using trio exome sequencing, we identified a PBX1 p.(Arg107Trp) mutation in a deceased one-day-old neonate presenting with CAKUT, asplenia, and severe bilateral diaphragmatic thinning and eventration. Further investigation by droplet digital PCR revealed that the mutation had occurred post-zygotically in the father, with different variant allele frequencies of the mosaic PBX1 mutation in blood (10%) and sperm (20%). Interestingly, the father had subclinical hydronephrosis in childhood. With an expected recurrence risk of one in five, chorionic villus sampling and prenatal diagnosis for the PBX1 mutation identified recurrence in a subsequent pregnancy. The family opted to continue the pregnancy and the second affected sibling was stillborn at 35 weeks, presenting with similar severe bilateral diaphragmatic eventration, microsplenia, and complete sex reversal (46, XY female). This study highlights the importance of follow-up studies for presumed de novo and low-level mosaic variants and broadens the phenotypic spectrum of developmental abnormalities caused by PBX1 mutations.
Keywords: Congenital Abnormalities; Exome; Fathers; Female; Gene Frequency; Humans; Infant, Newborn; Kidney; Male; Mosaicism; Mutation; Perinatal Death; Pre-B-Cell Leukemia Transcription Factor 1; Pregnancy; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing

Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly. - Tsai, Meng-Han; Muir, Alison M; Wang, Won-Jing; Kang, Yi-Ning; Yang, Kun-Chuan; Chao, Nian-Hsin; Wu, Mei-Feng; Chang, Ying-Chao; Porter, Brenda E; Jansen, Laura A; Sebire, Guillaume; Deconinck, Nicolas; et al. (Neuron, 2020)
Lissencephaly (LIS), denoting a "smooth brain," is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS.
Keywords: Adolescent; Adult; Age of Onset; Animals; Centrosome; Child; Child, Preschool; Chromosome Aberrations; Classical Lissencephalies and Subcortical Band Heterotopias; Cytoskeletal Proteins; Female; Gene Knockdown Techniques; Genetic Variation; Heterozygote; Humans; Infant; Magnetic Resonance Imaging; Male; Mice; Mutation; Oncogene Proteins, Fusion; Pedigree; Seizures; Young Adult

PEHO syndrome caused by compound heterozygote variants in ZNHIT3 gene. - Õunap, Katrin; Muru, Kai; Õiglane-Shlik, Eve; Ilves, Pilvi; Pajusalu, Sander; Kuus, Imbi; Wojcik, Monica H; Reimand, Tiia (Eur J Med Genet, 2020)
PEHO syndrome is characterized by Progressive Encephalopathy with Edema, Hypsarrhythmia, and Optic atrophy, which was first described in Finnish patients. A homozygous missense substitution p.Ser31Leu in ZNHIT3 was recently identified as the primary cause of PEHO syndrome in Finland. Variants in ZNHIT3 have not been identified in patients with PEHO or PEHO-like syndrome in other populations. It has therefore been suggested that PEHO syndrome caused by ZNHIT3 variants does not occur outside of the Finnish population. We describe the first patient outside Finland who carries compound heterozygous variants in ZNHIT3 gene causing PEHO syndrome. Trio genome sequencing was carried out and the identified variants were confirmed by Sanger sequencing. The patient filled all diagnostic clinical criteria of PEHO syndrome. We identified biallelic missense variants in ZNHIT3 gene: the c.92C > T p.(Ser31Leu) variant (NM_004773.3), which is described previously as causing PEHO syndrome and the second novel variant c.41G > T p.(Cys14Phe). There are only eight heterozygous carriers of c.41G > T variant in the gnomAD database and it is predicted damaging by multiple in silico algorithms. The ZNHIT3-associated PEHO syndrome exists outside of the Finnish population.
Keywords: Brain Edema; Databases, Genetic; Edema; Epileptic Syndromes; Female; Finland; Heterozygote; Humans; Infant, Newborn; Mutation, Missense; Neurodegenerative Diseases; Nuclear Proteins; Optic Atrophy; Phenotype; Spasms, Infantile; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

Phenotype expansion of heterozygous FOXC1 pathogenic variants toward involvement of congenital anomalies of the kidneys and urinary tract (CAKUT). - Wu, Chen-Han Wilfred; Mann, Nina; Nakayama, Makiko; Connaughton, Dervla M; Dai, Rufeng; Kolvenbach, Caroline M; Kause, Franziska; Ottlewski, Isabel; Wang, Chunyan; Klämbt, Verena; Seltzsam, Steve; Lai, Ethan W; et al. (Genet Med, 2020)
PURPOSE: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease in childhood and adolescence. We aim to identify novel monogenic causes of CAKUT. METHODS: Exome sequencing was performed in 550 CAKUT-affected families. RESULTS: We discovered seven FOXC1 heterozygous likely pathogenic variants within eight CAKUT families. These variants are either never reported, or present in <5 alleles in the gnomAD database with ~141,456 controls. FOXC1 is a causal gene for Axenfeld-Rieger syndrome type 3 and anterior segment dysgenesis 3. Pathogenic variants in FOXC1 have not been detected in patients with CAKUT yet. Interestingly, mouse models for Foxc1 show severe CAKUT phenotypes with incomplete penetrance and variable expressivity. The FOXC1 variants are enriched in the CAKUT cohort compared with the control. Genotype-phenotype correlations showed that Axenfeld-Rieger syndrome or anterior segment dysgenesis can be caused by both truncating and missense pathogenic variants, and the missense variants are located at the forkhead domain. In contrast, for CAKUT, there is no truncating pathogenic variant, and all variants except one are located outside the forkhead domain. CONCLUSION: We thereby expanded the phenotype of FOXC1 pathogenic variants toward involvement of CAKUT, which can potentially be explained by allelism.
Keywords: Child; Eye Abnormalities; Forkhead Transcription Factors; Heterozygote; Humans; Kidney; Phenotype; Urinary Tract

Phenotypic spectrum and transcriptomic profile associated with germline variants in TRAF7. - Castilla-Vallmanya, Laura; Selmer, Kaja K; Dimartino, Clémantine; Rabionet, Raquel; Blanco-Sánchez, Bernardo; Yang, Sandra; Reijnders, Margot R F; van Essen, Antonie J; Oufadem, Myriam; Vigeland, Magnus D; Stadheim, Barbro; Houge, Gunnar; et al. (Genet Med, 2020)
PURPOSE: Somatic variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) cause meningioma, while germline variants have recently been identified in seven patients with developmental delay and cardiac, facial, and digital anomalies. We aimed to define the clinical and mutational spectrum associated with TRAF7 germline variants in a large series of patients, and to determine the molecular effects of the variants through transcriptomic analysis of patient fibroblasts. METHODS: We performed exome, targeted capture, and Sanger sequencing of patients with undiagnosed developmental disorders, in multiple independent diagnostic or research centers. Phenotypic and mutational comparisons were facilitated through data exchange platforms. Whole-transcriptome sequencing was performed on RNA from patient- and control-derived fibroblasts. RESULTS: We identified heterozygous missense variants in TRAF7 as the cause of a developmental delay-malformation syndrome in 45 patients. Major features include a recognizable facial gestalt (characterized in particular by blepharophimosis), short neck, pectus carinatum, digital deviations, and patent ductus arteriosus. Almost all variants occur in the WD40 repeats and most are recurrent. Several differentially expressed genes were identified in patient fibroblasts. CONCLUSION: We provide the first large-scale analysis of the clinical and mutational spectrum associated with the TRAF7 developmental syndrome, and we shed light on its molecular etiology through transcriptome studies.
Keywords: Exome; Germ Cells; Humans; Intellectual Disability; Mutation, Missense; Phenotype; Transcriptome; Tumor Necrosis Factor Receptor-Associated Peptides and Proteins

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

Polygenic background modifies penetrance of monogenic variants for tier 1 genomic conditions. - Fahed, Akl C; Wang, Minxian; Homburger, Julian R; Patel, Aniruddh P; Bick, Alexander G; Neben, Cynthia L; Lai, Carmen; Brockman, Deanna; Philippakis, Anthony; Ellinor, Patrick T; Cassa, Christopher A; Lebo, Matthew; et al. (Nat Commun, 2020)
Genetic variation can predispose to disease both through (i) monogenic risk variants that disrupt a physiologic pathway with large effect on disease and (ii) polygenic risk that involves many variants of small effect in different pathways. Few studies have explored the interplay between monogenic and polygenic risk. Here, we study 80,928 individuals to examine whether polygenic background can modify penetrance of disease in tier 1 genomic conditions - familial hypercholesterolemia, hereditary breast and ovarian cancer, and Lynch syndrome. Among carriers of a monogenic risk variant, we estimate substantial gradients in disease risk based on polygenic background - the probability of disease by age 75 years ranged from 17% to 78% for coronary artery disease, 13% to 76% for breast cancer, and 11% to 80% for colon cancer. We propose that accounting for polygenic background is likely to increase accuracy of risk estimation for individuals who inherit a monogenic risk variant.
Keywords: Aged; Breast Neoplasms; Case-Control Studies; Colorectal Neoplasms; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Middle Aged; Multifactorial Inheritance; Odds Ratio; Penetrance; Risk Factors

Polymicrogyria is Associated With Pathogenic Variants in PTEN. - Shao, Diane D; Achkar, Christelle M; Lai, Abbe; Srivastava, Siddharth; Doan, Ryan N; Rodan, Lance H; Chen, Allen Y; Poduri, Annapurna; Yang, Edward; Walsh, Christopher A (Ann Neurol, 2020)
OBJECTIVE: Congenital structural brain malformations have been described in patients with pathogenic phosphatase and tensin homologue (PTEN) variants, but the frequency of cortical malformations in patients with PTEN variants and their impact on clinical phenotype are not well understood. Our goal was to systematically characterize brain malformations in patients with PTEN variants and assess the relevance of their brain malformations to clinical presentation. METHODS: We systematically searched a local radiology database for patients with PTEN variants who had available brain magnetic resonance imaging (MRI). The MRI scans were reviewed systematically for cortical abnormalities. We reviewed electroencephalogram (EEG) data and evaluated the electronic medical record for evidence of epilepsy and developmental delay. RESULTS: In total, we identified 22 patients with PTEN pathogenic variants for which brain MRIs were available (age range 0.4-17 years). Twelve among these 22 patients (54%) had polymicrogyria (PMG). Variants associated with PMG or atypical gyration encoded regions of the phosphatase or C2 domains of PTEN. Interestingly, epilepsy was present in only 2 of the 12 patients with PMG. We found a trend toward higher rates of global developmental delay (GDD), intellectual disability (ID), and motor delay in individuals with cortical abnormalities, although cohort size limited statistical significance. INTERPRETATION: Malformations of cortical development, PMG in particular, represent an under-recognized phenotype associated with PTEN pathogenic variants and may have an association with cognitive and motor delays. Epilepsy was infrequent compared to the previously reported high risk of epilepsy in patients with PMG. ANN NEUROL 2020;88:1153-1164.
Keywords: Adolescent; Brain; Child; Child, Preschool; Comorbidity; Databases, Genetic; Developmental Disabilities; Electroencephalography; Female; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Massachusetts; Neuroimaging; Polymicrogyria; PTEN Phosphohydrolase

Posterior Neocortex-Specific Regulation of Neuronal Migration by CEP85L Identifies Maternal Centriole-Dependent Activation of CDK5. - Kodani, Andrew; Kenny, Connor; Lai, Abbe; Gonzalez, Dilenny M; Stronge, Edward; Sejourne, Gabrielle M; Isacco, Laura; Partlow, Jennifer N; O'Donnell, Anne; McWalter, Kirsty; Byrne, Alicia B; Barkovich, A James; et al. (Neuron, 2020)
Genes mutated in human neuronal migration disorders encode tubulin proteins and a variety of tubulin-binding and -regulating proteins, but it is very poorly understood how these proteins function together to coordinate migration. Additionally, the way in which regional differences in neocortical migration are controlled is completely unknown. Here we describe a new syndrome with remarkably region-specific effects on neuronal migration in the posterior cortex, reflecting de novo variants in CEP85L. We show that CEP85L is required cell autonomously in vivo and in vitro for migration, that it localizes to the maternal centriole, and that it forms a complex with many other proteins required for migration, including CDK5, LIS1, NDE1, KIF2A, and DYNC1H1. Loss of CEP85L disrupts CDK5 localization and activation, leading to centrosome disorganization and disrupted microtubule cytoskeleton organization. Together, our findings suggest that CEP85L highlights a complex that controls CDK5 activity to promote neuronal migration.
Keywords: Cell Movement; Centrioles; Child; Child, Preschool; Cyclin-Dependent Kinase 5; Cytoskeletal Proteins; Female; Humans; Lissencephaly; Male; Microtubules; Neocortex; Nerve Tissue Proteins; Neurons; Oncogene Proteins, Fusion; Young Adult

Predominant and novel de novo variants in 29 individuals with ALG13 deficiency: Clinical description, biomarker status, biochemical analysis, and treatment suggestions. - Ng, Bobby G; Eklund, Erik A; Shiryaev, Sergey A; Dong, Yin Y; Abbott, Mary-Alice; Asteggiano, Carla; Bamshad, Michael J; Barr, Eileen; Bernstein, Jonathan A; Chelakkadan, Shabeed; Christodoulou, John; Chung, Wendy K; et al. (J Inherit Metab Dis, 2020)
Asparagine-linked glycosylation 13 homolog (ALG13) encodes a nonredundant, highly conserved, X-linked uridine diphosphate (UDP)-N-acetylglucosaminyltransferase required for the synthesis of lipid linked oligosaccharide precursor and proper N-linked glycosylation. De novo variants in ALG13 underlie a form of early infantile epileptic encephalopathy known as EIEE36, but given its essential role in glycosylation, it is also considered a congenital disorder of glycosylation (CDG), ALG13-CDG. Twenty-four previously reported ALG13-CDG cases had de novo variants, but surprisingly, unlike most forms of CDG, ALG13-CDG did not show the anticipated glycosylation defects, typically detected by altered transferrin glycosylation. Structural homology modeling of two recurrent de novo variants, p.A81T and p.N107S, suggests both are likely to impact the function of ALG13. Using a corresponding ALG13-deficient yeast strain, we show that expressing yeast ALG13 with either of the highly conserved hotspot variants rescues the observed growth defect, but not its glycosylation abnormality. We present molecular and clinical data on 29 previously unreported individuals with de novo variants in ALG13. This more than doubles the number of known cases. A key finding is that a vast majority of the individuals presents with West syndrome, a feature shared with other CDG types. Among these, the initial epileptic spasms best responded to adrenocorticotropic hormone or prednisolone, while clobazam and felbamate showed promise for continued epilepsy treatment. A ketogenic diet seems to play an important role in the treatment of these individuals.

Prenatal Diagnosis of a Ventral Abdominal Wall Defect. - Beam, Kristyn; Wojcik, Monica H; Agrawal, Pankaj B; Smithers, Charles; Estroff, Judy (Neoreviews, 2020)
Keywords: Abnormalities, Multiple; Echocardiography; Fatal Outcome; Female; Hernia, Abdominal; Hernia, Diaphragmatic; Hernia, Ventral; Humans; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prenatal Diagnosis; Ultrasonography, Prenatal

Recurrent arginine substitutions in the ACTG2 gene are the primary driver of disease burden and severity in visceral myopathy. - Assia Batzir, Nurit; Kishor Bhagwat, Pranjali; Larson, Austin; Coban Akdemir, Zeynep; Bagłaj, Maciej; Bofferding, Leon; Bosanko, Katherine B; Bouassida, Skander; Callewaert, Bert; Cannon, Ashley; Enchautegui Colon, Yazmin; Garnica, Adolfo D; et al. (Hum Mutat, 2020)
Visceral myopathy with abnormal intestinal and bladder peristalsis includes a clinical spectrum with megacystis-microcolon intestinal hypoperistalsis syndrome and chronic intestinal pseudo-obstruction. The vast majority of cases are caused by dominant variants in ACTG2; however, the overall genetic architecture of visceral myopathy has not been well-characterized. We ascertained 53 families, with visceral myopathy based on megacystis, functional bladder/gastrointestinal obstruction, or microcolon. A combination of targeted ACTG2 sequencing and exome sequencing was used. We report a molecular diagnostic rate of 64% (34/53), of which 97% (33/34) is attributed to ACTG2. Strikingly, missense mutations in five conserved arginine residues involving CpG dinucleotides accounted for 49% (26/53) of disease in the cohort. As a group, the ACTG2-negative cases had a more favorable clinical outcome and more restricted disease. Within the ACTG2-positive group, poor outcomes (characterized by total parenteral nutrition dependence, death, or transplantation) were invariably due to one of the arginine missense alleles. Analysis of specific residues suggests a severity spectrum of p.Arg178>p.Arg257>p.Arg40 along with other less-frequently reported sites p.Arg63 and p.Arg211. These results provide genotype-phenotype correlation for ACTG2-related disease and demonstrate the importance of arginine missense changes in visceral myopathy.

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Recurrent homozygous damaging mutation in , encoding a protein disulfide isomerase, in four families with microlissencephaly. - Ghosh, Shereen Georges; Wang, Lu; Breuss, Martin W; Green, Joshua D; Stanley, Valentina; Yang, Xiaoxu; Ross, Danica; Traynor, Bryan J; Alhashem, Amal M; Azam, Matloob; Selim, Laila; Bastaki, Laila; et al. (J Med Genet, 2020)
BACKGROUND: Protein disulfide isomerase (PDI) proteins are part of the thioredoxin protein superfamily. PDIs are involved in the formation and rearrangement of disulfide bonds between cysteine residues during protein folding in the endoplasmic reticulum and are implicated in stress response pathways. METHODS: Eight children from four consanguineous families residing in distinct geographies within the Middle East and Central Asia were recruited for study. All probands showed structurally similar microcephaly with lissencephaly (microlissencephaly) brain malformations. DNA samples from each family underwent whole exome sequencing, assessment for repeat expansions and confirmatory segregation analysis. RESULTS: An identical homozygous variant in (c.500G>A), encoding thioredoxin-related transmembrane protein 2, segregated with disease in all four families. This variant changed the last coding base of exon 6, and impacted mRNA stability. All patients presented with microlissencephaly, global developmental delay, intellectual disability and epilepsy. While is an activator of cellular repeat expansion toxicity, patients showed no evidence of repeat expansions. CONCLUSION: The c.500G>A allele associates with recessive microlissencephaly, and patients show no evidence of expansions. is the first PDI implicated in a recessive disease, suggesting a protein isomerisation defect in microlissencephaly.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Consanguinity; Endoplasmic Reticulum; Exons; Female; Genetic Predisposition to Disease; Homozygote; Humans; Male; Membrane Proteins; Microcephaly; Mutation; Protein Disulfide-Isomerases; Protein Folding; Thioredoxins; Whole Exome Sequencing

Recurrent Rare Copy Number Variants Increase Risk for Esotropia. - Whitman, Mary C; Di Gioia, Silvio Alessandro; Chan, Wai-Man; Gelber, Alon; Pratt, Brandon M; Bell, Jessica L; Collins, Thomas E; Knowles, James A; Armoskus, Christopher; Pato, Michele; Pato, Carlos; Shaaban, Sherin; et al. (Invest Ophthalmol Vis Sci, 2020)
Purpose: To determine whether rare copy number variants (CNVs) increase risk for comitant esotropia. Methods: CNVs were identified in 1614 Caucasian individuals with comitant esotropia and 3922 Caucasian controls from Illumina SNP genotyping using two Hidden Markov model (HMM) algorithms, PennCNV and QuantiSNP, which call CNVs based on logR ratio and B allele frequency. Deletions and duplications greater than 10 kb were included. Common CNVs were excluded. Association testing was performed with 1 million permutations in PLINK. Significant CNVs were confirmed with digital droplet polymerase chain reaction (ddPCR). Whole genome sequencing was performed to determine insertion location and breakpoints. Results: Esotropia patients have similar rates and proportions of CNVs compared with controls but greater total length and average size of both deletions and duplications. Three recurrent rare duplications significantly (P = 1 × 10-6) increase the risk of esotropia: chromosome 2p11.2 (hg19, 2:87428677-87965359), spanning one long noncoding RNA (lncRNA) and two microRNAs (OR 14.16; 95% confidence interval [CI] 5.4-38.1); chromosome 4p15.2 (hg19, 4:25554332-25577184), spanning one lncRNA (OR 11.1; 95% CI 4.6-25.2); chromosome 10q11.22 (hg19, 10:47049547-47703870) spanning seven protein-coding genes, one lncRNA, and four pseudogenes (OR 8.96; 95% CI 5.4-14.9). Overall, 114 cases (7%) and only 28 controls (0.7%) had one of the three rare duplications. No case nor control had more than one of these three duplications. Conclusions: Rare CNVs are a source of genetic variation that contribute to the genetic risk for comitant esotropia, which is likely polygenic. Future research into the functional consequences of these recurrent duplications may shed light on the pathophysiology of esotropia.
Keywords: Case-Control Studies; DNA Copy Number Variations; Esotropia; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Infant; Male; Markov Chains; Polymerase Chain Reaction; Risk Factors

Recurrent TTN metatranscript-only c.39974-11T>G splice variant associated with autosomal recessive arthrogryposis multiplex congenita and myopathy. - Bryen, Samantha J; Ewans, Lisa J; Pinner, Jason; MacLennan, Suzanna C; Donkervoort, Sandra; Castro, Diana; Topf, Ana; O'Grady, Gina; Cummings, Beryl; Chao, Katherine R; Weisburd, Ben; Francioli, Laurent; et al. (Hum Mutat, 2020)
We present eight families with arthrogryposis multiplex congenita and myopathy bearing a TTN intron 213 extended splice-site variant (NM_001267550.1:c.39974-11T>G), inherited in trans with a second pathogenic TTN variant. Muscle-derived RNA studies of three individuals confirmed mis-splicing induced by the c.39974-11T>G variant; in-frame exon 214 skipping or use of a cryptic 3' splice-site effecting a frameshift. Confounding interpretation of pathogenicity is the absence of exons 213-217 within the described skeletal muscle TTN N2A isoform. However, RNA-sequencing from 365 adult human gastrocnemius samples revealed that 56% specimens predominantly include exons 213-217 in TTN transcripts (inclusion rate ≥66%). Further, RNA-sequencing of five fetal muscle samples confirmed that 4/5 specimens predominantly include exons 213-217 (fifth sample inclusion rate 57%). Contractures improved significantly with age for four individuals, which may be linked to decreased expression of pathogenic fetal transcripts. Our study extends emerging evidence supporting a vital developmental role for TTN isoforms containing metatranscript-only exons.

Regulation of human cerebral cortical development by EXOC7 and EXOC8, components of the exocyst complex, and roles in neural progenitor cell proliferation and survival. - Coulter, Michael E; Musaev, Damir; DeGennaro, Ellen M; Zhang, Xiaochang; Henke, Katrin; James, Kiely N; Smith, Richard S; Hill, R Sean; Partlow, Jennifer N; Kamumbu, A Stacy; Hatem, Nicole; Barkovich, A James; et al. (Genet Med, 2020)
PURPOSE: The exocyst complex is a conserved protein complex that mediates fusion of intracellular vesicles to the plasma membrane and is implicated in processes including cell polarity, cell migration, ciliogenesis, cytokinesis, autophagy, and fusion of secretory vesicles. The essential role of these genes in human genetic disorders, however, is unknown. METHODS: We performed homozygosity mapping and exome sequencing of consanguineous families with recessively inherited brain development disorders. We modeled an EXOC7 splice variant in vitro and examined EXOC7 messenger RNA (mRNA) expression in developing mouse and human cortex. We modeled exoc7 loss-of-function in a zebrafish knockout. RESULTS: We report variants in exocyst complex members, EXOC7 and EXOC8, in a novel disorder of cerebral cortex development. In EXOC7, we identified four independent partial loss-of-function (LOF) variants in a recessively inherited disorder characterized by brain atrophy, seizures, and developmental delay, and in severe cases, microcephaly and infantile death. In EXOC8, we found a homozygous truncating variant in a family with a similar clinical disorder. We modeled exoc7 deficiency in zebrafish and found the absence of exoc7 causes microcephaly. CONCLUSION: Our results highlight the essential role of the exocyst pathway in normal cortical development and how its perturbation causes complex brain disorders.
Keywords: Animals; Brain Diseases; Cell Proliferation; Homozygote; Humans; Mice; Microcephaly; Zebrafish

Spectrum of genetic variants in moderate to severe sporadic hearing loss in Pakistan. - Ramzan, Memoona; Bashir, Rasheeda; Salman, Midhat; Mujtaba, Ghulam; Sobreira, Nara; Witmer, P Dane; Naz, Sadaf (Sci Rep, 2020)
Hearing loss affects 380 million people worldwide due to environmental or genetic causes. Determining the cause of deafness in individuals without previous family history of hearing loss is challenging and has been relatively unexplored in Pakistan. We investigated the spectrum of genetic variants in hearing loss in a cohort of singleton affected individuals born to consanguineous parents. Twenty-one individuals with moderate to severe hearing loss were recruited. We performed whole-exome sequencing on DNA samples from the participants, which identified seventeen variants in ten known deafness genes and one novel candidate gene. All identified variants were homozygous except for two. Eleven of the variants were novel, including one multi-exonic homozygous deletion in OTOA. A missense variant in ESRRB was implicated for recessively inherited moderate to severe hearing loss. Two individuals were heterozygous for variants in MYO7A and CHD7, respectively, consistent with de novo variants or dominant inheritance with incomplete penetrance as the reason for their hearing loss. Our results indicate that similar to familial cases of deafness, variants in a large number of genes are responsible for moderate to severe hearing loss in sporadic individuals born to consanguineous couples.
Keywords: Adolescent; Amino Acid Sequence; Audiometry, Pure-Tone; Child; Child, Preschool; Deafness; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Hearing Loss; Heterozygote; Homozygote; Humans; Mutation, Missense; Pakistan; Phenotype; Whole Exome Sequencing; Young Adult

A structural variation reference for medical and population genetics. - Collins, Ryan L; Brand, Harrison; Karczewski, Konrad J; Zhao, Xuefang; Alföldi, Jessica; Francioli, Laurent C; Khera, Amit V; Lowther, Chelsea; Gauthier, Laura D; Wang, Harold; Watts, Nicholas A; Solomonson, Matthew; et al. (Nature, 2020)
Structural variants (SVs) rearrange large segments of DNA and can have profound consequences in evolution and human disease. As national biobanks, disease-association studies, and clinical genetic testing have grown increasingly reliant on genome sequencing, population references such as the Genome Aggregation Database (gnomAD) have become integral in the interpretation of single-nucleotide variants (SNVs). However, there are no reference maps of SVs from high-coverage genome sequencing comparable to those for SNVs. Here we present a reference of sequence-resolved SVs constructed from 14,891 genomes across diverse global populations (54% non-European) in gnomAD. We discovered a rich and complex landscape of 433,371 SVs, from which we estimate that SVs are responsible for 25-29% of all rare protein-truncating events per genome. We found strong correlations between natural selection against damaging SNVs and rare SVs that disrupt or duplicate protein-coding sequence, which suggests that genes that are highly intolerant to loss-of-function are also sensitive to increased dosage. We also uncovered modest selection against noncoding SVs in cis-regulatory elements, although selection against protein-truncating SVs was stronger than all noncoding effects. Finally, we identified very large (over one megabase), rare SVs in 3.9% of samples, and estimate that 0.13% of individuals may carry an SV that meets the existing criteria for clinically important incidental findings. This SV resource is freely distributed via the gnomAD browser and will have broad utility in population genetics, disease-association studies, and diagnostic screening.
Keywords: Continental Population Groups; Disease; Female; Genetic Testing; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genotyping Techniques; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Reference Standards; Selection, Genetic; Whole Genome Sequencing

Systems Analysis Implicates WAVE2 Complex in the Pathogenesis of Developmental Left-Sided Obstructive Heart Defects. - Edwards, Jonathan J; Rouillard, Andrew D; Fernandez, Nicolas F; Wang, Zichen; Lachmann, Alexander; Shankaran, Sunita S; Bisgrove, Brent W; Demarest, Bradley; Turan, Nahid; Srivastava, Deepak; Bernstein, Daniel; Deanfield, John; et al. (JACC Basic Transl Sci, 2020)
Genetic variants are the primary driver of congenital heart disease (CHD) pathogenesis. However, our ability to identify causative variants is limited. To identify causal CHD genes that are associated with specific molecular functions, the study used prior knowledge to filter de novo variants from 2,881 probands with sporadic severe CHD. This approach enabled the authors to identify an association between left ventricular outflow tract obstruction lesions and genes associated with the WAVE2 complex and regulation of small GTPase-mediated signal transduction. Using CRISPR zebrafish knockdowns, the study confirmed that WAVE2 complex proteins , , and and the regulators of small GTPase signaling and are critical to cardiac development.

TBX6 missense variants expand the mutational spectrum in a non-Mendelian inheritance disease. - Chen, Weisheng; Lin, Jiachen; Wang, Lianlei; Li, Xiaoxin; Zhao, Sen; Liu, Jiaqi; Akdemir, Zeynep C; Zhao, Yanxue; Du, Renqian; Ye, Yongyu; Song, Xiaofei; Zhang, Yuanqiang; et al. (Hum Mutat, 2020)
Congenital scoliosis (CS) is a birth defect with variable clinical and anatomical manifestations due to spinal malformation. The genetic etiology underlying about 10% of CS cases in the Chinese population is compound inheritance by which the gene dosage is reduced below that of haploinsufficiency. In this genetic model, the trait manifests as a result of the combined effect of a rare variant and common pathogenic variant allele at a locus. From exome sequencing (ES) data of 523 patients in Asia and two patients in Texas, we identified six TBX6 gene-disruptive variants from 11 unrelated CS patients via ES and in vitro functional testing. The in trans mild hypomorphic allele was identified in 10 of the 11 subjects; as anticipated these 10 shared a similar spinal deformity of hemivertebrae. The remaining case has a homozygous variant in TBX6 (c.418C>T) and presents a more severe spinal deformity phenotype. We found decreased transcriptional activity and abnormal cellular localization as the molecular mechanisms for TBX6 missense loss-of-function alleles. Expanding the mutational spectrum of TBX6 pathogenic alleles enabled an increased molecular diagnostic detection rate, provided further evidence for the gene dosage-dependent genetic model underlying CS, and refined clinical classification.
Keywords: Alleles; Cell Line; Female; Gene Expression; Genes, Reporter; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inheritance Patterns; Male; Models, Molecular; Molecular Diagnostic Techniques; Mutation, Missense; Phenotype; Protein Conformation; Radiography; Sequence Analysis, DNA; Spine; Structure-Activity Relationship; T-Box Domain Proteins; Whole Exome Sequencing

Topical cholesterol/lovastatin for the treatment of porokeratosis: A pathogenesis-directed therapy. - Atzmony, Lihi; Lim, Young H; Hamilton, Claire; Leventhal, Jonathan S; Wagner, Annette; Paller, Amy S; Choate, Keith A (J Am Acad Dermatol, 2020)
BACKGROUND: Porokeratosis is associated with mevalonate pathway gene mutations. Therapeutic options are few and often limited in efficacy. We hypothesized that topical therapy that aims to replenish cholesterol, an essential mevalonate pathway end-product, and block the accumulation of mevalonate pathway toxic metabolites could alleviate porokeratosis. OBJECTIVE: To study the efficacy of topical cholesterol/lovastatin in different variants of porokeratosis. METHODS: We enrolled a series of 5 porokeratosis patients,1 with disseminated superficial actinic porokeratosis, 2 with porokeratosis palmaris et plantaris disseminata, and 2 with linear porokeratosis. Patients were genotyped before initiation of therapy. Patients then applied topical cholesterol/lovastatin twice daily to a unilaterally defined treatment area for up to 3 months. The response was evaluated and patients photographed at every visit. RESULTS: Three patients had MVD mutations, and 2 patients had PMVK mutations. Treatment with topical cholesterol/lovastatin (but not cholesterol alone) resulted in near complete clearance of disseminated superficial actinic porokeratosis lesions after 4 weeks of therapy and moderate improvement of porokeratosis palmaris et plantaris disseminata lesions and linear porokeratosis lesions. There were no adverse events. LIMITATIONS: Case series design with a small number of patients. CONCLUSION: Topical cholesterol/lovastatin is an effective and well-tolerated therapy for porokeratosis that underscores the utility of a pathogenesis-based therapy that replaces deficient end products and prevents accumulation of potentially toxic precursors.

Type 2 and interferon inflammation regulate SARS-CoV-2 entry factor expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Li, Yingchun; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel C Y; et al. (Nat Commun, 2020)
Coronavirus disease 2019 (COVID-19) is caused by SARS-CoV-2, an emerging virus that utilizes host proteins ACE2 and TMPRSS2 as entry factors. Understanding the factors affecting the pattern and levels of expression of these genes is important for deeper understanding of SARS-CoV-2 tropism and pathogenesis. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci for both ACE2 and TMPRSS2, that vary in frequency across world populations. We find TMPRSS2 is part of a mucus secretory network, highly upregulated by type 2 (T2) inflammation through the action of interleukin-13, and that the interferon response to respiratory viruses highly upregulates ACE2 expression. IL-13 and virus infection mediated effects on ACE2 expression were also observed at the protein level in the airway epithelium. Finally, we define airway responses to common coronavirus infections in children, finding that these infections generate host responses similar to other viral species, including upregulation of IL6 and ACE2. Our results reveal possible mechanisms influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.
Keywords: Angiotensin-Converting Enzyme 2; Betacoronavirus; Child; Coronavirus Infections; COVID-19; Epithelial Cells; Gene Expression Profiling; Gene Expression Regulation; Genetic Variation; Host-Pathogen Interactions; Humans; Inflammation; Interferons; Interleukin-13; Middle Aged; Nasal Mucosa; Pandemics; Peptidyl-Dipeptidase A; Pneumonia, Viral; SARS-CoV-2; Serine Endopeptidases; Virus Internalization

Type 2 and interferon inflammation strongly regulate SARS-CoV-2 related gene expression in the airway epithelium. - Sajuthi, Satria P; DeFord, Peter; Jackson, Nathan D; Montgomery, Michael T; Everman, Jamie L; Rios, Cydney L; Pruesse, Elmar; Nolin, James D; Plender, Elizabeth G; Wechsler, Michael E; Mak, Angel Cy; Eng, Celeste; et al. (bioRxiv, 2020)
Coronavirus disease 2019 (COVID-19) outcomes vary from asymptomatic infection to death. This disparity may reflect different airway levels of the SARS-CoV-2 receptor, ACE2, and the spike protein activator, TMPRSS2. Here we explore the role of genetics and co-expression networks in regulating these genes in the airway, through the analysis of nasal airway transcriptome data from 695 children. We identify expression quantitative trait loci (eQTL) for both and , that vary in frequency across world populations. Importantly, we find is part of a mucus secretory network, highly upregulated by T2 inflammation through the action of interleukin-13, and that interferon response to respiratory viruses highly upregulates expression. Finally, we define airway responses to coronavirus infections in children, finding that these infections upregulate while also stimulating a more pronounced cytotoxic immune response relative to other respiratory viruses. Our results reveal mechanisms likely influencing SARS-CoV-2 infectivity and COVID-19 clinical outcomes.

The utility of exome sequencing for fetal pleural effusions. - Jelin, Angie C; Sobreira, Nara; Wohler, Elizabeth; Solomon, Benjamin; Sparks, Teresa; Sagaser, Katelynn G; Forster, Katherine R; Miller, Jena; Witmer, P Dane; Hamosh, Ada; Valle, David; Blakemore, Karin (Prenat Diagn, 2020)
OBJECTIVE: We sought to evaluate the performance of exome sequencing (ES) in determining an underlying genetic etiology for cases of fetal pleural effusions. STUDY DESIGN: We examined a prospective cohort series of fetal pleural effusions visualized sonographically between 1 April 2016 and 31 August 2017. Fetal pleural effusions attributed to twin sharing, anemia, or structural anomalies were excluded, as were all cases with a genetic diagnosis established by karyotype or chromosomal microarray analysis. The remaining cases with pleural effusions of unclear etiology were offered ES. ES was performed by clinical sequencing and/or sequencing under the Baylor-Hopkins Center for Mendelian Genomics' (BHCMG) research platform. All cases were evaluated for novel genes or phenotypic expansion of disease-causing genes. RESULTS: ES was performed on six probands affected by pleural effusions. A pathogenic variant was identified in one case (16.7%). Four additional cases had variants of uncertain significance (VUS) in candidate genes of pathological interest. Neither clinical nor candidate genes were evident in the final case. CONCLUSION: ES should be considered in the evaluation of prenatally detected idiopathic pleural effusions when other diagnostic workup for a genetic etiology has failed.

Validation of a Genome-Wide Polygenic Score for Coronary Artery Disease in South Asians. - Wang, Minxian; Menon, Ramesh; Mishra, Sanghamitra; Patel, Aniruddh P; Chaffin, Mark; Tanneeru, Deepak; Deshmukh, Manjari; Mathew, Oshin; Apte, Sanika; Devanboo, Christina S; Sundaram, Sumathi; Lakshmipathy, Praveena; et al. (J Am Coll Cardiol, 2020)
BACKGROUND: Genome-wide polygenic scores (GPS) integrate information from many common DNA variants into a single number. Because rates of coronary artery disease (CAD) are substantially higher among South Asians, a GPS to identify high-risk individuals may be particularly useful in this population. OBJECTIVES: This analysis used summary statistics from a prior genome-wide association study to derive a new GPS for South Asians. METHODS: This GPS was validated in 7,244 South Asian UK Biobank participants and tested in 491 individuals from a case-control study in Bangladesh. Next, a static ancestry and GPS reference distribution was built using whole-genome sequencing from 1,522 Indian individuals, and a framework was tested for projecting individuals onto this static ancestry and GPS reference distribution using 1,800 CAD cases and 1,163 control subjects newly recruited in India. RESULTS: The GPS, containing 6,630,150 common DNA variants, had an odds ratio (OR) per SD of 1.58 in South Asian UK Biobank participants and 1.60 in the Bangladeshi study (p < 0.001 for each). Next, individuals of the Indian case-control study were projected onto static reference distributions, observing an OR/SD of 1.66 (p < 0.001). Compared with the middle quintile, risk for CAD was most pronounced for those in the top 5% of the GPS distribution-ORs of 4.16, 2.46, and 3.22 in the South Asian UK Biobank, Bangladeshi, and Indian studies, respectively (p < 0.05 for each). CONCLUSIONS: The new GPS has been developed and tested using 3 distinct South Asian studies, and provides a generalizable framework for ancestry-specific GPS assessment.
Keywords: Adult; Aged; Bangladesh; Case-Control Studies; Coronary Artery Disease; Female; Genome-Wide Association Study; Humans; India; Male; Middle Aged; Multifactorial Inheritance

variants are associated with multiple congenital anomalies including ciliopathy phenotypes. - Marquez, Jonathan; Mann, Nina; Arana, Kathya; Deniz, Engin; Ji, Weizhen; Konstantino, Monica; Mis, Emily K; Deshpande, Charu; Jeffries, Lauren; McGlynn, Julie; Hugo, Hannah; Widmeier, Eugen; et al. (J Med Genet, 2020)
BACKGROUND: Cilia are dynamic cellular extensions that generate and sense signals to orchestrate proper development and tissue homeostasis. They rely on the underlying polarisation of cells to participate in signalling. Cilia dysfunction is a well-known cause of several diseases that affect multiple organ systems including the kidneys, brain, heart, respiratory tract, skeleton and retina. METHODS: Among individuals from four unrelated families, we identified variants in ( that manifested in a variety of pathologies. In our proband, we also examined patient tissues. We depleted in frog embryos to generate a loss-of-function model. Finally, we tested the pathogenicity of patient variants through rescue experiments in the frog model. RESULTS: Patients with variants of were found to have a variety of phenotypes including cystic kidneys, nephrotic syndrome, hydrocephalus, limb abnormalities, congenital heart disease and craniofacial malformations. We also observed a loss of cilia in cystic kidney tissue of our proband. Knockdown of in embryos recapitulated many of these phenotypes and resulted in a loss of cilia in multiple tissues. Unlike introduction of wildtype in frog embryos depleted of introduction of patient variants was largely ineffective in restoring proper ciliation and tissue morphology in the kidney and brain suggesting that the variants were indeed detrimental to function. CONCLUSION: These findings in both patient tissues and shed light on how mutations in may lead to tissue-specific manifestations of disease. DLG5 is essential for cilia and many of the patient phenotypes are in the ciliopathy spectrum.

Variants in CAPZA2, a member of an F-actin capping complex, cause intellectual disability and developmental delay. - Huang, Yan; Mao, Xiao; van Jaarsveld, Richard H; Shu, Li; Terhal, Paulien A; Jia, Zhengjun; Xi, Hui; Peng, Ying; Yan, Huiming; Yuan, Shan; Li, Qibin; Wang, Hua; et al. (Hum Mol Genet, 2020)
The actin cytoskeleton is regulated by many proteins including capping proteins that stabilize actin filaments (F-actin) by inhibiting actin polymerization and depolymerization. Here, we report two pediatric probands who carry damaging heterozygous de novo mutations in CAPZA2 (HGNC: 1490) and exhibit neurological symptoms with shared phenotypes including global motor development delay, speech delay, intellectual disability, hypotonia and a history of seizures. CAPZA2 encodes a subunit of an F-actin-capping protein complex (CapZ). CapZ is an obligate heterodimer consisting of α and β heterodimer conserved from yeast to human. Vertebrate genomes contain three α subunits encoded by three different genes and CAPZA2 encodes the α2 subunit. The single orthologue of CAPZA genes in Drosophila is cpa. Loss of cpa leads to lethality in early development and expression of the human reference; CAPZA2 rescues this lethality. However, the two CAPZA2 variants identified in the probands rescue this lethality at lower efficiency than the reference. Moreover, expression of the CAPZA2 variants affects bristle morphogenesis, a process that requires extensive actin polymerization and bundling during development. Taken together, our findings suggest that variants in CAPZA2 lead to a non-syndromic neurodevelopmental disorder in children.

Whole exome sequencing in a large pedigree with DCM identifies a novel mutation in . - Robyns, Tomas; Willems, Rik; Van Cleemput, Johan; Jhangiani, Shalini; Muzny, Donna; Gibbs, Richard; Lupski, James R; Breckpot, Jeroen; Devriendt, Koenraad; Corveleyn, Anniek (Acta Cardiol, 2020)
Familial dilated cardiomyopathy (DCM) is genetically heterogeneous and is associated with mutations in at least 40 different genes. Apart from encoding the giant protein Titin, none of these genes have an expected diagnostic yield of more than 5% complicating genetic diagnosis. Whole exome sequencing (WES) is a powerful alternative for the identification of the causal gene, however variant interpretation remains challenging. We report on WES in a large family with autosomal dominant DCM complicated by end stage heart failure and non-sustained ventricular arrhythmias in whom no causative mutation was identified using a targeted gene panel including 28 genes. WES was applied on 2 affected cousins. Stringent filtering of the identified genetic variants was performed including population variant frequencies, in silico analysis, orthologous and paralogous conservation. Subsequently Sanger sequencing was performed for 10 potential disease causing variants in order to confirm the presence of the variant and to evaluate co-segregation. Only one variant in exon 9 of the RBM20 gene (c.2714T > A, p.Met950Lys, NM_001334363) showed full co-segregation in the 7 affected family members resulting in a maximum 2-point LOD score of 2.1 and suggesting this as the pathogenic mutation responsible for the phenotype. Recently mutations in RBM20 have been linked to arrhythmogenic dilated cardiomyopathy caused by defective splicing of the giant sarcomere protein titin and abnormal calcium handling. We report the identification of a novel mutation in RBM20 by WES in a large pedigree with DCM.

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Whole Exome Sequencing; Wolff-Parkinson-White Syndrome; Young Adult

Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

A2ML1 and otitis media: novel variants, differential expression, and relevant pathways. - Larson, Eric D; Magno, Jose Pedrito M; Steritz, Matthew J; Llanes, Erasmo Gonzalo D V; Cardwell, Jonathan; Pedro, Melquiadesa; Roberts, Tori Bootpetch; Einarsdottir, Elisabet; Rosanes, Rose Anne Q; Greenlee, Christopher; Santos, Rachel Ann P; Yousaf, Ayesha; et al. (Hum Mutat, 2019)
A genetic basis for otitis media is established, however, the role of rare variants in disease etiology is largely unknown. Previously a duplication variant within A2ML1 was identified as a significant risk factor for otitis media in an indigenous Filipino population and in US children. In this report exome and Sanger sequencing was performed using DNA samples from the indigenous Filipino population, Filipino cochlear implantees, US probands, Finnish, and Pakistani families with otitis media. Sixteen novel, damaging A2ML1 variants identified in otitis media patients were rare or low-frequency in population-matched controls. In the indigenous population, both gingivitis and A2ML1 variants including the known duplication variant and the novel splice variant c.4061 + 1 G>C were independently associated with otitis media. Sequencing of salivary RNA samples from indigenous Filipinos demonstrated lower A2ML1 expression according to the carriage of A2ML1 variants. Sequencing of additional salivary RNA samples from US patients with otitis media revealed differentially expressed genes that are highly correlated with A2ML1 expression levels. In particular, RND3 is upregulated in both A2ML1 variant carriers and high-A2ML1 expressors. These findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media.

Aberrant Function of the C-Terminal Tail of HIST1H1E Accelerates Cellular Senescence and Causes Premature Aging. - Flex, Elisabetta; Martinelli, Simone; Van Dijck, Anke; Ciolfi, Andrea; Cecchetti, Serena; Coluzzi, Elisa; Pannone, Luca; Andreoli, Cristina; Radio, Francesca Clementina; Pizzi, Simone; Carpentieri, Giovanna; Bruselles, Alessandro; et al. (Am J Hum Genet, 2019)
Histones mediate dynamic packaging of nuclear DNA in chromatin, a process that is precisely controlled to guarantee efficient compaction of the genome and proper chromosomal segregation during cell division and to accomplish DNA replication, transcription, and repair. Due to the important structural and regulatory roles played by histones, it is not surprising that histone functional dysregulation or aberrant levels of histones can have severe consequences for multiple cellular processes and ultimately might affect development or contribute to cell transformation. Recently, germline frameshift mutations involving the C-terminal tail of HIST1H1E, which is a widely expressed member of the linker histone family and facilitates higher-order chromatin folding, have been causally linked to an as-yet poorly defined syndrome that includes intellectual disability. We report that these mutations result in stable proteins that reside in the nucleus, bind to chromatin, disrupt proper compaction of DNA, and are associated with a specific methylation pattern. Cells expressing these mutant proteins have a dramatically reduced proliferation rate and competence, hardly enter into the S phase, and undergo accelerated senescence. Remarkably, clinical assessment of a relatively large cohort of subjects sharing these mutations revealed a premature aging phenotype as a previously unrecognized feature of the disorder. Our findings identify a direct link between aberrant chromatin remodeling, cellular senescence, and accelerated aging.

Allele-specific RNA interference prevents neuropathy in Charcot-Marie-Tooth disease type 2D mouse models. - Morelli, Kathryn H; Griffin, Laurie B; Pyne, Nettie K; Wallace, Lindsay M; Fowler, Allison M; Oprescu, Stephanie N; Takase, Ryuichi; Wei, Na; Meyer-Schuman, Rebecca; Mellacheruvu, Dattatreya; Kitzman, Jacob O; Kocen, Samuel G; et al. (J Clin Invest, 2019)
Gene therapy approaches are being deployed to treat recessive genetic disorders by restoring the expression of mutated genes. However, the feasibility of these approaches for dominantly inherited diseases - where treatment may require reduction in the expression of a toxic mutant protein resulting from a gain-of-function allele - is unclear. Here we show the efficacy of allele-specific RNAi as a potential therapy for Charcot-Marie-Tooth disease type 2D (CMT2D), caused by dominant mutations in glycyl-tRNA synthetase (GARS). A de novo mutation in GARS was identified in a patient with a severe peripheral neuropathy, and a mouse model precisely recreating the mutation was produced. These mice developed a neuropathy by 3-4 weeks of age, validating the pathogenicity of the mutation. RNAi sequences targeting mutant GARS mRNA, but not wild-type, were optimized and then packaged into AAV9 for in vivo delivery. This almost completely prevented the neuropathy in mice treated at birth. Delaying treatment until after disease onset showed modest benefit, though this effect decreased the longer treatment was delayed. These outcomes were reproduced in a second mouse model of CMT2D using a vector specifically targeting that allele. The effects were dose dependent, and persisted for at least 1 year. Our findings demonstrate the feasibility of AAV9-mediated allele-specific knockdown and provide proof of concept for gene therapy approaches for dominant neuromuscular diseases.

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Hu, Jianhong; Sedlazeck, Fritz J; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.

Bi-allelic GOT2 Mutations Cause a Treatable Malate-Aspartate Shuttle-Related Encephalopathy. - van Karnebeek, Clara D M; Ramos, Rúben J; Wen, Xiao-Yan; Tarailo-Graovac, Maja; Gleeson, Joseph G; Skrypnyk, Cristina; Brand-Arzamendi, Koroboshka; Karbassi, Farhad; Issa, Mahmoud Y; van der Lee, Robin; Drögemöller, Britt I; Koster, Janet; et al. (Am J Hum Genet, 2019)
Early-infantile encephalopathies with epilepsy are devastating conditions mandating an accurate diagnosis to guide proper management. Whole-exome sequencing was used to investigate the disease etiology in four children from independent families with intellectual disability and epilepsy, revealing bi-allelic GOT2 mutations. In-depth metabolic studies in individual 1 showed low plasma serine, hypercitrullinemia, hyperlactatemia, and hyperammonemia. The epilepsy was serine and pyridoxine responsive. Functional consequences of observed mutations were tested by measuring enzyme activity and by cell and animal models. Zebrafish and mouse models were used to validate brain developmental and functional defects and to test therapeutic strategies. GOT2 encodes the mitochondrial glutamate oxaloacetate transaminase. GOT2 enzyme activity was deficient in fibroblasts with bi-allelic mutations. GOT2, a member of the malate-aspartate shuttle, plays an essential role in the intracellular NAD(H) redox balance. De novo serine biosynthesis was impaired in fibroblasts with GOT2 mutations and GOT2-knockout HEK293 cells. Correcting the highly oxidized cytosolic NAD-redox state by pyruvate supplementation restored serine biosynthesis in GOT2-deficient cells. Knockdown of got2a in zebrafish resulted in a brain developmental defect associated with seizure-like electroencephalography spikes, which could be rescued by supplying pyridoxine in embryo water. Both pyridoxine and serine synergistically rescued embryonic developmental defects in zebrafish got2a morphants. The two treated individuals reacted favorably to their treatment. Our data provide a mechanistic basis for the biochemical abnormalities in GOT2 deficiency that may also hold for other MAS defects.

Biallelic mutations in valyl-tRNA synthetase gene VARS are associated with a progressive neurodevelopmental epileptic encephalopathy. - Friedman, Jennifer; Smith, Desiree E; Issa, Mahmoud Y; Stanley, Valentina; Wang, Rengang; Mendes, Marisa I; Wright, Meredith S; Wigby, Kristen; Hildreth, Amber; Crawford, John R; Koehler, Alanna E; Chowdhury, Shimul; et al. (Nat Commun, 2019)
Aminoacyl-tRNA synthetases (ARSs) function to transfer amino acids to cognate tRNA molecules, which are required for protein translation. To date, biallelic mutations in 31 ARS genes are known to cause recessive, early-onset severe multi-organ diseases. VARS encodes the only known valine cytoplasmic-localized aminoacyl-tRNA synthetase. Here, we report seven patients from five unrelated families with five different biallelic missense variants in VARS. Subjects present with a range of global developmental delay, epileptic encephalopathy and primary or progressive microcephaly. Longitudinal assessment demonstrates progressive cortical atrophy and white matter volume loss. Variants map to the VARS tRNA binding domain and adjacent to the anticodon domain, and disrupt highly conserved residues. Patient primary cells show intact VARS protein but reduced enzymatic activity, suggesting partial loss of function. The implication of VARS in pediatric neurodegeneration broadens the spectrum of human diseases due to mutations in tRNA synthetase genes.
Keywords: Alleles; Anticodon; Child; Child, Preschool; Disease Progression; Epilepsy; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Mutation; Neurodevelopmental Disorders; Pedigree; Protein Biosynthesis; Protein Interaction Domains and Motifs; RNA, Transfer; Valine-tRNA Ligase; Whole Exome Sequencing; Whole Genome Sequencing

Bi-allelic Variants in DYNC1I2 Cause Syndromic Microcephaly with Intellectual Disability, Cerebral Malformations, and Dysmorphic Facial Features. - Ansar, Muhammad; Ullah, Farid; Paracha, Sohail A; Adams, Darius J; Lai, Abbe; Pais, Lynn; Iwaszkiewicz, Justyna; Millan, Francisca; Sarwar, Muhammad T; Agha, Zehra; Shah, Sayyed Fahim; Qaisar, Azhar Ali; et al. (Am J Hum Genet, 2019)
Cargo transport along the cytoplasmic microtubular network is essential for neuronal function, and cytoplasmic dynein-1 is an established molecular motor that is critical for neurogenesis and homeostasis. We performed whole-exome sequencing, homozygosity mapping, and chromosomal microarray studies in five individuals from three independent pedigrees and identified likely-pathogenic variants in DYNC1I2 (Dynein Cytoplasmic 1 Intermediate Chain 2), encoding a component of the cytoplasmic dynein 1 complex. In a consanguineous Pakistani family with three affected individuals presenting with microcephaly, severe intellectual disability, simplification of cerebral gyration, corpus callosum hypoplasia, and dysmorphic facial features, we identified a homozygous splice donor site variant (GenBank: NM_001378.2:c.607+1G>A). We report two additional individuals who have similar neurodevelopmental deficits and craniofacial features and harbor deleterious variants; one individual bears a c.740A>G (p.Tyr247Cys) change in trans with a 374 kb deletion encompassing DYNC1I2, and an unrelated individual harbors the compound-heterozygous variants c.868C>T (p.Gln290) and c.740A>G (p.Tyr247Cys). Zebrafish larvae subjected to CRISPR-Cas9 gene disruption or transient suppression of dync1i2a displayed significantly altered craniofacial patterning with concomitant reduction in head size. We monitored cell death and cell cycle progression in dync1i2a zebrafish models and observed significantly increased apoptosis, likely due to prolonged mitosis caused by abnormal spindle morphology, and this finding offers initial insights into the cellular basis of microcephaly. Additionally, complementation studies in zebrafish demonstrate that p.Tyr247Cys attenuates gene function, consistent with protein structural analysis. Our genetic and functional data indicate that DYNC1I2 dysfunction probably causes an autosomal-recessive microcephaly syndrome and highlight further the critical roles of the dynein-1 complex in neurodevelopment.

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.

Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish. - Siekierska, Aleksandra; Stamberger, Hannah; Deconinck, Tine; Oprescu, Stephanie N; Partoens, Michèle; Zhang, Yifan; Sourbron, Jo; Adriaenssens, Elias; Mullen, Patrick; Wiencek, Patrick; Hardies, Katia; Lee, Jeong-Soo; et al. (Nat Commun, 2019)
Aminoacyl tRNA synthetases (ARSs) link specific amino acids with their cognate transfer RNAs in a critical early step of protein translation. Mutations in ARSs have emerged as a cause of recessive, often complex neurological disease traits. Here we report an allelic series consisting of seven novel and two previously reported biallelic variants in valyl-tRNA synthetase (VARS) in ten patients with a developmental encephalopathy with microcephaly, often associated with early-onset epilepsy. In silico, in vitro, and yeast complementation assays demonstrate that the underlying pathomechanism of these mutations is most likely a loss of protein function. Zebrafish modeling accurately recapitulated some of the key neurological disease traits. These results provide both genetic and biological insights into neurodevelopmental disease and pave the way for further in-depth research on ARS related recessive disorders and precision therapies.
Keywords: Alleles; Animals; Brain Diseases; Cell Line; Disease Models, Animal; Epilepsy; Female; Fibroblasts; Gene Knockout Techniques; Genetic Predisposition to Disease; Humans; Loss of Function Mutation; Male; Microcephaly; Models, Molecular; Neurodevelopmental Disorders; Pedigree; Prosencephalon; Valine-tRNA Ligase; Zebrafish

Bioinformatics-Based Identification of Expanded Repeats: A Non-reference Intronic Pentamer Expansion in RFC1 Causes CANVAS. - Rafehi, Haloom; Szmulewicz, David J; Bennett, Mark F; Sobreira, Nara L M; Pope, Kate; Smith, Katherine R; Gillies, Greta; Diakumis, Peter; Dolzhenko, Egor; Eberle, Michael A; Barcina, María García; Breen, David P; et al. (Am J Hum Genet, 2019)
Genomic technologies such as next-generation sequencing (NGS) are revolutionizing molecular diagnostics and clinical medicine. However, these approaches have proven inefficient at identifying pathogenic repeat expansions. Here, we apply a collection of bioinformatics tools that can be utilized to identify either known or novel expanded repeat sequences in NGS data. We performed genetic studies of a cohort of 35 individuals from 22 families with a clinical diagnosis of cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS). Analysis of whole-genome sequence (WGS) data with five independent algorithms identified a recessively inherited intronic repeat expansion [(AAGGG)] in the gene encoding Replication Factor C1 (RFC1). This motif, not reported in the reference sequence, localized to an Alu element and replaced the reference (AAAAG) short tandem repeat. Genetic analyses confirmed the pathogenic expansion in 18 of 22 CANVAS-affected families and identified a core ancestral haplotype, estimated to have arisen in Europe more than twenty-five thousand years ago. WGS of the four RFC1-negative CANVAS-affected families identified plausible variants in three, with genomic re-diagnosis of SCA3, spastic ataxia of the Charlevoix-Saguenay type, and SCA45. This study identified the genetic basis of CANVAS and demonstrated that these improved bioinformatics tools increase the diagnostic utility of WGS to determine the genetic basis of a heterogeneous group of clinically overlapping neurogenetic disorders.

Cerebral hypomyelination associated with biallelic variants of FIG4. - Lenk, Guy M; Berry, Ian R; Stutterd, Chloe A; Blyth, Moira; Green, Lydia; Vadlamani, Gayatri; Warren, Daniel; Craven, Ian; Fanjul-Fernandez, Miriam; Rodriguez-Casero, Victoria; Lockhart, Paul J; Vanderver, Adeline; et al. (Hum Mutat, 2019)
The lipid phosphatase gene FIG4 is responsible for Yunis-Varón syndrome and Charcot-Marie-Tooth disease Type 4J, a peripheral neuropathy. We now describe four families with FIG4 variants and prominent abnormalities of central nervous system (CNS) white matter (leukoencephalopathy), with onset in early childhood, ranging from severe hypomyelination to mild undermyelination, in addition to peripheral neuropathy. Affected individuals inherited biallelic FIG4 variants from heterozygous parents. Cultured fibroblasts exhibit enlarged vacuoles characteristic of FIG4 dysfunction. Two unrelated families segregate the same G > A variant in the +1 position of intron 21 in the homozygous state in one family and compound heterozygous in the other. This mutation in the splice donor site of exon 21 results in read-through from exon 20 into intron 20 and truncation of the final 115 C-terminal amino acids of FIG4, with retention of partial function. The observed CNS white matter disorder in these families is consistent with the myelination defects in the FIG4 null mouse and the known role of FIG4 in oligodendrocyte maturation. The families described here the expanded clinical spectrum of FIG4 deficiency to include leukoencephalopathy.

Characterization of Rare Variants in MC4R in African American and Latino Children With Severe Early-Onset Obesity. - De Rosa, Maria Caterina; Chesi, Alessandra; McCormack, Shana; Zhou, Justin; Weaver, Benjamin; McDonald, Molly; Christensen, Sinead; Liimatta, Kalle; Rosenbaum, Michael; Hakonarson, Hakon; Doege, Claudia A; Grant, Struan F A; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Mutations in melanocortin receptor (MC4R) are the most common cause of monogenic obesity in children of European ancestry, but little is known about their prevalence in children from the minority populations in the United States. OBJECTIVE: This study aims to identify the prevalence of MC4R mutations in children with severe early-onset obesity of African American or Latino ancestry. DESIGN AND SETTING: Participants were recruited from the weight management clinics at two hospitals and from the institutional biobank at a third hospital. Sequencing of the MC4R gene was performed by whole exome or Sanger sequencing. Functional testing was performed to establish the surface expression of the receptor and cAMP response to its cognate ligand α-melanocyte-stimulating hormone. PARTICIPANTS: Three hundred twelve children (1 to 18 years old, 50% girls) with body mass index (BMI) >120% of 95th percentile of Centers for Disease Control and Prevention 2000 growth charts at an age <6 years, with no known pathological cause of obesity, were enrolled. RESULTS: Eight rare MC4R mutations (2.6%) were identified in this study [R7S, F202L (n = 2), M215I, G252D, V253I, I269N, and F284I], three of which were not previously reported (G252D, F284I, and R7S). The pathogenicity of selected variants was confirmed by prior literature reports or functional testing. There was no significant difference in the BMI or height trajectories of children with or without MC4R mutations in this cohort. CONCLUSIONS: Although the prevalence of MC4R mutations in this cohort was similar to that reported for obese children of European ancestry, some of the variants were novel.

Clinical exome sequencing reveals locus heterogeneity and phenotypic variability of cohesinopathies. - Yuan, Bo; Neira, Juanita; Pehlivan, Davut; Santiago-Sim, Teresa; Song, Xiaofei; Rosenfeld, Jill; Posey, Jennifer E; Patel, Vipulkumar; Jin, Weihong; Adam, Margaret P; Baple, Emma L; Dean, John; et al. (Genet Med, 2019)
PURPOSE: Defects in the cohesin pathway are associated with cohesinopathies, notably Cornelia de Lange syndrome (CdLS). We aimed to delineate pathogenic variants in known and candidate cohesinopathy genes from a clinical exome perspective. METHODS: We retrospectively studied patients referred for clinical exome sequencing (CES, N = 10,698). Patients with causative variants in novel or recently described cohesinopathy genes were enrolled for phenotypic characterization. RESULTS: Pathogenic or likely pathogenic single-nucleotide and insertion/deletion variants (SNVs/indels) were identified in established disease genes including NIPBL (N = 5), SMC1A (N = 14), SMC3 (N = 4), RAD21 (N = 2), and HDAC8 (N = 8). The phenotypes in this genetically defined cohort skew towards the mild end of CdLS spectrum as compared with phenotype-driven cohorts. Candidate or recently reported cohesinopathy genes were supported by de novo SNVs/indels in STAG1 (N = 3), STAG2 (N = 5), PDS5A (N = 1), and WAPL (N = 1), and one inherited SNV in PDS5A. We also identified copy-number deletions affecting STAG1 (two de novo, one of unknown inheritance) and STAG2 (one of unknown inheritance). Patients with STAG1 and STAG2 variants presented with overlapping features yet without characteristic facial features of CdLS. CONCLUSION: CES effectively identified disease-causing alleles at the mild end of the cohensinopathy spectrum and enabled characterization of candidate disease genes.
Keywords: Adolescent; Alleles; Antigens, Nuclear; Biological Variation, Population; Carrier Proteins; Cell Cycle Proteins; Child; Child, Preschool; Chromosomal Proteins, Non-Histone; Cohort Studies; De Lange Syndrome; Exome; Female; Gene Frequency; Genetic Heterogeneity; Humans; INDEL Mutation; Male; Mutation; Nuclear Proteins; Phenotype; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins; Retrospective Studies; Whole Exome Sequencing

Clinical, genetic, and pathologic characterization of Mexican founder mutation c.1387A>G. - Lee, Angela J; Jones, Karra A; Butterfield, Russell J; Cox, Mary O; Konersman, Chamindra G; Grosmann, Carla; Abdenur, Jose E; Boyer, Monica; Beson, Brent; Wang, Ching; Dowling, James J; Gibbons, Melissa A; et al. (Neurol Genet, 2019)
Objective: To characterize the clinical phenotype, genetic origin, and muscle pathology of patients with the c.1387A>G mutation. Methods: Standardized clinical data were collected for all patients known to the authors with c.1387A>G mutations in . Muscle biopsies were reviewed and used for histopathology, immunostaining, Western blotting, and DNA extraction. Genetic analysis was performed on extracted DNA. Results: We report the clinical phenotypes of 6 patients homozygous for the c.1387A>G mutation in . Onset of symptoms was <2 years, and 5 of the 6 patients never learned to walk. Brain MRIs were normal. Cognition was normal to mildly impaired. Microarray analysis of 5 homozygous c.1387A>G patients revealed a 500-kb region of shared homozygosity at 19q13.32, including . All 4 muscle biopsies available for review showed end-stage dystrophic pathology, near absence of glycosylated α-dystroglycan (α-DG) by immunofluorescence, and reduced molecular weight of α-DG compared with controls and patients with homozygous c.826C>A limb-girdle muscular dystrophy. Conclusions: The clinical features and muscle pathology in these newly reported patients homozygous for c.1387A>G confirm that this mutation causes congenital muscular dystrophy. The clinical severity might be explained by the greater reduction in α-DG glycosylation compared with that seen with the c.826C>A mutation. The shared region of homozygosity at 19q13.32 indicates that c.1387A>G is a founder mutation with an estimated age of 60 generations (∼1,200-1,500 years).

Clinical Spectrum and Functional Consequences Associated with Bi-Allelic Pathogenic Variants. - Rius, Rocio; Van Bergen, Nicole J; Compton, Alison G; Riley, Lisa G; Kava, Maina P; Balasubramaniam, Shanti; Amor, David J; Fanjul-Fernandez, Miriam; Cowley, Mark J; Fahey, Michael C; Koenig, Mary K; Enns, Gregory M; et al. (J Clin Med, 2019)
(PNPase-polynucleotide phosphorylase) is involved in multiple RNA processing functions in the mitochondria. Bi-allelic pathogenic variants cause heterogeneous clinical phenotypes affecting multiple organs without any established genotype-phenotype correlations. Defects in PNPase can cause variable combined respiratory chain complex defects. Recently, it has been suggested that PNPase can lead to activation of an innate immune response. To better understand the clinical and molecular spectrum of patients with bi-allelic variants, we captured detailed clinical and molecular phenotypes of all 17 patients reported in the literature, plus seven new patients, including a 78-year-old male with the longest reported survival. A functional follow-up of genomic sequencing by cDNA studies confirmed a splicing defect in a novel, apparently synonymous, variant. Patient fibroblasts showed an accumulation of mitochondrial unprocessed transcripts, while blood showed an increased interferon response. Our findings suggest that functional analyses of the RNA processing function of PNPase are more sensitive than testing downstream defects in oxidative phosphorylation (OXPHPOS) enzyme activities. This research extends our knowledge of the clinical and functional consequences of bi-allelic pathogenic variants that may guide management and further efforts into understanding the pathophysiological mechanisms for therapeutic development.

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans. - Kitzler, Thomas M; Schneider, Ronen; Kohl, Stefan; Kolvenbach, Caroline M; Connaughton, Dervla M; Dai, Rufeng; Mann, Nina; Nakayama, Makiko; Majmundar, Amar J; Wu, Chen-Han W; Kari, Jameela A; El Desoky, Sherif M; et al. (Hum Genet, 2019)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of chronic kidney disease (~ 45%) that manifests before 30 years of age. The genetic locus containing COL4A1 (13q33-34) has been implicated in vesicoureteral reflux (VUR), but mutations in COL4A1 have not been reported in CAKUT. We hypothesized that COL4A1 mutations cause CAKUT in humans. We performed whole exome sequencing (WES) in 550 families with CAKUT. As negative control cohorts we used WES sequencing data from patients with nephronophthisis (NPHP) with no genetic cause identified (n = 257) and with nephrotic syndrome (NS) due to monogenic causes (n = 100). We identified a not previously reported heterozygous missense variant in COL4A1 in three siblings with isolated VUR. When examining 549 families with CAKUT, we identified nine additional different heterozygous missense mutations in COL4A1 in 11 individuals from 11 unrelated families with CAKUT, while no COL4A1 mutations were identified in a control cohort with NPHP and only one in the cohort with NS. Most individuals (12/14) had isolated CAKUT with no extrarenal features. The predominant phenotype was VUR (9/14). There were no clinical features of the COL4A1-related disorders (e.g., HANAC syndrome, porencephaly, tortuosity of retinal arteries). Whereas COL4A1-related disorders are typically caused by glycine substitutions in the collagenous domain (84.4% of variants), only one variant in our cohort is a glycine substitution within the collagenous domain (1/10). We identified heterozygous COL4A1 mutations as a potential novel autosomal dominant cause of CAKUT that is allelic to the established COL4A1-related disorders and predominantly caused by non-glycine substitutions.
Keywords: Alleles; Amino Acid Substitution; Collagen Type IV; Computational Biology; Congenital Abnormalities; Databases, Genetic; DNA Mutational Analysis; Evolution, Molecular; Female; Genetic Association Studies; Genetic Loci; Genomics; Heterozygote; Humans; Kidney; Kidney Diseases, Cystic; Male; Mutation; Nephrotic Syndrome; Phenotype; Urinary Tract; Web Browser; Whole Exome Sequencing

Complex Compound Inheritance of Lethal Lung Developmental Disorders Due to Disruption of the TBX-FGF Pathway. - Karolak, Justyna A; Vincent, Marie; Deutsch, Gail; Gambin, Tomasz; Cogné, Benjamin; Pichon, Olivier; Vetrini, Francesco; Mefford, Heather C; Dines, Jennifer N; Golden-Grant, Katie; Dipple, Katrina; Freed, Amanda S; et al. (Am J Hum Genet, 2019)
Primary defects in lung branching morphogenesis, resulting in neonatal lethal pulmonary hypoplasias, are incompletely understood. To elucidate the pathogenetics of human lung development, we studied a unique collection of samples obtained from deceased individuals with clinically and histopathologically diagnosed interstitial neonatal lung disorders: acinar dysplasia (n = 14), congenital alveolar dysplasia (n = 2), and other lethal lung hypoplasias (n = 10). We identified rare heterozygous copy-number variant deletions or single-nucleotide variants (SNVs) involving TBX4 (n = 8 and n = 2, respectively) or FGF10 (n = 2 and n = 2, respectively) in 16/26 (61%) individuals. In addition to TBX4, the overlapping ∼2 Mb recurrent and nonrecurrent deletions at 17q23.1q23.2 identified in seven individuals with lung hypoplasia also remove a lung-specific enhancer region. Individuals with coding variants involving either TBX4 or FGF10 also harbored at least one non-coding SNV in the predicted lung-specific enhancer region, which was absent in 13 control individuals with the overlapping deletions but without any structural lung anomalies. The occurrence of rare coding variants involving TBX4 or FGF10 with the putative hypomorphic non-coding SNVs implies a complex compound inheritance of these pulmonary hypoplasias. Moreover, they support the importance of TBX4-FGF10-FGFR2 epithelial-mesenchymal signaling in human lung organogenesis and help to explain the histopathological continuum observed in these rare lethal developmental disorders of the lung.
Keywords: DNA Copy Number Variations; Female; Fibroblast Growth Factor 10; Gene Expression Regulation; Gestational Age; Humans; Infant, Newborn; Infant, Newborn, Diseases; Lung; Lung Diseases; Male; Maternal Inheritance; Organogenesis; Paternal Inheritance; Pedigree; Polymorphism, Single Nucleotide; Receptor, Fibroblast Growth Factor, Type 2; Signal Transduction; T-Box Domain Proteins

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Yuan, Bo; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum. - Konrad, Enrico D H; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genet Med, 2019)
PURPOSE: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). METHODS: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. RESULTS: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. CONCLUSION: We significantly broaden the mutational and clinical spectrum ofCTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism. - Zawerton, Ash; Yao, Baojin; Yeager, J Paige; Pippucci, Tommaso; Haseeb, Abdul; Smith, Joshua D; Wischmann, Lisa; Kühl, Susanne J; Dean, John C S; Pilz, Daniela T; Holder, Susan E; McNeill, Alisdair; et al. (Am J Hum Genet, 2019)
SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share developmental delay, intellectual disability, and mild facial and digital morphological abnormalities. SOX4 is highly expressed in areas of active neurogenesis in human fetuses, and sox4 knockdown in Xenopus embryos diminishes brain and whole-body size. The SOX4 variants cluster in the highly conserved, SOX family-specific HMG domain, but each alters a different residue. In silico tools predict that each variant affects a distinct structural feature of this DNA-binding domain, and functional assays demonstrate that these SOX4 proteins carrying these variants are unable to bind DNA in vitro and transactivate SOX reporter genes in cultured cells. These variants are not found in the gnomAD database of individuals with presumably normal development, but 12 other SOX4 HMG-domain missense variants are recorded and all demonstrate partial to full activity in the reporter assay. Taken together, these findings point to specific SOX4 HMG-domain missense variants as the cause of a characteristic human neurodevelopmental disorder associated with mild facial and digital dysmorphism.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Child; Child, Preschool; Coffin-Lowry Syndrome; Cohort Studies; Conserved Sequence; DNA; Female; Heterozygote; HMG-Box Domains; Humans; Male; Mutation, Missense; Neurodevelopmental Disorders; SOXC Transcription Factors; Transcriptional Activation; Xenopus

De Novo Variants Disturbing the Transactivation Capacity of POU3F3 Cause a Characteristic Neurodevelopmental Disorder. - Snijders Blok, Lot; Kleefstra, Tjitske; Venselaar, Hanka; Maas, Saskia; Kroes, Hester Y; Lachmeijer, Augusta M A; van Gassen, Koen L I; Firth, Helen V; Tomkins, Susan; Bodek, Simon; Õunap, Katrin; Wojcik, Monica H; et al. (Am J Hum Genet, 2019)
POU3F3, also referred to as Brain-1, is a well-known transcription factor involved in the development of the central nervous system, but it has not previously been associated with a neurodevelopmental disorder. Here, we report the identification of 19 individuals with heterozygous POU3F3 disruptions, most of which are de novo variants. All individuals had developmental delays and/or intellectual disability and impairments in speech and language skills. Thirteen individuals had characteristic low-set, prominent, and/or cupped ears. Brain abnormalities were observed in seven of eleven MRI reports. POU3F3 is an intronless gene, insensitive to nonsense-mediated decay, and 13 individuals carried protein-truncating variants. All truncating variants that we tested in cellular models led to aberrant subcellular localization of the encoded protein. Luciferase assays demonstrated negative effects of these alleles on transcriptional activation of a reporter with a FOXP2-derived binding motif. In addition to the loss-of-function variants, five individuals had missense variants that clustered at specific positions within the functional domains, and one small in-frame deletion was identified. Two missense variants showed reduced transactivation capacity in our assays, whereas one variant displayed gain-of-function effects, suggesting a distinct pathophysiological mechanism. In bioluminescence resonance energy transfer (BRET) interaction assays, all the truncated POU3F3 versions that we tested had significantly impaired dimerization capacities, whereas all missense variants showed unaffected dimerization with wild-type POU3F3. Taken together, our identification and functional cell-based analyses of pathogenic variants in POU3F3, coupled with a clinical characterization, implicate disruptions of this gene in a characteristic neurodevelopmental disorder.

De novo variants in HK1 associated with neurodevelopmental abnormalities and visual impairment. - Okur, Volkan; Cho, Megan T; van Wijk, Richard; van Oirschot, Brigitte; Picker, Jonathan; Coury, Stephanie A; Grange, Dorothy; Manwaring, Linda; Krantz, Ian; Muraresku, Colleen Clark; Hulick, Peter J; May, Holley; et al. (Eur J Hum Genet, 2019)
Hexokinase 1 (HK1) phosphorylates glucose to glucose-6-phosphate, the first rate-limiting step in glycolysis. Homozygous and heterozygous variants in HK1 have been shown to cause autosomal recessive non-spherocytic hemolytic anemia, autosomal recessive Russe type hereditary motor and sensory neuropathy, and autosomal dominant retinitis pigmentosa (adRP). We report seven patients from six unrelated families with a neurodevelopmental disorder associated with developmental delay, intellectual disability, structural brain abnormality, and visual impairments in whom we identified four novel, de novo missense variants in the N-terminal half of HK1. Hexokinase activity in red blood cells of two patients was normal, suggesting that the disease mechanism is not due to loss of hexokinase enzymatic activity.

Deleterious de novo variants of X-linked ZC4H2 in females cause a variable phenotype with neurogenic arthrogryposis multiplex congenita. - Frints, Suzanna G M; Hennig, Friederike; Colombo, Roberto; Jacquemont, Sebastien; Terhal, Paulien; Zimmerman, Holly H; Hunt, David; Mendelsohn, Bryce A; Kordaß, Ulrike; Webster, Richard; Sinnema, Margje; Abdul-Rahman, Omar; et al. (Hum Mutat, 2019)
Pathogenic variants in the X-linked gene ZC4H2, which encodes a zinc-finger protein, cause an infrequently described syndromic form of arthrogryposis multiplex congenita (AMC) with central and peripheral nervous system involvement. We present genetic and detailed phenotypic information on 23 newly identified families and simplex cases that include 19 affected females from 18 families and 14 affected males from nine families. Of note, the 15 females with deleterious de novo ZC4H2 variants presented with phenotypes ranging from mild to severe, and their clinical features overlapped with those seen in affected males. By contrast, of the nine carrier females with inherited ZC4H2 missense variants that were deleterious in affected male relatives, four were symptomatic. We also compared clinical phenotypes with previously published cases of both sexes and provide an overview on 48 males and 57 females from 42 families. The spectrum of ZC4H2 defects comprises novel and recurrent mostly inherited missense variants in affected males, and de novo splicing, frameshift, nonsense, and partial ZC4H2 deletions in affected females. Pathogenicity of two newly identified missense variants was further supported by studies in zebrafish. We propose ZC4H2 as a good candidate for early genetic testing of males and females with a clinical suspicion of fetal hypo-/akinesia and/or (neurogenic) AMC.

Detailed genetic characteristics of an international large cohort of patients with Stargardt disease: ProgStar study report 8. - Fujinami, Kaoru; Strauss, Rupert W; Chiang, John Pei-Wen; Audo, Isabelle S; Bernstein, Paul S; Birch, David G; Bomotti, Samantha M; Cideciyan, Artur V; Ervin, Ann-Margret; Marino, Meghan J; Sahel, José-Alain; Mohand-Said, Saddek; et al. (Br J Ophthalmol, 2019)
BACKGROUND/AIMS: To describe the genetic characteristics of the cohort enrolled in the international multicentre progression of Stargardt disease 1 (STGD1) studies (ProgStar) and to determine geographic differences based on the allele frequency. METHODS: 345 participants with a clinical diagnosis of STGD1 and harbouring at least one disease-causing ABCA4 variant were enrolled from 9 centres in the USA and Europe. All variants were reviewed and analysis was performed including allele frequency in public databases and pathogenicity predictions. Participants with multiple likely pathogenic variants were classified into four national subgroups (USA, UK, France, Germany), with subsequent comparison analysis of the allele frequency for each prevalent allele. RESULTS: 211 likely pathogenic variants were identified in the total cohort, including missense (63%), splice site alteration (18%), stop (9%) and others. 50 variants were novel. Exclusively missense variants were detected in 139 (50%) of 279 patients with multiple pathogenic variants. The three most prevalent variants of these patients with multiple pathogenic variants were p.G1961E (15%), p.G863A (7%) and c.5461-10 T>C (5%). Subgroup analysis revealed a statistically significant difference between the four recruiting nations in the allele frequency of nine variants. CONCLUSIONS: There is a large spectrum of ABCA4 sequence variants, including 50 novel variants, in a well-characterised cohort thereby further adding to the unique allelic heterogeneity in STGD1. Approximately half of the cohort harbours missense variants only, indicating a relatively mild phenotype of the ProgStar cohort. There are significant differences in allele frequencies between nations, although the three most prevalent variants are shared as frequent variants.
Keywords: Adolescent; Adult; Age of Onset; Aged; ATP-Binding Cassette Transporters; Child; Child, Preschool; Cohort Studies; Databases, Factual; DNA Mutational Analysis; Female; Gene Frequency; Genotyping Techniques; Geography; Humans; Internationality; Macular Degeneration; Male; Middle Aged; Mutation; Polymerase Chain Reaction

Disruptive mutations in TANC2 define a neurodevelopmental syndrome associated with psychiatric disorders. - Guo, Hui; Bettella, Elisa; Marcogliese, Paul C; Zhao, Rongjuan; Andrews, Jonathan C; Nowakowski, Tomasz J; Gillentine, Madelyn A; Hoekzema, Kendra; Wang, Tianyun; Wu, Huidan; Jangam, Sharayu; Liu, Cenying; et al. (Nat Commun, 2019)
Postsynaptic density (PSD) proteins have been implicated in the pathophysiology of neurodevelopmental and psychiatric disorders. Here, we present detailed clinical and genetic data for 20 patients with likely gene-disrupting mutations in TANC2-whose protein product interacts with multiple PSD proteins. Pediatric patients with disruptive mutations present with autism, intellectual disability, and delayed language and motor development. In addition to a variable degree of epilepsy and facial dysmorphism, we observe a pattern of more complex psychiatric dysfunction or behavioral problems in adult probands or carrier parents. Although this observation requires replication to establish statistical significance, it also suggests that mutations in this gene are associated with a variety of neuropsychiatric disorders consistent with its postsynaptic function. We find that TANC2 is expressed broadly in the human developing brain, especially in excitatory neurons and glial cells, but shows a more restricted pattern in Drosophila glial cells where its disruption affects behavioral outcomes.

Distinct patterns of complex rearrangements and a mutational signature of microhomeology are frequently observed in PLP1 copy number gain structural variants. - Bahrambeigi, Vahid; Song, Xiaofei; Sperle, Karen; Beck, Christine R; Hijazi, Hadia; Grochowski, Christopher M; Gu, Shen; Seeman, Pavel; Woodward, Karen J; Carvalho, Claudia M B; Hobson, Grace M; Lupski, James R (Genome Med, 2019)
BACKGROUND: We investigated the features of the genomic rearrangements in a cohort of 50 male individuals with proteolipid protein 1 (PLP1) copy number gain events who were ascertained with Pelizaeus-Merzbacher disease (PMD; MIM: 312080). We then compared our new data to previous structural variant mutagenesis studies involving the Xq22 region of the human genome. The aggregate data from 159 sequenced join-points (discontinuous sequences in the reference genome that are joined during the rearrangement process) were studied. Analysis of these data from 150 individuals enabled the spectrum and relative distribution of the underlying genomic mutational signatures to be delineated. METHODS: Genomic rearrangements in PMD individuals with PLP1 copy number gain events were investigated by high-density customized array or clinical chromosomal microarray analysis and breakpoint junction sequence analysis. RESULTS: High-density customized array showed that the majority of cases (33/50; ~ 66%) present with single duplications, although complex genomic rearrangements (CGRs) are also frequent (17/50; ~ 34%). Breakpoint mapping to nucleotide resolution revealed further previously unknown structural and sequence complexities, even in single duplications. Meta-analysis of all studied rearrangements that occur at the PLP1 locus showed that single duplications were found in ~ 54% of individuals and that, among all CGR cases, triplication flanked by duplications is the most frequent CGR array CGH pattern observed. Importantly, in ~ 32% of join-points, there is evidence for a mutational signature of microhomeology (highly similar yet imperfect sequence matches). CONCLUSIONS: These data reveal a high frequency of CGRs at the PLP1 locus and support the assertion that replication-based mechanisms are prominent contributors to the formation of CGRs at Xq22. We propose that microhomeology can facilitate template switching, by stabilizing strand annealing of the primer using W-C base complementarity, and is a mutational signature for replicative repair.

Dominant-negative SOX9 mutations in campomelic dysplasia. - Csukasi, Fabiana; Duran, Ivan; Zhang, Wenjuan; Martin, Jorge H; Barad, Maya; Bamshad, Michael; Weis, Mary Ann; Eyre, David; Krakow, Deborah; Cohn, Daniel H (Hum Mutat, 2019)
Campomelic dysplasia (CD) is an autosomal dominant, perinatal lethal skeletal dysplasia characterized by a small chest and short long bones with bowing of the lower extremities. CD is the result of heterozygosity for mutations in the gene encoding the chondrogenesis master regulator, SOX9. Loss-of-function mutations have been identified in most CD cases so it has been assumed that the disease results from haploinsufficiency for SOX9. Here, we identified distal truncating SOX9 mutations in four unrelated CD cases. The mutations all leave the dimerization and DNA-binding domains intact and cultured chondrocytes from three of the four cases synthesized truncated SOX9. Relative to CD resulting from haploinsufficiency, there was decreased transactivation activity toward a major transcriptional target, COL2A1, consistent with the mutations exerting a dominant-negative effect. For one of the cases, the phenotypic consequence was a very severe form of CD, with a pronounced effect on vertebral and limb development. The data identify a novel molecular mechanism of disease in CD in which the truncated protein leads to a distinct and more significant effect on SOX9 function.

Enabling Global Clinical Collaborations on Identifiable Patient Data: The Minerva Initiative. - Nellaker, Christoffer; Alkuraya, Fowzan S; Baynam, Gareth; Bernier, Raphael A; Bernier, Francois P J; Boulanger, Vanessa; Brudno, Michael; Brunner, Han G; Clayton-Smith, Jill; Cogné, Benjamin; Dawkins, Hugh J S; deVries, Bert B A; et al. (Front Genet, 2019)
The clinical utility of computational phenotyping for both genetic and rare diseases is increasingly appreciated; however, its true potential is yet to be fully realized. Alongside the growing clinical and research availability of sequencing technologies, precise deep and scalable phenotyping is required to serve unmet need in genetic and rare diseases. To improve the lives of individuals affected with rare diseases through deep phenotyping, global big data interrogation is necessary to aid our understanding of disease biology, assist diagnosis, and develop targeted treatment strategies. This includes the application of cutting-edge machine learning methods to image data. As with most digital tools employed in health care, there are ethical and data governance challenges associated with using identifiable personal image data. There are also risks with failing to deliver on the patient benefits of these new technologies, the biggest of which is posed by data siloing. The Minerva Initiative has been designed to enable the public good of deep phenotyping while mitigating these ethical risks. Its open structure, enabling collaboration and data sharing between individuals, clinicians, researchers and private enterprise, is key for delivering precision public health.

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.

Exome sequencing of family trios from the National Birth Defects Prevention Study: Tapping into a rich resource of genetic and environmental data. - Jenkins, Mary M; Almli, Lynn M; Pangilinan, Faith; Chong, Jessica X; Blue, Elizabeth E; Shapira, Stuart K; White, Janson; McGoldrick, Daniel; Smith, Joshua D; Mullikin, James C; Bean, Christopher J; Nembhard, Wendy N; et al. (Birth Defects Res, 2019)
BACKGROUND: The National Birth Defects Prevention Study (NBDPS) is a multisite, population-based, case-control study of genetic and nongenetic risk factors for major structural birth defects. Eligible women had a pregnancy affected by a birth defect or a liveborn child without a birth defect between 1997 and 2011. They were invited to complete a telephone interview to collect pregnancy exposure data and were mailed buccal cell collection kits to collect specimens from themselves, their child (if living), and their child's father. Over 23,000 families representing more than 30 major structural birth defects provided DNA specimens. METHODS: To evaluate their utility for exome sequencing (ES), specimens from 20 children with colonic atresia were studied. Evaluations were conducted on specimens collected using cytobrushes stored and transported in open versus closed packaging, on native genomic DNA (gDNA) versus whole genome amplified (WGA) products and on a library preparation protocol adapted to low amounts of DNA. RESULTS: The DNA extracted from brushes in open packaging yielded higher quality sequence data than DNA from brushes in closed packaging. Quality metrics of sequenced gDNA were consistently higher than metrics from corresponding WGA products and were consistently high when using a low input protocol. CONCLUSIONS: This proof-of-principle study established conditions under which ES can be applied to NBDPS specimens. Successful sequencing of exomes from well-characterized NBDPS families indicated that this unique collection can be used to investigate the roles of genetic variation and gene-environment interaction effects in birth defect etiologies, providing a valuable resource for birth defect researchers.

The expanding phenotype of OFD1-related disorders: Hemizygous loss-of-function variants in three patients with primary ciliary dyskinesia. - Hannah, William B; DeBrosse, Suzanne; Kinghorn, BreAnna; Strausbaugh, Steven; Aitken, Moira L; Rosenfeld, Margaret; Wolf, Whitney E; Knowles, Michael R; Zariwala, Maimoona A (Mol Genet Genomic Med, 2019)
BACKGROUND: OFD1 has long been recognized as the gene implicated in the classic dysmorphology syndrome, oral-facial-digital syndrome type I (OFDSI). Over time, pathogenic variants in OFD1 were found to be associated with X-linked intellectual disability, Joubert syndrome type 10 (JBTS10), Simpson-Golabi-Behmel syndrome type 2 (SGBS2), and retinitis pigmentosa. Recently, OFD1 pathogenic variants have been implicated in primary ciliary dyskinesia (PCD), a disorder of the motile cilia with a phenotype that includes recurrent oto-sino-pulmonary infections, situs abnormalities, and decreased fertility. METHODS: We describe three male patients with PCD who were found to have hemizygous pathogenic variants in OFD1, further supporting that PCD is part of a clinical spectrum of OFD1-related disorders. In addition, we provide a review of the available clinical literature describing patients with OFD1 variants and highlight the phenotypic variability of OFD1-related disease. RESULTS: Some individuals with hemizygous OFD1 variants have PCD, either apparently isolated or in combination with other features of OFD1-related disorders. CONCLUSION: As clinicians consider the presence or absence of conditions allelic at OFD1, PCD should be considered part of the spectrum of OFD1-related disorders. Understanding the OFD1-related disease spectrum may allow for more focused genetic testing and more timely management of treatable sequelae.

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.

Genetic regulatory variation in populations informs transcriptome analysis in rare disease. - Mohammadi, Pejman; Castel, Stephane E; Cummings, Beryl B; Einson, Jonah; Sousa, Christina; Hoffman, Paul; Donkervoort, Sandra; Jiang, Zhuoxun; Mohassel, Payam; Foley, A Reghan; Wheeler, Heather E; Im, Hae Kyung; et al. (Science, 2019)
Transcriptome data can facilitate the interpretation of the effects of rare genetic variants. Here, we introduce ANEVA (analysis of expression variation) to quantify genetic variation in gene dosage from allelic expression (AE) data in a population. Application of ANEVA to the Genotype-Tissues Expression (GTEx) data showed that this variance estimate is robust and correlated with selective constraint in a gene. Using these variance estimates in a dosage outlier test (ANEVA-DOT) applied to AE data from 70 Mendelian muscular disease patients showed accuracy in detecting genes with pathogenic variants in previously resolved cases and led to one confirmed and several potential new diagnoses. Using our reference estimates from GTEx data, ANEVA-DOT can be incorporated in rare disease diagnostic pipelines to use RNA-sequencing data more effectively.

Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome. - Braun, Daniela A; Warejko, Jillian K; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Nakayama, Makiko; Schapiro, David; et al. (Nephrol Dial Transplant, 2019)
BACKGROUND: Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-α5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. METHODS: To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessive mutation. RESULTS: In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. CONCLUSION: We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.

Genome Sequencing Identifies the Pathogenic Variant Missed by Prior Testing in an Infant with Marfan Syndrome. - Wojcik, Monica H; Thiele, Katri; Grant, Carly F; Chao, Katherine; Goodrich, Julia; O'Donnell-Luria, Anne; Lacro, Ronald V; Tan, Wen-Hann; Agrawal, Pankaj B (J Pediatr, 2019)
We describe an infant with a phenotype typical of early onset Marfan syndrome whose genetic evaluation, including Sanger sequencing and deletion/duplication testing of FBN1 and exome sequencing, was negative. Ultimately, genome sequencing revealed a deletion missed on prior testing, demonstrating the unique utility of genome sequencing for molecular genetic diagnosis.

Heterozygous Variants in KMT2E Cause a Spectrum of Neurodevelopmental Disorders and Epilepsy. - O'Donnell-Luria, Anne H; Pais, Lynn S; Faundes, Víctor; Wood, Jordan C; Sveden, Abigail; Luria, Victor; Abou Jamra, Rami; Accogli, Andrea; Amburgey, Kimberly; Anderlid, Britt Marie; Azzarello-Burri, Silvia; Basinger, Alice A; et al. (Am J Hum Genet, 2019)
We delineate a KMT2E-related neurodevelopmental disorder on the basis of 38 individuals in 36 families. This study includes 31 distinct heterozygous variants in KMT2E (28 ascertained from Matchmaker Exchange and three previously reported), and four individuals with chromosome 7q22.2-22.23 microdeletions encompassing KMT2E (one previously reported). Almost all variants occurred de novo, and most were truncating. Most affected individuals with protein-truncating variants presented with mild intellectual disability. One-quarter of individuals met criteria for autism. Additional common features include macrocephaly, hypotonia, functional gastrointestinal abnormalities, and a subtle facial gestalt. Epilepsy was present in about one-fifth of individuals with truncating variants and was responsive to treatment with anti-epileptic medications in almost all. More than 70% of the individuals were male, and expressivity was variable by sex; epilepsy was more common in females and autism more common in males. The four individuals with microdeletions encompassing KMT2E generally presented similarly to those with truncating variants, but the degree of developmental delay was greater. The group of four individuals with missense variants in KMT2E presented with the most severe developmental delays. Epilepsy was present in all individuals with missense variants, often manifesting as treatment-resistant infantile epileptic encephalopathy. Microcephaly was also common in this group. Haploinsufficiency versus gain-of-function or dominant-negative effects specific to these missense variants in KMT2E might explain this divergence in phenotype, but requires independent validation. Disruptive variants in KMT2E are an under-recognized cause of neurodevelopmental abnormalities.

Homozygous Missense Variants in NTNG2, Encoding a Presynaptic Netrin-G2 Adhesion Protein, Lead to a Distinct Neurodevelopmental Disorder. - Dias, Caroline M; Punetha, Jaya; Zheng, Céline; Mazaheri, Neda; Rad, Abolfazl; Efthymiou, Stephanie; Petersen, Andrea; Dehghani, Mohammadreza; Pehlivan, Davut; Partlow, Jennifer N; Posey, Jennifer E; Salpietro, Vincenzo; et al. (Am J Hum Genet, 2019)
NTNG2 encodes netrin-G2, a membrane-anchored protein implicated in the molecular organization of neuronal circuitry and synaptic organization and diversification in vertebrates. In this study, through a combination of exome sequencing and autozygosity mapping, we have identified 16 individuals (from seven unrelated families) with ultra-rare homozygous missense variants in NTNG2; these individuals present with shared features of a neurodevelopmental disorder consisting of global developmental delay, severe to profound intellectual disability, muscle weakness and abnormal tone, autistic features, behavioral abnormalities, and variable dysmorphisms. The variants disrupt highly conserved residues across the protein. Functional experiments, including in silico analysis of the protein structure, in vitro assessment of cell surface expression, and in vitro knockdown, revealed potential mechanisms of pathogenicity of the variants, including loss of protein function and decreased neurite outgrowth. Our data indicate that appropriate expression of NTNG2 plays an important role in neurotypical development.

Hypomorphic caspase activation and recruitment domain 11 (CARD11) mutations associated with diverse immunologic phenotypes with or without atopic disease. - Dorjbal, Batsukh; Stinson, Jeffrey R; Ma, Chi A; Weinreich, Michael A; Miraghazadeh, Bahar; Hartberger, Julia M; Frey-Jakobs, Stefanie; Weidinger, Stephan; Moebus, Lena; Franke, Andre; Schäffer, Alejandro A; Bulashevska, Alla; et al. (J Allergy Clin Immunol, 2019)
BACKGROUND: Caspase activation and recruitment domain 11 (CARD11) encodes a scaffold protein in lymphocytes that links antigen receptor engagement with downstream signaling to nuclear factor κB, c-Jun N-terminal kinase, and mechanistic target of rapamycin complex 1. Germline CARD11 mutations cause several distinct primary immune disorders in human subjects, including severe combined immune deficiency (biallelic null mutations), B-cell expansion with nuclear factor κB and T-cell anergy (heterozygous, gain-of-function mutations), and severe atopic disease (loss-of-function, heterozygous, dominant interfering mutations), which has focused attention on CARD11 mutations discovered by using whole-exome sequencing. OBJECTIVES: We sought to determine the molecular actions of an extended allelic series of CARD11 and to characterize the expanding range of clinical phenotypes associated with heterozygous CARD11 loss-of-function alleles. METHODS: Cell transfections and primary T-cell assays were used to evaluate signaling and function of CARD11 variants. RESULTS: Here we report on an expanded cohort of patients harboring novel heterozygous CARD11 mutations that extend beyond atopy to include other immunologic phenotypes not previously associated with CARD11 mutations. In addition to (and sometimes excluding) severe atopy, heterozygous missense and indel mutations in CARD11 presented with immunologic phenotypes similar to those observed in signal transducer and activator of transcription 3 loss of function, dedicator of cytokinesis 8 deficiency, common variable immunodeficiency, neutropenia, and immune dysregulation, polyendocrinopathy, enteropathy, X-linked-like syndrome. Pathogenic variants exhibited dominant negative activity and were largely confined to the CARD or coiled-coil domains of the CARD11 protein. CONCLUSION: These results illuminate a broader phenotypic spectrum associated with CARD11 mutations in human subjects and underscore the need for functional studies to demonstrate that rare gene variants encountered in expected and unexpected phenotypes must nonetheless be validated for pathogenic activity.

Identification and therapeutic rescue of autophagosome and glutamate receptor defects in C9ORF72 and sporadic ALS neurons. - Shi, Yingxiao; Hung, Shu-Ting; Rocha, Gabriel; Lin, Shaoyu; Linares, Gabriel R; Staats, Kim A; Seah, Carina; Wang, Yaoming; Chickering, Michael; Lai, Jesse; Sugawara, Tohru; Sagare, Abhay P; et al. (JCI Insight, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease with diverse etiologies. Therefore, the identification of common disease mechanisms and therapeutics targeting these mechanisms could dramatically improve clinical outcomes. To this end, we developed induced motor neuron (iMN) models from C9ORF72 and sporadic ALS (sALS) patients to identify targets that are effective against these types of cases, which together comprise ~90% of patients. We find that iMNs from C9ORF72 and several sporadic ALS patients share two common defects - impaired autophagosome formation and the aberrant accumulation of glutamate receptors. Moreover, we show that an anticoagulation-deficient form of activated protein C, 3K3A-APC, rescues these defects in both C9ORF72 and sporadic ALS iMNs. As a result, 3K3A-APC treatment lowers C9ORF72 dipeptide repeat protein (DPR) levels, restores nuclear TDP-43 localization, and rescues the survival of both C9ORF72 and sporadic ALS iMNs. Importantly, 3K3A-APC also lowers glutamate receptor levels and rescues proteostasis in vivo in C9ORF72 gain- and loss-of-function mouse models. Thus, motor neurons from C9ORF72 and at least a subset of sporadic ALS patients share common, early defects in autophagosome formation and glutamate receptor homeostasis and a single therapeutic approach may be efficacious against these disease processes.

Infant mortality: the contribution of genetic disorders. - Wojcik, Monica H; Schwartz, Talia S; Thiele, Katri E; Paterson, Heather; Stadelmaier, Rachel; Mullen, Thomas E; VanNoy, Grace E; Genetti, Casie A; Madden, Jill A; Gubbels, Cynthia S; Yu, Timothy W; Tan, Wen-Hann; et al. (J Perinatol, 2019)
OBJECTIVE: To determine the proportion of infant deaths occurring in the setting of a confirmed genetic disorder. STUDY DESIGN: A retrospective analysis of the electronic medical records of infants born from 1 January, 2011 to 1 June, 2017, who died prior to 1 year of age. RESULTS: Five hundred and seventy three deceased infants were identified. One hundred and seventeen were confirmed to have a molecular or cytogenetic diagnosis in a clinical diagnostic laboratory and an additional seven were diagnosed by research testing for a total of 124/573 (22%) diagnosed infants. A total of 67/124 (54%) had chromosomal disorders and 58/124 (47%) had single gene disorders (one infant had both). The proportion of diagnoses made by sequencing technologies, such as exome sequencing, increased over the years. CONCLUSIONS: The prevalence of confirmed genetic disorders within our cohort of infant deaths is higher than that previously reported. Increased efforts are needed to further understand the mortality burden of genetic disorders in infancy.

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Lack of GAS2L2 Causes PCD by Impairing Cilia Orientation and Mucociliary Clearance. - Bustamante-Marin, Ximena M; Yin, Wei-Ning; Sears, Patrick R; Werner, Michael E; Brotslaw, Eva J; Mitchell, Brian J; Jania, Corey M; Zeman, Kirby L; Rogers, Troy D; Herring, Laura E; Refabért, Luc; Thomas, Lucie; et al. (Am J Hum Genet, 2019)
Primary ciliary dyskinesia (PCD) is a genetic disorder in which impaired ciliary function leads to chronic airway disease. Exome sequencing of a PCD subject identified an apparent homozygous frameshift variant, c.887_890delTAAG (p.Val296Glyfs13), in exon 5; this frameshift introduces a stop codon in amino acid 308 of the growth arrest-specific protein 2-like 2 (GAS2L2). Further genetic screening of unrelated PCD subjects identified a second proband with a compound heterozygous variant carrying the identical frameshift variant and a large deletion (c.867_343+1207del; p.?) starting in exon 5. Both individuals had clinical features of PCD but normal ciliary axoneme structure. In this research, using human nasal cells, mouse models, and X.laevis embryos, we show that GAS2L2 is abundant at the apical surface of ciliated cells, where it localizes with basal bodies, basal feet, rootlets, and actin filaments. Cultured GAS2L2-deficient nasal epithelial cells from one of the affected individuals showed defects in ciliary orientation and had an asynchronous and hyperkinetic (GAS2L2-deficient = 19.8 Hz versus control = 15.8 Hz) ciliary-beat pattern. These results were recapitulated in Gas2l2 mouse tracheal epithelial cell (mTEC) cultures and in X. laevis embryos treated with Gas2l2 morpholinos. In mice, the absence of Gas2l2 caused neonatal death, and the conditional deletion of Gas2l2 impaired mucociliary clearance (MCC) and led to mucus accumulation. These results show that a pathogenic variant in GAS2L2 causes a genetic defect in ciliary orientation and impairs MCC and results in PCD.
Keywords: Animals; Cilia; Ciliary Motility Disorders; Disease Models, Animal; Exons; Female; Gene Deletion; Genes, Lethal; Humans; Male; Mice; Mice, Knockout; Microfilament Proteins; Microtubule-Associated Proteins; Phenotype; Rotation; Xenopus

Loss of SMPD4 Causes a Developmental Disorder Characterized by Microcephaly and Congenital Arthrogryposis. - Magini, Pamela; Smits, Daphne J; Vandervore, Laura; Schot, Rachel; Columbaro, Marta; Kasteleijn, Esmee; van der Ent, Mees; Palombo, Flavia; Lequin, Maarten H; Dremmen, Marjolein; de Wit, Marie Claire Y; Severino, Mariasavina; et al. (Am J Hum Genet, 2019)
Sphingomyelinases generate ceramide from sphingomyelin as a second messenger in intracellular signaling pathways involved in cell proliferation, differentiation, or apoptosis. Children from 12 unrelated families presented with microcephaly, simplified gyral pattern of the cortex, hypomyelination, cerebellar hypoplasia, congenital arthrogryposis, and early fetal/postnatal demise. Genomic analysis revealed bi-allelic loss-of-function variants in SMPD4, coding for the neutral sphingomyelinase-3 (nSMase-3/SMPD4). Overexpression of human Myc-tagged SMPD4 showed localization both to the outer nuclear envelope and the ER and additionally revealed interactions with several nuclear pore complex proteins by proteomics analysis. Fibroblasts from affected individuals showed ER cisternae abnormalities, suspected for increased autophagy, and were more susceptible to apoptosis under stress conditions, while treatment with siSMPD4 caused delayed cell cycle progression. Our data show that SMPD4 links homeostasis of membrane sphingolipids to cell fate by regulating the cross-talk between the ER and the outer nuclear envelope, while its loss reveals a pathogenic mechanism in microcephaly.

Loss of the sphingolipid desaturase DEGS1 causes hypomyelinating leukodystrophy. - Pant, Devesh C; Dorboz, Imen; Schluter, Agatha; Fourcade, Stéphane; Launay, Nathalie; Joya, Javier; Aguilera-Albesa, Sergio; Yoldi, Maria Eugenia; Casasnovas, Carlos; Willis, Mary J; Ruiz, Montserrat; Ville, Dorothée; et al. (J Clin Invest, 2019)
Sphingolipid imbalance is the culprit in a variety of neurological diseases, some affecting the myelin sheath. We have used whole-exome sequencing in patients with undetermined leukoencephalopathies to uncover the endoplasmic reticulum lipid desaturase DEGS1 as the causative gene in 19 patients from 13 unrelated families. Shared features among the cases include severe motor arrest, early nystagmus, dystonia, spasticity, and profound failure to thrive. MRI showed hypomyelination, thinning of the corpus callosum, and progressive thalamic and cerebellar atrophy, suggesting a critical role of DEGS1 in myelin development and maintenance. This enzyme converts dihydroceramide (DhCer) into ceramide (Cer) in the final step of the de novo biosynthesis pathway. We detected a marked increase of the substrate DhCer and DhCer/Cer ratios in patients' fibroblasts and muscle. Further, we used a knockdown approach for disease modeling in Danio rerio, followed by a preclinical test with the first-line treatment for multiple sclerosis, fingolimod (FTY720, Gilenya). The enzymatic inhibition of Cer synthase by fingolimod, 1 step prior to DEGS1 in the pathway, reduced the critical DhCer/Cer imbalance and the severe locomotor disability, increasing the number of myelinating oligodendrocytes in a zebrafish model. These proof-of-concept results pave the way to clinical translation.

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Sedlazeck, Fritz J; Song, Xiaofei; Meng, Qingchang; Hu, Jianhong; Doddapaneni, Harsha; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.

MendelProb: probability and sample size calculations for Mendelian studies of exome and whole genome sequence data. - He, Zongxiao; Wang, Lu; DeWan, Andrew T; Leal, Suzanne M (Bioinformatics, 2019)
Motivation: For the design of genetic studies, it is necessary to perform power calculations. Although for Mendelian traits the power of detecting linkage for pedigree(s) can be determined, it is also of great interest to determine the probability of identifying multiple pedigrees or unrelated cases with variants in the same gene. For many diseases, due to extreme locus heterogeneity this probability can be small. If only one family is observed segregating a variant classified as likely pathogenic or of unknown significance, the gene cannot be implicated in disease etiology. The probability of identifying several disease families or cases is dependent on the gene-specific disease prevalence and the sample size. The observation of multiple disease families or cases with variants in the same gene as well as evidence of pathogenicity from other sources, e.g. in silico prediction, expression and functional studies, can aid in implicating a gene in disease etiology. MendelProb can determine the probability of detecting a minimum number of families or cases with variants in the same gene. It can also calculate the probability of detecting genes with variants in different data types, e.g. identifying a variant in at least one family that can establish linkage and more the two additional families regardless of their size. Additionally, for a specified probability MendelProb can determine the number of probands which need to be screened to detect a minimum number of individuals with variants within the same gene. Results: A single Mendelian disease family is not sufficient to implicate a gene in disease etiology. It is necessary to observe multiple families or cases with potentially pathogenic variants in the same gene. MendelProb, an R library, was developed to determine the probability of observing multiple families and cases with variants within a gene and to also establish the numbers of probands to screen to detect multiple observations of variants within a gene. Availability and implementation: https://github.com/statgenetics/mendelprob.
Keywords: Exome; Genetic Linkage; Genomics; Humans; Pedigree; Probability; Sample Size; Software

metaFARVAT: An Efficient Tool for Meta-Analysis of Family-Based, Case-Control, and Population-Based Rare Variant Association Studies. - Wang, Longfei; Lee, Sungyoung; Qiao, Dandi; Cho, Michael H; Silverman, Edwin K; Lange, Christoph; Won, Sungho (Front Genet, 2019)
Family-based designs have been shown to be powerful in detecting the significant rare variants associated with human diseases. However, very few significant results have been found owing to relatively small sample sizes and the fact that statistical analyses often suffer from high false-negative error rates. These limitations can be avoided by combining results from multiple studies via meta-analysis. However, statistical methods for meta-analysis with rare variants are limited for family-based samples. In this report, we propose a tool for the meta-analysis of family-based rare variant associations, metaFARVAT. metaFARVAT is based on a quasi-likelihood score for each variant. These scores are combined to generate burden test, variable-threshold test, sequence kernel association test (SKAT), and optimal SKAT statistics. The proposed method tests homogeneous and heterogeneous effects of variants among different studies and can be applied to both quantitative and dichotomous phenotypes. Simulation results demonstrated the robustness and efficiency of the proposed method in different scenarios. By applying metaFARVAT to data from a family-based study and a case-control study, we identified a few promising candidate genes, including , which is associated with chronic obstructive pulmonary disease.

Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.

Monogenic causes of chronic kidney disease in adults. - Connaughton, Dervla M; Kennedy, Claire; Shril, Shirlee; Mann, Nina; Murray, Susan L; Williams, Patrick A; Conlon, Eoin; Nakayama, Makiko; van der Ven, Amelie T; Ityel, Hadas; Kause, Franziska; Kolvenbach, Caroline M; et al. (Kidney Int, 2019)
Approximately 500 monogenic causes of chronic kidney disease (CKD) have been identified, mainly in pediatric populations. The frequency of monogenic causes among adults with CKD has been less extensively studied. To determine the likelihood of detecting monogenic causes of CKD in adults presenting to nephrology services in Ireland, we conducted whole exome sequencing (WES) in a multi-centre cohort of 114 families including 138 affected individuals with CKD. Affected adults were recruited from 78 families with a positive family history, 16 families with extra-renal features, and 20 families with neither a family history nor extra-renal features. We detected a pathogenic mutation in a known CKD gene in 42 of 114 families (37%). A monogenic cause was identified in 36% of affected families with a positive family history of CKD, 69% of those with extra-renal features, and only 15% of those without a family history or extra-renal features. There was no difference in the rate of genetic diagnosis in individuals with childhood versus adult onset CKD. Among the 42 families in whom a monogenic cause was identified, WES confirmed the clinical diagnosis in 17 (40%), corrected the clinical diagnosis in 9 (22%), and established a diagnosis for the first time in 16 families referred with CKD of unknown etiology (38%). In this multi-centre study of adults with CKD, a molecular genetic diagnosis was established in over one-third of families. In the evolving era of precision medicine, WES may be an important tool to identify the cause of CKD in adults.

MSTO1 mutations cause mtDNA depletion, manifesting as muscular dystrophy with cerebellar involvement. - Donkervoort, S; Sabouny, R; Yun, P; Gauquelin, L; Chao, K R; Hu, Y; Al Khatib, I; Töpf, A; Mohassel, P; Cummings, B B; Kaur, R; Saade, D; et al. (Acta Neuropathol, 2019)
MSTO1 encodes a cytosolic mitochondrial fusion protein, misato homolog 1 or MSTO1. While the full genotype-phenotype spectrum remains to be explored, pathogenic variants in MSTO1 have recently been reported in a small number of patients presenting with a phenotype of cerebellar ataxia, congenital muscle involvement with histologic findings ranging from myopathic to dystrophic and pigmentary retinopathy. The proposed underlying pathogenic mechanism of MSTO1-related disease is suggestive of impaired mitochondrial fusion secondary to a loss of function of MSTO1. Disorders of mitochondrial fusion and fission have been shown to also lead to mitochondrial DNA (mtDNA) depletion, linking them to the mtDNA depletion syndromes, a clinically and genetically diverse class of mitochondrial diseases characterized by a reduction of cellular mtDNA content. However, the consequences of pathogenic variants in MSTO1 on mtDNA maintenance remain poorly understood. We present extensive phenotypic and genetic data from 12 independent families, including 15 new patients harbouring a broad array of bi-allelic MSTO1 pathogenic variants, and we provide functional characterization from seven MSTO1-related disease patient fibroblasts. Bi-allelic loss-of-function variants in MSTO1 manifest clinically with a remarkably consistent phenotype of childhood-onset muscular dystrophy, corticospinal tract dysfunction and early-onset non-progressive cerebellar atrophy. MSTO1 protein was not detectable in the cultured fibroblasts of all seven patients evaluated, suggesting that pathogenic variants result in a loss of protein expression and/or affect protein stability. Consistent with impaired mitochondrial fusion, mitochondrial networks in fibroblasts were found to be fragmented. Furthermore, all fibroblasts were found to have depletion of mtDNA ranging from 30 to 70% along with alterations to mtDNA nucleoids. Our data corroborate the role of MSTO1 as a mitochondrial fusion protein and highlight a previously unrecognized link to mtDNA regulation. As impaired mitochondrial fusion is a recognized cause of mtDNA depletion syndromes, this novel link to mtDNA depletion in patient fibroblasts suggests that MSTO1-deficiency should also be considered a mtDNA depletion syndrome. Thus, we provide mechanistic insight into the disease pathogenesis associated with MSTO1 mutations and further define the clinical spectrum and the natural history of MSTO1-related disease.

Mutations in and previously unimplicated genes of the BMP, Wnt, and Hedgehog pathways in syndromic craniosynostosis. - Timberlake, Andrew T; Jin, Sheng Chih; Nelson-Williams, Carol; Wu, Robin; Furey, Charuta G; Islam, Barira; Haider, Shozeb; Loring, Erin; Galm, Amy; Steinbacher, Derek M; Larysz, Dawid; Staffenberg, David A; et al. (Proc Natl Acad Sci U S A, 2019)
Craniosynostosis (CS) is a frequent congenital anomaly featuring the premature fusion of 1 or more sutures of the cranial vault. Syndromic cases, featuring additional congenital anomalies, make up 15% of CS. While many genes underlying syndromic CS have been identified, the cause of many syndromic cases remains unknown. We performed exome sequencing of 12 syndromic CS cases and their parents, in whom previous genetic evaluations were unrevealing. Damaging de novo or transmitted loss of function (LOF) mutations were found in 8 genes that are highly intolerant to LOF mutation ( = 4.0 × 10); additionally, a rare damaging mutation in , which has a lower level of intolerance, was identified. Four probands had rare damaging mutations (2 de novo) in , a transcription factor that orchestrates neural crest cell migration and differentiation; this mutation burden is highly significant ( = 8.2 × 10). Three probands had rare damaging mutations in , , or , which function in the Hedgehog, BMP, and Wnt signaling pathways; other genes in these pathways have previously been implicated in syndromic CS. Similarly, damaging de novo mutations were identified in genes encoding the chromatin modifier , and , encoding catenin α-1. These findings establish as a CS gene, have implications for assessing risk to subsequent children in these families, and provide evidence implicating other genes in syndromic CS. This high yield indicates the value of performing exome sequencing of syndromic CS patients when sequencing of known disease loci is unrevealing.

Mutations in ANKLE2, a ZIKA Virus Target, Disrupt an Asymmetric Cell Division Pathway in Drosophila Neuroblasts to Cause Microcephaly. - Link, Nichole; Chung, Hyunglok; Jolly, Angad; Withers, Marjorie; Tepe, Burak; Arenkiel, Benjamin R; Shah, Priya S; Krogan, Nevan J; Aydin, Hatip; Geckinli, Bilgen B; Tos, Tulay; Isikay, Sedat; et al. (Dev Cell, 2019)
The apical Par complex, which contains atypical protein kinase C (aPKC), Bazooka (Par-3), and Par-6, is required for establishing polarity during asymmetric division of neuroblasts in Drosophila, and its activity depends on L(2)gl. We show that loss of Ankle2, a protein associated with microcephaly in humans and known to interact with Zika protein NS4A, reduces brain volume in flies and impacts the function of the Par complex. Reducing Ankle2 levels disrupts endoplasmic reticulum (ER) and nuclear envelope morphology, releasing the kinase Ballchen-VRK1 into the cytosol. These defects are associated with reduced phosphorylation of aPKC, disruption of Par-complex localization, and spindle alignment defects. Importantly, removal of one copy of ballchen or l(2)gl suppresses Ankle2 mutant phenotypes and restores viability and brain size. Human mutational studies implicate the above-mentioned genes in microcephaly and motor neuron disease. We suggest that NS4A, ANKLE2, VRK1, and LLGL1 define a pathway impinging on asymmetric determinants of neural stem cell division.

Mutations in KIRREL1, a slit diaphragm component, cause steroid-resistant nephrotic syndrome. - Solanki, Ashish K; Widmeier, Eugen; Arif, Ehtesham; Sharma, Shailza; Daga, Ankana; Srivastava, Pankaj; Kwon, Sang-Ho; Hugo, Hannah; Nakayama, Makiko; Mann, Nina; Majmundar, Amar J; Tan, Wei; et al. (Kidney Int, 2019)
Steroid-resistant nephrotic syndrome is a frequent cause of chronic kidney disease almost inevitably progressing to end-stage renal disease. More than 58 monogenic causes of SRNS have been discovered and majority of known steroid-resistant nephrotic syndrome causing genes are predominantly expressed in glomerular podocytes, placing them at the center of disease pathogenesis. Herein, we describe two unrelated families with steroid-resistant nephrotic syndrome with homozygous mutations in the KIRREL1 gene. One mutation showed high frequency in the European population (minor allele frequency 0.0011) and this patient achieved complete remission following treatment, but later progressed to chronic kidney disease. We found that mutant KIRREL1 proteins failed to localize to the podocyte cell membrane, indicating defective trafficking and impaired podocytes function. Thus, the KIRREL1 gene product has an important role in modulating the integrity of the slit diaphragm and maintaining glomerular filtration function.

Novel parent-of-origin-specific differentially methylated loci on chromosome 16. - Schulze, Katharina V; Szafranski, Przemyslaw; Lesmana, Harry; Hopkin, Robert J; Hamvas, Aaron; Wambach, Jennifer A; Shinawi, Marwan; Zapata, Gladys; Carvalho, Claudia M B; Liu, Qian; Karolak, Justyna A; Lupski, James R; et al. (Clin Epigenetics, 2019)
BACKGROUND: Congenital malformations associated with maternal uniparental disomy of chromosome 16, upd(16)mat, resemble those observed in newborns with the lethal developmental lung disease, alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV). Interestingly, ACDMPV-causative deletions, involving FOXF1 or its lung-specific upstream enhancer at 16q24.1, arise almost exclusively on the maternally inherited chromosome 16. Given the phenotypic similarities between upd(16)mat and ACDMPV, together with parental allelic bias in ACDMPV, we hypothesized that there may be unknown imprinted loci mapping to chromosome 16 that become functionally unmasked by chromosomal structural variants. RESULTS: To identify parent-of-origin biased DNA methylation, we performed high-resolution bisulfite sequencing of chromosome 16 on peripheral blood and cultured skin fibroblasts from individuals with maternal or paternal upd(16) as well as lung tissue from patients with ACDMPV-causative 16q24.1 deletions and a normal control. We identified 22 differentially methylated regions (DMRs) with ≥ 5 consecutive CpG methylation sites and varying tissue-specificity, including the known DMRs associated with the established imprinted gene ZNF597 and DMRs supporting maternal methylation of PRR25, thought to be paternally expressed in lymphoblastoid cells. Lastly, we found evidence of paternal methylation on 16q24.1 near LINC01082 mapping to the FOXF1 enhancer. CONCLUSIONS: Using high-resolution bisulfite sequencing to evaluate DNA methylation across chromosome 16, we found evidence for novel candidate imprinted loci on chromosome 16 that would not be evident in array-based assays and could contribute to the birth defects observed in patients with upd(16)mat or in ACDMPV.

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.

Pathogenic Abnormal Splicing Due to Intronic Deletions that Induce Biophysical Space Constraint for Spliceosome Assembly. - Bryen, Samantha J; Joshi, Himanshu; Evesson, Frances J; Girard, Cyrille; Ghaoui, Roula; Waddell, Leigh B; Testa, Alison C; Cummings, Beryl; Arbuckle, Susan; Graf, Nicole; Webster, Richard; MacArthur, Daniel G; et al. (Am J Hum Genet, 2019)
A precise genetic diagnosis is the single most important step for families with genetic disorders to enable personalized and preventative medicine. In addition to genetic variants in coding regions (exons) that can change a protein sequence, abnormal pre-mRNA splicing can be devastating for the encoded protein, inducing a frameshift or in-frame deletion/insertion of multiple residues. Non-coding variants that disrupt splicing are extremely challenging to identify. Stemming from an initial clinical discovery in two index Australian families, we define 25 families with genetic disorders caused by a class of pathogenic non-coding splice variant due to intronic deletions. These pathogenic intronic deletions spare all consensus splice motifs, though they critically shorten the minimal distance between the 5' splice-site (5'SS) and branchpoint. The mechanistic basis for abnormal splicing is due to biophysical constraint precluding U1/U2 spliceosome assembly, which stalls in A-complexes (that bridge the 5'SS and branchpoint). Substitution of deleted nucleotides with non-specific sequences restores spliceosome assembly and normal splicing, arguing against loss of an intronic element as the primary causal basis. Incremental lengthening of 5'SS-branchpoint length in our index EMD case subject defines 45-47 nt as the critical elongation enabling (inefficient) spliceosome assembly for EMD intron 5. The 5'SS-branchpoint space constraint mechanism, not currently factored by genomic informatics pipelines, is relevant to diagnosis and precision medicine across the breadth of Mendelian disorders and cancer genomics.

A Patient with Berardinelli-Seip Syndrome, Novel Splicesite Mutation and Concomitant Development of Non-diabetic Polyneuropathy - Oswiecimska, Joanna; Dawidziuk, Mateusz; Gambin, Tomasz; Ziora, Katarzyna; Marek, Marta; Rzonca, Sylwia; Guilbride, D. Lys; Jhangiani, Shalini N.; Obuchowicz, Anna; Sikora, Alicja; Lupski, James R.; Wiszniewski, Wojciech; et al. (J Clin Res Pediatr Endocrinol, 2019)
Primary polyneuropathy in the context of Seip-Berardinelli type 1 seipinopathy, or congenital generalized lipodystrophy type 1 (CGL1) has not been previously reported. We report the case history of a 27 year old female CGL1 patient presenting with an unusual additional development of non-diabetic peripheral neuropathy and learning disabilities in early adolescence. Whole exome sequencing (WES) of the patient genome identified a novel variant, homozygous for a 52 bp intronic deletion in the locus, coding for 1-acylglycerol-3-phosphate O-acyltransferase 2, which is uniquely associated with CGL1 seipinopathies, with no molecular evidence for dual diagnosis. Functional studies using RNA isolated from patient peripheral blood leucocytes showed abnormal RNA splicing resulting in the loss of 25 amino acids from the patient AGPAT2 protein coding sequence. Stability and transcription levels for the misspliced mRNA in our patient nonetheless remained normal. Any AGPAT2 protein produced in our patient is therefore likely to be dysfunctional. However, formal linkage of this deletion to the neuropathy observed remains to be shown. The classical clinical presentation of a patient with -associated lipodystrophy shows normal cognition and no development of polyneuropathy. Cognitive disabilities and polyneuropathy are features associated exclusively with clinical CGL type 2 arising from seipin gene mutations. This case study suggests that in some genetic contexts, mutations can also produce phenotypes with primary polyneuropathy.

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Yuan, Bo; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

Recessive DES cardio/myopathy without myofibrillar aggregates: intronic splice variant silences one allele leaving only missense L190P-desmin. - Riley, Lisa G; Waddell, Leigh B; Ghaoui, Roula; Evesson, Frances J; Cummings, Beryl B; Bryen, Samantha J; Joshi, Himanshu; Wang, Min-Xia; Brammah, Susan; Kritharides, Leonard; Corbett, Alastair; MacArthur, Daniel G; et al. (Eur J Hum Genet, 2019)
We establish autosomal recessive DES variants p.(Leu190Pro) and a deep intronic splice variant causing inclusion of a frameshift-inducing artificial exon/intronic fragment, as the likely cause of myopathy with cardiac involvement in female siblings. Both sisters presented in their twenties with slowly progressive limb girdle weakness, severe systolic dysfunction, and progressive, severe respiratory weakness. Desmin is an intermediate filament protein typically associated with autosomal dominant myofibrillar myopathy with cardiac involvement. However a few rare cases of autosomal recessive desminopathy are reported. In this family, a paternal missense p.(Leu190Pro) variant was viewed unlikely to be causative of autosomal dominant desminopathy, as the father and brothers carrying this variant were clinically unaffected. Clinical fit with a DES-related myopathy encouraged closer scrutiny of all DES variants, identifying a maternal deep intronic variant within intron-7, predicted to create a cryptic splice site, which segregated with disease. RNA sequencing and studies of muscle cDNA confirmed the deep intronic variant caused aberrant splicing of an artificial exon/intronic fragment into maternal DES mRNA transcripts, encoding a premature termination codon, and potently activating nonsense-mediate decay (92% paternal DES transcripts, 8% maternal). Western blot showed 60-75% reduction in desmin levels, likely comprised only of missense p.(Leu190Pro) desmin. Biopsy showed fibre size variation with increased central nuclei. Electron microscopy showed extensive myofibrillar disarray, duplication of the basal lamina, but no inclusions or aggregates. This study expands the phenotypic spectrum of recessive DES cardio/myopathy, and emphasizes the continuing importance of muscle biopsy for functional genomics pursuit of 'tricky' variants in neuromuscular conditions.

A recurrent COL6A1 pseudoexon insertion causes muscular dystrophy and is effectively targeted by splice-correction therapies. - Bolduc, Veronique; Foley, A Reghan; Solomon-Degefa, Herimela; Sarathy, Apurva; Donkervoort, Sandra; Hu, Ying; Chen, Grace S; Sizov, Katherine; Nalls, Matthew; Zhou, Haiyan; Aguti, Sara; Cummings, Beryl B; et al. (JCI Insight, 2019)
The clinical application of advanced next-generation sequencing technologies is increasingly uncovering novel classes of mutations that may serve as potential targets for precision medicine therapeutics. Here, we show that a deep intronic splice defect in the COL6A1 gene, originally discovered by applying muscle RNA sequencing in patients with clinical findings of collagen VI-related dystrophy (COL6-RD), inserts an in-frame pseudoexon into COL6A1 mRNA, encodes a mutant collagen α1(VI) protein that exerts a dominant-negative effect on collagen VI matrix assembly, and provides a unique opportunity for splice-correction approaches aimed at restoring normal gene expression. Using splice-modulating antisense oligomers, we efficiently skipped the pseudoexon in patient-derived fibroblast cultures and restored a wild-type matrix. Similarly, we used CRISPR/Cas9 to precisely delete an intronic sequence containing the pseudoexon and efficiently abolish its inclusion while preserving wild-type splicing. Considering that this splice defect is emerging as one of the single most frequent mutations in COL6-RD, the design of specific and effective splice-correction therapies offers a promising path for clinical translation.

Redefining the Etiologic Landscape of Cerebellar Malformations. - Aldinger, Kimberly A; Timms, Andrew E; Thomson, Zachary; Mirzaa, Ghayda M; Bennett, James T; Rosenberg, Alexander B; Roco, Charles M; Hirano, Matthew; Abidi, Fatima; Haldipur, Parthiv; Cheng, Chi V; Collins, Sarah; et al. (Am J Hum Genet, 2019)
Cerebellar malformations are diverse congenital anomalies frequently associated with developmental disability. Although genetic and prenatal non-genetic causes have been described, no systematic analysis has been performed. Here, we present a large-exome sequencing study of Dandy-Walker malformation (DWM) and cerebellar hypoplasia (CBLH). We performed exome sequencing in 282 individuals from 100 families with DWM or CBLH, and we established a molecular diagnosis in 36 of 100 families, with a significantly higher yield for CBLH (51%) than for DWM (16%). The 41 variants impact 27 neurodevelopmental-disorder-associated genes, thus demonstrating that CBLH and DWM are often features of monogenic neurodevelopmental disorders. Though only seven monogenic causes (19%) were identified in more than one individual, neuroimaging review of 131 additional individuals confirmed cerebellar abnormalities in 23 of 27 genetic disorders (85%). Prenatal risk factors were frequently found among individuals without a genetic diagnosis (30 of 64 individuals [47%]). Single-cell RNA sequencing of prenatal human cerebellar tissue revealed gene enrichment in neuronal and vascular cell types; this suggests that defective vasculogenesis may disrupt cerebellar development. Further, de novo gain-of-function variants in PDGFRB, a tyrosine kinase receptor essential for vascular progenitor signaling, were associated with CBLH, and this discovery links genetic and non-genetic etiologies. Our results suggest that genetic defects impact specific cerebellar cell types and implicate abnormal vascular development as a mechanism for cerebellar malformations. We also confirmed a major contribution for non-genetic prenatal factors in individuals with cerebellar abnormalities, substantially influencing diagnostic evaluation and counseling regarding recurrence risk and prognosis.

A retrospective analysis of the prevalence of imprinting disorders in Estonia from 1998 to 2016. - Yakoreva, Maria; Kahre, Tiina; Žordania, Riina; Reinson, Karit; Teek, Rita; Tillmann, Vallo; Peet, Aleksandr; Õiglane-Shlik, Eve; Pajusalu, Sander; Murumets, Ülle; Vals, Mari-Anne; Mee, Pille; et al. (Eur J Hum Genet, 2019)
Imprinting disorders (ImpDis) represent a small group of rare congenital diseases primarily affecting growth, development, and the hormonal and metabolic systems. The aim of present study was to identify the prevalence of the ImpDis in Estonia, to describe trends in the live birth prevalence of these disorders between 1998 and 2016, and to compare the results with previously published data. We retrospectively reviewed the records of all Estonian patients since 1998 with both molecularly and clinically diagnosed ImpDis. A prospective study was also conducted, in which all patients with clinical suspicion for an ImpDis were molecularly analyzed. Eighty-seven individuals with ImpDis were identified. Twenty-seven (31%) of them had Prader-Willi syndrome (PWS), 15 (17%) had Angelman syndrome (AS), 15 (17%) had Silver-Russell syndrome (SRS), 12 (14%) had Beckwith-Wiedemann syndrome (BWS), 10 (11%) had pseudo- or pseudopseudohypoparathyroidism, four had central precocious puberty, two had Temple syndrome, one had transient neonatal diabetes mellitus, and one had myoclonus-dystonia syndrome. One third of SRS and BWS cases fulfilled the diagnostic criteria for these disorders, but tested negative for genetic abnormalities. Seventy-six individuals were alive as of January 1, 2018, indicating the total prevalence of ImpDis in Estonia is 5.8/100,000 (95% CI 4.6/100,000-7.2/100,000). The minimum live birth prevalence of all ImpDis in Estonia in 2004-2016 was 1/3,462, PWS 1/13,599, AS 1/27,198, BWS 1/21,154, SRS 1/15,866, and PHP/PPHP 1/27,198. Our results are only partially consistent with previously published data. The worldwide prevalence of SRS and GNAS-gene-related ImpDis is likely underestimated and may be at least three times higher than expected.

ROBO4 variants predispose individuals to bicuspid aortic valve and thoracic aortic aneurysm. - Gould, Russell A; Aziz, Hamza; Woods, Courtney E; Seman-Senderos, Manuel Alejandro; Sparks, Elizabeth; Preuss, Christoph; Wünnemann, Florian; Bedja, Djahida; Moats, Cassandra R; McClymont, Sarah A; Rose, Rebecca; Sobreira, Nara; et al. (Nat Genet, 2019)
Bicuspid aortic valve (BAV) is a common congenital heart defect (population incidence, 1-2%) that frequently presents with ascending aortic aneurysm (AscAA). BAV/AscAA shows autosomal dominant inheritance with incomplete penetrance and male predominance. Causative gene mutations (for example, NOTCH1, SMAD6) are known for ≤1% of nonsyndromic BAV cases with and without AscAA, impeding mechanistic insight and development of therapeutic strategies. Here, we report the identification of variants in ROBO4 (which encodes a factor known to contribute to endothelial performance) that segregate with disease in two families. Targeted sequencing of ROBO4 showed enrichment for rare variants in BAV/AscAA probands compared with controls. Targeted silencing of ROBO4 or mutant ROBO4 expression in endothelial cell lines results in impaired barrier function and a synthetic repertoire suggestive of endothelial-to-mesenchymal transition. This is consistent with BAV/AscAA-associated findings in patients and in animal models deficient for ROBO4. These data identify a novel endothelial etiology for this common human disease phenotype.
Keywords: Animals; Aortic Aneurysm, Thoracic; Aortic Valve; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Female; Heart Valve Diseases; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Receptors, Cell Surface; Zebrafish

Spatially clustering de novo variants in CYFIP2, encoding the cytoplasmic FMRP interacting protein 2, cause intellectual disability and seizures. - Zweier, Markus; Begemann, Anaïs; McWalter, Kirsty; Cho, Megan T; Abela, Lucia; Banka, Siddharth; Behring, Bettina; Berger, Andrea; Brown, Chester W; Carneiro, Maryline; Chen, Jiani; Cooper, Gregory M; et al. (Eur J Hum Genet, 2019)
CYFIP2, encoding the evolutionary highly conserved cytoplasmic FMRP interacting protein 2, has previously been proposed as a candidate gene for intellectual disability and autism because of its important role linking FMRP-dependent transcription regulation and actin polymerization via the WAVE regulatory complex (WRC). Recently, de novo variants affecting the amino acid p.Arg87 of CYFIP2 were reported in four individuals with epileptic encephalopathy. We here report 12 independent patients harboring a variety of de novo variants in CYFIP2 broadening the molecular and clinical spectrum of a novel CYFIP2-related neurodevelopmental disorder. Using trio whole-exome or -genome sequencing, we identified 12 independent patients carrying a total of eight distinct de novo variants in CYFIP2 with a shared phenotype of intellectual disability, seizures, and muscular hypotonia. We detected seven different missense variants, of which two occurred recurrently (p.(Arg87Cys) and p.(Ile664Met)), and a splice donor variant in the last intron for which we showed exon skipping in the transcript. The latter is expected to escape nonsense-mediated mRNA decay resulting in a truncated protein. Despite the large spacing in the primary structure, the variants spatially cluster in the tertiary structure and are all predicted to weaken the interaction with WAVE1 or NCKAP1 of the actin polymerization regulating WRC-complex. Preliminary genotype-phenotype correlation indicates a profound phenotype in p.Arg87 substitutions and a more variable phenotype in other alterations. This study evidenced a variety of de novo variants in CYFIP2 as a novel cause of mostly severe intellectual disability with seizures and muscular hypotonia.

Targeted Treatment of Individuals With Psychosis Carrying a Copy Number Variant Containing a Genomic Triplication of the Glycine Decarboxylase Gene. - Bodkin, J Alexander; Coleman, Michael J; Godfrey, Laura J; Carvalho, Claudia M B; Morgan, Charity J; Suckow, Raymond F; Anderson, Thea; Öngür, Dost; Kaufman, Marc J; Lewandowski, Kathryn E; Siegel, Arthur J; Waldstreicher, Elliot; et al. (Biol Psychiatry, 2019)
BACKGROUND: The increased mutational burden for rare structural genomic variants in schizophrenia and other neurodevelopmental disorders has so far not yielded therapies targeting the biological effects of specific mutations. We identified two carriers (mother and son) of a triplication of the gene encoding glycine decarboxylase, GLDC, presumably resulting in reduced availability of the N-methyl-D-aspartate receptor coagonists glycine and D-serine and N-methyl-D-aspartate receptor hypofunction. Both carriers had a diagnosis of a psychotic disorder. METHODS: We carried out two double-blind, placebo-controlled clinical trials of N-methyl-D-aspartate receptor augmentation of psychotropic drug treatment in these two individuals. Glycine was used in the first clinical trial, and D-cycloserine was used in the second one. RESULTS: Glycine or D-cycloserine augmentation of psychotropic drug treatment each improved psychotic and mood symptoms in placebo-controlled trials. CONCLUSIONS: These results provide two independent proof-of-principle demonstrations of symptom relief by targeting a specific genotype and explicitly link an individual mutation to the pathophysiology of psychosis and treatment response.

TBX6 compound inheritance leads to congenital vertebral malformations in humans and mice. - Yang, Nan; Wu, Nan; Zhang, Ling; Zhao, Yanxue; Liu, Jiaqi; Liang, Xiangyu; Ren, Xiaojun; Li, Weiyu; Chen, Weisheng; Dong, Shuangshuang; Zhao, Sen; Lin, Jiachen; et al. (Hum Mol Genet, 2019)
Congenital vertebral malformations (CVMs) are associated with human TBX6 compound inheritance that combines a rare null allele and a common hypomorphic allele at the TBX6 locus. Our previous in vitro evidence suggested that this compound inheritance resulted in a TBX6 gene dosage of less than haploinsufficiency (i.e. <50%) as a potential mechanism of TBX6-associated CVMs. To further investigate this pathogenetic model, we ascertained and collected 108 Chinese CVM cases and found that 10 (9.3%) of them carried TBX6 null mutations in combination with common hypomorphic variants at the second TBX6 allele. For in vivo functional verification and genetic analysis of TBX6 compound inheritance, we generated both null and hypomorphic mutations in mouse Tbx6 using the CRISPR-Cas9 method. These Tbx6 mutants are not identical to the patient variants at the DNA sequence level, but instead functionally mimic disease-associated TBX6 variants. Intriguingly, as anticipated by the compound inheritance model, a high penetrance of CVM phenotype was only observed in the mice with combined null and hypomorphic alleles of Tbx6. These findings are consistent with our experimental observations in humans and supported the dosage effect of TBX6 in CVM etiology. In conclusion, our findings in the newly collected human CVM subjects and Tbx6 mouse models consistently support the contention that TBX6 compound inheritance causes CVMs, potentially via a gene dosage-dependent mechanism. Furthermore, mouse Tbx6 mutants mimicking human CVM-associated variants will be useful models for further mechanistic investigations of CVM pathogenesis in the cases associated with TBX6.
Keywords: Adolescent; Alleles; Animals; Child; Child, Preschool; Congenital Abnormalities; CRISPR-Cas Systems; Disease Models, Animal; Female; Haploinsufficiency; Humans; Infant; Male; Mice; Mutation; Phenotype; Scoliosis; Spine; T-Box Domain Proteins

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.

Unique bioinformatic approach and comprehensive reanalysis improve diagnostic yield of clinical exomes. - Schmitz-Abe, Klaus; Li, Qifei; Rosen, Samantha M; Nori, Neeharika; Madden, Jill A; Genetti, Casie A; Wojcik, Monica H; Ponnaluri, Sadhana; Gubbels, Cynthia S; Picker, Jonathan D; O'Donnell-Luria, Anne H; Yu, Timothy W; et al. (Eur J Hum Genet, 2019)
Clinical exome sequencing (CES) is increasingly being utilized; however, a large proportion of patients remain undiagnosed, creating a need for a systematic approach to increase the diagnostic yield. We have reanalyzed CES data for a clinically heterogeneous cohort of 102 probands with likely Mendelian conditions, including 74 negative cases and 28 cases with candidate variants, but reanalysis requested by clinicians. Reanalysis was performed by an interdisciplinary team using a validated custom-built pipeline, "Variant Explorer Pipeline" (VExP). This reanalysis approach and results were compared with existing literature. Reanalysis of candidate variants from CES in 28 cases revealed 1 interpretation that needed to be reclassified. A confirmed or potential genetic diagnosis was identified in 24 of 75 CES-negative/reclassified cases (32.0%), including variants in known disease-causing genes (n = 6) or candidate genes (n = 18). This yield was higher compared with similar studies demonstrating the utility of this approach. In summary, reanalysis of negative CES in a research setting enhances diagnostic yield by about a third. This study suggests the need for comprehensive, continued reanalysis of exome data when molecular diagnosis is elusive.

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

ZMIZ1 Variants Cause a Syndromic Neurodevelopmental Disorder. - Carapito, Raphael; Ivanova, Ekaterina L; Morlon, Aurore; Meng, Linyan; Molitor, Anne; Erdmann, Eva; Kieffer, Bruno; Pichot, Angélique; Naegely, Lydie; Kolmer, Aline; Paul, Nicodème; Hanauer, Antoine; et al. (Am J Hum Genet, 2019)
ZMIZ1 is a coactivator of several transcription factors, including p53, the androgen receptor, and NOTCH1. Here, we report 19 subjects with intellectual disability and developmental delay carrying variants in ZMIZ1. The associated features include growth failure, feeding difficulties, microcephaly, facial dysmorphism, and various other congenital malformations. Of these 19, 14 unrelated subjects carried de novo heterozygous single-nucleotide variants (SNVs) or single-base insertions/deletions, 3 siblings harbored a heterozygous single-base insertion, and 2 subjects had a balanced translocation disrupting ZMIZ1 or involving a regulatory region of ZMIZ1. In total, we identified 13 point mutations that affect key protein regions, including a SUMO acceptor site, a central disordered alanine-rich motif, a proline-rich domain, and a transactivation domain. All identified variants were absent from all available exome and genome databases. In vitro, ZMIZ1 showed impaired coactivation of the androgen receptor. In vivo, overexpression of ZMIZ1 mutant alleles in developing mouse brains using in utero electroporation resulted in abnormal pyramidal neuron morphology, polarization, and positioning, underscoring the importance of ZMIZ1 in neural development and supporting mutations in ZMIZ1 as the cause of a rare neurodevelopmental syndrome.
Keywords: Alleles; Animals; Child; Child, Preschool; Developmental Disabilities; Female; Humans; Infant; Intellectual Disability; Male; Mice; Point Mutation; Syndrome; Transcription Factors

and Mutations Implicate RAB5 Regulation in Nephrotic Syndrome. - Hermle, Tobias; Schneider, Ronen; Schapiro, David; Braun, Daniela A; van der Ven, Amelie T; Warejko, Jillian K; Daga, Ankana; Widmeier, Eugen; Nakayama, Makiko; Jobst-Schwan, Tilman; Majmundar, Amar J; Ashraf, Shazia; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of CKD. The discovery of monogenic causes of SRNS has revealed specific pathogenetic pathways, but these monogenic causes do not explain all cases of SRNS. METHODS: To identify novel monogenic causes of SRNS, we screened 665 patients by whole-exome sequencing. We then evaluated the functional significance of two genes and the mutations therein that we discovered through this sequencing and conducted complementary studies in podocyte-like nephrocytes. RESULTS: We identified conserved, homozygous missense mutations of in two families with early-onset NS and a homozygous missense mutation of in two siblings with SRNS. GAPVD1 and ANKFY1 interact with the endosomal regulator RAB5. Coimmunoprecipitation assays indicated interaction between GAPVD1 and ANKFY1 proteins, which also colocalized when expressed in HEK293T cells. Silencing either protein diminished the podocyte migration rate. Compared with wild-type GAPVD1 and ANKFY1, the mutated proteins produced upon ectopic expression of or bearing the patient-derived mutations exhibited altered binding affinity for active RAB5 and reduced ability to rescue the knockout-induced defect in podocyte migration. Coimmunoprecipitation assays further demonstrated a physical interaction between nephrin and GAPVD1, and immunofluorescence revealed partial colocalization of these proteins in rat glomeruli. The patient-derived mutations reduced nephrin-GAPVD1 binding affinity. In , silencing impaired endocytosis and caused mistrafficking of the nephrin ortholog. CONCLUSIONS: Mutations in and probably in are novel monogenic causes of NS. The discovery of these genes implicates RAB5 regulation in the pathogenesis of human NS.

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

Bi-allelic CCDC47 Variants Cause a Disorder Characterized by Woolly Hair, Liver Dysfunction, Dysmorphic Features, and Global Developmental Delay. - Morimoto, Marie; Waller-Evans, Helen; Ammous, Zineb; Song, Xiaofei; Strauss, Kevin A; Pehlivan, Davut; Gonzaga-Jauregui, Claudia; Puffenberger, Erik G; Holst, Charles R; Karaca, Ender; Brigatti, Karlla W; Maguire, Emily; et al. (Am J Hum Genet, 2018)
Ca signaling is vital for various cellular processes including synaptic vesicle exocytosis, muscle contraction, regulation of secretion, gene transcription, and cellular proliferation. The endoplasmic reticulum (ER) is the largest intracellular Ca store, and dysregulation of ER Ca signaling and homeostasis contributes to the pathogenesis of various complex disorders and Mendelian disease traits. We describe four unrelated individuals with a complex multisystem disorder characterized by woolly hair, liver dysfunction, pruritus, dysmorphic features, hypotonia, and global developmental delay. Through whole-exome sequencing and family-based genomics, we identified bi-allelic variants in CCDC47 that encodes the Ca-binding ER transmembrane protein CCDC47. CCDC47, also known as calumin, has been shown to bind Ca with low affinity and high capacity. In mice, loss of Ccdc47 leads to embryonic lethality, suggesting that Ccdc47 is essential for early development. Characterization of cells from individuals with predicted likely damaging alleles showed decreased CCDC47 mRNA expression and protein levels. In vitro cellular experiments showed decreased total ER Ca storage, impaired Ca signaling mediated by the IPR Ca release channel, and reduced ER Ca refilling via store-operated Ca entry. These results, together with the previously described role of CCDC47 in Ca signaling and development, suggest that bi-allelic loss-of-function variants in CCDC47 underlie the pathogenesis of this multisystem disorder.

Biallelic Mutations in ADPRHL2, Encoding ADP-Ribosylhydrolase 3, Lead to a Degenerative Pediatric Stress-Induced Epileptic Ataxia Syndrome. - Ghosh, Shereen G; Becker, Kerstin; Huang, He; Dixon-Salazar, Tracy; Chai, Guoliang; Salpietro, Vincenzo; Al-Gazali, Lihadh; Waisfisz, Quinten; Wang, Haicui; Vaux, Keith K; Stanley, Valentina; Manole, Andreea; et al. (Am J Hum Genet, 2018)
ADP-ribosylation, the addition of poly-ADP ribose (PAR) onto proteins, is a response signal to cellular challenges, such as excitotoxicity or oxidative stress. This process is catalyzed by a group of enzymes referred to as poly(ADP-ribose) polymerases (PARPs). Because the accumulation of proteins with this modification results in cell death, its negative regulation restores cellular homeostasis: a process mediated by poly-ADP ribose glycohydrolases (PARGs) and ADP-ribosylhydrolase proteins (ARHs). Using linkage analysis and exome or genome sequencing, we identified recessive inactivating mutations in ADPRHL2 in six families. Affected individuals exhibited a pediatric-onset neurodegenerative disorder with progressive brain atrophy, developmental regression, and seizures in association with periods of stress, such as infections. Loss of the Drosophila paralog Parg showed lethality in response to oxidative challenge that was rescued by human ADPRHL2, suggesting functional conservation. Pharmacological inhibition of PARP also rescued the phenotype, suggesting the possibility of postnatal treatment for this genetic condition.

Bi-allelic POLR3A Loss-of-Function Variants Cause Autosomal-Recessive Wiedemann-Rautenstrauch Syndrome. - Wambach, Jennifer A; Wegner, Daniel J; Patni, Nivedita; Kircher, Martin; Willing, Marcia C; Baldridge, Dustin; Xing, Chao; Agarwal, Anil K; Vergano, Samantha A Schrier; Patel, Chirag; Grange, Dorothy K; Kenney, Amy; et al. (Am J Hum Genet, 2018)
Wiedemann-Rautenstrauch syndrome (WRS), also known as neonatal progeroid syndrome, is a rare disorder of unknown etiology. It has been proposed to be autosomal-recessive and is characterized by variable clinical features, such as intrauterine growth restriction and poor postnatal weight gain, characteristic facial features (triangular appearance to the face, convex nasal profile or pinched nose, and small mouth), widened fontanelles, pseudohydrocephalus, prominent scalp veins, lipodystrophy, and teeth abnormalities. A previous report described a single WRS patient with bi-allelic truncating and splicing variants in POLR3A. Here we present seven additional infants, children, and adults with WRS and bi-allelic truncating and/or splicing variants in POLR3A. POLR3A, the largest subunit of RNA polymerase III, is a DNA-directed RNA polymerase that transcribes many small noncoding RNAs that regulate transcription, RNA processing, and translation. Bi-allelic missense variants in POLR3A have been associated with phenotypes distinct from WRS: hypogonadotropic hypogonadism and hypomyelinating leukodystrophy with or without oligodontia. Our findings confirm the association of bi-allelic POLR3A variants with WRS, expand the clinical phenotype of WRS, and suggest specific POLR3A genotypes associated with WRS and hypomyelinating leukodystrophy.

CLCN2 chloride channel mutations in familial hyperaldosteronism type II. - Scholl, Ute I; Stölting, Gabriel; Schewe, Julia; Thiel, Anne; Tan, Hua; Nelson-Williams, Carol; Vichot, Alfred A; Jin, Sheng Chih; Loring, Erin; Untiet, Verena; Yoo, Taekyeong; Choi, Jungmin; et al. (Nat Genet, 2018)
Primary aldosteronism, a common cause of severe hypertension , features constitutive production of the adrenal steroid aldosterone. We analyzed a multiplex family with familial hyperaldosteronism type II (FH-II) and 80 additional probands with unsolved early-onset primary aldosteronism. Eight probands had novel heterozygous variants in CLCN2, including two de novo mutations and four independent occurrences of a mutation encoding an identical p.Arg172Gln substitution; all relatives with early-onset primary aldosteronism carried the CLCN2 variant found in the proband. CLCN2 encodes a voltage-gated chloride channel expressed in adrenal glomerulosa that opens at hyperpolarized membrane potentials. Channel opening depolarizes glomerulosa cells and induces expression of aldosterone synthase, the rate-limiting enzyme for aldosterone biosynthesis. Mutant channels show gain of function, with higher open probabilities at the glomerulosa resting potential. These findings for the first time demonstrate a role of anion channels in glomerulosa membrane potential determination, aldosterone production and hypertension. They establish the cause of a substantial fraction of early-onset primary aldosteronism.

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease. - Liu, Jiaqi; Zhou, Yangzhong; Liu, Sen; Song, Xiaofei; Yang, Xin-Zhuang; Fan, Yanhui; Chen, Weisheng; Akdemir, Zeynep Coban; Yan, Zihui; Zuo, Yuzhi; Du, Renqian; Liu, Zhenlei; et al. (Hum Genet, 2018)
With the recent advance in genome-wide association studies (GWAS), disease-associated single nucleotide polymorphisms (SNPs) and copy number variants (CNVs) have been extensively reported. Accordingly, the issue of incorrect identification of recombination events that can induce the distortion of multi-allelic or hemizygous variants has received more attention. However, the potential distorted calculation bias or significance of a detected association in a GWAS due to the coexistence of CNVs and SNPs in the same genomic region may remain under-recognized. Here we performed the association study within a congenital scoliosis (CS) cohort whose genetic etiology was recently elucidated as a compound inheritance model, including mostly one rare variant deletion CNV null allele and one common variant non-coding hypomorphic haplotype of the TBX6 gene. We demonstrated that the existence of a deletion in TBX6 led to an overestimation of the contribution of the SNPs on the hypomorphic allele. Furthermore, we generalized a model to explain the calculation bias, or distorted significance calculation for an association study, that can be 'induced' by CNVs at a locus. Meanwhile, overlapping between the disease-associated SNPs from published GWAS and common CNVs (overlap 10%) and pathogenic/likely pathogenic CNVs (overlap 99.69%) was significantly higher than the random distribution (p < 1 × 10 and p = 0.034, respectively), indicating that such co-existence of CNV and SNV alleles might generally influence data interpretation and potential outcomes of a GWAS. We also verified and assessed the influence of colocalizing CNVs to the detection sensitivity of disease-associated SNP variant alleles in another adolescent idiopathic scoliosis (AIS) genome-wide association study. We proposed that detecting co-existent CNVs when evaluating the association signals between SNPs and disease traits could improve genetic model analyses and better integrate GWAS with robust Mendelian principles.
Keywords: Adolescent; Congenital Abnormalities; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genomics; Genotype; Haplotypes; Humans; Phenotype; Polymorphism, Single Nucleotide; Scoliosis

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

The Congenital Heart Disease Genetic Network Study: Cohort description. - Hoang, Thanh T; Goldmuntz, Elizabeth; Roberts, Amy E; Chung, Wendy K; Kline, Jennie K; Deanfield, John E; Giardini, Alessandro; Aleman, Adolfo; Gelb, Bruce D; Mac Neal, Meghan; Porter, George A; Kim, Richard; et al. (PLoS One, 2018)
The Pediatric Cardiac Genomics Consortium (PCGC) designed the Congenital Heart Disease Genetic Network Study to provide phenotype and genotype data for a large congenital heart defects (CHDs) cohort. This article describes the PCGC cohort, overall and by major types of CHDs (e.g., conotruncal defects) and subtypes of conotrucal heart defects (e.g., tetralogy of Fallot) and left ventricular outflow tract obstructions (e.g., hypoplastic left heart syndrome). Cases with CHDs were recruited through ten sites, 2010-2014. Information on cases (N = 9,727) and their parents was collected through interviews and medical record abstraction. Four case characteristics, eleven parental characteristics, and thirteen parent-reported neurodevelopment outcomes were summarized using counts and frequencies and compared across CHD types and subtypes. Eleven percent of cases had a genetic diagnosis. Among cases without a genetic diagnosis, the majority had conotruncal heart defects (40%) or left ventricular outflow tract obstruction (21%). Across CHD types, there were significant differences (p<0.05) in the distribution of all four case characteristics (e.g., sex), four parental characteristics (e.g., maternal pregestational diabetes), and five neurodevelopmental outcomes (e.g., learning disabilities). Several characteristics (e.g., sex) were also significantly different across CHD subtypes. The PCGC cohort is one of the largest CHD cohorts available for the study of genetic determinants of risk and outcomes. The majority of cases do not have a genetic diagnosis. This description of the PCGC cohort, including differences across CHD types and subtypes, provides a reference work for investigators who are interested in collaborating with or using publically available resources from the PCGC.
Keywords: Adult; Cohort Studies; Female; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Male; Phenotype

Congenital Titinopathy: Comprehensive characterization and pathogenic insights. - Oates, Emily C; Jones, Kristi J; Donkervoort, Sandra; Charlton, Amanda; Brammah, Susan; Smith, John E; Ware, James S; Yau, Kyle S; Swanson, Lindsay C; Whiffin, Nicola; Peduto, Anthony J; Bournazos, Adam; et al. (Ann Neurol, 2018)
OBJECTIVE: Comprehensive clinical characterization of congenital titinopathy to facilitate diagnosis and management of this important emerging disorder. METHODS: Using massively parallel sequencing we identified 30 patients from 27 families with 2 pathogenic nonsense, frameshift and/or splice site TTN mutations in trans. We then undertook a detailed analysis of the clinical, histopathological and imaging features of these patients. RESULTS: All patients had prenatal or early onset hypotonia and/or congenital contractures. None had ophthalmoplegia. Scoliosis and respiratory insufficiency typically developed early and progressed rapidly, whereas limb weakness was often slowly progressive, and usually did not prevent independent walking. Cardiac involvement was present in 46% of patients. Relatives of 2 patients had dilated cardiomyopathy. Creatine kinase levels were normal to moderately elevated. Increased fiber size variation, internalized nuclei and cores were common histopathological abnormalities. Cap-like regions, whorled or ring fibers, and mitochondrial accumulations were also observed. Muscle magnetic resonance imaging showed gluteal, hamstring and calf muscle involvement. Western blot analysis showed a near-normal sized titin protein in all samples. The presence of 2 mutations predicted to impact both N2BA and N2B cardiac isoforms appeared to be associated with greatest risk of cardiac involvement. One-third of patients had 1 mutation predicted to impact exons present in fetal skeletal muscle, but not included within the mature skeletal muscle isoform transcript. This strongly suggests developmental isoforms are involved in the pathogenesis of this congenital/early onset disorder. INTERPRETATION: This detailed clinical reference dataset will greatly facilitate diagnostic confirmation and management of patients, and has provided important insights into disease pathogenesis. Ann Neurol 2018;83:1105-1124.

Co-occurrence of frameshift mutations in and in a child with complex craniosynostosis. - Timberlake, Andrew T; Wu, Robin; Nelson-Williams, Carol; Furey, Charuta G; Hildebrand, Kristi I; Elton, Scott W; Wood, Jeyhan S; Persing, John A; Lifton, Richard P (Hum Genome Var, 2018)
Non-syndromic craniosynostosis (CS) affects 1 in 2350 live births. Recent studies have shown that a significant fraction of cases are caused by de novo or rare transmitted mutations that promote premature osteoblast differentiation in cranial sutures. Rare heterozygous loss-of-function (LOF) mutations in and are highly enriched in patients with non-syndromic sagittal and coronal CS, respectively. Interestingly, both mutations show striking incomplete penetrance, suggesting a role for modifying alleles; in the case of , a common variant near drastically increases penetrance of sagittal CS. Here, we report a proband presenting with both sagittal and coronal craniosynostosis with the highly unusual recurrence of CS within two months of initial surgery, requiring a second operation to re-establish suture patency at six months of age. Exome sequencing revealed a rare transmitted frameshift mutation in (p. 152 fs*27) inherited from an unaffected parent, absence of the common risk variant, and a de novo frameshift mutation in (p.E548fs*14). and independently inhibit transcriptional targets of BMP signaling. The findings are consistent with epistasis of these mutations, increasing penetrance and severity of CS in this proband. They also add to the list of composite phenotypes resulting from two Mendelian mutations, and support the utility of exome sequencing in atypical CS cases.

De Novo Sequence and Copy Number Variants Are Strongly Associated with Tourette Disorder and Implicate Cell Polarity in Pathogenesis. - Wang, Sheng; Mandell, Jeffrey D; Kumar, Yogesh; Sun, Nawei; Morris, Montana T; Arbelaez, Juan; Nasello, Cara; Dong, Shan; Duhn, Clif; Zhao, Xin; Yang, Zhiyu; Padmanabhuni, Shanmukha S; et al. (Cell Rep, 2018)
We previously established the contribution of de novo damaging sequence variants to Tourette disorder (TD) through whole-exome sequencing of 511 trios. Here, we sequence an additional 291 TD trios and analyze the combined set of 802 trios. We observe an overrepresentation of de novo damaging variants in simplex, but not multiplex, families; we identify a high-confidence TD risk gene, CELSR3 (cadherin EGF LAG seven-pass G-type receptor 3); we find that the genes mutated in TD patients are enriched for those related to cell polarity, suggesting a common pathway underlying pathobiology; and we confirm a statistically significant excess of de novo copy number variants in TD. Finally, we identify significant overlap of de novo sequence variants between TD and obsessive-compulsive disorder and de novo copy number variants between TD and autism spectrum disorder, consistent with shared genetic risk.

De novo variants in congenital diaphragmatic hernia identify MYRF as a new syndrome and reveal genetic overlaps with other developmental disorders. - Qi, Hongjian; Yu, Lan; Zhou, Xueya; Wynn, Julia; Zhao, Haoquan; Guo, Yicheng; Zhu, Na; Kitaygorodsky, Alexander; Hernan, Rebecca; Aspelund, Gudrun; Lim, Foong-Yen; Crombleholme, Timothy; et al. (PLoS Genet, 2018)
Congenital diaphragmatic hernia (CDH) is a severe birth defect that is often accompanied by other congenital anomalies. Previous exome sequencing studies for CDH have supported a role of de novo damaging variants but did not identify any recurrently mutated genes. To investigate further the genetics of CDH, we analyzed de novo coding variants in 362 proband-parent trios including 271 new trios reported in this study. We identified four unrelated individuals with damaging de novo variants in MYRF (P = 5.3x10(-8)), including one likely gene-disrupting (LGD) and three deleterious missense (D-mis) variants. Eight additional individuals with de novo LGD or missense variants were identified from our other genetic studies or from the literature. Common phenotypes of MYRF de novo variant carriers include CDH, congenital heart disease and genitourinary abnormalities, suggesting that it represents a novel syndrome. MYRF is a membrane associated transcriptional factor highly expressed in developing diaphragm and is depleted of LGD variants in the general population. All de novo missense variants aggregated in two functional protein domains. Analyzing the transcriptome of patient-derived diaphragm fibroblast cells suggest that disease associated variants abolish the transcription factor activity. Furthermore, we showed that the remaining genes with damaging variants in CDH significantly overlap with genes implicated in other developmental disorders. Gene expression patterns and patient phenotypes support pleiotropic effects of damaging variants in these genes on CDH and other developmental disorders. Finally, functional enrichment analysis implicates the disruption of regulation of gene expression, kinase activities, intra-cellular signaling, and cytoskeleton organization as pathogenic mechanisms in CDH.
Keywords: Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Variation; Heart Defects, Congenital; Hernias, Diaphragmatic, Congenital; Humans; Infant, Newborn; Longitudinal Studies; Male; Membrane Proteins; Mutation; Mutation, Missense; Phenotype; Sequence Analysis, RNA; Syndrome; Transcription Factors; Whole Exome Sequencing; Whole Genome Sequencing

Detection of variants in dystroglycanopathy-associated genes through the application of targeted whole-exome sequencing analysis to a large cohort of patients with unexplained limb-girdle muscle weakness. - Johnson, Katherine; Bertoli, Marta; Phillips, Lauren; Topf, Ana; Van den Bergh, Peter; Vissing, John; Witting, Nanna; Nafissi, Shahriar; Jamal-Omidi, Shirin; Łusakowska, Anna; Kostera-Pruszczyk, Anna; Potulska-Chromik, Anna; et al. (Skelet Muscle, 2018)
BACKGROUND: Dystroglycanopathies are a clinically and genetically heterogeneous group of disorders that are typically characterised by limb-girdle muscle weakness. Mutations in 18 different genes have been associated with dystroglycanopathies, the encoded proteins of which typically modulate the binding of α-dystroglycan to extracellular matrix ligands by altering its glycosylation. This results in a disruption of the structural integrity of the myocyte, ultimately leading to muscle degeneration. METHODS: Deep phenotypic information was gathered using the PhenoTips online software for 1001 patients with unexplained limb-girdle muscle weakness from 43 different centres across 21 European and Middle Eastern countries. Whole-exome sequencing with at least 250 ng DNA was completed using an Illumina exome capture and a 38 Mb baited target. Genes known to be associated with dystroglycanopathies were analysed for disease-causing variants. RESULTS: Suspected pathogenic variants were detected in DPM3, ISPD, POMT1 and FKTN in one patient each, in POMK in two patients, in GMPPB in three patients, in FKRP in eight patients and in POMT2 in ten patients. This indicated a frequency of 2.7% for the disease group within the cohort of 1001 patients with unexplained limb-girdle muscle weakness. The phenotypes of the 27 patients were highly variable, yet with a fundamental presentation of proximal muscle weakness and elevated serum creatine kinase. CONCLUSIONS: Overall, we have identified 27 patients with suspected pathogenic variants in dystroglycanopathy-associated genes. We present evidence for the genetic and phenotypic diversity of the dystroglycanopathies as a disease group, while also highlighting the advantage of incorporating next-generation sequencing into the diagnostic pathway of rare diseases.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Child; Child, Preschool; Dystroglycans; Female; Genetic Predisposition to Disease; Genetic Variation; Glycosylation; Heterozygote; Homozygote; Humans; Male; Middle Aged; Muscle Proteins; Muscular Dystrophies, Limb-Girdle; Mutation; Phenotype; Whole Exome Sequencing; Young Adult

Dissecting the Causal Mechanism of X-Linked Dystonia-Parkinsonism by Integrating Genome and Transcriptome Assembly. - Aneichyk, Tatsiana; Hendriks, William T; Yadav, Rachita; Shin, David; Gao, Dadi; Vaine, Christine A; Collins, Ryan L; Domingo, Aloysius; Currall, Benjamin; Stortchevoi, Alexei; Multhaupt-Buell, Trisha; Penney, Ellen B; et al. (Cell, 2018)
X-linked Dystonia-Parkinsonism (XDP) is a Mendelian neurodegenerative disease that is endemic to the Philippines and is associated with a founder haplotype. We integrated multiple genome and transcriptome assembly technologies to narrow the causal mutation to the TAF1 locus, which included a SINE-VNTR-Alu (SVA) retrotransposition into intron 32 of the gene. Transcriptome analyses identified decreased expression of the canonical cTAF1 transcript among XDP probands, and de novo assembly across multiple pluripotent stem-cell-derived neuronal lineages discovered aberrant TAF1 transcription that involved alternative splicing and intron retention (IR) in proximity to the SVA that was anti-correlated with overall TAF1 expression. CRISPR/Cas9 excision of the SVA rescued this XDP-specific transcriptional signature and normalized TAF1 expression in probands. These data suggest an SVA-mediated aberrant transcriptional mechanism associated with XDP and may provide a roadmap for layered technologies and integrated assembly-based analyses for other unsolved Mendelian disorders.
Keywords: Alternative Splicing; Alu Elements; Base Sequence; Cohort Studies; CRISPR-Cas Systems; Dystonic Disorders; Family; Female; Genetic Diseases, X-Linked; Genetic Loci; Genome, Human; Haplotypes; High-Throughput Nucleotide Sequencing; Histone Acetyltransferases; Humans; Induced Pluripotent Stem Cells; Introns; Male; Minisatellite Repeats; Models, Genetic; Nerve Degeneration; Neural Stem Cells; Neurons; RNA, Messenger; Short Interspersed Nucleotide Elements; TATA-Binding Protein Associated Factors; Transcription Factor TFIID; Transcriptome

Dual Molecular Effects of Dominant RORA Mutations Cause Two Variants of Syndromic Intellectual Disability with Either Autism or Cerebellar Ataxia. - Guissart, Claire; Latypova, Xénia; Rollier, Paul; Khan, Tahir N; Stamberger, Hannah; McWalter, Kirsty; Cho, Megan T; Kjaergaard, Susanne; Weckhuysen, Sarah; Lesca, Gaetan; Besnard, Thomas; Õunap, Katrin; et al. (Am J Hum Genet, 2018)
RORα, the RAR-related orphan nuclear receptor alpha, is essential for cerebellar development. The spontaneous mutant mouse staggerer, with an ataxic gait caused by neurodegeneration of cerebellar Purkinje cells, was discovered two decades ago to result from homozygous intragenic Rora deletions. However, RORA mutations were hitherto undocumented in humans. Through a multi-centric collaboration, we identified three copy-number variant deletions (two de novo and one dominantly inherited in three generations), one de novo disrupting duplication, and nine de novo point mutations (three truncating, one canonical splice site, and five missense mutations) involving RORA in 16 individuals from 13 families with variable neurodevelopmental delay and intellectual disability (ID)-associated autistic features, cerebellar ataxia, and epilepsy. Consistent with the human and mouse data, disruption of the D. rerio ortholog, roraa, causes significant reduction in the size of the developing cerebellum. Systematic in vivo complementation studies showed that, whereas wild-type human RORA mRNA could complement the cerebellar pathology, missense variants had two distinct pathogenic mechanisms of either haploinsufficiency or a dominant toxic effect according to their localization in the ligand-binding or DNA-binding domains, respectively. This dichotomous direction of effect is likely relevant to the phenotype in humans: individuals with loss-of-function variants leading to haploinsufficiency show ID with autistic features, while individuals with de novo dominant toxic variants present with ID, ataxia, and cerebellar atrophy. Our combined genetic and functional data highlight the complex mutational landscape at the human RORA locus and suggest that dual mutational effects likely determine phenotypic outcome.
Keywords: Adolescent; Adult; Aged, 80 and over; Alleles; Animals; Autistic Disorder; Brain; Cerebellar Ataxia; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Female; Genes, Dominant; Genetic Complementation Test; Humans; Intellectual Disability; Larva; Magnetic Resonance Imaging; Male; Middle Aged; Mutation, Missense; Nuclear Receptor Subfamily 1, Group F, Member 1; Purkinje Cells; Syndrome; Zebrafish

ERCC4 variants identified in a cohort of patients with segmental progeroid syndromes. - Mori, Takayasu; Yousefzadeh, Matthew J; Faridounnia, Maryam; Chong, Jessica X; Hisama, Fuki M; Hudgins, Louanne; Mercado, Gabriela; Wade, Erin A; Barghouthy, Amira S; Lee, Lin; Martin, George M; Nickerson, Deborah A; et al. (Hum Mutat, 2018)
Pathogenic variants in genes, which encode DNA repair and damage response proteins, result in a number of genomic instability syndromes with features of accelerated aging. ERCC4 (XPF) encodes a protein that forms a complex with ERCC1 and is required for the 5' incision during nucleotide excision repair. ERCC4 is also FANCQ, illustrating a critical role in interstrand crosslink repair. Pathogenic variants in this gene cause xeroderma pigmentosum, XFE progeroid syndrome, Cockayne syndrome (CS), and Fanconi anemia. We performed massive parallel sequencing for 42 unsolved cases submitted to the International Registry of Werner Syndrome. Two cases, each carrying two novel heterozygous ERCC4 variants, were identified. The first case was a compound heterozygote for: c.2395C > T (p.Arg799Trp) and c.388+1164_792+795del (p.Gly130Aspfs*18). Further molecular and cellular studies indicated that the ERCC4 variants in this patient are responsible for a phenotype consistent with a variant of CS. The second case was heterozygous for two variants in cis: c.[1488A > T; c.2579C > A] (p.[Gln496His; Ala860Asp]). While the second case also had several phenotypic features of accelerated aging, we were unable to provide biological evidence supporting the pathogenic roles of the associated ERCC4 variants. Precise genetic causes and disease mechanism of the second case remains to be determined.
Keywords: Actins; Aged; Cockayne Syndrome; DNA Repair; DNA-Binding Proteins; Fanconi Anemia; Female; Genetic Predisposition to Disease; Humans; Lamin Type A; Male; Middle Aged; Pedigree; Xeroderma Pigmentosum

FOXP3 mutations causing early-onset insulin-requiring diabetes but without other features of immune dysregulation, polyendocrinopathy, enteropathy, X-linked syndrome. - Hwang, Jessica L; Park, Soo-Young; Ye, Honggang; Sanyoura, May; Pastore, Ashley N; Carmody, David; Del Gaudio, Daniela; Wilson, Janna F; Hanis, Craig L; Liu, Xiaoming; Atzmon, Gil; Glaser, Benjamin; et al. (Pediatr Diabetes, 2018)
Diabetes occurs in 1/90 000 to 1/160 000 births and when diagnosed under 6 months of age is very likely to have a primary genetic cause. FOXP3 encodes a transcription factor critical for T regulatory cell function and mutations are known to cause "immune dysregulation, polyendocrinopathy (including insulin-requiring diabetes), enteropathy, X-linked" (IPEX) syndrome. This condition is often fatal unless patients receive a bone-marrow transplant. Here we describe the phenotype of male neonates and infants who had insulin-requiring diabetes without other features of IPEX syndrome and were found to have mutations in FOXP3. Whole-exome or next generation sequencing of genes of interest was carried out in subjects with isolated neonatal diabetes without a known genetic cause. RT-PCR was carried out to investigate the effects on RNA splicing of a novel intronic splice-site variant. Four male subjects were found to have FOXP3 variants in the hemizygous state: p.Arg114Trp, p.Arg347His, p.Lys393Met, and c.1044+5G>A which was detected in 2 unrelated probands and in a brother diagnosed with diabetes at 2.1 years of age. Of these, p.Arg114Trp is likely a benign rare variant found in individuals of Ashkenazi Jewish ancestry and p.Arg347His has been previously described in patients with classic IPEX syndrome. The p.Lys393Met and c.1044+5G>A variants are novel to this study. RT-PCR studies of the c.1044+5G>A splice variant confirmed it affected RNA splicing by generating both a wild type and truncated transcript. We conclude that FOXP3 mutations can cause early-onset insulin-requiring diabetes with or without other features of IPEX syndrome.
Keywords: Diabetes Mellitus; Diabetes Mellitus, Type 1; Diarrhea; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immune System Diseases; Infant; Infant, Newborn; Male; Registries

Functional Dysregulation of CDC42 Causes Diverse Developmental Phenotypes. - Martinelli, Simone; Krumbach, Oliver H F; Pantaleoni, Francesca; Coppola, Simona; Amin, Ehsan; Pannone, Luca; Nouri, Kazem; Farina, Luciapia; Dvorsky, Radovan; Lepri, Francesca; Buchholzer, Marcel; Konopatzki, Raphael; et al. (Am J Hum Genet, 2018)
Exome sequencing has markedly enhanced the discovery of genes implicated in Mendelian disorders, particularly for individuals in whom a known clinical entity could not be assigned. This has led to the recognition that phenotypic heterogeneity resulting from allelic mutations occurs more commonly than previously appreciated. Here, we report that missense variants in CDC42, a gene encoding a small GTPase functioning as an intracellular signaling node, underlie a clinically heterogeneous group of phenotypes characterized by variable growth dysregulation, facial dysmorphism, and neurodevelopmental, immunological, and hematological anomalies, including a phenotype resembling Noonan syndrome, a developmental disorder caused by dysregulated RAS signaling. In silico, in vitro, and in vivo analyses demonstrate that mutations variably perturb CDC42 function by altering the switch between the active and inactive states of the GTPase and/or affecting CDC42 interaction with effectors, and differentially disturb cellular and developmental processes. These findings reveal the remarkably variable impact that dominantly acting CDC42 mutations have on cell function and development, creating challenges in syndrome definition, and exemplify the importance of functional profiling for syndrome recognition and delineation.

FUT2 Variants Confer Susceptibility to Familial Otitis Media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Frank, Daniel N; Ryan, Allen F; Giese, Arnaud P J; Bootpetch Roberts, Tori; Daly, Kathleen A; Steritz, Matthew J; Szeremeta, Wasyl; Pedro, Melquiadesa; Pine, Harold; Yarza, Talitha Karisse L; et al. (Am J Hum Genet, 2018)
Non-secretor status due to homozygosity for the common FUT2 variant c.461G>A (p.Trp154) is associated with either risk for autoimmune diseases or protection against viral diarrhea and HIV. We determined the role of FUT2 in otitis media susceptibility by obtaining DNA samples from 609 multi-ethnic families and simplex case subjects with otitis media. Exome and Sanger sequencing, linkage analysis, and Fisher exact and transmission disequilibrium tests (TDT) were performed. The common FUT2 c.604C>T (p.Arg202) variant co-segregates with otitis media in a Filipino pedigree (LOD = 4.0). Additionally, a rare variant, c.412C>T (p.Arg138Cys), is associated with recurrent/chronic otitis media in European-American children (p = 1.2 × 10) and US trios (TDT p = 0.01). The c.461G>A (p.Trp154) variant was also over-transmitted in US trios (TDT p = 0.01) and was associated with shifts in middle ear microbiota composition (PERMANOVA p < 10) and increased biodiversity. When all missense and nonsense variants identified in multi-ethnic US trios with CADD > 20 were combined, FUT2 variants were over-transmitted in trios (TDT p = 0.001). Fut2 is transiently upregulated in mouse middle ear after inoculation with non-typeable Haemophilus influenzae. Four FUT2 variants-namely p.Ala104Val, p.Arg138Cys, p.Trp154, and p.Arg202-reduced A antigen in mutant-transfected COS-7 cells, while the nonsense variants also reduced FUT2 protein levels. Common and rare FUT2 variants confer susceptibility to otitis media, likely by modifying the middle ear microbiome through regulation of A antigen levels in epithelial cells. Our families demonstrate marked intra-familial genetic heterogeneity, suggesting that multiple combinations of common and rare variants plus environmental factors influence the individual otitis media phenotype as a complex trait.

Genetic analysis of CHARGE syndrome identifies overlapping molecular biology. - Moccia, Amanda; Srivastava, Anshika; Skidmore, Jennifer M; Bernat, John A; Wheeler, Marsha; Chong, Jessica X; Nickerson, Deborah; Bamshad, Michael; Hefner, Margaret A; Martin, Donna M; Bielas, Stephanie L (Genet Med, 2018)
PURPOSE: CHARGE syndrome is an autosomal-dominant, multiple congenital anomaly condition characterized by vision and hearing loss, congenital heart disease, and malformations of craniofacial and other structures. Pathogenic variants in CHD7, encoding adenosine triphosphate-dependent chromodomain helicase DNA binding protein 7, are present in the majority of affected individuals. However, no causal variant can be found in 5-30% (depending on the cohort) of individuals with a clinical diagnosis of CHARGE syndrome. METHODS: We performed whole-exome sequencing (WES) on 28 families from which at least one individual presented with features highly suggestive of CHARGE syndrome. RESULTS: Pathogenic variants in CHD7 were present in 15 of 28 individuals (53.6%), whereas 4 (14.3%) individuals had pathogenic variants in other genes (RERE, KMT2D, EP300, or PUF60). A variant of uncertain clinical significance in KDM6A was identified in one (3.5%) individual. The remaining eight (28.6%) individuals were not found to have pathogenic variants by WES. CONCLUSION: These results demonstrate that the phenotypic features of CHARGE syndrome overlap with multiple other rare single-gene syndromes. Additionally, they implicate a shared molecular pathology that disrupts epigenetic regulation of multiple-organ development.
Keywords: Adolescent; Adult; Carrier Proteins; CHARGE Syndrome; Child; Child, Preschool; Cohort Studies; DNA Helicases; DNA-Binding Proteins; E1A-Associated p300 Protein; Epigenesis, Genetic; Female; Genetic Testing; Humans; Infant; Male; Mutation; Neoplasm Proteins; Phenotype; Repressor Proteins; RNA Splicing Factors

Genetic variants in components of the NALCN-UNC80-UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies). - Bramswig, Nuria C; Bertoli-Avella, Aida M; Albrecht, Beate; Al Aqeel, Aida I; Alhashem, Amal; Al-Sannaa, Nouriya; Bah, Maissa; Bröhl, Katharina; Depienne, Christel; Dorison, Nathalie; Doummar, Diane; Ehmke, Nadja; et al. (Hum Genet, 2018)
NALCN is a conserved cation channel, which conducts a permanent sodium leak current and regulates resting membrane potential and neuronal excitability. It is part of a large ion channel complex, the "NALCN channelosome", consisting of multiple proteins including UNC80 and UNC79. The predominant neuronal expression pattern and its function suggest an important role in neuronal function and disease. So far, biallelic NALCN and UNC80 variants have been described in a small number of individuals leading to infantile hypotonia, psychomotor retardation, and characteristic facies 1 (IHPRF1, OMIM 615419) and 2 (IHPRF2, OMIM 616801), respectively. Heterozygous de novo NALCN missense variants in the S5/S6 pore-forming segments lead to congenital contractures of the limbs and face, hypotonia, and developmental delay (CLIFAHDD, OMIM 616266) with some clinical overlap. In this study, we present detailed clinical information of 16 novel individuals with biallelic NALCN variants, 1 individual with a heterozygous de novo NALCN missense variant and an interesting clinical phenotype without contractures, and 12 individuals with biallelic UNC80 variants. We report for the first time a missense NALCN variant located in the predicted S6 pore-forming unit inherited in an autosomal-recessive manner leading to mild IHPRF1. We show evidence of clinical variability, especially among IHPRF1-affected individuals, and discuss differences between the IHPRF1- and IHPRF2 phenotypes. In summary, we provide a comprehensive overview of IHPRF1 and IHPRF2 phenotypes based on the largest cohort of individuals reported so far and provide additional insights into the clinical phenotypes of these neurodevelopmental diseases to help improve counseling of affected families.
Keywords: Adolescent; Adult; Carrier Proteins; Channelopathies; Child; Child, Preschool; Developmental Disabilities; Female; Genetic Markers; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Phenotype; Sodium Channels; Young Adult

A homozygous missense variant in VWA2, encoding an interactor of the Fraser-complex, in a patient with vesicoureteral reflux. - van der Ven, Amelie T; Kobbe, Birgit; Kohl, Stefan; Shril, Shirlee; Pogoda, Hans-Martin; Imhof, Thomas; Ityel, Hadas; Vivante, Asaf; Chen, Jing; Hwang, Daw-Yang; Connaughton, Dervla M; Mann, Nina; et al. (PLoS One, 2018)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause (40-50%) of chronic kidney disease (CKD) in children. About 40 monogenic causes of CAKUT have so far been discovered. To date less than 20% of CAKUT cases can be explained by mutations in these 40 genes. To identify additional monogenic causes of CAKUT, we performed whole exome sequencing (WES) and homozygosity mapping (HM) in a patient with CAKUT from Indian origin and consanguineous descent. We identified a homozygous missense mutation (c.1336C>T, p.Arg446Cys) in the gene Von Willebrand factor A domain containing 2 (VWA2). With immunohistochemistry studies on kidneys of newborn (P1) mice, we show that Vwa2 and Fraser extracellular matrix complex subunit 1 (Fras1) co-localize in the nephrogenic zone of the renal cortex. We identified a pronounced expression of Vwa2 in the basement membrane of the ureteric bud (UB) and derivatives of the metanephric mesenchyme (MM). By applying in vitro assays, we demonstrate that the Arg446Cys mutation decreases translocation of monomeric VWA2 protein and increases translocation of aggregated VWA2 protein into the extracellular space. This is potentially due to the additional, unpaired cysteine residue in the mutated protein that is used for intermolecular disulfide bond formation. VWA2 is a known, direct interactor of FRAS1 of the Fraser-Complex (FC). FC-encoding genes and interacting proteins have previously been implicated in the pathogenesis of syndromic and/or isolated CAKUT phenotypes in humans. VWA2 therefore constitutes a very strong candidate in the search for novel CAKUT-causing genes. Our results from in vitro experiments indicate a dose-dependent neomorphic effect of the Arg446Cys homozygous mutation in VWA2.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Animals; Animals, Newborn; Biomarkers, Tumor; Child; Consanguinity; Conserved Sequence; Exons; Extracellular Matrix Proteins; Fraser Syndrome; Gene Expression Regulation, Developmental; Homozygote; Humans; Male; Mice; Models, Animal; Models, Molecular; Mutation, Missense; Pedigree; Sequence Homology, Amino Acid; Urogenital Abnormalities; Urogenital System; Vesico-Ureteral Reflux

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hülya; Petty, Lauren E; Muzny, Donna M; Below, Jennifer E; Boerwinkle, Eric; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Boerwinkle, Eric; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.

Loss of Protocadherin-12 Leads to Diencephalic-Mesencephalic Junction Dysplasia Syndrome. - Guemez-Gamboa, Alicia; Çağlayan, Ahmet Okay; Stanley, Valentina; Gregor, Anne; Zaki, Maha S; Saleem, Sahar N; Musaev, Damir; McEvoy-Venneri, Jennifer; Belandres, Denice; Akizu, Naiara; Silhavy, Jennifer L; Schroth, Jana; et al. (Ann Neurol, 2018)
OBJECTIVE: To identify causes of the autosomal-recessive malformation, diencephalic-mesencephalic junction dysplasia (DMJD) syndrome. METHODS: Eight families with DMJD were studied by whole-exome or targeted sequencing, with detailed clinical and radiological characterization. Patient-derived induced pluripotent stem cells were derived into neural precursor and endothelial cells to study gene expression. RESULTS: All patients showed biallelic mutations in the nonclustered protocadherin-12 (PCDH12) gene. The characteristic clinical presentation included progressive microcephaly, craniofacial dysmorphism, psychomotor disability, epilepsy, and axial hypotonia with variable appendicular spasticity. Brain imaging showed brainstem malformations and with frequent thinned corpus callosum with punctate brain calcifications, reflecting expression of PCDH12 in neural and endothelial cells. These cells showed lack of PCDH12 expression and impaired neurite outgrowth. INTERPRETATION: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12-related conditions. Ann Neurol 2018;84:646-655.

Loss of tubulin deglutamylase CCP1 causes infantile-onset neurodegeneration. - Shashi, Vandana; Magiera, Maria M; Klein, Dennis; Zaki, Maha; Schoch, Kelly; Rudnik-Schöneborn, Sabine; Norman, Andrew; Lopes Abath Neto, Osorio; Dusl, Marina; Yuan, Xidi; Bartesaghi, Luca; De Marco, Patrizia; et al. (EMBO J, 2018)
A set of glutamylases and deglutamylases controls levels of tubulin polyglutamylation, a prominent post-translational modification of neuronal microtubules. Defective tubulin polyglutamylation was first linked to neurodegeneration in the () mouse, which lacks deglutamylase CCP1, displays massive cerebellar atrophy, and accumulates abnormally glutamylated tubulin in degenerating neurons. We found biallelic rare and damaging variants in the gene encoding CCP1 in 13 individuals with infantile-onset neurodegeneration and confirmed the absence of functional CCP1 along with dysregulated tubulin polyglutamylation. The human disease mainly affected the cerebellum, spinal motor neurons, and peripheral nerves. We also demonstrate previously unrecognized peripheral nerve and spinal motor neuron degeneration in mice, which thus recapitulated key features of the human disease. Our findings link human neurodegeneration to tubulin polyglutamylation, entailing this post-translational modification as a potential target for drug development for neurodegenerative disorders.

LTBP3 Pathogenic Variants Predispose Individuals to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Pinard, Amelie; Chen, Jiyuan; Lee, Kwanghyuk; Rigelsky, Christina; Zilberberg, Lior; Hostetler, Ellen M; Aldred, Micheala; Wallace, Stephanie E; Prakash, Siddharth K; Leal, Suzanne M; et al. (Am J Hum Genet, 2018)
The major diseases affecting the thoracic aorta are aneurysms and acute dissections, and pathogenic variants in 11 genes are confirmed to lead to heritable thoracic aortic disease. However, many families in which multiple members have thoracic aortic disease do not have alterations in the known aortopathy genes. Genes highly expressed in the aorta were assessed for rare variants in exome sequencing data from such families, and compound rare heterozygous variants (p.Pro45Argfs25 and p.Glu750) in LTBP3 were identified in affected members of one family. A homozygous variant (p.Asn678_Gly681delinsThrCys) that introduces an additional cysteine into an epidermal growth factor (EGF)-like domain in the corresponding protein, latent TGF-β binding protein (LTBP-3), was identified in a second family. Individuals with compound heterozygous or homozygous variants in these families have aneurysms and dissections of the thoracic aorta, as well as aneurysms of the abdominal aorta and other arteries, along with dental abnormalities and short stature. Heterozygous carriers of the p.Asn678_Gly681delinsThrCys variant have later onset of thoracic aortic disease, as well as dental abnormalities. In these families, LTBP3 variants segregated with thoracic aortic disease with a combined LOD score of 3.9. Additionally, heterozygous rare LTBP3 variants were found in individuals with early onset of acute aortic dissections, and some of these variants disrupted LTBP-3 levels or EGF-like domains. When compared to wild-type mice, Ltbp3 mice have enlarged aortic roots and ascending aortas. In summary, homozygous LTBP3 pathogenic variants predispose individuals to thoracic aortic aneurysms and dissections, along with the previously described skeletal and dental abnormalities.
Keywords: Adult; Aged, 80 and over; Aneurysm, Dissecting; Animals; Aortic Aneurysm, Thoracic; Blood Pressure; Female; Genetic Predisposition to Disease; Homozygote; Humans; Latent TGF-beta Binding Proteins; Male; Mice; Middle Aged; Mutation; Pedigree

MACF1 Mutations Encoding Highly Conserved Zinc-Binding Residues of the GAR Domain Cause Defects in Neuronal Migration and Axon Guidance. - Dobyns, William B; Aldinger, Kimberly A; Ishak, Gisele E; Mirzaa, Ghayda M; Timms, Andrew E; Grout, Megan E; Dremmen, Marjolein H G; Schot, Rachel; Vandervore, Laura; van Slegtenhorst, Marjon A; Wilke, Martina; Kasteleijn, Esmee; et al. (Am J Hum Genet, 2018)
To date, mutations in 15 actin- or microtubule-associated genes have been associated with the cortical malformation lissencephaly and variable brainstem hypoplasia. During a multicenter review, we recognized a rare lissencephaly variant with a complex brainstem malformation in three unrelated children. We searched our large brain-malformation databases and found another five children with this malformation (as well as one with a less severe variant), analyzed available whole-exome or -genome sequencing data, and tested ciliogenesis in two affected individuals. The brain malformation comprised posterior predominant lissencephaly and midline crossing defects consisting of absent anterior commissure and a striking W-shaped brainstem malformation caused by small or absent pontine crossing fibers. We discovered heterozygous de novo missense variants or an in-frame deletion involving highly conserved zinc-binding residues within the GAR domain of MACF1 in the first eight subjects. We studied cilium formation and found a higher proportion of mutant cells with short cilia than of control cells with short cilia. A ninth child had similar lissencephaly but only subtle brainstem dysplasia associated with a heterozygous de novo missense variant in the spectrin repeat domain of MACF1. Thus, we report variants of the microtubule-binding GAR domain of MACF1 as the cause of a distinctive and most likely pathognomonic brain malformation. A gain-of-function or dominant-negative mechanism appears likely given that many heterozygous mutations leading to protein truncation are included in the ExAC Browser. However, three de novo variants in MACF1 have been observed in large schizophrenia cohorts.

matchbox: An open-source tool for patient matching via the Matchmaker Exchange. - Arachchi, Harindra; Wojcik, Monica H; Weisburd, Benjamin; Jacobsen, Julius O B; Valkanas, Elise; Baxter, Samantha; Byrne, Alicia B; O'Donnell-Luria, Anne H; Haendel, Melissa; Smedley, Damian; MacArthur, Daniel G; Philippakis, Anthony A; et al. (Hum Mutat, 2018)
Rare disease investigators constantly face challenges in identifying additional cases to build evidence for gene-disease causality. The Matchmaker Exchange (MME) addresses this limitation by providing a mechanism for matching patients across genomic centers via a federated network. The MME has revolutionized searching for additional cases by making it possible to query across institutional boundaries, so that what was once a laborious and manual process of contacting researchers is now automated and computable. However, while the MME network is beginning to scale, the growth of additional nodes is limited by the lack of easy-to-use solutions that can be implemented by any rare disease database owner, even one without significant software engineering resources. Here, we describe matchbox, which is an open-source, platform-independent, portable bridge between any given rare disease genomic center and the MME network, which has already led to novel gene discoveries. We also describe how matchbox greatly reduces the barrier to participation by overcoming challenges for new databases to join the MME.

Mutations in LNPK, Encoding the Endoplasmic Reticulum Junction Stabilizer Lunapark, Cause a Recessive Neurodevelopmental Syndrome. - Breuss, Martin W; Nguyen, An; Song, Qiong; Nguyen, Thai; Stanley, Valentina; James, Kiely N; Musaev, Damir; Chai, Guoliang; Wirth, Sara A; Anzenberg, Paula; George, Renee D; Johansen, Anide; et al. (Am J Hum Genet, 2018)
The dynamic shape of the endoplasmic reticulum (ER) is a reflection of its wide variety of critical cell biological functions. Consequently, perturbation of ER-shaping proteins can cause a range of human phenotypes. Here, we describe three affected children (from two consanguineous families) who carry homozygous loss-of-function mutations in LNPK (previously known as KIAA1715); this gene encodes lunapark, which is proposed to serve as a curvature-stabilizing protein within tubular three-way junctions of the ER. All individuals presented with severe psychomotor delay, intellectual disability, hypotonia, epilepsy, and corpus callosum hypoplasia, and two of three showed mild cerebellar hypoplasia and atrophy. Consistent with a proposed role in neurodevelopmental disease, LNPK was expressed during brain development in humans and mice and was present in neurite-like processes in differentiating human neural progenitor cells. Affected cells showed the absence of full-length lunapark, aberrant ER structures, and increased luminal mass density. Together, our results implicate the ER junction stabilizer lunapark in establishing the corpus callosum.

Mutations in multiple components of the nuclear pore complex cause nephrotic syndrome. - Braun, Daniela A; Lovric, Svjetlana; Schapiro, David; Schneider, Ronen; Marquez, Jonathan; Asif, Maria; Hussain, Muhammad Sajid; Daga, Ankana; Widmeier, Eugen; Rao, Jia; Ashraf, Shazia; Tan, Weizhen; et al. (J Clin Invest, 2018)
Steroid-resistant nephrotic syndrome (SRNS) almost invariably progresses to end-stage renal disease. Although more than 50 monogenic causes of SRNS have been described, a large proportion of SRNS remains unexplained. Recently, it was discovered that mutations of NUP93 and NUP205, encoding 2 proteins of the inner ring subunit of the nuclear pore complex (NPC), cause SRNS. Here, we describe mutations in genes encoding 4 components of the outer rings of the NPC, namely NUP107, NUP85, NUP133, and NUP160, in 13 families with SRNS. Using coimmunoprecipitation experiments, we showed that certain pathogenic alleles weakened the interaction between neighboring NPC subunits. We demonstrated that morpholino knockdown of nup107, nup85, or nup133 in Xenopus disrupted glomerulogenesis. Re-expression of WT mRNA, but not of mRNA reflecting mutations from SRNS patients, mitigated this phenotype. We furthermore found that CRISPR/Cas9 knockout of NUP107, NUP85, or NUP133 in podocytes activated Cdc42, an important effector of SRNS pathogenesis. CRISPR/Cas9 knockout of nup107 or nup85 in zebrafish caused developmental anomalies and early lethality. In contrast, an in-frame mutation of nup107 did not affect survival, thus mimicking the allelic effects seen in humans. In conclusion, we discovered here that mutations in 4 genes encoding components of the outer ring subunits of the NPC cause SRNS and thereby provide further evidence that specific hypomorphic mutations in these essential genes cause a distinct, organ-specific phenotype.

Mutations in WDR4 as a new cause of Galloway-Mowat syndrome. - Braun, Daniela A; Shril, Shirlee; Sinha, Aditi; Schneider, Ronen; Tan, Weizhen; Ashraf, Shazia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Daga, Ankana; Warejko, Jillian K; et al. (Am J Med Genet A, 2018)
Galloway-Mowat syndrome (GAMOS) is a phenotypically heterogeneous disorder characterized by neurodevelopmental defects combined with renal-glomerular disease, manifesting with proteinuria. To identify additional monogenic disease causes, we here performed whole exome sequencing (WES), linkage analysis, and homozygosity mapping in three affected siblings of an Indian family with GAMOS. Applying established criteria for variant filtering, we identify a novel homozygous splice site mutation in the gene WDR4 as the likely disease-causing mutation in this family. In line with previous reports, we observe growth deficiency, microcephaly, developmental delay, and intellectual disability as phenotypic features resulting from WDR4 mutations. However, the newly identified allele additionally gives rise to proteinuria and nephrotic syndrome, a phenotype that was never reported in patients with WDR4 mutations. Our data thus expand the phenotypic spectrum of WDR4 mutations by demonstrating that, depending on the specific mutated allele, a renal phenotype may be present. This finding suggests that GAMOS may occupy a phenotypic spectrum with other microcephalic diseases. Furthermore, WDR4 is an additional example of a gene that encodes a tRNA modifying enzyme and gives rise to GAMOS, if mutated. Our findings thereby support the recent observation that, like neurons, podocytes of the renal glomerulus are particularly vulnerable to cellular defects resulting from altered tRNA modifications.

Nemaline myopathy and distal arthrogryposis associated with an autosomal recessive TNNT3 splice variant. - Sandaradura, Sarah A; Bournazos, Adam; Mallawaarachchi, Amali; Cummings, Beryl B; Waddell, Leigh B; Jones, Kristi J; Troedson, Christopher; Sudarsanam, Annapurna; Nash, Benjamin M; Peters, Gregory B; Algar, Elizabeth M; MacArthur, Daniel G; et al. (Hum Mutat, 2018)
A male neonate presented with severe weakness, hypotonia, contractures and congenital scoliosis. Skeletal muscle specimens showed marked atrophy and degeneration of fast fibers with striking nemaline rods and hypertrophy of slow fibers that were ultrastructurally normal. A neuromuscular gene panel identified a homozygous essential splice variant in TNNT3 (chr11:1956150G > A, NM_006757.3:c.681+1G > A). TNNT3 encodes skeletal troponin-T and is associated with autosomal dominant distal arthrogryposis. TNNT3 has not previously been associated with nemaline myopathy (NM), a rare congenital myopathy linked to defects in proteins associated with thin filament structure and regulation. cDNA studies confirmed pathogenic consequences of the splice variant, eliciting exon-skipping and intron retention events leading to a frameshift. Western blot showed deficiency of troponin-T protein with secondary loss of troponin-I . We establish a homozygous splice variant in TNNT3 as the likely cause of severe congenital NM with distal arthrogryposis, characterized by specific involvement of Type-2 fibers and deficiency of troponin-T .
Keywords: Arthrogryposis; Genes, Recessive; Humans; Infant; Infant, Newborn; Male; Myopathies, Nemaline; RNA Splice Sites; RNA Splicing; RNA, Messenger; Troponin T

A novel NAA10 variant with impaired acetyltransferase activity causes developmental delay, intellectual disability, and hypertrophic cardiomyopathy. - Støve, Svein Isungset; Blenski, Marina; Stray-Pedersen, Asbjørg; Wierenga, Klaas J; Jhangiani, Shalini N; Akdemir, Zeynep Coban; Crawford, David; McTiernan, Nina; Myklebust, Line M; Purcarin, Gabriela; McNall-Knapp, Rene; Wadley, Alexandrea; et al. (Eur J Hum Genet, 2018)
The NAA10-NAA15 complex (NatA) is an N-terminal acetyltransferase that catalyzes N-terminal acetylation of ~40% of all human proteins. N-terminal acetylation has several different roles in the cell, including altering protein stability and degradation, protein localization and protein-protein interactions. In recent years several X-linked NAA10 variants have been associated with genetic disorders. We have identified a previously undescribed NAA10 c.215T>C p.(Ile72Thr) variant in three boys from two unrelated families with a milder phenotypic spectrum in comparison to most of the previously described patients with NAA10 variants. These boys have development delay, intellectual disability, and cardiac abnormalities as overlapping phenotypes. Functional studies reveal that NAA10 Ile72Thr is destabilized, while binding to NAA15 most likely is intact. Surprisingly, the NatA activity of NAA10 Ile72Thr appears normal while its monomeric activity is decreased. This study further broadens the phenotypic spectrum associated with NAA10 deficiency, and adds to the evidence that genotype-phenotype correlations for NAA10 variants are much more complex than initially anticipated.
Keywords: Cardiomyopathy, Hypertrophic; Child, Preschool; Developmental Disabilities; Enzyme Stability; HeLa Cells; Humans; Infant; Intellectual Disability; Male; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Phenotype; Protein Binding; Syndrome

Novel STAT1 Gain-of-Function Mutation Presenting as Combined Immunodeficiency. - Hartono, Stella P; Vargas-Hernandez, Alexander; Ponsford, Mark J; Chinn, Ivan K; Jolles, Stephen; Wilson, Keith; Forbes, Lisa R (J Clin Immunol, 2018)

Peripheral Cone Dystrophy: Expanded Clinical Spectrum, Multimodal and Ultrawide-Field Imaging, and Genomic Analysis. - Sisk, Robert A; Hufnagel, Robert B; Laham, Ailee; Wohler, Elizabeth S; Sobreira, Nara; Ahmed, Zubair M (J Ophthalmol, 2018)
Purpose: To present new clinical features, multimodal and ultrawide-field imaging characteristics of peripheral cone dystrophy (PCD), and results of laboratory and genetic investigation to decipher the etiology. Methods: Retrospective observational case-series. Results: Three patients with PCD presented with bilateral paracentral scotomas and a mean visual acuity of 20/25. All exhibited confluent macular hyperautofluorescence with a central bull's eye lesion. Spectral-domain optical coherence tomography revealed loss of outer retinal elements, particularly the inner segment ellipsoid band and external limiting membrane, within the area of macular hyperautofluorescence. This area corresponded with a lightened fundus appearance and variable retinal pigment epithelium (RPE) abnormalities. Full field and multifocal electroretinography distinguished PCD from other photoreceptor dystrophies. Ultrawide-field imaging revealed irregular peripheral retinal lesions in a distribution greater nasally than temporally and not contiguous with the macular lesion. Functional and anatomic testing remained stable over a mean follow-up of 3 years. Laboratory investigation for causes of uveitis was negative. Whole exome sequencing identified rare variants in genes associated with macular or cone dystrophy or degeneration. Conclusions: In contrast to the original description, the funduscopic and fluorescein angiographic appearance of PCD is abnormal, although the defects are subtle. Peripheral lesions may be observed in some patients. Bilateral, symmetric, macular hyperautofluorescence associated with outer retinal atrophy that spares the fovea is a characteristic of PCD. Pathogenic variants in the same gene were not shared across the cohort, suggesting genetic heterogeneity. Further evaluation is warranted.

Perturbations of BMP/TGF-β and VEGF/VEGFR signalling pathways in non-syndromic sporadic brain arteriovenous malformations (BAVM). - Wang, Kun; Zhao, Sen; Liu, Bowen; Zhang, Qianqian; Li, Yaqi; Liu, Jiaqi; Shen, Yan; Ding, Xinghuan; Lin, Jiachen; Wu, Yong; Yan, Zihui; Chen, Jia; et al. (J Med Genet, 2018)
BACKGROUND: Brain arteriovenous malformations (BAVM) represent a congenital anomaly of the cerebral vessels with a prevalence of 10-18/100 000. BAVM is the leading aetiology of intracranial haemorrhage in children. Our objective was to identify gene variants potentially contributing to disease and to better define the molecular aetiology underlying non-syndromic sporadic BAVM. METHODS: We performed whole-exome trio sequencing of 100 unrelated families with a clinically uniform BAVM phenotype. Pathogenic variants were then studied in vivo using a transgenic zebrafish model. RESULTS: We identified four pathogenic heterozygous variants in four patients, including one in the established BAVM-related gene, , and three damaging variants in novel candidate genes: , and , which we then functionally validated in zebrafish. In addition, eight likely pathogenic heterozygous variants (, and ) were identified in eight patients, and 16 patients carried one or more variants of uncertain significance. Potential oligogenic inheritance ( with , with and with ) was identified in three patients. Regulation of sma- and mad-related proteins (SMADs) (involved in bone morphogenic protein (BMP)/transforming growth factor beta (TGF-β) signalling) and vascular endothelial growth factor (VEGF)/vascular endotheliual growth factor recepter 2 (VEGFR2) binding and activity (affecting the VEGF signalling pathway) were the most significantly affected biological process involved in the pathogenesis of BAVM. CONCLUSIONS: Our study highlights the specific role of BMP/TGF-β and VEGF/VEGFR signalling in the aetiology of BAVM and the efficiency of intensive parallel sequencing in the challenging context of genetically heterogeneous paradigm.

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, LaDonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

The phenotypic spectrum of Xia-Gibbs syndrome. - Jiang, Yunyun; Wangler, Michael F; McGuire, Amy L; Lupski, James R; Posey, Jennifer E; Khayat, Michael M; Murdock, David R; Sanchez-Pulido, Luis; Ponting, Chris P; Xia, Fan; Hunter, Jill V; Meng, Qingchang; et al. (Am J Med Genet A, 2018)
Xia-Gibbs syndrome (XGS: OMIM # 615829) results from de novo truncating mutations within the AT-Hook DNA Binding Motif Containing 1 gene (AHDC1). To further define the phenotypic and molecular spectrum of this disorder, we established an XGS Registry and recruited patients from a worldwide pool of approximately 60 probands. Additional de novo truncating mutations were observed among 25 individuals, extending both the known number of mutation sites and the range of positions within the coding region that were sensitive to alteration. Detailed phenotypic examination of 20 of these patients via clinical records review and data collection from additional surveys showed a wider age range than previously described. Data from developmental milestones showed evidence for delayed speech and that males were more severely affected. Neuroimaging from six available patients showed an associated thinning of the corpus callosum and posterior fossa cysts. An increased risk of both scoliosis and seizures relative to the population burden was also observed. Data from a modified autism screening tool revealed that XGS shares significant overlap with autism spectrum disorders. These details of the phenotypic heterogeneity of XGS implicate specific genotype/phenotype correlations and suggest potential clinical management guidelines.

Severe neurocognitive and growth disorders due to variation in THOC2, an essential component of nuclear mRNA export machinery. - Kumar, Raman; Gardner, Alison; Homan, Claire C; Douglas, Evelyn; Mefford, Heather; Wieczorek, Dagmar; Lüdecke, Hermann-Josef; Stark, Zornitza; Sadedin, Simon; Nowak, Catherine Bearce; Douglas, Jessica; Parsons, Gretchen; et al. (Hum Mutat, 2018)
Highly conserved TREX-mediated mRNA export is emerging as a key pathway in neuronal development and differentiation. TREX subunit variants cause neurodevelopmental disorders (NDDs) by interfering with mRNA export from the cell nucleus to the cytoplasm. Previously we implicated four missense variants in the X-linked THOC2 gene in intellectual disability (ID). We now report an additional six affected individuals from five unrelated families with two de novo and three maternally inherited pathogenic or likely pathogenic variants in THOC2 extending the genotypic and phenotypic spectrum. These comprise three rare missense THOC2 variants that affect evolutionarily conserved amino acid residues and reduce protein stability and two with canonical splice-site THOC2 variants that result in C-terminally truncated THOC2 proteins. We present detailed clinical assessment and functional studies on a de novo variant in a female with an epileptic encephalopathy and discuss an additional four families with rare variants in THOC2 with supportive evidence for pathogenicity. Severe neurocognitive features, including movement and seizure disorders, were observed in this cohort. Taken together our data show that even subtle alterations to the canonical molecular pathways such as mRNA export, otherwise essential for cellular life, can be compatible with life, but lead to NDDs in humans.

Somatic SLC35A2 variants in the brain are associated with intractable neocortical epilepsy. - Winawer, Melodie R; Griffin, Nicole G; Samanamud, Jorge; Baugh, Evan H; Rathakrishnan, Dinesh; Ramalingam, Senthilmurugan; Zagzag, David; Schevon, Catherine A; Dugan, Patricia; Hegde, Manu; Sheth, Sameer A; McKhann, Guy M; et al. (Ann Neurol, 2018)
OBJECTIVE: Somatic variants are a recognized cause of epilepsy-associated focal malformations of cortical development (MCD). We hypothesized that somatic variants may underlie a wider range of focal epilepsy, including nonlesional focal epilepsy (NLFE). Through genetic analysis of brain tissue, we evaluated the role of somatic variation in focal epilepsy with and without MCD. METHODS: We identified somatic variants through high-depth exome and ultra-high-depth candidate gene sequencing of DNA from epilepsy surgery specimens and leukocytes from 18 individuals with NLFE and 38 with focal MCD. RESULTS: We observed somatic variants in 5 cases in SLC35A2, a gene associated with glycosylation defects and rare X-linked epileptic encephalopathies. Nonsynonymous variants in SLC35A2 were detected in resected brain, and absent from leukocytes, in 3 of 18 individuals (17%) with NLFE, 1 female and 2 males, with variant allele frequencies (VAFs) in brain-derived DNA of 2 to 14%. Pathologic evaluation revealed focal cortical dysplasia type Ia (FCD1a) in 2 of the 3 NLFE cases. In the MCD cohort, nonsynonymous variants in SCL35A2 were detected in the brains of 2 males with intractable epilepsy, developmental delay, and magnetic resonance imaging suggesting FCD, with VAFs of 19 to 53%; Evidence for FCD was not observed in either brain tissue specimen. INTERPRETATION: We report somatic variants in SLC35A2 as an explanation for a substantial fraction of NLFE, a largely unexplained condition, as well as focal MCD, previously shown to result from somatic mutation but until now only in PI3K-AKT-mTOR pathway genes. Collectively, our findings suggest a larger role than previously recognized for glycosylation defects in the intractable epilepsies. Ann Neurol 2018.

SYT1-associated neurodevelopmental disorder: a case series. - Baker, Kate; Gordon, Sarah L; Melland, Holly; Bumbak, Fabian; Scott, Daniel J; Jiang, Tess J; Owen, David; Turner, Bradley J; Boyd, Stewart G; Rossi, Mari; Al-Raqad, Mohammed; Elpeleg, Orly; et al. (Brain, 2018)
Synaptotagmin 1 (SYT1) is a critical mediator of fast, synchronous, calcium-dependent neurotransmitter release and also modulates synaptic vesicle endocytosis. This paper describes 11 patients with de novo heterozygous missense mutations in SYT1. All mutations alter highly conserved residues, and cluster in two regions of the SYT1 C2B domain at positions Met303 (M303K), Asp304 (D304G), Asp366 (D366E), Ile368 (I368T) and Asn371 (N371K). Phenotypic features include infantile hypotonia, congenital ophthalmic abnormalities, childhood-onset hyperkinetic movement disorders, motor stereotypies, and developmental delay varying in severity from moderate to profound. Behavioural characteristics include sleep disturbance and episodic agitation. Absence of epileptic seizures and normal orbitofrontal head circumference are important negative features. Structural MRI is unremarkable but EEG disturbance is universal, characterized by intermittent low frequency high amplitude oscillations. The functional impact of these five de novo SYT1 mutations has been assessed by expressing rat SYT1 protein containing the equivalent human variants in wild-type mouse primary hippocampal cultures. All mutant forms of SYT1 were expressed at levels approximately equal to endogenous wild-type protein, and correctly localized to nerve terminals at rest, except for SYT1M303K, which was expressed at a lower level and failed to localize at nerve terminals. Following stimulation, SYT1I368T and SYT1N371K relocalized to nerve terminals at least as efficiently as wild-type SYT1. However, SYT1D304G and SYT1D366E failed to relocalize to nerve terminals following stimulation, indicative of impairments in endocytic retrieval and trafficking of SYT1. In addition, the presence of SYT1 variants at nerve terminals induced a slowing of exocytic rate following sustained action potential stimulation. The extent of disturbance to synaptic vesicle kinetics is mirrored by the severity of the affected individuals' phenotypes, suggesting that the efficiency of SYT1-mediated neurotransmitter release is critical to cognitive development. In summary, de novo dominant SYT1 missense mutations are associated with a recognizable neurodevelopmental syndrome, and further cases can now be diagnosed based on clinical features, electrophysiological signature and mutation characteristics. Variation in phenotype severity may reflect mutation-specific impact on the diverse physiological functions of SYT1.

Truncating Variants in NAA15 Are Associated with Variable Levels of Intellectual Disability, Autism Spectrum Disorder, and Congenital Anomalies. - Cheng, Hanyin; Dharmadhikari, Avinash V; Varland, Sylvia; Ma, Ning; Domingo, Deepti; Kleyner, Robert; Rope, Alan F; Yoon, Margaret; Stray-Pedersen, Asbjørg; Posey, Jennifer E; Crews, Sarah R; Eldomery, Mohammad K; et al. (Am J Hum Genet, 2018)
N-alpha-acetylation is a common co-translational protein modification that is essential for normal cell function in humans. We previously identified the genetic basis of an X-linked infantile lethal Mendelian disorder involving a c.109T>C (p.Ser37Pro) missense variant in NAA10, which encodes the catalytic subunit of the N-terminal acetyltransferase A (NatA) complex. The auxiliary subunit of the NatA complex, NAA15, is the dimeric binding partner for NAA10. Through a genotype-first approach with whole-exome or genome sequencing (WES/WGS) and targeted sequencing analysis, we identified and phenotypically characterized 38 individuals from 33 unrelated families with 25 different de novo or inherited, dominantly acting likely gene disrupting (LGD) variants in NAA15. Clinical features of affected individuals with LGD variants in NAA15 include variable levels of intellectual disability, delayed speech and motor milestones, and autism spectrum disorder. Additionally, mild craniofacial dysmorphology, congenital cardiac anomalies, and seizures are present in some subjects. RNA analysis in cell lines from two individuals showed degradation of the transcripts with LGD variants, probably as a result of nonsense-mediated decay. Functional assays in yeast confirmed a deleterious effect for two of the LGD variants in NAA15. Further supporting a mechanism of haploinsufficiency, individuals with copy-number variant (CNV) deletions involving NAA15 and surrounding genes can present with mild intellectual disability, mild dysmorphic features, motor delays, and decreased growth. We propose that defects in NatA-mediated N-terminal acetylation (NTA) lead to variable levels of neurodevelopmental disorders in humans, supporting the importance of the NatA complex in normal human development.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Autism Spectrum Disorder; Cell Line; Child; Exons; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Genetic Variation; Humans; Intellectual Disability; Male; Middle Aged; Mutation; N-Terminal Acetyltransferase A; N-Terminal Acetyltransferase E; Pedigree; Phenotype; RNA, Messenger; Saccharomyces cerevisiae

Whole exome sequencing analysis in severe chronic obstructive pulmonary disease. - Qiao, Dandi; Ameli, Asher; Prokopenko, Dmitry; Chen, Han; Kho, Alvin T; Parker, Margaret M; Morrow, Jarrett; Hobbs, Brian D; Liu, Yanhong; Beaty, Terri H; Crapo, James D; Barnes, Kathleen C; et al. (Hum Mol Genet, 2018)
Chronic obstructive pulmonary disease (COPD), one of the leading causes of death worldwide, is substantially influenced by genetic factors. Alpha-1 antitrypsin deficiency demonstrates that rare coding variants of large effect can influence COPD susceptibility. To identify additional rare coding variants in patients with severe COPD, we conducted whole exome sequencing analysis in 2543 subjects from two family-based studies (Boston Early-Onset COPD Study and International COPD Genetics Network) and one case-control study (COPDGene). Applying a gene-based segregation test in the family-based data, we identified significant segregation of rare loss of function variants in TBC1D10A and RFPL1 (P-value < 2x10-6), but were unable to find similar variants in the case-control study. In single-variant, gene-based and pathway association analyses, we were unable to find significant findings that replicated or were significant in meta-analysis. However, we found that the top results in the two datasets were in proximity to each other in the protein-protein interaction network (P-value = 0.014), suggesting enrichment of these results for similar biological processes. A network of these association results and their neighbors was significantly enriched in the transforming growth factor beta-receptor binding and cilia-related pathways. Finally, in a more detailed examination of candidate genes, we identified individuals with putative high-risk variants, including patients harboring homozygous mutations in genes associated with cutis laxa and Niemann-Pick Disease Type C. Our results likely reflect heterogeneity of genetic risk for COPD along with limitations of statistical power and functional annotation, and highlight the potential of network analysis to gain insight into genetic association studies.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; DNA Mutational Analysis; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Whole Exome Sequencing; Young Adult

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing of Patients with Steroid-Resistant Nephrotic Syndrome. - Warejko, Jillian K; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. RESULTS: In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. , , , and were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. CONCLUSIONS: Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract. - van der Ven, Amelie T; Connaughton, Dervla M; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A; Schmidt, Johanna Magdalena; Schapiro, David; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. METHODS: We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. RESULTS: In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). CONCLUSIONS: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.

WNT Signaling Perturbations Underlie the Genetic Heterogeneity of Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Coban-Akdemir, Zeynep; Bayram, Yavuz; Bahrambeigi, Vahid; Hoischen, Alexander; van Bon, Bregje W M; Gezdirici, Alper; Gulec, Elif Yilmaz; Ramond, Francis; Touraine, Renaud; Thevenon, Julien; et al. (Am J Hum Genet, 2018)
Locus heterogeneity characterizes a variety of skeletal dysplasias often due to interacting or overlapping signaling pathways. Robinow syndrome is a skeletal disorder historically refractory to molecular diagnosis, potentially stemming from substantial genetic heterogeneity. All current known pathogenic variants reside in genes within the noncanonical Wnt signaling pathway including ROR2, WNT5A, and more recently, DVL1 and DVL3. However, ∼70% of autosomal-dominant Robinow syndrome cases remain molecularly unsolved. To investigate this missing heritability, we recruited 21 families with at least one family member clinically diagnosed with Robinow or Robinow-like phenotypes and performed genetic and genomic studies. In total, four families with variants in FZD2 were identified as well as three individuals from two families with biallelic variants in NXN that co-segregate with the phenotype. Importantly, both FZD2 and NXN are relevant protein partners in the WNT5A interactome, supporting their role in skeletal development. In addition to confirming that clustered -1 frameshifting variants in DVL1 and DVL3 are the main contributors to dominant Robinow syndrome, we also found likely pathogenic variants in candidate genes GPC4 and RAC3, both linked to the Wnt signaling pathway. These data support an initial hypothesis that Robinow syndrome results from perturbation of the Wnt/PCP pathway, suggest specific relevant domains of the proteins involved, and reveal key contributors in this signaling cascade during human embryonic development. Contrary to the view that non-allelic genetic heterogeneity hampers gene discovery, this study demonstrates the utility of rare disease genomic studies to parse gene function in human developmental pathways.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Chromosome Segregation; Craniofacial Abnormalities; Diagnosis, Differential; Dwarfism; Female; Genes, Dominant; Genetic Association Studies; Genetic Heterogeneity; Humans; Limb Deformities, Congenital; Male; Middle Aged; Mutation, Missense; Phenotype; Urogenital Abnormalities; Wnt Signaling Pathway

Activation of a cryptic splice site in the mitochondrial elongation factor GFM1 causes combined OXPHOS deficiency. - Simon, Mariella T; Ng, Bobby G; Friederich, Marisa W; Wang, Raymond Y; Boyer, Monica; Kircher, Martin; Collard, Renata; Buckingham, Kati J; Chang, Richard; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; et al. (Mitochondrion, 2017)
We report the clinical, biochemical, and molecular findings in two brothers with encephalopathy and multi-systemic disease. Abnormal transferrin glycoforms were suggestive of a type I congenital disorder of glycosylation (CDG). While exome sequencing was negative for CDG related candidate genes, the testing revealed compound heterozygous mutations in the mitochondrial elongation factor G gene (GFM1). One of the mutations had been reported previously while the second, novel variant was found deep in intron 6, activating a cryptic splice site. Functional studies demonstrated decreased GFM1 protein levels, suggested disrupted assembly of mitochondrial complexes III and V and decreased activities of mitochondrial complexes I and IV, all indicating combined OXPHOS deficiency.
Keywords: Child; Child, Preschool; Congenital Abnormalities; Gene Expression; Humans; Infant; Infant, Newborn; Male; Mitochondrial Proteins; Oxidative Phosphorylation; Peptide Elongation Factor G; RNA Splice Sites

Advillin acts upstream of phospholipase C ϵ1 in steroid-resistant nephrotic syndrome. - Rao, Jia; Ashraf, Shazia; Tan, Weizhen; van der Ven, Amelie T; Gee, Heon Yung; Braun, Daniela A; Fehér, Krisztina; George, Sudeep P; Esmaeilniakooshkghazi, Amin; Choi, Won-Il; Jobst-Schwan, Tilman; Schneider, Ronen; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) is a frequent cause of chronic kidney disease. Here, we identified recessive mutations in the gene encoding the actin-binding protein advillin (AVIL) in 3 unrelated families with SRNS. While all AVIL mutations resulted in a marked loss of its actin-bundling ability, truncation of AVIL also disrupted colocalization with F-actin, thereby leading to impaired actin binding and severing. Additionally, AVIL colocalized and interacted with the phospholipase enzyme PLCE1 and with the ARP2/3 actin-modulating complex. Knockdown of AVIL in human podocytes reduced actin stress fibers at the cell periphery, prevented recruitment of PLCE1 to the ARP3-rich lamellipodia, blocked EGF-induced generation of diacylglycerol (DAG) by PLCE1, and attenuated the podocyte migration rate (PMR). These effects were reversed by overexpression of WT AVIL but not by overexpression of any of the 3 patient-derived AVIL mutants. The PMR was increased by overexpression of WT Avil or PLCE1, or by EGF stimulation; however, this increased PMR was ameliorated by inhibition of the ARP2/3 complex, indicating that ARP-dependent lamellipodia formation occurs downstream of AVIL and PLCE1 function. Together, these results delineate a comprehensive pathogenic axis of SRNS that integrates loss of AVIL function with alterations in the action of PLCE1, an established SRNS protein.
Keywords: Actin-Related Protein 2-3 Complex; Cell Movement; Diglycerides; Female; Humans; Male; Microfilament Proteins; Mutation; Nephrotic Syndrome; Phosphoinositide Phospholipase C; Podocytes; Pseudopodia

Asprosin is a centrally acting orexigenic hormone. - Duerrschmid, Clemens; He, Yanlin; Wang, Chunmei; Li, Chia; Bournat, Juan C; Romere, Chase; Saha, Pradip K; Lee, Mark E; Phillips, Kevin J; Jain, Mahim; Jia, Peilin; Zhao, Zhongming; et al. (Nat Med, 2017)
Asprosin is a recently discovered fasting-induced hormone that promotes hepatic glucose production. Here we demonstrate that asprosin in the circulation crosses the blood-brain barrier and directly activates orexigenic AgRP neurons via a cAMP-dependent pathway. This signaling results in inhibition of downstream anorexigenic proopiomelanocortin (POMC)-positive neurons in a GABA-dependent manner, which then leads to appetite stimulation and a drive to accumulate adiposity and body weight. In humans, a genetic deficiency in asprosin causes a syndrome characterized by low appetite and extreme leanness; this is phenocopied by mice carrying similar mutations and can be fully rescued by asprosin. Furthermore, we found that obese humans and mice had pathologically elevated concentrations of circulating asprosin, and neutralization of asprosin in the blood with a monoclonal antibody reduced appetite and body weight in obese mice, in addition to improving their glycemic profile. Thus, in addition to performing a glucogenic function, asprosin is a centrally acting orexigenic hormone that is a potential therapeutic target in the treatment of both obesity and diabetes.
Keywords: Adolescent; Adult; Animals; Appetite Depressants; Appetite Regulation; Female; Humans; Hypothalamus; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microfilament Proteins; Neurons; Peptide Fragments; Peptide Hormones; Rats; Signal Transduction; Young Adult

Biallelic mutations in IRF8 impair human NK cell maturation and function. - Mace, Emily M; Bigley, Venetia; Gunesch, Justin T; Chinn, Ivan K; Angelo, Laura S; Care, Matthew A; Maisuria, Sheetal; Keller, Michael D; Togi, Sumihito; Watkin, Levi B; LaRosa, David F; Jhangiani, Shalini N; et al. (J Clin Invest, 2017)
Human NK cell deficiencies are rare yet result in severe and often fatal disease, particularly as a result of viral susceptibility. NK cells develop from hematopoietic stem cells, and few monogenic errors that specifically interrupt NK cell development have been reported. Here we have described biallelic mutations in IRF8, which encodes an interferon regulatory factor, as a cause of familial NK cell deficiency that results in fatal and severe viral disease. Compound heterozygous or homozygous mutations in IRF8 in 3 unrelated families resulted in a paucity of mature CD56dim NK cells and an increase in the frequency of the immature CD56bright NK cells, and this impairment in terminal maturation was also observed in Irf8-/-, but not Irf8+/-, mice. We then determined that impaired maturation was NK cell intrinsic, and gene expression analysis of human NK cell developmental subsets showed that multiple genes were dysregulated by IRF8 mutation. The phenotype was accompanied by deficient NK cell function and was stable over time. Together, these data indicate that human NK cells require IRF8 for development and functional maturation and that dysregulation of this function results in severe human disease, thereby emphasizing a critical role for NK cells in human antiviral defense.
Keywords: Alleles; Animals; CD56 Antigen; Female; Gene Expression Regulation; Genetic Predisposition to Disease; Humans; Interferon Regulatory Factors; Killer Cells, Natural; Male; Mice; Mice, Knockout; Mutation; Virus Diseases

Biallelic mutations in the 3' exonuclease TOE1 cause pontocerebellar hypoplasia and uncover a role in snRNA processing. - Lardelli, Rea M; Schaffer, Ashleigh E; Eggens, Veerle R C; Zaki, Maha S; Grainger, Stephanie; Sathe, Shashank; Van Nostrand, Eric L; Schlachetzki, Zinayida; Rosti, Basak; Akizu, Naiara; Scott, Eric; Silhavy, Jennifer L; et al. (Nat Genet, 2017)
Deadenylases are best known for degrading the poly(A) tail during mRNA decay. The deadenylase family has expanded throughout evolution and, in mammals, consists of 12 Mg-dependent 3'-end RNases with substrate specificity that is mostly unknown. Pontocerebellar hypoplasia type 7 (PCH7) is a unique recessive syndrome characterized by neurodegeneration and ambiguous genitalia. We studied 12 human families with PCH7, uncovering biallelic, loss-of-function mutations in TOE1, which encodes an unconventional deadenylase. toe1-morphant zebrafish displayed midbrain and hindbrain degeneration, modeling PCH-like structural defects in vivo. Surprisingly, we found that TOE1 associated with small nuclear RNAs (snRNAs) incompletely processed spliceosomal. These pre-snRNAs contained 3' genome-encoded tails often followed by post-transcriptionally added adenosines. Human cells with reduced levels of TOE1 accumulated 3'-end-extended pre-snRNAs, and the immunoisolated TOE1 complex was sufficient for 3'-end maturation of snRNAs. Our findings identify the cause of a neurodegenerative syndrome linked to snRNA maturation and uncover a key factor involved in the processing of snRNA 3' ends.
Keywords: Alleles; Animals; Cerebellar Diseases; Exonucleases; Female; Humans; Male; Mice; Mutation; Neurodegenerative Diseases; Nuclear Proteins; RNA, Messenger; RNA, Small Nuclear; Spliceosomes; Zebrafish

Clinically severe CACNA1A alleles affect synaptic function and neurodegeneration differentially. - Luo, Xi; Rosenfeld, Jill A; Yamamoto, Shinya; Harel, Tamar; Zuo, Zhongyuan; Hall, Melissa; Wierenga, Klaas J; Pastore, Matthew T; Bartholomew, Dennis; Delgado, Mauricio R; Rotenberg, Joshua; Lewis, Richard Alan; et al. (PLoS Genet, 2017)
Dominant mutations in CACNA1A, encoding the α-1A subunit of the neuronal P/Q type voltage-dependent Ca2+ channel, can cause diverse neurological phenotypes. Rare cases of markedly severe early onset developmental delay and congenital ataxia can be due to de novo CACNA1A missense alleles, with variants affecting the S4 transmembrane segments of the channel, some of which are reported to be loss-of-function. Exome sequencing in five individuals with severe early onset ataxia identified one novel variant (p.R1673P), in a girl with global developmental delay and progressive cerebellar atrophy, and a recurrent, de novo p.R1664Q variant, in four individuals with global developmental delay, hypotonia, and ophthalmologic abnormalities. Given the severity of these phenotypes we explored their functional impact in Drosophila. We previously generated null and partial loss-of-function alleles of cac, the homolog of CACNA1A in Drosophila. Here, we created transgenic wild type and mutant genomic rescue constructs with the two noted conserved point mutations. The p.R1673P mutant failed to rescue cac lethality, displayed a gain-of-function phenotype in electroretinograms (ERG) recorded from mutant clones, and evolved a neurodegenerative phenotype in aging flies, based on ERGs and transmission electron microscopy. In contrast, the p.R1664Q variant exhibited loss of function and failed to develop a neurodegenerative phenotype. Hence, the novel R1673P allele produces neurodegenerative phenotypes in flies and human, likely due to a toxic gain of function.
Keywords: Alleles; Animals; Animals, Genetically Modified; Calcium Channels; Cerebellar Ataxia; Child; Child, Preschool; Drosophila melanogaster; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Microscopy, Electron, Transmission; Mutation, Missense; Neurodegenerative Diseases; Neuroimaging; Phenotype; Point Mutation

Congenital heart defects and left ventricular non-compaction in males with loss-of-function variants in NONO. - Scott, Daryl A; Hernandez-Garcia, Andres; Azamian, Mahshid S; Jordan, Valerie K; Kim, Bum Jun; Starkovich, Molly; Zhang, Jinglan; Wong, Lee-Jun; Darilek, Sandra A; Breman, Amy M; Yang, Yaping; Lupski, James R; et al. (J Med Genet, 2017)
BACKGROUND: The non-POU domain containing octamer-binding gene (NONO) is located on chromosome Xq13.1 and encodes a member of a small family of RNA-binding and DNA-binding proteins that perform a variety of tasks involved in RNA synthesis, transcriptional regulation and DNA repair. Loss-of-function variants in NONO have been described as a cause of intellectual disability in males but have not been described in association with congenital heart defects or cardiomyopathy. In this article, we seek to further define the phenotypic consequences of NONO depletion in human subjects. METHODS: We searched a clinical database of over 6000 individuals referred for exome sequencing and over 60 000 individuals referred for CNV analysis. RESULTS: We identified two males with atrial and ventricular septal defects, left ventricular non-compaction (LVNC), developmental delay and intellectual disability, who harboured de novo, loss-of-function variants in NONO. We also identified a male infant with developmental delay, congenital brain anomalies and severe LVNC requiring cardiac transplantation, who inherited a single-gene deletion of NONO from his asymptomatic mother. CONCLUSIONS: We conclude that in addition to global developmental delay and intellectual disability, males with loss-of-function variants in NONO may also be predisposed to developing congenital heart defects and LVNC with the penetrance of these cardiac-related problems being influenced by genetic, epigenetic, environmental or stochastic factors. Brain imaging of males with NONO deficiency may reveal structural defects with abnormalities of the corpus callosum being the most common. Although dysmorphic features vary between affected individuals, relative macrocephaly is a common feature.
Keywords: Child; Child, Preschool; Developmental Disabilities; DNA-Binding Proteins; Exome; Heart Defects, Congenital; Heart Ventricles; Humans; Infant; Male; Nuclear Matrix-Associated Proteins; Octamer Transcription Factors; RNA-Binding Proteins

Contribution of rare inherited and de novo variants in 2,871 congenital heart disease probands. - Jin, Sheng Chih; Homsy, Jason; Zaidi, Samir; Lu, Qiongshi; Morton, Sarah; DePalma, Steven R; Zeng, Xue; Qi, Hongjian; Chang, Weni; Sierant, Michael C; Hung, Wei-Chien; Haider, Shozeb; et al. (Nat Genet, 2017)
Congenital heart disease (CHD) is the leading cause of mortality from birth defects. Here, exome sequencing of a single cohort of 2,871 CHD probands, including 2,645 parent-offspring trios, implicated rare inherited mutations in 1.8%, including a recessive founder mutation in GDF1 accounting for ∼5% of severe CHD in Ashkenazim, recessive genotypes in MYH6 accounting for ∼11% of Shone complex, and dominant FLT4 mutations accounting for 2.3% of Tetralogy of Fallot. De novo mutations (DNMs) accounted for 8% of cases, including ∼3% of isolated CHD patients and ∼28% with both neurodevelopmental and extra-cardiac congenital anomalies. Seven genes surpassed thresholds for genome-wide significance, and 12 genes not previously implicated in CHD had >70% probability of being disease related. DNMs in ∼440 genes were inferred to contribute to CHD. Striking overlap between genes with damaging DNMs in probands with CHD and autism was also found.
Keywords: Adult; Autistic Disorder; Cardiac Myosins; Case-Control Studies; Child; Exome; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 1; Heart Defects, Congenital; Heterozygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Mutation; Myosin Heavy Chains; Pedigree; Risk; Vascular Endothelial Growth Factor Receptor-3

De novo mutations in HNRNPU result in a neurodevelopmental syndrome. - Yates, T Michael; Vasudevan, Pradeep C; Chandler, Kate E; Donnelly, Deirdre E; Stark, Zornitza; Sadedin, Simon; Willoughby, Josh; Balasubramanian, Meena (Am J Med Genet A, 2017)
Exome sequencing in the context of developmental disorders is a useful technique, but variants found need to be interpreted in the context of detailed phenotypic information. Whole gene deletions and loss-of-function-mutations in the HNRNPU gene have been associated with intellectual disability and seizures in some patients. However, a unifying syndromic phenotype has not been previously elucidated. Here, we report a total of seven patients (six patients identified through the Wellcome Trust Deciphering Developmental Disorders study, with one additional patient), who have heterozygous de novo mutations in HNRNPU. These were found via trio-based exome sequencing. All but one of the mutations is predicted to cause loss-of-function. These patients have dysmorphic features in common, including prominent eyebrows, long palpebral fissures, overhanging columella, and thin upper lip. All patients have developmental delay and intellectual disability (ID), ranging from moderate to severe. Seizures are common from early childhood. These initially occur in the context of febrile episodes. This series demonstrates common phenotypic features, including emerging dysmorphism, associated with heterozygous HNRNPU mutations. This allows us to define a novel neurodevelopmental syndrome, with a likely mechanism of haploinsufficiency.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Genetic Predisposition to Disease; Haploinsufficiency; Heterogeneous-Nuclear Ribonucleoprotein U; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Neurodevelopmental Disorders; Phenotype; Seizures; Young Adult

A defect in myoblast fusion underlies Carey-Fineman-Ziter syndrome. - Di Gioia, Silvio Alessandro; Connors, Samantha; Matsunami, Norisada; Cannavino, Jessica; Rose, Matthew F; Gilette, Nicole M; Artoni, Pietro; de Macena Sobreira, Nara Lygia; Chan, Wai-Man; Webb, Bryn D; Robson, Caroline D; Cheng, Long; et al. (Nat Commun, 2017)
Multinucleate cellular syncytial formation is a hallmark of skeletal muscle differentiation. Myomaker, encoded by Mymk (Tmem8c), is a well-conserved plasma membrane protein required for myoblast fusion to form multinucleated myotubes in mouse, chick, and zebrafish. Here, we report that autosomal recessive mutations in MYMK (OMIM 615345) cause Carey-Fineman-Ziter syndrome in humans (CFZS; OMIM 254940) by reducing but not eliminating MYMK function. We characterize MYMK-CFZS as a congenital myopathy with marked facial weakness and additional clinical and pathologic features that distinguish it from other congenital neuromuscular syndromes. We show that a heterologous cell fusion assay in vitro and allelic complementation experiments in mymk knockdown and mymk zebrafish in vivo can differentiate between MYMK wild type, hypomorphic and null alleles. Collectively, these data establish that MYMK activity is necessary for normal muscle development and maintenance in humans, and expand the spectrum of congenital myopathies to include cell-cell fusion deficits.
Keywords: Adult; Amino Acid Sequence; Animals; Cell Fusion; Child; Disease Models, Animal; Embryo, Nonmammalian; Female; Gene Expression; Genes, Recessive; Genetic Complementation Test; Humans; Infant; Male; Membrane Proteins; Mobius Syndrome; Morphogenesis; Muscle Proteins; Muscle, Skeletal; Muscular Diseases; Mutation; Myoblasts; Pedigree; Pierre Robin Syndrome; Sequence Alignment; Sequence Homology, Amino Acid; Zebrafish; Zebrafish Proteins

A Dominant Mutation in Nuclear Receptor Interacting Protein 1 Causes Urinary Tract Malformations Dysregulation of Retinoic Acid Signaling. - Vivante, Asaf; Mann, Nina; Yonath, Hagith; Weiss, Anna-Carina; Getwan, Maike; Kaminski, Michael M; Bohnenpoll, Tobias; Teyssier, Catherine; Chen, Jing; Shril, Shirlee; van der Ven, Amelie T; Ityel, Hadas; et al. (J Am Soc Nephrol, 2017)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of CKD in the first three decades of life. However, for most patients with CAKUT, the causative mutation remains unknown. We identified a kindred with an autosomal dominant form of CAKUT. By whole-exome sequencing, we identified a heterozygous truncating mutation (c.279delG, p.Trp93fs*) of the nuclear receptor interacting protein 1 gene () in all seven affected members. encodes a nuclear receptor transcriptional cofactor that directly interacts with the retinoic acid receptors (RARs) to modulate retinoic acid transcriptional activity. Unlike wild-type NRIP1, the altered NRIP1 protein did not translocate to the nucleus, did not interact with RAR, and failed to inhibit retinoic acid-dependent transcriptional activity upon expression in HEK293 cells. Notably, we also showed that treatment with retinoic acid enhanced NRIP1 binding to RAR RNA hybridization confirmed expression in the developing urogenital system of the mouse. In explant cultures of embryonic kidney rudiments, retinoic acid stimulated expression, whereas a pan-RAR antagonist strongly reduced it. Furthermore, mice heterozygous for a null allele of showed a CAKUT-spectrum phenotype. Finally, expression and knockdown experiments in confirmed an evolutionarily conserved role for in renal development. These data indicate that dominant mutations can cause CAKUT by interference with retinoic acid transcriptional signaling, shedding light on the well documented association between abnormal vitamin A levels and renal malformations in humans, and suggest a possible gene-environment pathomechanism in this disease.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Mice; Mutation; Nuclear Proteins; Nuclear Receptor Interacting Protein 1; Signal Transduction; Tretinoin; Urinary Tract

Dual molecular diagnosis contributes to atypical Prader-Willi phenotype in monozygotic twins. - Jehee, Fernanda S; de Oliveira, Valdirene T; Gurgel-Giannetti, Juliana; Pietra, Rafaella X; Rubatino, Fernando V M; Carobin, Natália V; Vianna, Gabrielle S; de Freitas, Mariana L; Fernandes, Karla S; Ribeiro, Beatriz S V; Brüggenwirth, Hennie T; Ali-Amin, Roza; et al. (Am J Med Genet A, 2017)
We describe monozygotic twin girls with genetic variation at two separate loci resulting in a blended phenotype of Prader-Willi syndrome and Pitt-Hopkins syndrome. These girls were diagnosed in early infancy with Prader-Willi syndrome, but developed an atypical phenotype, with apparent intellectual deficiency and lack of obesity. Array-comparative genomic hybridization confirmed a de novo paternal deletion of the 15q11.2q13 region and exome sequencing identified a second mutational event in both girls, which was a novel variant c.145+1G>A affecting a TCF4 canonical splicing site inherited from the mosaic mother. RNA studies showed that the variant abolished the donor splicing site, which was accompanied by activation of an alternative non-canonical splicing-site which then predicts a premature stop codon in the following exon. Clinical re-evaluation of the twins indicated that both variants are likely contributing to the more severe phenotypic presentation. Our data show that atypical clinical presentations may actually be the expression of blended clinical phenotypes arising from independent pathogenic events at two loci.
Keywords: Adolescent; Base Sequence; Child; Chromosome Deletion; Chromosomes, Human, Pair 15; Comparative Genomic Hybridization; Exome; Facies; Female; Humans; Hyperventilation; Intellectual Disability; Obesity; Pathology, Molecular; Phenotype; Prader-Willi Syndrome; Transcription Factor 4; Twins, Monozygotic

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin; Whole Exome Sequencing

Exome-wide Association Study Identifies GREB1L Mutations in Congenital Kidney Malformations. - Sanna-Cherchi, Simone; Khan, Kamal; Westland, Rik; Krithivasan, Priya; Fievet, Lorraine; Rasouly, Hila Milo; Ionita-Laza, Iuliana; Capone, Valentina P; Fasel, David A; Kiryluk, Krzysztof; Kamalakaran, Sitharthan; Bodria, Monica; et al. (Am J Hum Genet, 2017)
Renal agenesis and hypodysplasia (RHD) are major causes of pediatric chronic kidney disease and are highly genetically heterogeneous. We conducted whole-exome sequencing in 202 case subjects with RHD and identified diagnostic mutations in genes known to be associated with RHD in 7/202 case subjects. In an additional affected individual with RHD and a congenital heart defect, we found a homozygous loss-of-function (LOF) variant in SLIT3, recapitulating phenotypes reported with Slit3 inactivation in the mouse. To identify genes associated with RHD, we performed an exome-wide association study with 195 unresolved case subjects and 6,905 control subjects. The top signal resided in GREB1L, a gene implicated previously in Hoxb1 and Shha signaling in zebrafish. The significance of the association, which was p = 2.0 × 10 for novel LOF, increased to p = 4.1 × 10 for LOF and deleterious missense variants combined, and augmented further after accounting for segregation and de novo inheritance of rare variants (joint p = 2.3 × 10). Finally, CRISPR/Cas9 disruption or knockdown of greb1l in zebrafish caused specific pronephric defects, which were rescued by wild-type human GREB1L mRNA, but not mRNA containing alleles identified in case subjects. Together, our study provides insight into the genetic landscape of kidney malformations in humans, presents multiple candidates, and identifies SLIT3 and GREB1L as genes implicated in the pathogenesis of RHD.
Keywords: Alleles; Animals; Case-Control Studies; Clustered Regularly Interspaced Short Palindromic Repeats; Congenital Abnormalities; Exome; Female; Genetic Heterogeneity; Genome-Wide Association Study; Genotype; Heredity; Homozygote; Humans; Kidney; Kidney Diseases; Male; Membrane Proteins; Mice; Mutation; Neoplasm Proteins; Phenotype; RNA, Long Noncoding; Urinary Tract; Urogenital Abnormalities; Zebrafish

First Case of Deficiency in Ecuador, Diagnosed after Whole Exome Sequencing in a Patient with Severe Cutaneous Histoplasmosis. - Pedroza, Luis Alberto; Guerrero, Nina; Stray-Pedersen, Asbjørg; Tafur, Cristina; Macias, Roque; Muñoz, Greta; Akdemir, Zeynep Coban; Jhangiani, Shalini N; Watkin, Levi B; Chinn, Ivan K; Lupski, James R; Orange, Jordan S (Front Pediatr, 2017)
Severe infections with are commonly observed in patient with secondary immunodeficiency disorders. We report a two and a half years old boy previously healthy with disseminated cutaneous histoplasmosis. Using whole exome sequencing, we found an mutation at the gene, suggesting a diagnosis of hyper-IgM (HIGM) syndrome, even in the absence of the usual features for the disease. Interestingly, the patient lives in a region endemic for histoplasmosis. The unusual infections in our case suggest that in children with severe histoplasmosis and resident in endemic areas, HIGM syndrome should be considered as a diagnosis.

Gene-based segregation method for identifying rare variants in family-based sequencing studies. - Qiao, Dandi; Lange, Christoph; Laird, Nan M; Won, Sungho; Hersh, Craig P; Morrow, Jarrett; Hobbs, Brian D; Lutz, Sharon M; Ruczinski, Ingo; Beaty, Terri H; Silverman, Edwin K; Cho, Michael H (Genet Epidemiol, 2017)
Whole-exome sequencing using family data has identified rare coding variants in Mendelian diseases or complex diseases with Mendelian subtypes, using filters based on variant novelty, functionality, and segregation with the phenotype within families. However, formal statistical approaches are limited. We propose a gene-based segregation test (GESE) that quantifies the uncertainty of the filtering approach. It is constructed using the probability of segregation events under the null hypothesis of Mendelian transmission. This test takes into account different degrees of relatedness in families, the number of functional rare variants in the gene, and their minor allele frequencies in the corresponding population. In addition, a weighted version of this test allows incorporating additional subject phenotypes to improve statistical power. We show via simulations that the GESE and weighted GESE tests maintain appropriate type I error rate, and have greater power than several commonly used region-based methods. We apply our method to whole-exome sequencing data from 49 extended pedigrees with severe, early-onset chronic obstructive pulmonary disease (COPD) in the Boston Early-Onset COPD study (BEOCOPD) and identify several promising candidate genes. Our proposed methods show great potential for identifying rare coding variants of large effect and high penetrance for family-based sequencing data. The proposed tests are implemented in an R package that is available on CRAN (https://cran.r-project.org/web/packages/GESE/).
Keywords: Age of Onset; Boston; Computer Simulation; Databases, Genetic; Family; Genetic Variation; Genome, Human; Humans; Models, Genetic; Penetrance; Pulmonary Disease, Chronic Obstructive; Reference Standards; Sequence Analysis, DNA

Genetic Drivers of Kidney Defects in the DiGeorge Syndrome. - Lopez-Rivera, Esther; Liu, Yangfan P; Verbitsky, Miguel; Anderson, Blair R; Capone, Valentina P; Otto, Edgar A; Yan, Zhonghai; Mitrotti, Adele; Martino, Jeremiah; Steers, Nicholas J; Fasel, David A; Vukojevic, Katarina; et al. (N Engl J Med, 2017)
BACKGROUND: The DiGeorge syndrome, the most common of the microdeletion syndromes, affects multiple organs, including the heart, the nervous system, and the kidney. It is caused by deletions on chromosome 22q11.2; the genetic driver of the kidney defects is unknown. METHODS: We conducted a genomewide search for structural variants in two cohorts: 2080 patients with congenital kidney and urinary tract anomalies and 22,094 controls. We performed exome and targeted resequencing in samples obtained from 586 additional patients with congenital kidney anomalies. We also carried out functional studies using zebrafish and mice. RESULTS: We identified heterozygous deletions of 22q11.2 in 1.1% of the patients with congenital kidney anomalies and in 0.01% of population controls (odds ratio, 81.5; P=4.5×10). We localized the main drivers of renal disease in the DiGeorge syndrome to a 370-kb region containing nine genes. In zebrafish embryos, an induced loss of function in snap29, aifm3, and crkl resulted in renal defects; the loss of crkl alone was sufficient to induce defects. Five of 586 patients with congenital urinary anomalies had newly identified, heterozygous protein-altering variants, including a premature termination codon, in CRKL. The inactivation of Crkl in the mouse model induced developmental defects similar to those observed in patients with congenital urinary anomalies. CONCLUSIONS: We identified a recurrent 370-kb deletion at the 22q11.2 locus as a driver of kidney defects in the DiGeorge syndrome and in sporadic congenital kidney and urinary tract anomalies. Of the nine genes at this locus, SNAP29, AIFM3, and CRKL appear to be critical to the phenotype, with haploinsufficiency of CRKL emerging as the main genetic driver. (Funded by the National Institutes of Health and others.).
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Animals; Child; Chromosome Deletion; Chromosomes, Human, Pair 22; DiGeorge Syndrome; Exome; Female; Haploinsufficiency; Heterozygote; Humans; Infant; Infant, Newborn; Kidney; Male; Mice; Models, Animal; Nuclear Proteins; Sequence Analysis, DNA; Urinary Tract; Young Adult; Zebrafish

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Muzny, Donna M; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Signal Transduction

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features. - Zhang, Jing; Gambin, Tomasz; Yuan, Bo; Szafranski, Przemyslaw; Rosenfeld, Jill A; Balwi, Mohammed Al; Alswaid, Abdulrahman; Al-Gazali, Lihadh; Shamsi, Aisha M Al; Komara, Makanko; Ali, Bassam R; Roeder, Elizabeth; et al. (Hum Genet, 2017)
Impairment of ubiquitin-proteasome system activity involving ubiquitin ligase genes UBE3A, UBE3B, and HUWE1 and deubiquitinating enzyme genes USP7 and USP9X has been reported in patients with neurodevelopmental delays. To date, only a handful of single-nucleotide variants (SNVs) and copy-number variants (CNVs) involving TRIP12, encoding a member of the HECT domain E3 ubiquitin ligases family on chromosome 2q36.3 have been reported. Using chromosomal microarray analysis and whole-exome sequencing (WES), we have identified, respectively, five deletion CNVs and four inactivating SNVs (two frameshifts, one missense, and one splicing) in TRIP12. Seven of these variants were found to be de novo; parental studies could not be completed in two families. Quantitative PCR analyses of the splicing mutation showed a dramatically decreased level of TRIP12 mRNA in the proband compared to the family controls, indicating a loss-of-function mechanism. The shared clinical features include intellectual disability with or without autistic spectrum disorders, speech delay, and facial dysmorphism. Our findings demonstrate that E3 ubiquitin ligase TRIP12 plays an important role in nervous system development and function. The nine presented pathogenic variants further document that TRIP12 haploinsufficiency causes a childhood-onset neurodevelopmental disorder. Finally, our data enable expansion of the phenotypic spectrum of ubiquitin-proteasome dependent disorders.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Cohort Studies; DNA Copy Number Variations; Facies; Female; Haploinsufficiency; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Ubiquitin-Protein Ligases

High Rate of Recurrent De Novo Mutations in Developmental and Epileptic Encephalopathies. - Hamdan, Fadi F; Myers, Candace T; Cossette, Patrick; Lemay, Philippe; Spiegelman, Dan; Laporte, Alexandre Dionne; Nassif, Christina; Diallo, Ousmane; Monlong, Jean; Cadieux-Dion, Maxime; Dobrzeniecka, Sylvia; Meloche, Caroline; et al. (Am J Hum Genet, 2017)
Developmental and epileptic encephalopathy (DEE) is a group of conditions characterized by the co-occurrence of epilepsy and intellectual disability (ID), typically with developmental plateauing or regression associated with frequent epileptiform activity. The cause of DEE remains unknown in the majority of cases. We performed whole-genome sequencing (WGS) in 197 individuals with unexplained DEE and pharmaco-resistant seizures and in their unaffected parents. We focused our attention on de novo mutations (DNMs) and identified candidate genes containing such variants. We sought to identify additional subjects with DNMs in these genes by performing targeted sequencing in another series of individuals with DEE and by mining various sequencing datasets. We also performed meta-analyses to document enrichment of DNMs in candidate genes by leveraging our WGS dataset with those of several DEE and ID series. By combining these strategies, we were able to provide a causal link between DEE and the following genes: NTRK2, GABRB2, CLTC, DHDDS, NUS1, RAB11A, GABBR2, and SNAP25. Overall, we established a molecular diagnosis in 63/197 (32%) individuals in our WGS series. The main cause of DEE in these individuals was de novo point mutations (53/63 solved cases), followed by inherited mutations (6/63 solved cases) and de novo CNVs (4/63 solved cases). De novo missense variants explained a larger proportion of individuals in our series than in other series that were primarily ascertained because of ID. Moreover, these DNMs were more frequently recurrent than those identified in ID series. These observations indicate that the genetic landscape of DEE might be different from that of ID without epilepsy.
Keywords: Brain Diseases; Child; Child, Preschool; Epilepsy; Female; Genome, Human; Genome-Wide Association Study; Humans; Intellectual Disability; Male; Mutation; Recurrence; Seizures

Homozygous Mutations in TBC1D23 Lead to a Non-degenerative Form of Pontocerebellar Hypoplasia. - Marin-Valencia, Isaac; Gerondopoulos, Andreas; Zaki, Maha S; Ben-Omran, Tawfeg; Almureikhi, Mariam; Demir, Ercan; Guemez-Gamboa, Alicia; Gregor, Anne; Issa, Mahmoud Y; Appelhof, Bart; Roosing, Susanne; Musaev, Damir; et al. (Am J Hum Genet, 2017)
Pontocerebellar hypoplasia (PCH) represents a group of recessive developmental disorders characterized by impaired growth of the pons and cerebellum, which frequently follows a degenerative course. Currently, there are 10 partially overlapping clinical subtypes and 13 genes known mutated in PCH. Here, we report biallelic TBC1D23 mutations in six individuals from four unrelated families manifesting a non-degenerative form of PCH. In addition to reduced volume of pons and cerebellum, affected individuals had microcephaly, psychomotor delay, and ataxia. In zebrafish, tbc1d23 morphants replicated the human phenotype showing hindbrain volume loss. TBC1D23 localized at the trans-Golgi and was regulated by the small GTPases Arl1 and Arl8, suggesting a role in trans-Golgi membrane trafficking. Altogether, this study provides a causative link between TBC1D23 mutations and PCH and suggests a less severe clinical course than other PCH subtypes.
Keywords: Adolescent; Animals; Cerebellar Diseases; Child; Child, Preschool; Female; GTPase-Activating Proteins; HeLa Cells; Homozygote; Humans; Male; Microcephaly; Mutation; Pedigree; Phenotype; Zebrafish

Identification of novel candidate disease genes from de novo exonic copy number variants. - Gambin, Tomasz; Yuan, Bo; Bi, Weimin; Liu, Pengfei; Rosenfeld, Jill A; Coban-Akdemir, Zeynep; Pursley, Amber N; Nagamani, Sandesh C S; Marom, Ronit; Golla, Sailaja; Dengle, Lauren; Petrie, Heather G; et al. (Genome Med, 2017)
BACKGROUND: Exon-targeted microarrays can detect small (<1000 bp) intragenic copy number variants (CNVs), including those that affect only a single exon. This genome-wide high-sensitivity approach increases the molecular diagnosis for conditions with known disease-associated genes, enables better genotype-phenotype correlations, and facilitates variant allele detection allowing novel disease gene discovery. METHODS: We retrospectively analyzed data from 63,127 patients referred for clinical chromosomal microarray analysis (CMA) at Baylor Genetics laboratories, including 46,755 individuals tested using exon-targeted arrays, from 2007 to 2017. Small CNVs harboring a single gene or two to five non-disease-associated genes were identified; the genes involved were evaluated for a potential disease association. RESULTS: In this clinical population, among rare CNVs involving any single gene reported in 7200 patients (11%), we identified 145 de novo autosomal CNVs (117 losses and 28 intragenic gains), 257 X-linked deletion CNVs in males, and 1049 inherited autosomal CNVs (878 losses and 171 intragenic gains); 111 known disease genes were potentially disrupted by de novo autosomal or X-linked (in males) single-gene CNVs. Ninety-one genes, either recently proposed as candidate disease genes or not yet associated with diseases, were disrupted by 147 single-gene CNVs, including 37 de novo deletions and ten de novo intragenic duplications on autosomes and 100 X-linked CNVs in males. Clinical features in individuals with de novo or X-linked CNVs encompassing at most five genes (224 bp to 1.6 Mb in size) were compared to those in individuals with larger-sized deletions (up to 5 Mb in size) in the internal CMA database or loss-of-function single nucleotide variants (SNVs) detected by clinical or research whole-exome sequencing (WES). This enabled the identification of recently published genes (BPTF, NONO, PSMD12, TANGO2, and TRIP12), novel candidate disease genes (ARGLU1 and STK3), and further confirmation of disease association for two recently proposed disease genes (MEIS2 and PTCHD1). Notably, exon-targeted CMA detected several pathogenic single-exon CNVs missed by clinical WES analyses. CONCLUSIONS: Together, these data document the efficacy of exon-targeted CMA for detection of genic and exonic CNVs, complementing and extending WES in clinical diagnostics, and the potential for discovery of novel disease genes by genome-wide assay.
Keywords: Cohort Studies; DNA Copy Number Variations; Exons; Genetic Diseases, Inborn; Genome, Human; Homeodomain Proteins; Humans; Intracellular Signaling Peptides and Proteins; Membrane Proteins; Neurodevelopmental Disorders; Protein-Serine-Threonine Kinases; Retrospective Studies; Transcription Factors; Whole Genome Sequencing

Identification of STAC3 variants in non-Native American families with overlapping features of Carey-Fineman-Ziter syndrome and Moebius syndrome. - Telegrafi, Aida; Webb, Bryn D; Robbins, Sarah M; Speck-Martins, Carlos E; FitzPatrick, David; Fleming, Leah; Redett, Richard; Dufke, Andreas; Houge, Gunnar; van Harssel, Jeske J T; Verloes, Alain; Robles, Angela; et al. (Am J Med Genet A, 2017)
Horstick et al. (2013) previously reported a homozygous p.Trp284Ser variant in STAC3 as the cause of Native American myopathy (NAM) in 5 Lumbee Native American families with congenital hypotonia and weakness, cleft palate, short stature, ptosis, kyphoscoliosis, talipes deformities, and susceptibility to malignant hyperthermia (MH). Here we present two non-Native American families, who were found to have STAC3 pathogenic variants. The first proband and her affected older sister are from a consanguineous Qatari family with a suspected clinical diagnosis of Carey-Fineman-Ziter syndrome (CFZS) based on features of hypotonia, myopathic facies with generalized weakness, ptosis, normal extraocular movements, cleft palate, growth delay, and kyphoscoliosis. We identified the homozygous c.851G>C;p.Trp284Ser variant in STAC3 in both sisters. The second proband and his affected sister are from a non-consanguineous, Puerto Rican family who was evaluated for a possible diagnosis of Moebius syndrome (MBS). His features included facial and generalized weakness, minimal limitation of horizontal gaze, cleft palate, and hypotonia, and he has a history of MH. The siblings were identified to be compound heterozygous for STAC3 variants c.851G>C;p.Trp284Ser and c.763_766delCTCT;p.Leu255IlefsX58. Given the phenotypic overlap of individuals with CFZS, MBS, and NAM, we screened STAC3 in 12 individuals diagnosed with CFZS and in 50 individuals diagnosed with MBS or a congenital facial weakness disorder. We did not identify any rare coding variants in STAC3. NAM should be considered in patients presenting with facial and generalized weakness, normal or mildly abnormal extraocular movement, hypotonia, cleft palate, and scoliosis, particularly if there is a history of MH.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Child; Female; Humans; Male; Mobius Syndrome; Muscular Diseases; Mutation; Pedigree; Pierre Robin Syndrome; Prognosis; Young Adult

Improving genetic diagnosis in Mendelian disease with transcriptome sequencing. - Cummings, Beryl B; Marshall, Jamie L; Tukiainen, Taru; Lek, Monkol; Donkervoort, Sandra; Foley, A Reghan; Bolduc, Veronique; Waddell, Leigh B; Sandaradura, Sarah A; O'Grady, Gina L; Estrella, Elicia; Reddy, Hemakumar M; et al. (Sci Transl Med, 2017)
Exome and whole-genome sequencing are becoming increasingly routine approaches in Mendelian disease diagnosis. Despite their success, the current diagnostic rate for genomic analyses across a variety of rare diseases is approximately 25 to 50%. We explore the utility of transcriptome sequencing [RNA sequencing (RNA-seq)] as a complementary diagnostic tool in a cohort of 50 patients with genetically undiagnosed rare muscle disorders. We describe an integrated approach to analyze patient muscle RNA-seq, leveraging an analysis framework focused on the detection of transcript-level changes that are unique to the patient compared to more than 180 control skeletal muscle samples. We demonstrate the power of RNA-seq to validate candidate splice-disrupting mutations and to identify splice-altering variants in both exonic and deep intronic regions, yielding an overall diagnosis rate of 35%. We also report the discovery of a highly recurrent de novo intronic mutation in that results in a dominantly acting splice-gain event, disrupting the critical glycine repeat motif of the triple helical domain. We identify this pathogenic variant in a total of 27 genetically unsolved patients in an external collagen VI-like dystrophy cohort, thus explaining approximately 25% of patients clinically suggestive of having collagen VI dystrophy in whom prior genetic analysis is negative. Overall, this study represents a large systematic application of transcriptome sequencing to rare disease diagnosis and highlights its utility for the detection and interpretation of variants missed by current standard diagnostic approaches.
Keywords: Collagen Type VI; High-Throughput Nucleotide Sequencing; Humans; Muscular Diseases; Mutation; Transcriptome

Intensification: A Resource for Amplifying Population-Genetic Signals with Protein Repeats. - Chen, Jieming; Wang, Bo; Regan, Lynne; Gerstein, Mark (J Mol Biol, 2017)
Large-scale genome sequencing holds great promise for the interpretation of protein structures through the discovery of many, rare functional variants in the human population. However, because protein-coding regions are under high selective constraints, these variants occur at low frequencies, such that there is often insufficient statistics for downstream calculations. To address this problem, we develop the Intensification approach, which uses the modular structure of repeat protein domains to amplify signals of selection from population genetics and traditional interspecies conservation. In particular, we are able to aggregate variants at the codon level to identify important positions in repeat domains that show strong conservation signals. This allows us to compare conservation over different evolutionary timescales. It also enables us to visualize population-genetic measures on protein structures. We make available the Intensification results as an online resource (http://intensification.gersteinlab.org) and illustrate the approach through a case study on the tetratricopeptide repeat.
Keywords: Amino Acid Sequence; Chromosome Mapping; Codon; Computational Biology; Databases, Genetic; Evolution, Molecular; Genetics, Population; Humans; Internet; Molecular Structure; Protein Conformation; Proteins; Signal Processing, Computer-Assisted; X-Rays

Isolated polycystic liver disease genes define effectors of polycystin-1 function. - Besse, Whitney; Dong, Ke; Choi, Jungmin; Punia, Sohan; Fedeles, Sorin V; Choi, Murim; Gallagher, Anna-Rachel; Huang, Emily B; Gulati, Ashima; Knight, James; Mane, Shrikant; Tahvanainen, Esa; et al. (J Clin Invest, 2017)
Dominantly inherited isolated polycystic liver disease (PCLD) consists of liver cysts that are radiologically and pathologically identical to those seen in autosomal dominant polycystic kidney disease, but without clinically relevant kidney cysts. The causative genes are known for fewer than 40% of PCLD index cases. Here, we have used whole exome sequencing in a discovery cohort of 102 unrelated patients who were excluded for mutations in the 2 most common PCLD genes, PRKCSH and SEC63, to identify heterozygous loss-of-function mutations in 3 additional genes, ALG8, GANAB, and SEC61B. Similarly to PRKCSH and SEC63, these genes encode proteins that are integral to the protein biogenesis pathway in the endoplasmic reticulum. We inactivated these candidate genes in cell line models to show that loss of function of each results in defective maturation and trafficking of polycystin-1, the central determinant of cyst pathogenesis. Despite acting in a common pathway, each PCLD gene product demonstrated distinct effects on polycystin-1 biogenesis. We also found enrichment on a genome-wide basis of heterozygous mutations in the autosomal recessive polycystic kidney disease gene PKHD1, indicating that adult PKHD1 carriers can present with clinical PCLD. These findings define genetic and biochemical modulators of polycystin-1 function and provide a more complete definition of the spectrum of dominant human polycystic diseases.
Keywords: Adult; Animals; Cell Line, Transformed; Cysts; Endoplasmic Reticulum; Female; Genome-Wide Association Study; Glucosidases; Glucosyltransferases; Heterozygote; Humans; Intracellular Signaling Peptides and Proteins; Liver Diseases; Male; Membrane Proteins; Mice; Mutation; SEC Translocation Channels; TRPP Cation Channels

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Loss-of-Function Variants in MYLK Cause Recessive Megacystis Microcolon Intestinal Hypoperistalsis Syndrome. - Halim, Danny; Brosens, Erwin; Muller, Françoise; Wangler, Michael F; Beaudet, Arthur L; Lupski, James R; Akdemir, Zeynep H Coban; Doukas, Michael; Stoop, Hans J; de Graaf, Bianca M; Brouwer, Rutger W W; van Ijcken, Wilfred F J; et al. (Am J Hum Genet, 2017)
Megacystis microcolon intestinal hypoperistalsis syndrome (MMIHS) is a congenital disorder characterized by loss of smooth muscle contraction in the bladder and intestine. To date, three genes are known to be involved in MMIHS pathogenesis: ACTG2, MYH11, and LMOD1. However, for approximately 10% of affected individuals, the genetic cause of the disease is unknown, suggesting that other loci are most likely involved. Here, we report on three MMIHS-affected subjects from two consanguineous families with no variants in the known MMIHS-associated genes. By performing homozygosity mapping and whole-exome sequencing, we found homozygous variants in myosin light chain kinase (MYLK) in both families. We identified a 7 bp duplication (c.3838_3844dupGAAAGCG [p.Glu1282_Glyfs51]) in one family and a putative splice-site variant (c.3985+5C>A) in the other. Expression studies and splicing assays indicated that both variants affect normal MYLK expression. Because MYLK encodes an important kinase required for myosin activation and subsequent interaction with actin filaments, it is likely that in its absence, contraction of smooth muscle cells is impaired. The existence of a conditional-Mylk-knockout mouse model with severe gut dysmotility and abnormal function of the bladder supports the involvement of this gene in MMIHS pathogenesis. In aggregate, our findings implicate MYLK as a gene involved in the recessive form of MMIHS, confirming that this disease of the visceral organs is heterogeneous with a myopathic origin.
Keywords: Abnormalities, Multiple; Base Sequence; Colon; Female; Genes, Recessive; Homozygote; Humans; Intestinal Pseudo-Obstruction; Male; Mutation; Myosin-Light-Chain Kinase; Pedigree; Urinary Bladder

Molecular outcomes, clinical consequences, and genetic diagnosis of Oculocutaneous Albinism in Pakistani population. - Shahzad, Mohsin; Yousaf, Sairah; Waryah, Yar M; Gul, Hadia; Kausar, Tasleem; Tariq, Nabeela; Mahmood, Umair; Ali, Muhammad; Khan, Muzammil A; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; et al. (Sci Rep, 2017)
Nonsyndromic oculocutaneous Albinism (nsOCA) is clinically characterized by the loss of pigmentation in the skin, hair, and iris. OCA is amongst the most common causes of vision impairment in children. To date, pathogenic variants in six genes have been identified in individuals with nsOCA. Here, we determined the identities, frequencies, and clinical consequences of OCA alleles in 94 previously unreported Pakistani families. Combination of Sanger and Exome sequencing revealed 38 alleles, including 22 novel variants, segregating with nsOCA phenotype in 80 families. Variants of TYR and OCA2 genes were the most common cause of nsOCA, occurring in 43 and 30 families, respectively. Twenty-two novel variants include nine missense, four splice site, two non-sense, one insertion and six gross deletions. In vitro studies revealed retention of OCA proteins harboring novel missense alleles in the endoplasmic reticulum (ER) of transfected cells. Exon-trapping assays with constructs containing splice site alleles revealed errors in splicing. As eight alleles account for approximately 56% (95% CI: 46.52-65.24%) of nsOCA cases, primarily enrolled from Punjab province of Pakistan, hierarchical strategies for variant detection would be feasible and cost-efficient genetic tests for OCA in families with similar origin. Thus, we developed Tetra-primer ARMS assays for rapid, reliable, reproducible and economical screening of most of these common alleles.
Keywords: Albinism, Oculocutaneous; Alleles; Female; Gene Frequency; Humans; Male; Membrane Transport Proteins; Mutation, Missense; Pakistan

Multilevel analyses of SCN5A mutations in arrhythmogenic right ventricular dysplasia/cardiomyopathy suggest non-canonical mechanisms for disease pathogenesis. - Te Riele, Anneline S J M; Agullo-Pascual, Esperanza; James, Cynthia A; Leo-Macias, Alejandra; Cerrone, Marina; Zhang, Mingliang; Lin, Xianming; Lin, Bin; Sobreira, Nara L; Amat-Alarcon, Nuria; Marsman, Roos F; Murray, Brittney; et al. (Cardiovasc Res, 2017)
AIMS: Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy (ARVD/C) is often associated with desmosomal mutations. Recent studies suggest an interaction between the desmosome and sodium channel protein Na1.5. We aimed to determine the prevalence and biophysical properties of mutations in SCN5A (the gene encoding Na1.5) in ARVD/C. METHODS AND RESULTS: We performed whole-exome sequencing in six ARVD/C patients (33% male, 38.2 ± 12.1 years) without a desmosomal mutation. We found a rare missense variant (p.Arg1898His; R1898H) in SCN5A in one patient. We generated induced pluripotent stem cell-derived cardiomyocytes (hIPSC-CMs) from the patient's peripheral blood mononuclear cells. The variant was then corrected (R1898R) using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology, allowing us to study the impact of the R1898H substitution in the same cellular background. Whole-cell patch clamping revealed a 36% reduction in peak sodium current (P = 0.002); super-resolution fluorescence microscopy showed reduced abundance of Na1.5 (P = 0.005) and N-Cadherin (P = 0.026) clusters at the intercalated disc. Subsequently, we sequenced SCN5A in an additional 281 ARVD/C patients (60% male, 34.8 ± 13.7 years, 52% desmosomal mutation-carriers). Five (1.8%) subjects harboured a putatively pathogenic SCN5A variant (p.Tyr416Cys, p.Leu729del, p.Arg1623Ter, p.Ser1787Asn, and p.Val2016Met). SCN5A variants were associated with prolonged QRS duration (119 ± 15 vs. 94 ± 14 ms, P < 0.01) and all SCN5A variant carriers had major structural abnormalities on cardiac imaging. CONCLUSIONS: Almost 2% of ARVD/C patients harbour rare SCN5A variants. For one of these variants, we demonstrated reduced sodium current, Na1.5 and N-Cadherin clusters at junctional sites. This suggests that Na1.5 is in a functional complex with adhesion molecules, and reveals potential non-canonical mechanisms by which Na1.5 dysfunction causes cardiomyopathy.
Keywords: Adult; Antigens, CD; Arrhythmogenic Right Ventricular Dysplasia; Cadherins; Cell Differentiation; CRISPR-Cas Systems; DNA Mutational Analysis; Electrocardiography; Exome; Female; Gene Editing; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Magnetic Resonance Imaging; Male; Membrane Potentials; Middle Aged; Multilevel Analysis; Mutation, Missense; Myocytes, Cardiac; NAV1.5 Voltage-Gated Sodium Channel; Netherlands; Phenotype; Sodium; Transfection; United States; Young Adult

Mutations in IFT-A satellite core component genes and produce short rib polydactyly syndrome with distinctive campomelia. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Qureshi, Faisal; Jacques, Suzanne M; Wallerstein, Robert; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Cilia, 2017)
BACKGROUND: Skeletal ciliopathies comprise a spectrum of ciliary malfunction disorders that have a profound effect on the skeleton. Most common among these disorders is short rib polydactyly syndrome (SRPS), a recessively inherited perinatal lethal condition characterized by a long narrow chest, markedly shortened long bones, polydactyly and, often, multi-organ system involvement. SRPS shows extensive locus heterogeneity with mutations in genes encoding proteins that participate in cilia formation and/or function. RESULTS: Herein we describe mutations in , a satellite member of the retrograde IFT-A complex, that produce a form of SRPS with unusual bending of the ribs and appendicular bones. These newly described mutations disrupted cilia formation, produced abnormalities in cartilage growth plate architecture thus contributing to altered endochondral ossification. We further show that the SRPS phenotype is similar to SRPS resulting from mutations in the gene encoding IFT121 (WDR35), a direct interactor with IFT43. CONCLUSIONS: This study defines a new -associated phenotype, identifying an additional locus for SRPS. The data demonstrate that IFT43 is essential for ciliogenesis and that the mutations disrupted the orderly proliferation and differentiation of growth plate chondrocytes, resulting in a severe effect on endochondral ossification and mineralization. Phenotypic similarities with SRPS cases resulting from mutations in the gene encoding the IFT43 direct interacting protein IFT121 suggests that similar mechanisms may be disrupted by defects in these two IFT-A satellite interactors.

Mutations in KEOPS-complex genes cause nephrotic syndrome with primary microcephaly. - Braun, Daniela A; Rao, Jia; Mollet, Geraldine; Schapiro, David; Daugeron, Marie-Claire; Tan, Weizhen; Gribouval, Olivier; Boyer, Olivia; Revy, Patrick; Jobst-Schwan, Tilman; Schmidt, Johanna Magdalena; Lawson, Jennifer A; et al. (Nat Genet, 2017)
Galloway-Mowat syndrome (GAMOS) is an autosomal-recessive disease characterized by the combination of early-onset nephrotic syndrome (SRNS) and microcephaly with brain anomalies. Here we identified recessive mutations in OSGEP, TP53RK, TPRKB, and LAGE3, genes encoding the four subunits of the KEOPS complex, in 37 individuals from 32 families with GAMOS. CRISPR-Cas9 knockout in zebrafish and mice recapitulated the human phenotype of primary microcephaly and resulted in early lethality. Knockdown of OSGEP, TP53RK, or TPRKB inhibited cell proliferation, which human mutations did not rescue. Furthermore, knockdown of these genes impaired protein translation, caused endoplasmic reticulum stress, activated DNA-damage-response signaling, and ultimately induced apoptosis. Knockdown of OSGEP or TP53RK induced defects in the actin cytoskeleton and decreased the migration rate of human podocytes, an established intermediate phenotype of SRNS. We thus identified four new monogenic causes of GAMOS, describe a link between KEOPS function and human disease, and delineate potential pathogenic mechanisms.
Keywords: Animals; Apoptosis; Carrier Proteins; Cell Movement; CRISPR-Cas Systems; Cytoskeleton; DNA Repair; Endoplasmic Reticulum Stress; Gene Knockout Techniques; Hernia, Hiatal; Humans; Intracellular Signaling Peptides and Proteins; Metalloendopeptidases; Mice; Microcephaly; Models, Molecular; Multiprotein Complexes; Mutation; Nephrosis; Nephrotic Syndrome; Podocytes; Protein Conformation; Protein-Serine-Threonine Kinases; RNA Processing, Post-Transcriptional; RNA, Transfer; Telomere Homeostasis; Zebrafish; Zebrafish Proteins

Mutations in sphingosine-1-phosphate lyase cause nephrosis with ichthyosis and adrenal insufficiency. - Lovric, Svjetlana; Goncalves, Sara; Gee, Heon Yung; Oskouian, Babak; Srinivas, Honnappa; Choi, Won-Il; Shril, Shirlee; Ashraf, Shazia; Tan, Weizhen; Rao, Jia; Airik, Merlin; Schapiro, David; et al. (J Clin Invest, 2017)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease cases. A mutation in 1 of over 40 monogenic genes can be detected in approximately 30% of individuals with SRNS whose symptoms manifest before 25 years of age. However, in many patients, the genetic etiology remains unknown. Here, we have performed whole exome sequencing to identify recessive causes of SRNS. In 7 families with SRNS and facultative ichthyosis, adrenal insufficiency, immunodeficiency, and neurological defects, we identified 9 different recessive mutations in SGPL1, which encodes sphingosine-1-phosphate (S1P) lyase. All mutations resulted in reduced or absent SGPL1 protein and/or enzyme activity. Overexpression of cDNA representing SGPL1 mutations resulted in subcellular mislocalization of SGPL1. Furthermore, expression of WT human SGPL1 rescued growth of SGPL1-deficient dpl1Δ yeast strains, whereas expression of disease-associated variants did not. Immunofluorescence revealed SGPL1 expression in mouse podocytes and mesangial cells. Knockdown of Sgpl1 in rat mesangial cells inhibited cell migration, which was partially rescued by VPC23109, an S1P receptor antagonist. In Drosophila, Sply mutants, which lack SGPL1, displayed a phenotype reminiscent of nephrotic syndrome in nephrocytes. WT Sply, but not the disease-associated variants, rescued this phenotype. Together, these results indicate that SGPL1 mutations cause a syndromic form of SRNS.
Keywords: Aldehyde-Lyases; Animals; Cell Line; Cell Movement; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Ichthyosis, Lamellar; Male; Mesangial Cells; Mice; Mice, Knockout; Mutation; Nephrotic Syndrome; Protein Transport; Rats

A novel mutation in GMPPA in siblings with apparent intellectual disability, epilepsy, dysmorphism, and autonomic dysfunction. - Gold, Wendy A; Sobreira, Nara; Wiame, Elsa; Marbaix, Alexandre; Van Schaftingen, Emile; Franzka, Patricia; Riley, Lisa G; Worgan, Lisa; Hübner, Christian A; Christodoulou, John; Adès, Lesley C (Am J Med Genet A, 2017)
GMPPA encodes the GDP-mannose pyrophosphorylase A protein (GMPPA). The function of GMPPA is not well defined, however it is a homolog of GMPPB which catalyzes the reaction that converts mannose-1-phosphate and guanosine-5'-triphosphate to GDP-mannose. Previously, biallelic mutations in GMPPA were reported to cause a disorder characterized by achalasia, alacrima, neurological deficits, and intellectual disability. In this study, we report a female proband with achalasia, alacrima, hypohydrosis, apparent intellectual disability, seizures, microcephaly, esotropia, and craniofacial dysmorphism. Exome sequencing identified a previously unreported homozygous c.853+1G>A variant in GMPPA in the proband and her affected sister. Their unaffected parents were heterozygous, and unaffected brother homozygous wild type for this variant. Lymphoblast cells from the affected sisters showed complete loss of the GMPPA protein by Western blotting, and increased levels of GDP-mannose in lymphoblasts on high performance liquid chromatography. Based on our findings and the previous report describing patients with an overlapping phenotype, we conclude that this novel variant in GMPPA, identified by exome sequencing in the proband and her affected sister, is the genetic cause of their phenotype and may expand the known phenotype of this recently described glycosylation disorder.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; Craniofacial Abnormalities; Epilepsy; Exome; Facies; Female; Heterozygote; Humans; Intellectual Disability; Microcephaly; Muscular Atrophy; Mutation, Missense; Nucleotidyltransferases; Pedigree; Phenotype; Seizures

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Phenotypic and molecular characterisation of CDK13-related congenital heart defects, dysmorphic facial features and intellectual developmental disorders. - Bostwick, Bret L; McLean, Scott; Posey, Jennifer E; Streff, Haley E; Gripp, Karen W; Blesson, Alyssa; Powell-Hamilton, Nina; Tusi, Jessica; Stevenson, David A; Farrelly, Ellyn; Hudgins, Louanne; Yang, Yaping; et al. (Genome Med, 2017)
BACKGROUND: De novo missense variants in CDK13 have been described as the cause of syndromic congenital heart defects in seven individuals ascertained from a large congenital cardiovascular malformations cohort. We aimed to further define the phenotypic and molecular spectrum of this newly described disorder. METHODS: To minimise ascertainment bias, we recruited nine additional individuals with CDK13 pathogenic variants from clinical and research exome laboratory sequencing cohorts. Each individual underwent dysmorphology exam and comprehensive medical history review. RESULTS: We demonstrate greater than expected phenotypic heterogeneity, including 33% (3/9) of individuals without structural heart disease on echocardiogram. There was a high penetrance for a unique constellation of facial dysmorphism and global developmental delay, as well as less frequently seen renal and sacral anomalies. Two individuals had novel CDK13 variants (p.Asn842Asp, p.Lys734Glu), while the remaining seven unrelated individuals had a recurrent, previously published p.Asn842Ser variant. Summary of all variants published to date demonstrates apparent restriction of pathogenic variants to the protein kinase domain with clustering in the ATP and magnesium binding sites. CONCLUSIONS: Here we provide detailed phenotypic and molecular characterisation of individuals with pathogenic variants in CDK13 and propose management guidelines based upon the estimated prevalence of anomalies identified.
Keywords: Adolescent; Adult; CDC2 Protein Kinase; Child; Child, Preschool; Face; Female; Heart Defects, Congenital; Humans; Infant; Intellectual Disability; Male; Mutation; Phenotype; Syndrome

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

PRUNE is crucial for normal brain development and mutated in microcephaly with neurodevelopmental impairment. - Zollo, Massimo; Ahmed, Mustafa; Ferrucci, Veronica; Salpietro, Vincenzo; Asadzadeh, Fatemeh; Carotenuto, Marianeve; Maroofian, Reza; Al-Amri, Ahmed; Singh, Royana; Scognamiglio, Iolanda; Mojarrad, Majid; Musella, Luca; et al. (Brain, 2017)
PRUNE is a member of the DHH (Asp-His-His) phosphoesterase protein superfamily of molecules important for cell motility, and implicated in cancer progression. Here we investigated multiple families from Oman, India, Iran and Italy with individuals affected by a new autosomal recessive neurodevelopmental and degenerative disorder in which the cardinal features include primary microcephaly and profound global developmental delay. Our genetic studies identified biallelic mutations of PRUNE1 as responsible. Our functional assays of disease-associated variant alleles revealed impaired microtubule polymerization, as well as cell migration and proliferation properties, of mutant PRUNE. Additionally, our studies also highlight a potential new role for PRUNE during microtubule polymerization, which is essential for the cytoskeletal rearrangements that occur during cellular division and proliferation. Together these studies define PRUNE as a molecule fundamental for normal human cortical development and define cellular and clinical consequences associated with PRUNE mutation.
Keywords: Adolescent; Brain; Carrier Proteins; Cell Differentiation; Cell Movement; Cerebral Cortex; Child; Child, Preschool; Cytoskeleton; Developmental Disabilities; Female; Genes, Recessive; Heredodegenerative Disorders, Nervous System; Humans; Infant; Male; Microcephaly; Microtubules; Mutation; Pedigree; Young Adult

A Recurrent De Novo Variant in NACC1 Causes a Syndrome Characterized by Infantile Epilepsy, Cataracts, and Profound Developmental Delay. - Schoch, Kelly; Meng, Linyan; Szelinger, Szabolcs; Bearden, David R; Stray-Pedersen, Asbjorg; Busk, Oyvind L; Stong, Nicholas; Liston, Eriskay; Cohn, Ronald D; Scaglia, Fernando; Rosenfeld, Jill A; Tarpinian, Jennifer; et al. (Am J Hum Genet, 2017)
Whole-exome sequencing (WES) has increasingly enabled new pathogenic gene variant identification for undiagnosed neurodevelopmental disorders and provided insights into both gene function and disease biology. Here, we describe seven children with a neurodevelopmental disorder characterized by microcephaly, profound developmental delays and/or intellectual disability, cataracts, severe epilepsy including infantile spasms, irritability, failure to thrive, and stereotypic hand movements. Brain imaging in these individuals reveals delay in myelination and cerebral atrophy. We observe an identical recurrent de novo heterozygous c.892C>T (p.Arg298Trp) variant in the nucleus accumbens associated 1 (NACC1) gene in seven affected individuals. One of the seven individuals is mosaic for this variant. NACC1 encodes a transcriptional repressor implicated in gene expression and has not previously been associated with germline disorders. The probability of finding the same missense NACC1 variant by chance in 7 out of 17,228 individuals who underwent WES for diagnoses of neurodevelopmental phenotypes is extremely small and achieves genome-wide significance (p = 1.25 × 10). Selective constraint against missense variants in NACC1 makes this excess of an identical missense variant in all seven individuals more remarkable. Our findings are consistent with a germline recurrent mutational hotspot associated with an allele-specific neurodevelopmental phenotype in NACC1.
Keywords: Alleles; Amino Acid Sequence; Brain; Cataract; Child; Child, Preschool; Female; Genetic Variation; Genome-Wide Association Study; Humans; Infant; Intellectual Disability; Magnetic Resonance Imaging; Male; Microcephaly; Mutation, Missense; Neoplasm Proteins; Pedigree; Phenotype; Repressor Proteins; Spasms, Infantile

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

SLC13A5 is the second gene associated with Kohlschütter-Tönz syndrome. - Schossig, Anna; Bloch-Zupan, Agnès; Lussi, Adrian; Wolf, Nicole I; Raskin, Salmo; Cohen, Monika; Giuliano, Fabienne; Jurgens, Julie; Krabichler, Birgit; Koolen, David A; de Macena Sobreira, Nara Lygia; Maurer, Elisabeth; et al. (J Med Genet, 2017)
BACKGROUND: Kohlschütter-Tönz syndrome (KTZS) is a rare autosomal-recessive disease characterised by epileptic encephalopathy, intellectual disability and amelogenesis imperfecta (AI). It is frequently caused by biallelic mutations in ROGDI. Here, we report on individuals with ROGDI-negative KTZS carrying biallelic SLC13A5 mutations. METHODS: In the present cohort study, nine individuals from four families with the clinical diagnosis of KTZS and absence of ROGDI mutations as well as one patient with unexplained epileptic encephalopathy were investigated by clinical and dental evaluation, parametric linkage analysis (one family), and exome and/or Sanger sequencing. Dental histological investigations were performed on teeth from individuals with SLC13A5-associated and ROGDI-associated KTZS. RESULTS: Biallelic mutations in SLC13A5 were identified in 10 affected individuals. Epileptic encephalopathy usually presents in the neonatal and (less frequently) early infantile period. Yellowish to orange discolouration of both deciduous and permanent teeth, as well as wide interdental spaces and abnormal crown forms are major clinical signs of individuals with biallelic SLC13A5 mutations. Histological dental investigations confirmed the clinical diagnosis of hypoplastic AI. In comparison, the histological evaluation of a molar assessed from an individual with ROGDI-associated KTZS revealed hypocalcified AI. CONCLUSIONS: We conclude that SLC13A5 is the second major gene associated with the clinical diagnosis of KTZS, characterised by neonatal epileptic encephalopathy and hypoplastic AI. Careful clinical and dental delineation provides clues whether ROGDI or SLC13A5 is the causative gene. Hypersensitivity of teeth as well as high caries risk requires individual dental prophylaxis and attentive dental management.
Keywords: Alleles; Amelogenesis Imperfecta; Brain Diseases; Cohort Studies; Dementia; Epilepsy; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Mutation; Nuclear Proteins; Pedigree; Symporters; Tooth

SMCHD1 mutations associated with a rare muscular dystrophy can also cause isolated arhinia and Bosma arhinia microphthalmia syndrome. - Shaw, Natalie D; Brand, Harrison; Kupchinsky, Zachary A; Bengani, Hemant; Plummer, Lacey; Jones, Takako I; Erdin, Serkan; Williamson, Kathleen A; Rainger, Joe; Stortchevoi, Alexei; Samocha, Kaitlin; Currall, Benjamin B; et al. (Nat Genet, 2017)
Arhinia, or absence of the nose, is a rare malformation of unknown etiology that is often accompanied by ocular and reproductive defects. Sequencing of 40 people with arhinia revealed that 84% of probands harbor a missense mutation localized to a constrained region of SMCHD1 encompassing the ATPase domain. SMCHD1 mutations cause facioscapulohumeral muscular dystrophy type 2 (FSHD2) via a trans-acting loss-of-function epigenetic mechanism. We discovered shared mutations and comparable DNA hypomethylation patterning between these distinct disorders. CRISPR/Cas9-mediated alteration of smchd1 in zebrafish yielded arhinia-relevant phenotypes. Transcriptome and protein analyses in arhinia probands and controls showed no differences in SMCHD1 mRNA or protein abundance but revealed regulatory changes in genes and pathways associated with craniofacial patterning. Mutations in SMCHD1 thus contribute to distinct phenotypic spectra, from craniofacial malformation and reproductive disorders to muscular dystrophy, which we speculate to be consistent with oligogenic mechanisms resulting in pleiotropic outcomes.
Keywords: Adolescent; Child; Child, Preschool; Choanal Atresia; Chromosomal Proteins, Non-Histone; Female; Genetic Predisposition to Disease; Humans; Infant; Male; Microphthalmos; Muscular Dystrophies; Mutation; Nose; Phenotype

SVachra: a tool to identify genomic structural variation in mate pair sequencing data containing inward and outward facing reads. - Hampton, Oliver A; English, Adam C; Wang, Mark; Salerno, William J; Liu, Yue; Muzny, Donna M; Han, Yi; Wheeler, David A; Worley, Kim C; Lupski, James R; Gibbs, Richard A (BMC Genomics, 2017)
BACKGROUND: Characterization of genomic structural variation (SV) is essential to expanding the research and clinical applications of genome sequencing. Reliance upon short DNA fragment paired end sequencing has yielded a wealth of single nucleotide variants and internal sequencing read insertions-deletions, at the cost of limited SV detection. Multi-kilobase DNA fragment mate pair sequencing has supplemented the void in SV detection, but introduced new analytic challenges requiring SV detection tools specifically designed for mate pair sequencing data. Here, we introduce SVachra - Structural Variation Assessment of CHRomosomal Aberrations, a breakpoint calling program that identifies large insertions-deletions, inversions, inter- and intra-chromosomal translocations utilizing both inward and outward facing read types generated by mate pair sequencing. RESULTS: We demonstrate SVachra's utility by executing the program on large-insert (Illumina Nextera) mate pair sequencing data from the personal genome of a single subject (HS1011). An additional data set of long-read (Pacific BioSciences RSII) was also generated to validate SV calls from SVachra and other comparison SV calling programs. SVachra exhibited the highest validation rate and reported the widest distribution of SV types and size ranges when compared to other SV callers. CONCLUSIONS: SVachra is a highly specific breakpoint calling program that exhibits a more unbiased SV detection methodology than other callers.
Keywords: Genetic Variation; Genomics; Sequence Analysis, DNA

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Muzny, Donna M; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-Genome Sequencing of Cytogenetically Balanced Chromosome Translocations Identifies Potentially Pathological Gene Disruptions and Highlights the Importance of Microhomology in the Mechanism of Formation. - Nilsson, Daniel; Pettersson, Maria; Gustavsson, Peter; Förster, Alisa; Hofmeister, Wolfgang; Wincent, Josephine; Zachariadis, Vasilios; Anderlid, Britt-Marie; Nordgren, Ann; Mäkitie, Outi; Wirta, Valtteri; Käller, Max; et al. (Hum Mutat, 2017)
Most balanced translocations are thought to result mechanistically from nonhomologous end joining or, in rare cases of recurrent events, by nonallelic homologous recombination. Here, we use low-coverage mate pair whole-genome sequencing to fine map rearrangement breakpoint junctions in both phenotypically normal and affected translocation carriers. In total, 46 junctions from 22 carriers of balanced translocations were characterized. Genes were disrupted in 48% of the breakpoints; recessive genes in four normal carriers and known dominant intellectual disability genes in three affected carriers. Finally, seven candidate disease genes were disrupted in five carriers with neurocognitive disabilities (SVOPL, SUSD1, TOX, NCALD, SLC4A10) and one XX-male carrier with Tourette syndrome (LYPD6, GPC5). Breakpoint junction analyses revealed microhomology and small templated insertions in a substantive fraction of the analyzed translocations (17.4%; n = 4); an observation that was substantiated by reanalysis of 37 previously published translocation junctions. Microhomology associated with templated insertions is a characteristic seen in the breakpoint junctions of rearrangements mediated by error-prone replication-based repair mechanisms. Our data implicate that a mechanism involving template switching might contribute to the formation of at least 15% of the interchromosomal translocation events.
Keywords: Base Sequence; Chromosome Breakage; Chromosome Mapping; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Genetic Association Studies; Genomics; Genotype; Homologous Recombination; Humans; In Situ Hybridization, Fluorescence; Karyotype; Male; Phenotype; Translocation, Genetic; Whole Genome Sequencing

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Assessment of estimated retinal atrophy progression in Stargardt macular dystrophy using spectral-domain optical coherence tomography. - Strauss, Rupert W; Muñoz, Beatriz; Wolfson, Yulia; Sophie, Raafay; Fletcher, Emily; Bittencourt, Millena G; Scholl, Hendrik P N (Br J Ophthalmol, 2016)
AIMS: To estimate disease progression based on analysis of macular volume measured by spectral-domain optical coherence tomography (SD-OCT) in patients affected by Stargardt macular dystrophy (STGD1) and to evaluate the influence of software errors on these measurements. METHODS: 58 eyes of 29 STGD1 patients were included. Numbers and types of algorithm errors were recorded and manually corrected. In a subgroup of 36 eyes of 18 patients with at least two examinations over time, total macular volume (TMV) and volumes of all nine Early Treatment of Diabetic Retinopathy Study (ETDRS) subfields were obtained. Random effects models were used to estimate the rate of change per year for the population, and empirical Bayes slopes were used to estimate yearly decline in TMV for individual eyes. RESULTS: 6958 single B-scans from 190 macular cube scans were analysed. 2360 (33.9%) showed algorithm errors. Mean observation period for follow-up data was 15 months (range 3-40). The median (IQR) change in TMV using the empirical Bayes estimates for the individual eyes was -0.103 (-0.145, -0.059) mm per year. The mean (±SD) TMV was 6.321±1.000 mm at baseline, and rate of decline was -0.118 mm per year (p=0.003). Yearly mean volume change was -0.004 mm in the central subfield (mean baseline=0.128 mm), -0.032 mm in the inner (mean baseline=1.484 mm) and -0.079 mm in the outer ETDRS subfields (mean baseline=5.206 mm). CONCLUSIONS: SD-OCT measurements allow monitoring the decline in retinal volume in STGD1; however, they require significant manual correction of software errors.
Keywords: Adolescent; Adult; Aged; Child; Disease Progression; Female; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Reproducibility of Results; Retrospective Studies; Tomography, Optical Coherence; Visual Acuity; Young Adult

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Ataxia-Pancytopenia Syndrome Is Caused by Missense Mutations in SAMD9L. - Chen, Dong-Hui; Below, Jennifer E; Shimamura, Akiko; Keel, Sioban B; Matsushita, Mark; Wolff, John; Sul, Youngmee; Bonkowski, Emily; Castella, Maria; Taniguchi, Toshiyasu; Nickerson, Deborah; Papayannopoulou, Thalia; et al. (Am J Hum Genet, 2016)
Ataxia-pancytopenia (AP) syndrome is characterized by cerebellar ataxia, variable hematologic cytopenias, and predisposition to marrow failure and myeloid leukemia, sometimes associated with monosomy 7. Here, in the four-generation family UW-AP, linkage analysis revealed four regions that provided the maximal LOD scores possible, one of which was in a commonly microdeleted chromosome 7q region. Exome sequencing identified a missense mutation (c.2640C>A, p.His880Gln) in the sterile alpha motif domain containing 9-like gene (SAMD9L) that completely cosegregated with disease. By targeted sequencing of SAMD9L, we subsequently identified a different missense mutation (c.3587G>C, p.Cys1196Ser) in affected members of the first described family with AP syndrome, Li-AP. Neither variant is reported in the public databases, both affect highly conserved amino acid residues, and both are predicted to be damaging. With time in culture, lymphoblastic cell lines (LCLs) from two affected individuals in family UW-AP exhibited copy-neutral loss of heterozygosity for large portions of the long arm of chromosome 7, resulting in retention of only the wild-type SAMD9L allele. Newly established LCLs from both individuals demonstrated the same phenomenon. In addition, targeted capture and sequencing of SAMD9L in uncultured blood DNA from both individuals showed bias toward the wild-type allele. These observations indicate in vivo hematopoietic mosaicism. The hematopoietic cytopenias that characterize AP syndrome and the selective advantage for clones that have lost the mutant allele support the postulated role of SAMD9L in the regulation of cell proliferation. Furthermore, we show that AP syndrome is distinct from the dyskeratoses congenita telomeropathies, with which it shares some clinical characteristics.
Keywords: Adolescent; Adult; Cerebellar Ataxia; Child; Chromosome Aberrations; Chromosomes, Human, Pair 7; Exome; Female; Genetic Linkage; Genotype; High-Throughput Nucleotide Sequencing; Humans; Intracellular Signaling Peptides and Proteins; Loss of Heterozygosity; Male; Middle Aged; Mutation, Missense; Pancytopenia; Pedigree; Proteins; Tumor Suppressor Proteins; Young Adult

Autosomal-Recessive Hearing Impairment Due to Rare Missense Variants within S1PR2. - Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Ansar, Muhammad; Wang, Xin; Morell, Robert J; Isaacson, Rivka; Belyantseva, Inna A; Dai, Hang; Acharya, Anushree; Qaiser, Tanveer A; et al. (Am J Hum Genet, 2016)
The sphingosine-1-phosphate receptors (S1PRs) are a well-studied class of transmembrane G protein-coupled sphingolipid receptors that mediate multiple cellular processes. However, S1PRs have not been previously reported to be involved in the genetic etiology of human traits. S1PR2 lies within the autosomal-recessive nonsyndromic hearing impairment (ARNSHI) locus DFNB68 on 19p13.2. From exome sequence data we identified two pathogenic S1PR2 variants, c.323G>C (p.Arg108Pro) and c.419A>G (p.Tyr140Cys). Each of these variants co-segregates with congenital profound hearing impairment in consanguineous Pakistani families with maximum LOD scores of 6.4 for family DEM4154 and 3.3 for family PKDF1400. Neither S1PR2 missense variant was reported among ∼120,000 chromosomes in the Exome Aggregation Consortium database, in 76 unrelated Pakistani exomes, or in 720 Pakistani control chromosomes. Both DNA variants affect highly conserved residues of S1PR2 and are predicted to be damaging by multiple bioinformatics tools. Molecular modeling predicts that these variants affect binding of sphingosine-1-phosphate (p.Arg108Pro) and G protein docking (p.Tyr140Cys). In the previously reported S1pr2(-/-) mice, stria vascularis abnormalities, organ of Corti degeneration, and profound hearing loss were observed. Additionally, hair cell defects were seen in both knockout mice and morphant zebrafish. Family PKDF1400 presents with ARNSHI, which is consistent with the lack of gross malformations in S1pr2(-/-) mice, whereas family DEM4154 has lower limb malformations in addition to hearing loss. Our findings suggest the possibility of developing therapies against hair cell damage (e.g., from ototoxic drugs) through targeted stimulation of S1PR2.
Keywords: Amino Acid Sequence; Asian Continental Ancestry Group; Chromosomes, Human, Pair 19; Exome; Genes, Recessive; Hearing Loss; Humans; Lod Score; Logistic Models; Lysophospholipids; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype; Receptors, Lysosphingolipid; Sphingosine

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

Chimeric transcripts resulting from complex duplications in chromosome Xq28. - Zuccherato, Luciana W; Alleva, Benjamin; Whiters, Marjorie A; Carvalho, Claudia M B; Lupski, James R (Hum Genet, 2016)
Gene fusions have been observed in somatic alterations in cancer and in schizophrenia. However, the underlying mechanism(s) for their formation are poorly understood. We experimentally demonstrated the expression of splicing variants of in silico predicted chimeric genes F8/CSAG1 and BCAP31/TEX28 in two individuals with de novo complex genomic rearrangements of Xq28; F8/CSAG1 includes exonization of an ERVL-MaLR intronic repetitive element. We provide evidence that replicative repair may contribute to exon shuffling processes and diversify the repertoire of expressed transcripts.
Keywords: Antigens, Neoplasm; Base Sequence; Cell Line; Chromosomes, Human, X; Exons; Gene Duplication; Gene Expression Regulation; Gene Rearrangement; Humans; Introns; Male; Membrane Proteins; Molecular Sequence Data; Neoplasm Proteins; RNA Splicing; RNA, Messenger; Transcription, Genetic

The ciliopathy-associated CPLANE proteins direct basal body recruitment of intraflagellar transport machinery. - Toriyama, Michinori; Lee, Chanjae; Taylor, S Paige; Duran, Ivan; Cohn, Daniel H; Bruel, Ange-Line; Tabler, Jacqueline M; Drew, Kevin; Kelly, Marcus R; Kim, Sukyoung; Park, Tae Joo; Braun, Daniela A; et al. (Nat Genet, 2016)
Cilia use microtubule-based intraflagellar transport (IFT) to organize intercellular signaling. Ciliopathies are a spectrum of human diseases resulting from defects in cilia structure or function. The mechanisms regulating the assembly of ciliary multiprotein complexes and the transport of these complexes to the base of cilia remain largely unknown. Combining proteomics, in vivo imaging and genetic analysis of proteins linked to planar cell polarity (Inturned, Fuzzy and Wdpcp), we identified and characterized a new genetic module, which we term CPLANE (ciliogenesis and planar polarity effector), and an extensive associated protein network. CPLANE proteins physically and functionally interact with the poorly understood ciliopathy-associated protein Jbts17 at basal bodies, where they act to recruit a specific subset of IFT-A proteins. In the absence of CPLANE, defective IFT-A particles enter the axoneme and IFT-B trafficking is severely perturbed. Accordingly, mutation of CPLANE genes elicits specific ciliopathy phenotypes in mouse models and is associated with ciliopathies in human patients.
Keywords: Animals; Ciliopathies; Flagella; Humans; Mice; Mutation; Phenotype; Protein Binding; Protein Transport; Proteins

Comparison of Short-Wavelength Reduced-Illuminance and Conventional Autofluorescence Imaging in Stargardt Macular Dystrophy. - Strauss, Rupert W; Muñoz, Beatriz; Jha, Anamika; Ho, Alexander; Cideciyan, Artur V; Kasilian, Melissa L; Wolfson, Yulia; Sadda, SriniVas; West, Sheila; Scholl, Hendrik P N; Michaelides, Michel (Am J Ophthalmol, 2016)
PURPOSE: To compare grading results between short-wavelength reduced-illuminance and conventional autofluorescence imaging in Stargardt macular dystrophy. DESIGN: Reliability study. METHODS: setting: Moorfields Eye Hospital, London (United Kingdom). PATIENTS: Eighteen patients (18 eyes) with Stargardt macular dystrophy. OBSERVATION PROCEDURES: A series of 3 fundus autofluorescence images using 3 different acquisition parameters on a custom-patched device were obtained: (1) 25% laser power and total sensitivity 87; (2) 25% laser power and freely adjusted sensitivity; and (3) 100% laser power and freely adjusted total sensitivity (conventional). The total area of 2 hypoautofluorescent lesion types (definitely decreased autofluorescence and poorly demarcated questionably decreased autofluorescence) was measured. MAIN OUTCOME MEASURES: Agreement in grading between the 3 imaging methods was assessed by kappa coefficients (κ) and intraclass correlation coefficients. RESULTS: The mean ± standard deviation area for images acquired with 25% laser power and freely adjusted total sensitivity was 2.04 ± 1.87 mm(2) for definitely decreased autofluorescence (n = 15) and 1.86 ± 2.14 mm(2) for poorly demarcated questionably decreased autofluorescence (n = 12). The intraclass correlation coefficient (95% confidence interval) was 0.964 (0.929, 0.999) for definitely decreased autofluorescence and 0.268 (0.000, 0.730) for poorly demarcated questionably decreased autofluorescence. CONCLUSIONS: Short-wavelength reduced-illuminance and conventional fundus autofluorescence imaging showed good concordance in assessing areas of definitely decreased autofluorescence. However, there was significantly higher variability between imaging modalities for assessing areas of poorly demarcated questionably decreased autofluorescence.
Keywords: Adult; Female; Fluorescein Angiography; Fundus Oculi; Humans; Macula Lutea; Macular Degeneration; Male; Middle Aged; Ophthalmoscopy; Optical Imaging; Reproducibility of Results; Stargardt Disease

Copy-Number Variation Contributes to the Mutational Load of Bardet-Biedl Syndrome. - Lindstrand, Anna; Frangakis, Stephan; Carvalho, Claudia M B; Richardson, Ellen B; McFadden, Kelsey A; Willer, Jason R; Pehlivan, Davut; Liu, Pengfei; Pediaditakis, Igor L; Sabo, Aniko; Lewis, Richard Alan; Banin, Eyal; et al. (Am J Hum Genet, 2016)
Bardet-Biedl syndrome (BBS) is a defining ciliopathy, notable for extensive allelic and genetic heterogeneity, almost all of which has been identified through sequencing. Recent data have suggested that copy-number variants (CNVs) also contribute to BBS. We used a custom oligonucleotide array comparative genomic hybridization (aCGH) covering 20 genes that encode intraflagellar transport (IFT) components and 74 ciliopathy loci to screen 92 unrelated individuals with BBS, irrespective of their known mutational burden. We identified 17 individuals with exon-disruptive CNVs (18.5%), including 13 different deletions in eight BBS genes (BBS1, BBS2, ARL6/BBS3, BBS4, BBS5, BBS7, BBS9, and NPHP1) and a deletion and a duplication in other ciliopathy-associated genes (ALMS1 and NPHP4, respectively). By contrast, we found a single heterozygous exon-disruptive event in a BBS-associated gene (BBS9) in 229 control subjects. Superimposing these data with resequencing revealed CNVs to (1) be sufficient to cause disease, (2) Mendelize heterozygous deleterious alleles, and (3) contribute oligogenic alleles by combining point mutations and exonic CNVs in multiple genes. Finally, we report a deletion and a splice site mutation in IFT74, inherited under a recessive paradigm, defining a candidate BBS locus. Our data suggest that CNVs contribute pathogenic alleles to a substantial fraction of BBS-affected individuals and highlight how either deletions or point mutations in discrete splice isoforms can induce hypomorphic mutations in genes otherwise intolerant to deleterious variation. Our data also suggest that CNV analyses and resequencing studies unbiased for previous mutational burden is necessary to delineate the complexity of disease architecture.
Keywords: Adolescent; Adult; Alleles; Animals; Bardet-Biedl Syndrome; Child; Child, Preschool; Chromosome Breakpoints; Cytoskeletal Proteins; DNA Copy Number Variations; Exons; Female; Gastrulation; Genes, Recessive; Humans; Infant; Male; Mutation; Pedigree; Young Adult; Zebrafish; Zebrafish Proteins

De Novo and Rare Variants at Multiple Loci Support the Oligogenic Origins of Atrioventricular Septal Heart Defects. - Priest, James R; Osoegawa, Kazutoyo; Mohammed, Nebil; Nanda, Vivek; Kundu, Ramendra; Schultz, Kathleen; Lammer, Edward J; Girirajan, Santhosh; Scheetz, Todd; Waggott, Daryl; Haddad, Francois; Reddy, Sushma; et al. (PLoS Genet, 2016)
Congenital heart disease (CHD) has a complex genetic etiology, and recent studies suggest that high penetrance de novo mutations may account for only a small fraction of disease. In a multi-institutional cohort surveyed by exome sequencing, combining analysis of 987 individuals (discovery cohort of 59 affected trios and 59 control trios, and a replication cohort of 100 affected singletons and 533 unaffected singletons) we observe variation at novel and known loci related to a specific cardiac malformation the atrioventricular septal defect (AVSD). In a primary analysis, by combining developmental coexpression networks with inheritance modeling, we identify a de novo mutation in the DNA binding domain of NR1D2 (p.R175W). We show that p.R175W changes the transcriptional activity of Nr1d2 using an in vitro transactivation model in HUVEC cells. Finally, we demonstrate previously unrecognized cardiovascular malformations in the Nr1d2tm1-Dgen knockout mouse. In secondary analyses we map genetic variation to protein-interaction networks suggesting a role for two collagen genes in AVSD, which we corroborate by burden testing in a second replication cohort of 100 AVSDs and 533 controls (p = 8.37e-08). Finally, we apply a rare-disease inheritance model to identify variation in genes previously associated with CHD (ZFPM2, NSD1, NOTCH1, VCAN, and MYH6), cardiac malformations in mouse models (ADAM17, CHRD, IFT140, PTPRJ, RYR1 and ATE1), and hypomorphic alleles of genes causing syndromic CHD (EHMT1, SRCAP, BBS2, NOTCH2, and KMT2D) in 14 of 59 trios, greatly exceeding variation in control trios without CHD (p = 9.60e-06). In total, 32% of trios carried at least one putatively disease-associated variant across 19 loci,suggesting that inherited and de novo variation across a heterogeneous group of loci may contribute to disease risk.
Keywords: Animals; Female; Heart Septal Defects; Heterozygote; Homozygote; Humans; Male; Mice; Mice, Knockout; Mutation; Pedigree

De novo missense variants in PPP1CB are associated with intellectual disability and congenital heart disease. - Ma, Lijiang; Bayram, Yavuz; McLaughlin, Heather M; Cho, Megan T; Krokosky, Alyson; Turner, Clesson E; Lindstrom, Kristin; Bupp, Caleb P; Mayberry, Katey; Mu, Weiyi; Bodurtha, Joann; Weinstein, Veronique; et al. (Hum Genet, 2016)
Intellectual disabilities are genetically heterogeneous and can be associated with congenital anomalies. Using whole-exome sequencing (WES), we identified five different de novo missense variants in the protein phosphatase-1 catalytic subunit beta (PPP1CB) gene in eight unrelated individuals who share an overlapping phenotype of dysmorphic features, macrocephaly, developmental delay or intellectual disability (ID), congenital heart disease, short stature, and skeletal and connective tissue abnormalities. Protein phosphatase-1 (PP1) is a serine/threonine-specific protein phosphatase involved in the dephosphorylation of a variety of proteins. The PPP1CB gene encodes a PP1 subunit that regulates the level of protein phosphorylation. All five altered amino acids we observed are highly conserved among the PP1 subunit family, and all are predicted to disrupt PP1 subunit binding and impair dephosphorylation. Our data suggest that our heterozygous de novo PPP1CB pathogenic variants are associated with syndromic intellectual disability.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Defects, Congenital; Humans; Intellectual Disability; Male; Mutation, Missense; Phosphorylation; Protein Phosphatase 1

De Novo Mutations in SON Disrupt RNA Splicing of Genes Essential for Brain Development and Metabolism, Causing an Intellectual-Disability Syndrome. - Kim, Jung-Hyun; Shinde, Deepali N; Reijnders, Margot R F; Hauser, Natalie S; Belmonte, Rebecca L; Wilson, Gregory R; Bosch, Daniëlle G M; Bubulya, Paula A; Shashi, Vandana; Petrovski, Slavé; Stone, Joshua K; Park, Eun Young; et al. (Am J Hum Genet, 2016)
The overall understanding of the molecular etiologies of intellectual disability (ID) and developmental delay (DD) is increasing as next-generation sequencing technologies identify genetic variants in individuals with such disorders. However, detailed analyses conclusively confirming these variants, as well as the underlying molecular mechanisms explaining the diseases, are often lacking. Here, we report on an ID syndrome caused by de novo heterozygous loss-of-function (LoF) mutations in SON. The syndrome is characterized by ID and/or DD, malformations of the cerebral cortex, epilepsy, vision problems, musculoskeletal abnormalities, and congenital malformations. Knockdown of son in zebrafish resulted in severe malformation of the spine, brain, and eyes. Importantly, analyses of RNA from affected individuals revealed that genes critical for neuronal migration and cortex organization (TUBG1, FLNA, PNKP, WDR62, PSMD3, and HDAC6) and metabolism (PCK2, PFKL, IDH2, ACY1, and ADA) are significantly downregulated because of the accumulation of mis-spliced transcripts resulting from erroneous SON-mediated RNA splicing. Our data highlight SON as a master regulator governing neurodevelopment and demonstrate the importance of SON-mediated RNA splicing in human development.
Keywords: Animals; Brain; Developmental Disabilities; DNA-Binding Proteins; Eye Abnormalities; Female; Genes, Essential; Haploinsufficiency; Head; Heterozygote; Humans; Intellectual Disability; Male; Metabolic Diseases; Minor Histocompatibility Antigens; Mutation; Pedigree; RNA Splicing; RNA, Messenger; Spine; Syndrome; Zebrafish

Disrupted nitric oxide signaling due to GUCY1A3 mutations increases risk for moyamoya disease, achalasia and hypertension. - Wallace, S; Guo, D-C; Regalado, E; Mellor-Crummey, L; Bamshad, M; Nickerson, D A; Dauser, R; Hanchard, N; Marom, R; Martin, E; Berka, V; Sharina, I; et al. (Clin Genet, 2016)
Moyamoya disease (MMD) is a progressive vasculopathy characterized by occlusion of the terminal portion of the internal carotid arteries and its branches, and the formation of compensatory moyamoya collateral vessels. Homozygous mutations in GUCY1A3 have been reported as a cause of MMD and achalasia. Probands (n = 96) from unrelated families underwent sequencing of GUCY1A3. Functional studies were performed to confirm the pathogenicity of identified GUCY1A3 variants. Two affected individuals from the unrelated families were found to have compound heterozygous mutations in GUCY1A3. MM041 was diagnosed with achalasia at 4 years of age, hypertension and MMD at 18 years of age. MM149 was diagnosed with MMD and hypertension at the age of 20 months. Both individuals carry one allele that is predicted to lead to haploinsufficiency and a second allele that is predicted to produce a mutated protein. Biochemical studies of one of these alleles, GUCY1A3 Cys517Tyr, showed that the mutant protein (a subunit of soluble guanylate cyclase) has a significantly blunted signaling response with exposure to nitric oxide (NO). GUCY1A3 missense and haploinsufficiency mutations disrupt NO signaling leading to MMD and hypertension, with or without achalasia.
Keywords: Adolescent; Adult; Animals; Child; Child, Preschool; Cohort Studies; Esophageal Achalasia; Female; Humans; Hypertension; Infant; Male; Middle Aged; Moyamoya Disease; Mutation; Nitric Oxide; Nonlinear Dynamics; Regression Analysis; Sf9 Cells; Signal Transduction; Soluble Guanylyl Cyclase

Dominant de novo DSP mutations cause erythrokeratodermia-cardiomyopathy syndrome. - Boyden, Lynn M; Kam, Chen Y; Hernández-Martín, Angela; Zhou, Jing; Craiglow, Brittany G; Sidbury, Robert; Mathes, Erin F; Maguiness, Sheilagh M; Crumrine, Debra A; Williams, Mary L; Hu, Ronghua; Lifton, Richard P; et al. (Hum Mol Genet, 2016)
Disorders of keratinization (DOK) show marked genotypic and phenotypic heterogeneity. In most cases, disease is primarily cutaneous, and further clinical evaluation is therefore rarely pursued. We have identified subjects with a novel DOK featuring erythrokeratodermia and initially-asymptomatic, progressive, potentially fatal cardiomyopathy, a finding not previously associated with erythrokeratodermia. We show that de novo missense mutations clustered tightly within a single spectrin repeat of DSP cause this novel cardio-cutaneous disorder, which we term erythrokeratodermia-cardiomyopathy (EKC) syndrome. We demonstrate that DSP mutations in our EKC syndrome subjects affect localization of desmosomal proteins and connexin 43 in the skin, and result in desmosome aggregation, widening of intercellular spaces, and lipid secretory defects. DSP encodes desmoplakin, a primary component of desmosomes, intercellular adhesion junctions most abundant in the epidermis and heart. Though mutations in DSP are known to cause other disorders, our cohort features the unique clinical finding of severe whole-body erythrokeratodermia, with distinct effects on localization of desmosomal proteins and connexin 43. These findings add a severe, previously undescribed syndrome featuring erythrokeratodermia and cardiomyopathy to the spectrum of disease caused by mutation in DSP, and identify a specific region of the protein critical to the pathobiology of EKC syndrome and to DSP function in the heart and skin.
Keywords: Amino Acid Sequence; Cardiomyopathies; Child; Child, Preschool; Connexin 43; Desmoplakins; Desmosomes; Female; Humans; Infant; Male; Molecular Sequence Data; Mutation, Missense; Myocardium; Protein Transport; Sequence Alignment; Skin; Skin Diseases, Genetic; Syndrome

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Evidence of macular pigment in the central macula in albinism. - Wolfson, Yulia; Fletcher, Emily; Strauss, Rupert W; Scholl, Hendrik P N (Exp Eye Res, 2016)
PURPOSE: Albinism represents a spectrum of disorders with diminished to absent amounts of melanin pigmentation including the posterior segment of the eye. Macular pigment (MP) consists of two main carotenoids, lutein and zeaxanthin, concentrated in the macula. MP serves as blue light absorbent, antioxidant, and may reduce chromatic aberration and glare. It remains unclear if albinos have detectable MP. The purpose was to investigate the distribution of MP in albino patients with psychophysical and imaging techniques. METHODS: MP was measured at the eccentricity of 0.5° by heterochromatic flicker perimetry (QuantifEye(®); Tinsley Precision Instruments Ltd.) or by scanning laser ophthalmoscopy (MPOD module, MultiColor Spectralis(®), Heidelberg Engineering, Heidelberg, Germany) in four albino patients, who were also investigated with multimodal ophthalmic imaging. RESULTS: Visual acuity ranged from 20/32 to 20/125, nystagmus was present in three patients, and all patients showed typical foveal hypoplasia on fundus exam and optical coherence tomography. Fundus autofluorescence (FAF) demonstrated various degrees of central FAF signal attenuation. Genetic testing was available in three patients and confirmed the diagnosis. Measurable amounts of MP were detected in all four patients and ranged from 0.05 to 0.24, which is below the normal range. CONCLUSIONS: We conclude that MP can be demonstrated and measured in albinos. Further studies are needed to investigate MP accumulation following carotenoid supplementation and its impact on visual performance.
Keywords: Adult; Aged; Albinism, Ocular; Fluorescein Angiography; Humans; Macula Lutea; Macular Pigment; Male; Middle Aged; Tomography, Optical Coherence; Visual Acuity; Visual Field Tests; Visual Fields

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

Family Based Whole Exome Sequencing Reveals the Multifaceted Role of Notch Signaling in Congenital Heart Disease. - Preuss, Christoph; Capredon, Melanie; Wünnemann, Florian; Chetaille, Philippe; Prince, Andrea; Godard, Beatrice; Leclerc, Severine; Sobreira, Nara; Ling, Hua; Awadalla, Philip; Thibeault, Maryse; Khairy, Paul; et al. (PLoS Genet, 2016)
Left-ventricular outflow tract obstructions (LVOTO) encompass a wide spectrum of phenotypically heterogeneous heart malformations which frequently cluster in families. We performed family based whole-exome and targeted re-sequencing on 182 individuals from 51 families with multiple affected members. Central to our approach is the family unit which serves as a reference to identify causal genotype-phenotype correlations. Screening a multitude of 10 overlapping phenotypes revealed disease associated and co-segregating variants in 12 families. These rare or novel protein altering mutations cluster predominantly in genes (NOTCH1, ARHGAP31, MAML1, SMARCA4, JARID2, JAG1) along the Notch signaling cascade. This is in line with a significant enrichment (Wilcoxon, p< 0.05) of variants with a higher pathogenicity in the Notch signaling pathway in patients compared to controls. The significant enrichment of novel protein truncating and missense mutations in NOTCH1 highlights the allelic and phenotypic heterogeneity in our pediatric cohort. We identified novel co-segregating pathogenic mutations in NOTCH1 associated with left and right-sided cardiac malformations in three independent families with a total of 15 affected individuals. In summary, our results suggest that a small but highly pathogenic fraction of family specific mutations along the Notch cascade are a common cause of LVOTO.
Keywords: Aortic Valve; Codon, Nonsense; Constriction, Pathologic; Exome; Female; Genetic Association Studies; Genetic Linkage; Genome, Human; Heart Defects, Congenital; Humans; Male; Pedigree; Receptor, Notch1; Receptors, Notch; Sequence Deletion; Signal Transduction; Ventricular Outflow Obstruction

Family-Based Rare Variant Association Analysis: A Fast and Efficient Method of Multivariate Phenotype Association Analysis. - Wang, Longfei; Lee, Sungyoung; Gim, Jungsoo; Qiao, Dandi; Cho, Michael; Elston, Robert C; Silverman, Edwin K; Won, Sungho (Genet Epidemiol, 2016)
Family-based designs have been repeatedly shown to be powerful in detecting the significant rare variants associated with human diseases. Furthermore, human diseases are often defined by the outcomes of multiple phenotypes, and thus we expect multivariate family-based analyses may be very efficient in detecting associations with rare variants. However, few statistical methods implementing this strategy have been developed for family-based designs. In this report, we describe one such implementation: the multivariate family-based rare variant association tool (mFARVAT). mFARVAT is a quasi-likelihood-based score test for rare variant association analysis with multiple phenotypes, and tests both homogeneous and heterogeneous effects of each variant on multiple phenotypes. Simulation results show that the proposed method is generally robust and efficient for various disease models, and we identify some promising candidate genes associated with chronic obstructive pulmonary disease. The software of mFARVAT is freely available at http://healthstat.snu.ac.kr/software/mfarvat/, implemented in C++ and supported on Linux and MS Windows.
Keywords: Computer Simulation; Genetic Association Studies; Genetic Variation; Humans; Likelihood Functions; Models, Genetic; Phenotype

FARVATX: Family-Based Rare Variant Association Test for X-Linked Genes. - Choi, Sungkyoung; Lee, Sungyoung; Qiao, Dandi; Hardin, Megan; Cho, Michael H; Silverman, Edwin K; Park, Taesung; Won, Sungho (Genet Epidemiol, 2016)
Although the X chromosome has many genes that are functionally related to human diseases, the complicated biological properties of the X chromosome have prevented efficient genetic association analyses, and only a few significantly associated X-linked variants have been reported for complex traits. For instance, dosage compensation of X-linked genes is often achieved via the inactivation of one allele in each X-linked variant in females; however, some X-linked variants can escape this X chromosome inactivation. Efficient genetic analyses cannot be conducted without prior knowledge about the gene expression process of X-linked variants, and misspecified information can lead to power loss. In this report, we propose new statistical methods for rare X-linked variant genetic association analysis of dichotomous phenotypes with family-based samples. The proposed methods are computationally efficient and can complete X-linked analyses within a few hours. Simulation studies demonstrate the statistical efficiency of the proposed methods, which were then applied to rare-variant association analysis of the X chromosome in chronic obstructive pulmonary disease. Some promising significant X-linked genes were identified, illustrating the practical importance of the proposed methods.
Keywords: Alleles; Chromosomes, Human, X; Female; Genes, X-Linked; Genetic Variation; Humans; Models, Genetic; Pedigree; Phenotype; X Chromosome Inactivation

FAT1 mutations cause a glomerulotubular nephropathy. - Gee, Heon Yung; Sadowski, Carolin E; Aggarwal, Pardeep K; Porath, Jonathan D; Yakulov, Toma A; Schueler, Markus; Lovric, Svjetlana; Ashraf, Shazia; Braun, Daniela A; Halbritter, Jan; Fang, Humphrey; Airik, Rannar; et al. (Nat Commun, 2016)
Steroid-resistant nephrotic syndrome (SRNS) causes 15% of chronic kidney disease (CKD). Here we show that recessive mutations in FAT1 cause a distinct renal disease entity in four families with a combination of SRNS, tubular ectasia, haematuria and facultative neurological involvement. Loss of FAT1 results in decreased cell adhesion and migration in fibroblasts and podocytes and the decreased migration is partially reversed by a RAC1/CDC42 activator. Podocyte-specific deletion of Fat1 in mice induces abnormal glomerular filtration barrier development, leading to podocyte foot process effacement. Knockdown of Fat1 in renal tubular cells reduces migration, decreases active RAC1 and CDC42, and induces defects in lumen formation. Knockdown of fat1 in zebrafish causes pronephric cysts, which is partially rescued by RAC1/CDC42 activators, confirming a role of the two small GTPases in the pathogenesis. These findings provide new insights into the pathogenesis of SRNS and tubulopathy, linking FAT1 and RAC1/CDC42 to podocyte and tubular cell function.
Keywords: Animals; Cadherins; cdc42 GTP-Binding Protein; Cell Adhesion; Cell Movement; Dilatation, Pathologic; Fibroblasts; Gene Knockdown Techniques; Hematuria; Humans; Kidney Tubules; Lissencephaly; Mice; Mutation; Nephrotic Syndrome; Podocytes; rac1 GTP-Binding Protein; Syndrome; Zebrafish; Zebrafish Proteins

Genetic Candidate Variants in Two Multigenerational Families with Childhood Apraxia of Speech. - Peter, Beate; Wijsman, Ellen M; Nato, Alejandro Q; Matsushita, Mark M; Chapman, Kathy L; Stanaway, Ian B; Wolff, John; Oda, Kaori; Gabo, Virginia B; Raskind, Wendy H (PLoS One, 2016)
Childhood apraxia of speech (CAS) is a severe and socially debilitating form of speech sound disorder with suspected genetic involvement, but the genetic etiology is not yet well understood. Very few known or putative causal genes have been identified to date, e.g., FOXP2 and BCL11A. Building a knowledge base of the genetic etiology of CAS will make it possible to identify infants at genetic risk and motivate the development of effective very early intervention programs. We investigated the genetic etiology of CAS in two large multigenerational families with familial CAS. Complementary genomic methods included Markov chain Monte Carlo linkage analysis, copy-number analysis, identity-by-descent sharing, and exome sequencing with variant filtering. No overlaps in regions with positive evidence of linkage between the two families were found. In one family, linkage analysis detected two chromosomal regions of interest, 5p15.1-p14.1, and 17p13.1-q11.1, inherited separately from the two founders. Single-point linkage analysis of selected variants identified CDH18 as a primary gene of interest and additionally, MYO10, NIPBL, GLP2R, NCOR1, FLCN, SMCR8, NEK8, and ANKRD12, possibly with additive effects. Linkage analysis in the second family detected five regions with LOD scores approaching the highest values possible in the family. A gene of interest was C4orf21 (ZGRF1) on 4q25-q28.2. Evidence for previously described causal copy-number variations and validated or suspected genes was not found. Results are consistent with a heterogeneous CAS etiology, as is expected in many neurogenic disorders. Future studies will investigate genome variants in these and other families with CAS.
Keywords: Apraxias; DNA Copy Number Variations; Exome; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Humans; Lod Score; Male; Pedigree; Risk; Speech

A genome-wide association study of congenital cardiovascular left-sided lesions shows association with a locus on chromosome 20. - Hanchard, Neil A; Swaminathan, Shanker; Bucasas, Kristine; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid S; Wang, Xueqing; Lewin, Mark; Towbin, Jeffrey A; D'Alessandro, Lisa C A; Morris, Shaine A; Dreyer, William; et al. (Hum Mol Genet, 2016)
Congenital heart defects involving left-sided lesions (LSLs) are relatively common birth defects with substantial morbidity and mortality. Previous studies have suggested a high heritability with a complex genetic architecture, such that only a few LSL loci have been identified. We performed a genome-wide case-control association study to address the role of common variants using a discovery cohort of 778 cases and 2756 controls. We identified a genome-wide significant association mapping to a 200 kb region on chromosome 20q11 [P= 1.72 × 10 for rs3746446; imputed Single Nucleotide Polymorphism (SNP) rs6088703 P= 3.01 × 10, odds ratio (OR)= 1.6 for both]. This result was supported by transmission disequilibrium analyses using a subset of 541 case families (lowest P in region= 4.51 × 10, OR= 1.5). Replication in a cohort of 367 LSL cases and 5159 controls showed nominal association (P= 0.03 for rs3746446) resulting in P= 9.49 × 10 for rs3746446 upon meta-analysis of the combined cohorts. In addition, a group of seven SNPs on chromosome 1q21.3 met threshold for suggestive association (lowest P= 9.35 × 10 for rs12045807). Both regions include genes involved in cardiac development-MYH7B/miR499A on chromosome 20 and CTSK, CTSS and ARNT on chromosome 1. Genome-wide heritability analysis using case-control genotyped SNPs suggested that the mean heritability of LSLs attributable to common variants is moderately high ([Formula: see text] range= 0.26-0.34) and consistent with previous assertions. These results provide evidence for the role of common variation in LSLs, proffer new genes as potential biological candidates, and give further insight to the complex genetic architecture of congenital heart disease.
Keywords: Chromosome Mapping; Chromosomes, Human, Pair 20; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Defects, Congenital; Heart Ventricles; Humans; Male; Polymorphism, Single Nucleotide

Germline De Novo Mutations in GNB1 Cause Severe Neurodevelopmental Disability, Hypotonia, and Seizures. - Petrovski, Slavé; Küry, Sébastien; Myers, Candace T; Anyane-Yeboa, Kwame; Cogné, Benjamin; Bialer, Martin; Xia, Fan; Hemati, Parisa; Riviello, James; Mehaffey, Michele; Besnard, Thomas; Becraft, Emily; et al. (Am J Hum Genet, 2016)
Whole-exome sequencing of 13 individuals with developmental delay commonly accompanied by abnormal muscle tone and seizures identified de novo missense mutations enriched within a sub-region of GNB1, a gene encoding the guanine nucleotide-binding protein subunit beta-1, Gβ. These 13 individuals were identified among a base of 5,855 individuals recruited for various undiagnosed genetic disorders. The probability of observing 13 or more de novo mutations by chance among 5,855 individuals is very low (p = 7.1 × 10(-21)), implicating GNB1 as a genome-wide-significant disease-associated gene. The majority of these 13 mutations affect known Gβ binding sites, which suggests that a likely disease mechanism is through the disruption of the protein interface required for Gα-Gβγ interaction (resulting in a constitutively active Gβγ) or through the disruption of residues relevant for interaction between Gβγ and certain downstream effectors (resulting in reduced interaction with the effectors). Strikingly, 8 of the 13 individuals recruited here for a neurodevelopmental disorder have a germline de novo GNB1 mutation that overlaps a set of five recurrent somatic tumor mutations for which recent functional studies demonstrated a gain-of-function effect due to constitutive activation of G protein downstream signaling cascades for some of the affected residues.
Keywords: Adolescent; Adult; Child; Child, Preschool; Developmental Disabilities; Exome; Female; Germ-Line Mutation; GTP-Binding Protein beta Subunits; Humans; Infant; Intellectual Disability; Male; Muscle Hypotonia; Phenotype; Protein Conformation; Seizures; Signal Transduction; Young Adult

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Yuan, Bo; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Walker, Kimberly; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

Identification and clinical characterization of Hermansky-Pudlak syndrome alleles in the Pakistani population. - Yousaf, Sairah; Shahzad, Mohsin; Kausar, Tasleem; Sheikh, Shakeel A; Tariq, Nabeela; Shabbir, Asra S; Ali, Muhammad; Waryah, Ali M; Shaikh, Rehan S; Riazuddin, Saima; Ahmed, Zubair M (Pigment Cell Melanoma Res, 2016)
Keywords: Adolescent; Adult; Alleles; Child; Child, Preschool; Female; Hermanski-Pudlak Syndrome; Humans; Infant; Male; Membrane Proteins; Middle Aged; Pakistan; Pedigree

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

KIF5A mutations cause an infantile onset phenotype including severe myoclonus with evidence of mitochondrial dysfunction. - Duis, Jessica; Dean, Shannon; Applegate, Carolyn; Harper, Amy; Xiao, Rui; He, Weimin; Dollar, James D; Sun, Lisa R; Waberski, Marta Biderman; Crawford, Thomas O; Hamosh, Ada; Stafstrom, Carl E (Ann Neurol, 2016)
Missense mutations in kinesin family member 5A (KIF5A) cause spastic paraplegia 10. We report on 2 patients with de novo stop-loss frameshift variants in KIF5A resulting in a novel phenotype that includes severe infantile onset myoclonus, hypotonia, optic nerve abnormalities, dysphagia, apnea, and early developmental arrest. We propose that alteration and elongation of the carboxy-terminus of the protein has a dominant-negative effect, causing mitochondrial dysfunction in the setting of an abnormal kinesin "motor." These results highlight the role of expanded testing and whole-exome sequencing in critically ill infants and emphasize the importance of accurate test interpretation. Ann Neurol 2016;80:633-637.
Keywords: Apnea; Child, Preschool; Deglutition Disorders; Developmental Disabilities; Fatal Outcome; Female; Frameshift Mutation; Humans; Infant; Kinesins; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Myoclonus; Optic Nerve

Loss of B Cells in Patients with Heterozygous Mutations in IKAROS. - Kuehn, H S; Boisson, B; Cunningham-Rundles, C; Reichenbach, J; Stray-Pedersen, A; Gelfand, E W; Maffucci, P; Pierce, K R; Abbott, J K; Voelkerding, K V; South, S T; Augustine, N H; et al. (N Engl J Med, 2016)
BACKGROUND: Common variable immunodeficiency (CVID) is characterized by late-onset hypogammaglobulinemia in the absence of predisposing factors. The genetic cause is unknown in the majority of cases, and less than 10% of patients have a family history of the disease. Most patients have normal numbers of B cells but lack plasma cells. METHODS: We used whole-exome sequencing and array-based comparative genomic hybridization to evaluate a subset of patients with CVID and low B-cell numbers. Mutant proteins were analyzed for DNA binding with the use of an electrophoretic mobility-shift assay (EMSA) and confocal microscopy. Flow cytometry was used to analyze peripheral-blood lymphocytes and bone marrow aspirates. RESULTS: Six different heterozygous mutations in IKZF1, the gene encoding the transcription factor IKAROS, were identified in 29 persons from six families. In two families, the mutation was a de novo event in the proband. All the mutations, four amino acid substitutions, an intragenic deletion, and a 4.7-Mb multigene deletion involved the DNA-binding domain of IKAROS. The proteins bearing missense mutations failed to bind target DNA sequences on EMSA and confocal microscopy; however, they did not inhibit the binding of wild-type IKAROS. Studies in family members showed progressive loss of B cells and serum immunoglobulins. Bone marrow aspirates in two patients had markedly decreased early B-cell precursors, but plasma cells were present. Acute lymphoblastic leukemia developed in 2 of the 29 patients. CONCLUSIONS: Heterozygous mutations in the transcription factor IKAROS caused an autosomal dominant form of CVID that is associated with a striking decrease in B-cell numbers. (Funded by the National Institutes of Health and others.).
Keywords: Adolescent; Adult; Antigens, CD; B-Lymphocytes; Bone Marrow; Bone Marrow Examination; Child; Child, Preschool; Chromosomes, Human, Pair 7; Common Variable Immunodeficiency; Exome; Female; Heterozygote; Humans; Ikaros Transcription Factor; Immunoglobulin G; Lymphocyte Count; Male; Mutation; Pedigree; Sequence Analysis, DNA

Loss of carbonic anhydrase XII function in individuals with elevated sweat chloride concentration and pulmonary airway disease. - Lee, Melissa; Vecchio-Pagán, Briana; Sharma, Neeraj; Waheed, Abdul; Li, Xiaopeng; Raraigh, Karen S; Robbins, Sarah; Han, Sangwoo T; Franca, Arianna L; Pellicore, Matthew J; Evans, Taylor A; Arcara, Kristin M; et al. (Hum Mol Genet, 2016)
Elevated sweat chloride levels, failure to thrive (FTT), and lung disease are characteristic features of cystic fibrosis (CF, OMIM #219700). Here we describe variants in CA12 encoding carbonic anhydrase XII in two pedigrees exhibiting CF-like phenotypes. Exome sequencing of a white American adult diagnosed with CF due to elevated sweat chloride, recurrent hyponatremia, infantile FTT and lung disease identified deleterious variants in each CA12 gene: c.908-1 G>A in a splice acceptor and a novel frameshift insertion c.859_860insACCT. In an unrelated consanguineous Omani family, two children with elevated sweat chloride, infantile FTT, and recurrent hyponatremia were homozygous for a novel missense variant (p.His121Gln). Deleterious CFTR variants were absent in both pedigrees. CA XII protein was localized apically in human bronchiolar epithelia and basolaterally in the reabsorptive duct of human sweat glands. Respiratory epithelial cell RNA from the adult proband revealed only aberrant CA12 transcripts and in vitro analysis showed greatly reduced CA XII protein. Studies of ion transport across respiratory epithelial cells in vivo and in culture revealed intact CFTR-mediated chloride transport in the adult proband. CA XII protein bearing either p.His121Gln or a previously identified p.Glu143Lys missense variant localized to the basolateral membranes of polarized Madin-Darby canine kidney (MDCK) cells, but enzyme activity was severely diminished when assayed at physiologic concentrations of extracellular chloride. Our findings indicate that loss of CA XII function should be considered in individuals without CFTR mutations who exhibit CF-like features in the sweat gland and lung.
Keywords: Adolescent; Adult; Animals; Carbonic Anhydrases; Child; Child, Preschool; Chlorides; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Dogs; Female; Gene Expression Regulation, Enzymologic; Homozygote; Humans; Lung; Lung Diseases; Madin Darby Canine Kidney Cells; Male; Mutation; Pedigree; Phenotype; Sweat

Loss-of-Function Mutations in FRRS1L Lead to an Epileptic-Dyskinetic Encephalopathy. - Madeo, Marianna; Stewart, Michelle; Sun, Yuyang; Sahir, Nadia; Wiethoff, Sarah; Chandrasekar, Indra; Yarrow, Anna; Rosenfeld, Jill A; Yang, Yaping; Cordeiro, Dawn; McCormick, Elizabeth M; Muraresku, Colleen C; et al. (Am J Hum Genet, 2016)
Glutamatergic neurotransmission governs excitatory signaling in the mammalian brain, and abnormalities of glutamate signaling have been shown to contribute to both epilepsy and hyperkinetic movement disorders. The etiology of many severe childhood movement disorders and epilepsies remains uncharacterized. We describe a neurological disorder with epilepsy and prominent choreoathetosis caused by biallelic pathogenic variants in FRRS1L, which encodes an AMPA receptor outer-core protein. Loss of FRRS1L function attenuates AMPA-mediated currents, implicating chronic abnormalities of glutamatergic neurotransmission in this monogenic neurological disease of childhood.
Keywords: alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Brain Diseases; Electrophysiology; Epilepsy; Female; Humans; Hyperkinesis; Infant; Male; Membrane Proteins; Mutation; Nerve Tissue Proteins; Pedigree; Synaptic Transmission

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Metcalf, Ginger A; Muzny, Donna M; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Gibbs, Richard A; Boerwinkle, Eric (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Mutations in DCDC2 (doublecortin domain containing protein 2) in neonatal sclerosing cholangitis. - Grammatikopoulos, Tassos; Sambrotta, Melissa; Strautnieks, Sandra; Foskett, Pierre; Knisely, A S; Wagner, Bart; Deheragoda, Maesha; Starling, Chris; Mieli-Vergani, Giorgina; Smith, Joshua; Bull, Laura; Thompson, Richard J (J Hepatol, 2016)
BACKGROUND & AIMS: Neonatal sclerosing cholangitis (NSC) is a severe neonatal-onset cholangiopathy commonly leading to liver transplantation (LT) for end-stage liver disease in childhood. Liver biopsy findings histopathologically resemble those in biliary atresia (BA); however, in NSC extrahepatic bile ducts are patent, whilst in BA their lumina are obliterated. NSC is commonly seen in consanguineous kindreds, suggesting autosomal recessive inheritance. METHODS: From 29 NSC patients (24 families) identified, DNA was available in 24 (21 families). Thirteen (7 male) patients (12 families) of consanguineous parentage were selected for whole exome sequencing. Sequence variants were filtered for homozygosity, pathogenicity, minor allele frequency, quality score, and encoded protein expression pattern. RESULTS: Four of 13 patients were homozygous and two were compound heterozygous for mutations in the doublecortin domain containing 2 gene (DCDC2), which encodes DCDC2 protein and is expressed in cholangiocyte cilia. Another 11 patients were sequenced: one (with one sibling pair) was compound heterozygous for DCDC2 mutations. All mutations were protein-truncating. In available liver tissue from patients with DCDC2 mutations, immunostaining for human DCDC2 and the ciliary protein acetylated alpha-tubulin (ACALT) showed no expression (n=6) and transmission electron microscopy found that cholangiocytes lacked primary cilia (n=5). DCDC2 and ACALT were expressed in NSC patients without DCDC2 mutations (n=22). Of the patients carrying DCDC2 mutations, one died awaiting LT; five came to LT, of whom one died 2years later. The other 4 are well. CONCLUSION: Among 24 NSC patients with available DNA, 7 had mutations in DCDC2 (6 of 19 families). NSC patients in substantial proportion harbour mutations in DCDC2. Their disease represents a novel liver-based ciliopathy. LAY SUMMARY: Neonatal sclerosing cholangitis (NSC) is a rare genetic form of liver disease presenting in infancy. Through next generation sequencing we identified mutations in the gene encoding for doublecortin domain containing 2 (DCDC2) protein in a group of NSC children. DCDC2 is a signalling and structural protein found in primary cilia of cholangiocytes. Cholangiocytes are the cells forming the biliary system which is the draining system of the liver.
Keywords: Cholangitis, Sclerosing; Female; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Microtubule-Associated Proteins; Mutation

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Overlapping 16p13.11 deletion and gain of copies variations associated with childhood onset psychosis include genes with mechanistic implications for autism associated pathways: Two case reports. - Brownstein, Catherine A; Kleiman, Robin J; Engle, Elizabeth C; Towne, Meghan C; D'Angelo, Eugene J; Yu, Timothy W; Beggs, Alan H; Picker, Jonathan; Fogler, Jason M; Carroll, Devon; Schmitt, Rachel C O; Wolff, Robert R; et al. (Am J Med Genet A, 2016)
Copy number variability at 16p13.11 has been associated with intellectual disability, autism, schizophrenia, epilepsy, and attention-deficit hyperactivity disorder. Adolescent/adult- onset psychosis has been reported in a subset of these cases. Here, we report on two children with CNVs in 16p13.11 that developed psychosis before the age of 7. The genotype and neuropsychiatric abnormalities of these patients highlight several overlapping genes that have possible mechanistic relevance to pathways previously implicated in Autism Spectrum Disorders, including the mTOR signaling and the ubiquitin-proteasome cascades. A careful screening of the 16p13.11 region is warranted in patients with childhood onset psychosis.
Keywords: Autistic Disorder; Child; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Developmental Disabilities; DNA Copy Number Variations; Female; Genetic Association Studies; Humans; Male; Psychotic Disorders; Schizophrenia; Signal Transduction

PADRE: Pedigree-Aware Distant-Relationship Estimation. - Staples, Jeffrey; Witherspoon, David J; Jorde, Lynn B; Nickerson, Deborah A; Below, Jennifer E; Huff, Chad D (Am J Hum Genet, 2016)
Accurate estimation of shared ancestry is an important component of many genetic studies; current prediction tools accurately estimate pairwise genetic relationships up to the ninth degree. Pedigree-aware distant-relationship estimation (PADRE) combines relationship likelihoods generated by estimation of recent shared ancestry (ERSA) with likelihoods from family networks reconstructed by pedigree reconstruction and identification of a maximum unrelated set (PRIMUS), improving the power to detect distant relationships between pedigrees. Using PADRE, we estimated relationships from simulated pedigrees and three extended pedigrees, correctly predicting 20% more fourth- through ninth-degree simulated relationships than when using ERSA alone. By leveraging pedigree information, PADRE can even identify genealogical relationships between individuals who are genetically unrelated. For example, although 95% of 13(th)-degree relatives are genetically unrelated, in simulations, PADRE correctly predicted 50% of 13(th)-degree relationships to within one degree of relatedness. The improvement in prediction accuracy was consistent between simulated and actual pedigrees. We also applied PADRE to the HapMap3 CEU samples and report new cryptic relationships and validation of previously described relationships between families. PADRE greatly expands the range of relationships that can be estimated by using genetic data in pedigrees.
Keywords: Algorithms; Female; Haplotypes; Humans; Male; Models, Genetic; Pedigree; Reproducibility of Results

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Muzny, Donna M; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Boerwinkle, Eric; Gibbs, Richard A; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Periodontal Ehlers-Danlos Syndrome Is Caused by Mutations in C1R and C1S, which Encode Subcomponents C1r and C1s of Complement. - Kapferer-Seebacher, Ines; Pepin, Melanie; Werner, Roland; Aitman, Timothy J; Nordgren, Ann; Stoiber, Heribert; Thielens, Nicole; Gaboriaud, Christine; Amberger, Albert; Schossig, Anna; Gruber, Robert; Giunta, Cecilia; et al. (Am J Hum Genet, 2016)
Periodontal Ehlers-Danlos syndrome (pEDS) is an autosomal-dominant disorder characterized by early-onset periodontitis leading to premature loss of teeth, joint hypermobility, and mild skin findings. A locus was mapped to an approximately 5.8 Mb region at 12p13.1 but no candidate gene was identified. In an international consortium we recruited 19 independent families comprising 107 individuals with pEDS to identify the locus, characterize the clinical details in those with defined genetic causes, and try to understand the physiological basis of the condition. In 17 of these families, we identified heterozygous missense or in-frame insertion/deletion mutations in C1R (15 families) or C1S (2 families), contiguous genes in the mapped locus that encode subunits C1r and C1s of the first component of the classical complement pathway. These two proteins form a heterotetramer that then combines with six C1q subunits. Pathogenic variants involve the subunit interfaces or inter-domain hinges of C1r and C1s and are associated with intracellular retention and mild endoplasmic reticulum enlargement. Clinical features of affected individuals in these families include rapidly progressing periodontitis with onset in the teens or childhood, a previously unrecognized lack of attached gingiva, pretibial hyperpigmentation, skin and vascular fragility, easy bruising, and variable musculoskeletal symptoms. Our findings open a connection between the inflammatory classical complement pathway and connective tissue homeostasis.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromosome Mapping; Chromosomes, Human, Pair 12; Complement C1r; Complement C1s; Ehlers-Danlos Syndrome; Endoplasmic Reticulum; Exome; Female; Gene Deletion; Genetic Loci; Humans; Male; Mutation, Missense; Pedigree; Periodontitis; Protein Conformation; Young Adult

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

PRIMUS: improving pedigree reconstruction using mitochondrial and Y haplotypes. - Staples, Jeffrey; Ekunwe, Lynette; Lange, Ethan; Wilson, James G; Nickerson, Deborah A; Below, Jennifer E (Bioinformatics, 2016)
UNLABELLED: PRIMUS is a pedigree reconstruction algorithm that uses estimates of genome-wide identity by descent to reconstruct pedigrees consistent with observed genetic data. However, when genetic data for individuals within a pedigree are missing, often multiple pedigrees can be reconstructed that fit the data. We report a major expansion of PRIMUS that uses mitochondrial (mtDNA) and non-recombining Y chromosome (NRY) haplotypes to eliminate many pedigree structures that are inconsistent with the genetic data. We demonstrate that discordances in mtDNA and NRY haplotypes substantially reduce the number of potential pedigrees, and often lead to the identification of the correct pedigree. AVAILABILITY AND IMPLEMENTATION: We have implemented PRIMUS updates in PERL and it is available at primus.gs.washington.edu.
Keywords: Algorithms; Chromosomes, Human, Y; Computer Simulation; DNA, Mitochondrial; Genetics, Population; Haplotypes; Humans; Linkage Disequilibrium; Pedigree; Software

Rapid molecular diagnostics of severe primary immunodeficiency determined by using targeted next-generation sequencing. - Yu, Hui; Zhang, Victor Wei; Stray-Pedersen, Asbjørg; Hanson, Imelda Celine; Forbes, Lisa R; de la Morena, M Teresa; Chinn, Ivan K; Gorman, Elizabeth; Mendelsohn, Nancy J; Pozos, Tamara; Wiszniewski, Wojciech; Nicholas, Sarah K; et al. (J Allergy Clin Immunol, 2016)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are inherited disorders of the immune system. The most severe form, severe combined immunodeficiency (SCID), presents with profound deficiencies of T cells, B cells, or both at birth. If not treated promptly, affected patients usually do not live beyond infancy because of infections. Genetic heterogeneity of SCID frequently delays the diagnosis; a specific diagnosis is crucial for life-saving treatment and optimal management. OBJECTIVE: We developed a next-generation sequencing (NGS)-based multigene-targeted panel for SCID and other severe PIDDs requiring rapid therapeutic actions in a clinical laboratory setting. METHODS: The target gene capture/NGS assay provides an average read depth of approximately 1000×. The deep coverage facilitates simultaneous detection of single nucleotide variants and exonic copy number variants in one comprehensive assessment. Exons with insufficient coverage (<20× read depth) or high sequence homology (pseudogenes) are complemented by amplicon-based sequencing with specific primers to ensure 100% coverage of all targeted regions. RESULTS: Analysis of 20 patient samples with low T-cell receptor excision circle numbers on newborn screening or a positive family history or clinical suspicion of SCID or other severe PIDD identified deleterious mutations in 14 of them. Identified pathogenic variants included both single nucleotide variants and exonic copy number variants, such as hemizygous nonsense, frameshift, and missense changes in IL2RG; compound heterozygous changes in ATM, RAG1, and CIITA; homozygous changes in DCLRE1C and IL7R; and a heterozygous nonsense mutation in CHD7. CONCLUSION: High-throughput deep sequencing analysis with complete clinical validation greatly increases the diagnostic yield of severe primary immunodeficiency. Establishing a molecular diagnosis enables early immune reconstitution through prompt therapeutic intervention and guides management for improved long-term quality of life.
Keywords: Adolescent; Child; Female; Genetic Variation; Humans; Male; Pathology, Molecular; Sequence Analysis, DNA; Severe Combined Immunodeficiency

Recessive Inactivating Mutations in TBCK, Encoding a Rab GTPase-Activating Protein, Cause Severe Infantile Syndromic Encephalopathy. - Chong, Jessica X; Caputo, Viviana; Phelps, Ian G; Stella, Lorenzo; Worgan, Lisa; Dempsey, Jennifer C; Nguyen, Alina; Leuzzi, Vincenzo; Webster, Richard; Pizzuti, Antonio; Marvin, Colby T; Ishak, Gisele E; et al. (Am J Hum Genet, 2016)
Infantile encephalopathies are a group of clinically and biologically heterogeneous disorders for which the genetic basis remains largely unknown. Here, we report a syndromic neonatal encephalopathy characterized by profound developmental disability, severe hypotonia, seizures, diminished respiratory drive requiring mechanical ventilation, brain atrophy, dysgenesis of the corpus callosum, cerebellar vermis hypoplasia, and facial dysmorphism. Biallelic inactivating mutations in TBCK (TBC1-domain-containing kinase) were independently identified by whole-exome sequencing as the cause of this condition in four unrelated families. Matching these families was facilitated by the sharing of phenotypic profiles and WES data in a recently released web-based tool (Geno2MP) that links phenotypic information to rare variants in families with Mendelian traits. TBCK is a putative GTPase-activating protein (GAP) for small GTPases of the Rab family and has been shown to control cell growth and proliferation, actin-cytoskeleton dynamics, and mTOR signaling. Two of the three mutations (c.376C>T [p.Arg126(∗)] and c.1363A>T [p.Lys455(∗)]) are predicted to truncate the protein, and loss of the major TBCK isoform was confirmed in primary fibroblasts from one affected individual. The third mutation, c.1532G>A (p.Arg511His), alters a conserved residue within the TBC1 domain. Structural analysis implicated Arg511 as a required residue for Rab-GAP function, and in silico homology modeling predicted impaired GAP function in the corresponding mutant. These results suggest that loss of Rab-GAP activity is the underlying mechanism of disease. In contrast to other disorders caused by dysregulated mTOR signaling associated with focal or global brain overgrowth, impaired TBCK function results in progressive loss of brain volume.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Brain Diseases; Child; Child, Preschool; Corpus Callosum; Female; GTPase-Activating Proteins; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Protein-Serine-Threonine Kinases; Signal Transduction; TOR Serine-Threonine Kinases

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; European Continental Ancestry Group; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic Americans; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

Somatic mosaicism for a lethal TRPV4 mutation results in non-lethal metatropic dysplasia. - Weinstein, Michael M; Kang, Taekyu; Lachman, Ralph S; Bamshad, Michael; Nickerson, Deborah A; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2016)
Dominant mutations in TRPV4, which encodes the Transient Receptor Potential Cation Channel Subfamily V Member 4 calcium channel, result in a series of musculoskeletal disorders that include a set of peripheral neuropathies and a broad phenotypic spectrum of skeletal dysplasias. The skeletal phenotypes range from brachyolmia, in which there is scoliosis with mild short stature, through perinatal lethal metatropic dysplasia. We describe a case with phenotypic findings consistent with metatropic dysplasia, but in whom no TRPV4 mutation was detected by Sanger sequence analysis. Exome sequence analysis identified a known lethal metatropic dysplasia mutation, TRPV4 , which was present at lower frequency than would be expected for a heterozygous change. The affected individual was shown to be a somatic mosaic for the mutation, providing an explanation for the milder than expected phenotype. The data illustrate that high-throughput sequencing of genomic DNA can facilitate detection of mosaicism with higher sensitivity than Sanger sequence analysis and identify a new genetic mechanism for metatropic dysplasia. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; DNA Mutational Analysis; Dwarfism; Exons; Genetic Association Studies; Humans; Infant; Magnetic Resonance Imaging; Mosaicism; Mutation; Osteochondrodysplasias; Phenotype; Physical Examination; Radiography; TRPV Cation Channels

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

Two novel germline DDX41 mutations in a family with inherited myelodysplasia/acute myeloid leukemia. - Li, Ruijuan; Sobreira, Nara; Witmer, P Dane; Pratz, Keith W; Braunstein, Evan M (Haematologica, 2016)
Keywords: DEAD-box RNA Helicases; Family; Female; Germ-Line Mutation; Humans; Leukemia, Myeloid, Acute; Male; Myelodysplastic Syndromes; Neoplasm Proteins

Variants in SLC18A3, vesicular acetylcholine transporter, cause congenital myasthenic syndrome. - O'Grady, Gina L; Verschuuren, Corien; Yuen, Michaela; Webster, Richard; Menezes, Manoj; Fock, Johanna M; Pride, Natalie; Best, Heather A; Benavides Damm, Tatiana; Turner, Christian; Lek, Monkol; Engel, Andrew G; et al. (Neurology, 2016)
OBJECTIVE: To describe the clinical and genetic characteristics of presynaptic congenital myasthenic syndrome secondary to biallelic variants in SLC18A3. METHODS: Individuals from 2 families were identified with biallelic variants in SLC18A3, the gene encoding the vesicular acetylcholine transporter (VAChT), through whole-exome sequencing. RESULTS: The patients demonstrated features seen in presynaptic congenital myasthenic syndrome, including ptosis, ophthalmoplegia, fatigable weakness, apneic crises, and deterioration of symptoms in cold water for patient 1. Both patients demonstrated moderate clinical improvement on pyridostigmine. Patient 1 had a broader phenotype, including learning difficulties and left ventricular dysfunction. Electrophysiologic studies were typical for a presynaptic defect. Both patients showed profound electrodecrement on low-frequency repetitive stimulation followed by a prolonged period of postactivation exhaustion. In patient 1, this was unmasked only after isometric contraction, a recognized feature of presynaptic disease, emphasizing the importance of activation procedures. CONCLUSIONS: VAChT is responsible for uptake of acetylcholine into presynaptic vesicles. The clinical and electrographic characteristics of the patients described are consistent with previously reported mouse models of VAChT deficiency. These findings make it very likely that defects in VAChT due to variants in SLC18A3 are a cause of congenital myasthenic syndrome in humans.
Keywords: Adolescent; Child; Diagnosis, Differential; Female; Genetic Variation; Humans; Male; Myasthenic Syndromes, Congenital; Vesicular Acetylcholine Transport Proteins

Variants in the Oxidoreductase PYROXD1 Cause Early-Onset Myopathy with Internalized Nuclei and Myofibrillar Disorganization. - O'Grady, Gina L; Best, Heather A; Sztal, Tamar E; Schartner, Vanessa; Sanjuan-Vazquez, Myriam; Donkervoort, Sandra; Abath Neto, Osorio; Sutton, Roger Bryan; Ilkovski, Biljana; Romero, Norma Beatriz; Stojkovic, Tanya; Dastgir, Jahannaz; et al. (Am J Hum Genet, 2016)
This study establishes PYROXD1 variants as a cause of early-onset myopathy and uses biospecimens and cell lines, yeast, and zebrafish models to elucidate the fundamental role of PYROXD1 in skeletal muscle. Exome sequencing identified recessive variants in PYROXD1 in nine probands from five families. Affected individuals presented in infancy or childhood with slowly progressive proximal and distal weakness, facial weakness, nasal speech, swallowing difficulties, and normal to moderately elevated creatine kinase. Distinctive histopathology showed abundant internalized nuclei, myofibrillar disorganization, desmin-positive inclusions, and thickened Z-bands. PYROXD1 is a nuclear-cytoplasmic pyridine nucleotide-disulphide reductase (PNDR). PNDRs are flavoproteins (FAD-binding) and catalyze pyridine-nucleotide-dependent (NAD/NADH) reduction of thiol residues in other proteins. Complementation experiments in yeast lacking glutathione reductase glr1 show that human PYROXD1 has reductase activity that is strongly impaired by the disease-associated missense mutations. Immunolocalization studies in human muscle and zebrafish myofibers demonstrate that PYROXD1 localizes to the nucleus and to striated sarcomeric compartments. Zebrafish with ryroxD1 knock-down recapitulate features of PYROXD1 myopathy with sarcomeric disorganization, myofibrillar aggregates, and marked swimming defect. We characterize variants in the oxidoreductase PYROXD1 as a cause of early-onset myopathy with distinctive histopathology and introduce altered redox regulation as a primary cause of congenital muscle disease.
Keywords: Amino Acid Sequence; Animals; Cell Nucleus; Cercopithecus aethiops; Cohort Studies; COS Cells; Creatine Kinase; Cytoplasm; Distal Myopathies; ELAV-Like Protein 4; Female; Flavoproteins; Gene Deletion; Genetic Variation; Genome-Wide Association Study; Glutathione Reductase; HEK293 Cells; Humans; Male; Muscle, Skeletal; Mutation, Missense; Myopathies, Structural, Congenital; Oxidoreductases; Pedigree; Protein Conformation; Saccharomyces cerevisiae Proteins; Zebrafish

Whole-exome sequencing identifies novel variants in PNPT1 causing oxidative phosphorylation defects and severe multisystem disease. - Alodaib, Ahmad; Sobreira, Nara; Gold, Wendy A; Riley, Lisa G; Van Bergen, Nicole J; Wilson, Meredith J; Bennetts, Bruce; Thorburn, David R; Boehm, Corinne; Christodoulou, John (Eur J Hum Genet, 2016)
Recent advances in next-generation sequencing strategies have led to the discovery of many novel disease genes. We describe here a non-consanguineous family with two affected boys presenting with early onset of severe axonal neuropathy, optic atrophy, intellectual disability, auditory neuropathy and chronic respiratory and gut disturbances. Whole-exome sequencing (WES) was performed on all family members and we identified compound heterozygous variants (c.[760C>A];[1528G>C];p.[(Gln254Lys);(Ala510Pro)] in the polyribonucleotide nucleotidyltransferase 1 (PNPT1) gene in both affected individuals. PNPT1 encodes the polynucleotide phosphorylase (PNPase) protein, which is involved in the transport of small RNAs into the mitochondria. These RNAs are involved in the mitochondrial translation machinery, responsible for the synthesis of mitochondrially encoded subunits of the oxidative phosphorylation (OXPHOS) complexes. Both PNPT1 variants are within highly conserved regions and predicted to be damaging. These variants resulted in quaternary defects in the PNPase protein and a clear reduction in protein and mRNA expression of PNPT1 in patient fibroblasts compared with control cells. Protein analysis of the OXPHOS complexes showed a significant reduction in complex I (CI), complex III (CIII) and complex IV (CIV). Enzyme activity of CI and CIV was clearly reduced in patient fibroblasts compared with controls along with a 33% reduction in total mitochondrial protein synthesis. In vitro rescue experiments, using exogenous expression of wild-type PNPT1 in patient fibroblasts, ameliorated the deficiencies in the OXPHOS complex protein expression, supporting the likely pathogenicity of these variants and the importance of WES in efficiently identifying rare genetic disease genes.
Keywords: Axons; Exome; Exoribonucleases; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Male; Mitochondria; Mutation; Optic Atrophy; Oxidative Phosphorylation; Pedigree; Protein Structure, Quaternary

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Boerwinkle, Eric; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Gibbs, Richard A; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Muzny, Donna; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, André; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; African Americans; Alleles; Coronary Disease; European Continental Ancestry Group; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation

Biallelic mutations in SNX14 cause a syndromic form of cerebellar atrophy and lysosome-autophagosome dysfunction. - Akizu, Naiara; Cantagrel, Vincent; Zaki, Maha S; Al-Gazali, Lihadh; Wang, Xin; Rosti, Rasim Ozgur; Dikoglu, Esra; Gelot, Antoinette Bernabe; Rosti, Basak; Vaux, Keith K; Scott, Eric M; Silhavy, Jennifer L; et al. (Nat Genet, 2015)
Pediatric-onset ataxias often present clinically as developmental delay and intellectual disability, with prominent cerebellar atrophy as a key neuroradiographic finding. Here we describe a new clinically distinguishable recessive syndrome in 12 families with cerebellar atrophy together with ataxia, coarsened facial features and intellectual disability, due to truncating mutations in the sorting nexin gene SNX14, encoding a ubiquitously expressed modular PX domain-containing sorting factor. We found SNX14 localized to lysosomes and associated with phosphatidylinositol (3,5)-bisphosphate, a key component of late endosomes/lysosomes. Patient-derived cells showed engorged lysosomes and a slower autophagosome clearance rate upon autophagy induction by starvation. Zebrafish morphants for snx14 showed dramatic loss of cerebellar parenchyma, accumulation of autophagosomes and activation of apoptosis. Our results characterize a unique ataxia syndrome due to biallelic SNX14 mutations leading to lysosome-autophagosome dysfunction.
Keywords: Animals; Atrophy; Autophagy; Cerebellar Diseases; Cerebellum; Child, Preschool; Female; Gene Frequency; Humans; Infant; Lod Score; Lysosomal Storage Diseases; Lysosomes; Male; Mutation; Phagosomes; Sorting Nexins; Spinocerebellar Ataxias; Syndrome; Zebrafish

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

Collapsed haplotype pattern method for linkage analysis of next-generation sequence data. - Wang, Gao T; Zhang, Di; Li, Biao; Dai, Hang; Leal, Suzanne M (Eur J Hum Genet, 2015)
Recent advances in next-generation sequencing (NGS) make it possible to directly sequence genomes and exomes of individuals with Mendelian diseases and screen sequence data for causal variants. With the reduction in cost of NGS, DNA samples from entire families can be sequenced and linkage analysis can be performed directly using NGS data. Inspired by 'burden' tests, which are used for complex trait rare variant association studies, we developed the collapsed haplotype pattern (CHP) method for linkage analysis. Using data from several deafness genes we demonstrate that the CHP method is substantially more powerful than analyzing individual variants. Unlike applying NGS data filtering approaches, the CHP method provides statistical evidence of a gene's involvement in disease etiology and is also less likely to exclude causal variants in the presence of phenocopies and/or reduced penetrance. The CHP method was implemented in the SEQLinkage software package, which can perform linkage analysis on NGS data or can generate data compatible with many linkage analysis programs, reviving them for use in NGS era.
Keywords: Chromosome Mapping; Genetic Linkage; Haplotypes; Hearing Loss; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Comparative Genomic Analyses of the Human NPHP1 Locus Reveal Complex Genomic Architecture and Its Regional Evolution in Primates. - Yuan, Bo; Liu, Pengfei; Gupta, Aditya; Beck, Christine R; Tejomurtula, Anusha; Campbell, Ian M; Gambin, Tomasz; Simmons, Alexandra D; Withers, Marjorie A; Harris, R Alan; Rogers, Jeffrey; Schwartz, David C; et al. (PLoS Genet, 2015)
Many loci in the human genome harbor complex genomic structures that can result in susceptibility to genomic rearrangements leading to various genomic disorders. Nephronophthisis 1 (NPHP1, MIM# 256100) is an autosomal recessive disorder that can be caused by defects of NPHP1; the gene maps within the human 2q13 region where low copy repeats (LCRs) are abundant. Loss of function of NPHP1 is responsible for approximately 85% of the NPHP1 cases-about 80% of such individuals carry a large recurrent homozygous NPHP1 deletion that occurs via nonallelic homologous recombination (NAHR) between two flanking directly oriented ~45 kb LCRs. Published data revealed a non-pathogenic inversion polymorphism involving the NPHP1 gene flanked by two inverted ~358 kb LCRs. Using optical mapping and array-comparative genomic hybridization, we identified three potential novel structural variant (SV) haplotypes at the NPHP1 locus that may protect a haploid genome from the NPHP1 deletion. Inter-species comparative genomic analyses among primate genomes revealed massive genomic changes during evolution. The aggregated data suggest that dynamic genomic rearrangements occurred historically within the NPHP1 locus and generated SV haplotypes observed in the human population today, which may confer differential susceptibility to genomic instability and the NPHP1 deletion within a personal genome. Our study documents diverse SV haplotypes at a complex LCR-laden human genomic region. Comparative analyses provide a model for how this complex region arose during primate evolution, and studies among humans suggest that intra-species polymorphism may potentially modulate an individual's susceptibility to acquiring disease-associated alleles.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Comparative Genomic Hybridization; Evolution, Molecular; Gene Dosage; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Haplotypes; Humans; Kidney Diseases, Cystic; Membrane Proteins; Primates

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

CRB1-Related Maculopathy With Cystoid Macular Edema. - Wolfson, Yulia; Applegate, Carolyn D; Strauss, Rupert W; Han, Ian C; Scholl, Hendrik P (JAMA Ophthalmol, 2015)
Keywords: Administration, Topical; Carbonic Anhydrase Inhibitors; Child; Diseases in Twins; DNA Mutational Analysis; Electroretinography; Eye Proteins; Female; Fluorescein Angiography; Humans; Macular Edema; Membrane Proteins; Mutation; Nerve Tissue Proteins; Ophthalmic Solutions; Retinal Dystrophies; Sulfonamides; Thiophenes; Tomography, Optical Coherence; Twins, Monozygotic; Visual Acuity

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

De novo mutations in NALCN cause a syndrome characterized by congenital contractures of the limbs and face, hypotonia, and developmental delay. - Chong, Jessica X; McMillin, Margaret J; Shively, Kathryn M; Beck, Anita E; Marvin, Colby T; Armenteros, Jose R; Buckingham, Kati J; Nkinsi, Naomi T; Boyle, Evan A; Berry, Margaret N; Bocian, Maureen; Foulds, Nicola; et al. (Am J Hum Genet, 2015)
Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; this is a unique condition that we now refer to as CLIFAHDD syndrome. Exome sequencing identified missense mutations in the sodium leak channel, non-selective (NALCN) in four families affected by CLIFAHDD syndrome. We used molecular-inversion probes to screen for NALCN in a cohort of 202 distal arthrogryposis (DA)-affected individuals as well as concurrent exome sequencing of six other DA-affected individuals, thus revealing NALCN mutations in ten additional families with "atypical" forms of DA. All 14 mutations were missense variants predicted to alter amino acid residues in or near the S5 and S6 pore-forming segments of NALCN, highlighting the functional importance of these segments. In vitro functional studies demonstrated that NALCN alterations nearly abolished the expression of wild-type NALCN, suggesting that alterations that cause CLIFAHDD syndrome have a dominant-negative effect. In contrast, homozygosity for mutations in other regions of NALCN has been reported in three families affected by an autosomal-recessive condition characterized mainly by hypotonia and severe intellectual disability. Accordingly, mutations in NALCN can cause either a recessive or dominant condition characterized by varied though overlapping phenotypic features, perhaps based on the type of mutation and affected protein domain(s).
Keywords: Arthrogryposis; Contracture; Craniofacial Dysostosis; Cytoskeletal Proteins; Exome; Extremities; Face; Female; Gene Frequency; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant; Male; Muscle Hypotonia; Mutation, Missense; Sodium Channels

DNA REPAIR. Mus81 and converging forks limit the mutagenicity of replication fork breakage. - Mayle, Ryan; Campbell, Ian M; Beck, Christine R; Yu, Yang; Wilson, Marenda; Shaw, Chad A; Bjergbaek, Lotte; Lupski, James R; Ira, Grzegorz (Science, 2015)
Most spontaneous DNA double-strand breaks (DSBs) result from replication-fork breakage. Break-induced replication (BIR), a genome rearrangement-prone repair mechanism that requires the Pol32/POLD3 subunit of eukaryotic DNA Polδ, was proposed to repair broken forks, but how genome destabilization is avoided was unknown. We show that broken fork repair initially uses error-prone Pol32-dependent synthesis, but that mutagenic synthesis is limited to within a few kilobases from the break by Mus81 endonuclease and a converging fork. Mus81 suppresses template switches between both homologous sequences and diverged human Alu repetitive elements, highlighting its importance for stability of highly repetitive genomes. We propose that lack of a timely converging fork or Mus81 may propel genome instability observed in cancer.
Keywords: Alu Elements; Base Sequence; DNA Breaks, Double-Stranded; DNA Repair; DNA Replication; DNA-Binding Proteins; DNA-Directed DNA Polymerase; Endonucleases; Genomic Instability; Humans; Molecular Sequence Data; Neoplasms; Saccharomyces cerevisiae; Saccharomyces cerevisiae Proteins

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hülya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Early-onset lymphoproliferation and autoimmunity caused by germline STAT3 gain-of-function mutations. - Milner, Joshua D; Vogel, Tiphanie P; Forbes, Lisa; Ma, Chi A; Stray-Pedersen, Asbjørg; Niemela, Julie E; Lyons, Jonathan J; Engelhardt, Karin R; Zhang, Yu; Topcagic, Nermina; Roberson, Elisha D O; Matthews, Helen; et al. (Blood, 2015)
Germline loss-of-function mutations in the transcription factor signal transducer and activator of transcription 3 (STAT3) cause immunodeficiency, whereas somatic gain-of-function mutations in STAT3 are associated with large granular lymphocytic leukemic, myelodysplastic syndrome, and aplastic anemia. Recently, germline mutations in STAT3 have also been associated with autoimmune disease. Here, we report on 13 individuals from 10 families with lymphoproliferation and early-onset solid-organ autoimmunity associated with 9 different germline heterozygous mutations in STAT3. Patients exhibited a variety of clinical features, with most having lymphadenopathy, autoimmune cytopenias, multiorgan autoimmunity (lung, gastrointestinal, hepatic, and/or endocrine dysfunction), infections, and short stature. Functional analyses demonstrate that these mutations confer a gain-of-function in STAT3 leading to secondary defects in STAT5 and STAT1 phosphorylation and the regulatory T-cell compartment. Treatment targeting a cytokine pathway that signals through STAT3 led to clinical improvement in 1 patient, suggesting a potential therapeutic option for such patients. These results suggest that there is a broad range of autoimmunity caused by germline STAT3 gain-of-function mutations, and that hematologic autoimmunity is a major component of this newly described disorder. Some patients for this study were enrolled in a trial registered at www.clinicaltrials.gov as #NCT00001350.
Keywords: Adolescent; Adult; Autoimmune Diseases; Child; Child, Preschool; Female; Genetic Diseases, Inborn; Humans; Infant; Lymphoproliferative Disorders; Male; Mutation; Phosphorylation; STAT1 Transcription Factor; STAT3 Transcription Factor; STAT5 Transcription Factor; T-Lymphocytes, Regulatory

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing links mutations in PARN and RTEL1 with familial pulmonary fibrosis and telomere shortening. - Stuart, Bridget D; Choi, Jungmin; Zaidi, Samir; Xing, Chao; Holohan, Brody; Chen, Rui; Choi, Mihwa; Dharwadkar, Pooja; Torres, Fernando; Girod, Carlos E; Weissler, Jonathan; Fitzgerald, John; et al. (Nat Genet, 2015)
Idiopathic pulmonary fibrosis (IPF) is an age-related disease featuring progressive lung scarring. To elucidate the molecular basis of IPF, we performed exome sequencing of familial kindreds with pulmonary fibrosis. Gene burden analysis comparing 78 European cases and 2,816 controls implicated PARN, an exoribonuclease with no previous connection to telomere biology or disease, with five new heterozygous damaging mutations in unrelated cases and none in controls (P = 1.3 × 10(-8)); mutations were shared by all affected relatives (odds in favor of linkage = 4,096:1). RTEL1, an established locus for dyskeratosis congenita, harbored significantly more new damaging and missense variants at conserved residues in cases than in controls (P = 1.6 × 10(-6)). PARN and RTEL1 mutation carriers had shortened leukocyte telomere lengths, and we observed epigenetic inheritance of short telomeres in family members. Together, these genes explain ~7% of familial pulmonary fibrosis and strengthen the link between lung fibrosis and telomere dysfunction.
Keywords: Adult; Aged; Aged, 80 and over; Amino Acid Sequence; Case-Control Studies; Cells, Cultured; DNA Helicases; DNA Mutational Analysis; Exome; Exoribonucleases; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Idiopathic Pulmonary Fibrosis; Leukocytes; Lod Score; Male; Middle Aged; Molecular Sequence Data; Pedigree; Telomere; Telomere Shortening

Exome sequencing reveals pathogenic mutations in 91 strains of mice with Mendelian disorders. - Fairfield, Heather; Srivastava, Anuj; Ananda, Guruprasad; Liu, Rangjiao; Kircher, Martin; Lakshminarayana, Anuradha; Harris, Belinda S; Karst, Son Yong; Dionne, Louise A; Kane, Coleen C; Curtain, Michelle; Berry, Melissa L; et al. (Genome Res, 2015)
Spontaneously arising mouse mutations have served as the foundation for understanding gene function for more than 100 years. We have used exome sequencing in an effort to identify the causative mutations for 172 distinct, spontaneously arising mouse models of Mendelian disorders, including a broad range of clinically relevant phenotypes. To analyze the resulting data, we developed an analytics pipeline that is optimized for mouse exome data and a variation database that allows for reproducible, user-defined data mining as well as nomination of mutation candidates through knowledge-based integration of sample and variant data. Using these new tools, putative pathogenic mutations were identified for 91 (53%) of the strains in our study. Despite the increased power offered by potentially unlimited pedigrees and controlled breeding, about half of our exome cases remained unsolved. Using a combination of manual analyses of exome alignments and whole-genome sequencing, we provide evidence that a large fraction of unsolved exome cases have underlying structural mutations. This result directly informs efforts to investigate the similar proportion of apparently Mendelian human phenotypes that are recalcitrant to exome sequencing.
Keywords: Animals; Exome; Female; Genetic Diseases, Inborn; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Male; Mice; Mutation; Phenotype; Reproducibility of Results

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Muzny, Donna; Gibbs, Richard A; Boerwinkle, Eric; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Generation of sequence-based data for pedigree-segregating Mendelian or Complex traits. - Li, Biao; Wang, Gao T; Leal, Suzanne M (Bioinformatics, 2015)
MOTIVATION: There is great interest in analyzing next generation sequence data that has been generated for pedigrees. However, unlike for population-based data there are only a limited number of rare variant methods to analyze pedigree data. One limitation is the ability to evaluate type I and II errors for family-based methods, due to lack of software that can simulate realistic sequence data for pedigrees. SUMMARY: We developed RarePedSim (Rare-variant Pedigree-based Simulator), a program to simulate region/gene-level genotype and phenotype data for complex and Mendelian traits for any given pedigree structure. Using a genetic model, sequence variant data can be generated either conditionally or unconditionally on pedigree members' qualitative or quantitative phenotypes. Additionally, qualitative or quantitative traits can be generated conditional on variant data. Sequence data can either be simulated using realistic population demographic models or obtained from sequence-based studies. Variant sites can be annotated with positions, allele frequencies and functionality. For rare variants, RarePedSim is the only program that can efficiently generate both genotypes and phenotypes, regardless of pedigree structure. Data generated by RarePedSim are in standard Linkage file (.ped) and Variant Call (.vcf) formats, ready to be used for a variety of purposes, including evaluation of type I error and power, for association methods including mixed models and linkage analysis methods. AVAILABILITY AND IMPLEMENTATION: bioinformatics.org/simped/rare CONTACT: sleal@bcm.edu.
Keywords: Base Sequence; Chromosome Segregation; Humans; Pedigree; Quantitative Trait, Heritable; Sequence Analysis; Software

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Genetic linkage analysis in the age of whole-genome sequencing. - Ott, Jurg; Wang, Jing; Leal, Suzanne M (Nat Rev Genet, 2015)
For many years, linkage analysis was the primary tool used for the genetic mapping of Mendelian and complex traits with familial aggregation. Linkage analysis was largely supplanted by the wide adoption of genome-wide association studies (GWASs). However, with the recent increased use of whole-genome sequencing (WGS), linkage analysis is again emerging as an important and powerful analysis method for the identification of genes involved in disease aetiology, often in conjunction with WGS filtering approaches. Here, we review the principles of linkage analysis and provide practical guidelines for carrying out linkage studies using WGS data.
Keywords: Algorithms; Female; Genetic Linkage; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Lod Score; Male; Pedigree; Penetrance; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Software

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gözde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Identification and functional characterization of natural human melanocortin 1 receptor mutant alleles in Pakistani population. - Shahzad, Mohsin; Sires Campos, Julia; Tariq, Nabeela; Herraiz Serrano, Cecilia; Yousaf, Rizwan; Jiménez-Cervantes, Celia; Yousaf, Sairah; Waryah, Yar M; Dad, Haseeb A; Blue, Elizabeth M; Sobreira, Nara; López-Giráldez, Francesc; et al. (Pigment Cell Melanoma Res, 2015)
Melanocortin 1 receptor (MC1R), a Gs protein-coupled receptor of the melanocyte's plasma membrane, is a major determinant of skin pigmentation and phototype. Upon activation by α-melanocyte stimulating hormone, MC1R triggers the cAMP cascade to stimulate eumelanogenesis. We used whole-exome sequencing to identify causative alleles in Pakistani families with skin and hair hypopigmentation. Six MC1R mutations segregated with the phenotype in seven families, including a p.Val174del in-frame deletion and a p.Tyr298* nonsense mutation, that were analyzed for function in heterologous HEK293 cells. p.Tyr298* MC1R showed no agonist-induced signaling to the cAMP or ERK pathways, nor detectable agonist binding. Conversely, signaling was comparable for p.Val174del and wild-type in HEK cells overexpressing the proteins, but binding analysis suggested impaired cell surface expression. Flow cytometry and confocal imaging studies revealed reduced plasma membrane expression of p.Val174del and p.Tyr298*. Therefore, p.Tyr298* was a total loss-of-function (LOF) allele, while p.Val174del displayed a partial LOF attribute.
Keywords: Alleles; Family; Female; Humans; Hypopigmentation; Male; Mutation; Pakistan; Pedigree; Phenotype; Receptor, Melanocortin, Type 1

Inactivating mutations in MFSD2A, required for omega-3 fatty acid transport in brain, cause a lethal microcephaly syndrome. - Guemez-Gamboa, Alicia; Nguyen, Long N; Yang, Hongbo; Zaki, Maha S; Kara, Majdi; Ben-Omran, Tawfeg; Akizu, Naiara; Rosti, Rasim Ozgur; Rosti, Basak; Scott, Eric; Schroth, Jana; Copeland, Brett; et al. (Nat Genet, 2015)
Docosahexanoic acid (DHA) is the most abundant omega-3 fatty acid in brain, and, although it is considered essential, deficiency has not been linked to disease. Despite the large mass of DHA in phospholipids, the brain does not synthesize it. DHA is imported across the blood-brain barrier (BBB) through the major facilitator superfamily domain-containing 2a (MFSD2A) protein. MFSD2A transports DHA as well as other fatty acids in the form of lysophosphatidylcholine (LPC). We identify two families displaying MFSD2A mutations in conserved residues. Affected individuals exhibited a lethal microcephaly syndrome linked to inadequate uptake of LPC lipids. The MFSD2A mutations impaired transport activity in a cell-based assay. Moreover, when expressed in mfsd2aa-morphant zebrafish, mutants failed to rescue microcephaly, BBB breakdown and lethality. Our results establish a link between transport of DHA and LPCs by MFSD2A and human brain growth and function, presenting the first evidence of monogenic disease related to transport of DHA in humans.
Keywords: Adolescent; Animals; Biological Transport; Blood-Brain Barrier; Brain; Case-Control Studies; Child; Child, Preschool; Consanguinity; Fatty Acids, Omega-3; Female; Genes, Lethal; Genetic Association Studies; HEK293 Cells; Humans; Infant; Male; Mice, Knockout; Microcephaly; Mutation, Missense; Syndrome; Tumor Suppressor Proteins; Zebrafish

KIAA0586 is Mutated in Joubert Syndrome. - Bachmann-Gagescu, Ruxandra; Phelps, Ian G; Dempsey, Jennifer C; Sharma, Vivek A; Ishak, Gisele E; Boyle, Evan A; Wilson, Meredith; Marques Lourenço, Charles; Arslan, Mutluay; Shendure, Jay; Doherty, Dan (Hum Mutat, 2015)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by a distinctive mid-hindbrain malformation. JS is part of a group of disorders called ciliopathies based on their overlapping phenotypes and common underlying pathophysiology linked to primary cilium dysfunction. Biallelic mutations in one of 28 genes, all encoding proteins localizing to the primary cilium or basal body, can cause JS. Despite this large number of genes, the genetic cause can currently be determined in about 62% of individuals with JS. To identify novel JS genes, we performed whole exome sequencing on 35 individuals with JS and found biallelic rare deleterious variants (RDVs) in KIAA0586, encoding a centrosomal protein required for ciliogenesis, in one individual. Targeted next-generation sequencing in a large JS cohort identified biallelic RDVs in eight additional families for an estimated prevalence of 2.5% (9/366 JS families). All affected individuals displayed JS phenotypes toward the mild end of the spectrum.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Alternative Splicing; Brain; Cell Cycle Proteins; Cerebellum; Child; Child, Preschool; DNA Mutational Analysis; Eye Abnormalities; Gene Order; Genetic Association Studies; Humans; Kidney Diseases, Cystic; Magnetic Resonance Imaging; Mutation; Phenotype; Retina; Young Adult

The Matchmaker Exchange: a platform for rare disease gene discovery. - Philippakis, Anthony A; Azzariti, Danielle R; Beltran, Sergi; Brookes, Anthony J; Brownstein, Catherine A; Brudno, Michael; Brunner, Han G; Buske, Orion J; Carey, Knox; Doll, Cassie; Dumitriu, Sergiu; Dyke, Stephanie O M; et al. (Hum Mutat, 2015)
There are few better examples of the need for data sharing than in the rare disease community, where patients, physicians, and researchers must search for "the needle in a haystack" to uncover rare, novel causes of disease within the genome. Impeding the pace of discovery has been the existence of many small siloed datasets within individual research or clinical laboratory databases and/or disease-specific organizations, hoping for serendipitous occasions when two distant investigators happen to learn they have a rare phenotype in common and can "match" these cases to build evidence for causality. However, serendipity has never proven to be a reliable or scalable approach in science. As such, the Matchmaker Exchange (MME) was launched to provide a robust and systematic approach to rare disease gene discovery through the creation of a federated network connecting databases of genotypes and rare phenotypes using a common application programming interface (API). The core building blocks of the MME have been defined and assembled. Three MME services have now been connected through the API and are available for community use. Additional databases that support internal matching are anticipated to join the MME network as it continues to grow.
Keywords: Database Management Systems; Databases, Genetic; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Information Dissemination; Rare Diseases; Software

Mutation of ATF6 causes autosomal recessive achromatopsia. - Ansar, Muhammad; Santos-Cortez, Regie Lyn P; Saqib, Muhammad Arif Nadeem; Zulfiqar, Fareeha; Lee, Kwanghyuk; Ashraf, Naeem Mahmood; Ullah, Ehsan; Wang, Xin; Sajid, Sundus; Khan, Falak Sher; Amin-ud-Din, Muhammad; Smith, Joshua D; et al. (Hum Genet, 2015)
Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1-q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome sequencing. Within the ATF6 gene, a single-base insertion variant c.355_356dupG (p.Glu119Glyfs*8) was identified, which completely segregates with the ACHM phenotype within the family. The frameshift variant was absent in public variant databases, in 130 exomes from unrelated Pakistani individuals, and in 235 ethnically matched controls. The variant is predicted to result in a truncated protein that lacks the DNA binding and transmembrane domains and therefore affects the function of ATF6 as a transcription factor that initiates the unfolded protein response during endoplasmic reticulum (ER) stress. Immunolabeling with anti-ATF6 antibodies showed localization throughout the mouse neuronal retina, including retinal pigment epithelium, photoreceptor cells, inner nuclear layer, inner and outer plexiform layers, with a more prominent signal in retinal ganglion cells. In contrast to cytoplasmic expression of wild-type protein, in heterologous cells ATF6 protein with the p.Glu119Glyfs*8 variant is mainly confined to the nucleus. Our results imply that response to ER stress as mediated by the ATF6 pathway is essential for color vision in humans.
Keywords: Activating Transcription Factor 6; Adolescent; Animals; Asian Continental Ancestry Group; Color Vision Defects; Consanguinity; DNA Mutational Analysis; Exome; Female; Frameshift Mutation; Genotyping Techniques; Homozygote; Humans; Limit of Detection; Male; Mice; Mice, Inbred C57BL; Pakistan; Pedigree; Phenotype; Retina; Signal Transduction

Mutations in DYNC2LI1 disrupt cilia function and cause short rib polydactyly syndrome. - Taylor, S Paige; Dantas, Tiago J; Duran, Ivan; Wu, Sulin; Lachman, Ralph S; Nelson, Stanley F; Cohn, Daniel H; Vallee, Richard B; Krakow, Deborah (Nat Commun, 2015)
The short rib polydactyly syndromes (SRPSs) are a heterogeneous group of autosomal recessive, perinatal lethal skeletal disorders characterized primarily by short, horizontal ribs, short limbs and polydactyly. Mutations in several genes affecting intraflagellar transport (IFT) cause SRPS but they do not account for all cases. Here we identify an additional SRPS gene and further unravel the functional basis for IFT. We perform whole-exome sequencing and identify mutations in a new disease-producing gene, cytoplasmic dynein-2 light intermediate chain 1, DYNC2LI1, segregating with disease in three families. Using primary fibroblasts, we show that DYNC2LI1 is essential for dynein-2 complex stability and that mutations in DYNC2LI1 result in variable length, including hyperelongated, cilia, Hedgehog pathway impairment and ciliary IFT accumulations. The findings in this study expand our understanding of SRPS locus heterogeneity and demonstrate the importance of DYNC2LI1 in dynein-2 complex stability, cilium function, Hedgehog regulation and skeletogenesis.
Keywords: Biological Transport; Cilia; Cytoplasmic Dyneins; Cytoskeleton; Female; Fibroblasts; Flagella; Hedgehog Proteins; Humans; Male; Mutation; Pedigree; Short Rib-Polydactyly Syndrome

Mutations in SPATA5 Are Associated with Microcephaly, Intellectual Disability, Seizures, and Hearing Loss. - Tanaka, Akemi J; Cho, Megan T; Millan, Francisca; Juusola, Jane; Retterer, Kyle; Joshi, Charuta; Niyazov, Dmitriy; Garnica, Adolfo; Gratz, Edward; Deardorff, Matthew; Wilkins, Alisha; Ortiz-Gonzalez, Xilma; et al. (Am J Hum Genet, 2015)
Using whole-exome sequencing, we have identified in ten families 14 individuals with microcephaly, developmental delay, intellectual disability, hypotonia, spasticity, seizures, sensorineural hearing loss, cortical visual impairment, and rare autosomal-recessive predicted pathogenic variants in spermatogenesis-associated protein 5 (SPATA5). SPATA5 encodes a ubiquitously expressed member of the ATPase associated with diverse activities (AAA) protein family and is involved in mitochondrial morphogenesis during early spermatogenesis. It might also play a role in post-translational modification during cell differentiation in neuronal development. Mutations in SPATA5 might affect brain development and function, resulting in microcephaly, developmental delay, and intellectual disability.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Base Sequence; Exome; Female; Gene Frequency; Genes, Recessive; Hearing Loss; Homeodomain Proteins; Humans; Intellectual Disability; Male; Microcephaly; Molecular Sequence Data; Mutation; Seizures; Sequence Alignment; Sequence Analysis, DNA

Mutations in TBX18 Cause Dominant Urinary Tract Malformations via Transcriptional Dysregulation of Ureter Development. - Vivante, Asaf; Kleppa, Marc-Jens; Schulz, Julian; Kohl, Stefan; Sharma, Amita; Chen, Jing; Shril, Shirlee; Hwang, Daw-Yang; Weiss, Anna-Carina; Kaminski, Michael M; Shukrun, Rachel; Kemper, Markus J; et al. (Am J Hum Genet, 2015)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in the first three decades of life. Identification of single-gene mutations that cause CAKUT permits the first insights into related disease mechanisms. However, for most cases the underlying defect remains elusive. We identified a kindred with an autosomal-dominant form of CAKUT with predominant ureteropelvic junction obstruction. By whole exome sequencing, we identified a heterozygous truncating mutation (c.1010delG) of T-Box transcription factor 18 (TBX18) in seven affected members of the large kindred. A screen of additional families with CAKUT identified three families harboring two heterozygous TBX18 mutations (c.1570C>T and c.487A>G). TBX18 is essential for developmental specification of the ureteric mesenchyme and ureteric smooth muscle cells. We found that all three TBX18 altered proteins still dimerized with the wild-type protein but had prolonged protein half life and exhibited reduced transcriptional repression activity compared to wild-type TBX18. The p.Lys163Glu substitution altered an amino acid residue critical for TBX18-DNA interaction, resulting in impaired TBX18-DNA binding. These data indicate that dominant-negative TBX18 mutations cause human CAKUT by interference with TBX18 transcriptional repression, thus implicating ureter smooth muscle cell development in the pathogenesis of human CAKUT.
Keywords: Base Sequence; Electrophoretic Mobility Shift Assay; Exome; Gene Expression Regulation, Developmental; Genes, Dominant; HEK293 Cells; Humans; Immunohistochemistry; Immunoprecipitation; Microscopy, Fluorescence; Molecular Sequence Data; Muscle, Smooth; Mutation; Pedigree; Sequence Analysis, DNA; T-Box Domain Proteins; Ureter; Urinary Tract

PacBio-LITS: a large-insert targeted sequencing method for characterization of human disease-associated chromosomal structural variations. - Wang, Min; Beck, Christine R; English, Adam C; Meng, Qingchang; Buhay, Christian; Han, Yi; Doddapaneni, Harsha V; Yu, Fuli; Boerwinkle, Eric; Lupski, James R; Muzny, Donna M; Gibbs, Richard A (BMC Genomics, 2015)
BACKGROUND: Generation of long (>5 Kb) DNA sequencing reads provides an approach for interrogation of complex regions in the human genome. Currently, large-insert whole genome sequencing (WGS) technologies from Pacific Biosciences (PacBio) enable analysis of chromosomal structural variations (SVs), but the cost to achieve the required sequence coverage across the entire human genome is high. RESULTS: We developed a method (termed PacBio-LITS) that combines oligonucleotide-based DNA target-capture enrichment technologies with PacBio large-insert library preparation to facilitate SV studies at specific chromosomal regions. PacBio-LITS provides deep sequence coverage at the specified sites at substantially reduced cost compared with PacBio WGS. The efficacy of PacBio-LITS is illustrated by delineating the breakpoint junctions of low copy repeat (LCR)-associated complex structural rearrangements on chr17p11.2 in patients diagnosed with Potocki-Lupski syndrome (PTLS; MIM#610883). We successfully identified previously determined breakpoint junctions in three PTLS cases, and also were able to discover novel junctions in repetitive sequences, including LCR-mediated breakpoints. The new information has enabled us to propose mechanisms for formation of these structural variants. CONCLUSIONS: The new method leverages the cost efficiency of targeted capture-sequencing as well as the mappability and scaffolding capabilities of long sequencing reads generated by the PacBio platform. It is therefore suitable for studying complex SVs, especially those involving LCRs, inversions, and the generation of chimeric Alu elements at the breakpoints. Other genomic research applications, such as haplotype phasing and small insertion and deletion validation could also benefit from this technology.
Keywords: Chromosome Aberrations; Gene Library; Gene Rearrangement; Genetic Association Studies; Genomics; High-Throughput Nucleotide Sequencing; Humans; Workflow

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA

Root anomalies and dentin dysplasia in autosomal recessive hyperphosphatemic familial tumoral calcinosis (HFTC). - Vieira, Alexandre R; Lee, Moses; Vairo, Filippo; Loguercio Leite, Julio Cesar; Munerato, Maria Cristina; Visioli, Fernanda; D'Ávila, Stéphanie Rodrigues; Wang, Shih-Kai; Choi, Murim; Simmer, James P; Hu, Jan C-C (Oral Surg Oral Med Oral Pathol Oral Radiol, 2015)
Hyperphosphatemic familial tumoral calcinosis (HFTC, OMIM #211900) is an autosomal recessive metabolic disorder characterized by hyperphosphatemia, tooth root defects, and the progressive deposition of calcium phosphate crystals in periarticular spaces, soft tissues, and sometimes bone.(1) In this HFTC case report, we document the dental phenotype associated with a homozygous missense mutation (g.29077 C>T; c.484 C>T; p.Arg162*) in GALNT3 (OMIM 6017563), a gene encoding UDP-GalNAc transferase 3 that catalyzes the first step of O-linked oligosaccharide biosynthesis in the Golgi. The medical and dental pathology is believed to be caused primarily by high serum phosphate levels (hyperphosphatemia), which, in turn, is caused by failure of GALNT3 to glycosylate the phosphate regulator protein FGF23, impairing its ability inhibit reabsorption of filtered phosphate in the kidneys.
Keywords: Adolescent; Calcinosis; Dentin Dysplasia; Humans; Hyperostosis, Cortical, Congenital; Hyperphosphatemia; Male; Mutation, Missense; N-Acetylgalactosaminyltransferases; Pedigree; Phenotype; Radiography, Panoramic; Tooth Root

Safety and Proof-of-Concept Study of Oral QLT091001 in Retinitis Pigmentosa Due to Inherited Deficiencies of Retinal Pigment Epithelial 65 Protein (RPE65) or Lecithin:Retinol Acyltransferase (LRAT). - Scholl, Hendrik P N; Moore, Anthony T; Koenekoop, Robert K; Wen, Yuquan; Fishman, Gerald A; van den Born, L Ingeborgh; Bittner, Ava; Bowles, Kristen; Fletcher, Emily C; Collison, Frederick T; Dagnelie, Gislin; Degli Eposti, Simona; et al. (PLoS One, 2015)
UNLABELLED: Restoring vision in inherited retinal degenerations remains an unmet medical need. In mice exhibiting a genetically engineered block of the visual cycle, vision was recently successfully restored by oral administration of 9-cis-retinyl acetate (QLT091001). Safety and visual outcomes of a once-daily oral dose of 40 mg/m2/day QLT091001 for 7 consecutive days was investigated in an international, multi-center, open-label, proof-of-concept study in 18 patients with RPE65- or LRAT-related retinitis pigmentosa. Eight of 18 patients (44%) showed a ≥20% increase and 4 of 18 (22%) showed a ≥40% increase in functional retinal area determined from Goldmann visual fields; 12 (67%) and 5 (28%) of 18 patients showed a ≥5 and ≥10 ETDRS letter score increase of visual acuity, respectively, in one or both eyes at two or more visits within 2 months of treatment. In two patients who underwent fMRI, a significant positive response was measured to stimuli of medium contrast, moving, pattern targets in both left and right hemispheres of the occipital cortex. There were no serious adverse events. Treatment-related adverse events were transient and the most common included headache, photophobia, nausea, vomiting, and minor biochemical abnormalities. Measuring the outer segment length of the photoreceptor layer with high-definition optical coherence tomography was highly predictive of treatment responses with responders having a significantly larger baseline outer segment thickness (11.7 ± 4.8 μm, mean ± 95% CI) than non-responders (3.5 ± 1.2 μm). This structure-function relationship suggests that treatment with QLT091001 is more likely to be efficacious if there is sufficient photoreceptor integrity. TRIAL REGISTRATION: ClinicalTrials.gov NCT01014052.
Keywords: Acyltransferases; Administration, Oral; Adult; Anticarcinogenic Agents; Cerebral Cortex; Child; cis-trans-Isomerases; Drug Dosage Calculations; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Radiography; Retinal Ganglion Cells; Retinal Neurons; Retinitis Pigmentosa; Treatment Outcome; Visual Acuity; Visual Fields; Vitamin A; Young Adult

A second locus for Schneckenbecken dysplasia identified by a mutation in the gene encoding inositol polyphosphate phosphatase-like 1 (INPPL1). - Lee, Hane; Nevarez, Lisette; Lachman, Ralph S; Wilcox, William R; Krakow, Deborah; Cohn, Daniel H (Am J Med Genet A, 2015)
Keywords: Exome; Gene Expression; Genetic Loci; Gestational Age; Homozygote; Humans; Hydrops Fetalis; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Stillbirth

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Muzny, Donna M; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Gibbs, Richard A; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

An siRNA-based functional genomics screen for the identification of regulators of ciliogenesis and ciliopathy genes. - Wheway, Gabrielle; Schmidts, Miriam; Mans, Dorus A; Szymanska, Katarzyna; Nguyen, Thanh-Minh T; Racher, Hilary; Phelps, Ian G; Toedt, Grischa; Kennedy, Julie; Wunderlich, Kirsten A; Sorusch, Nasrin; Abdelhamed, Zakia A; et al. (Nat Cell Biol, 2015)
Defects in primary cilium biogenesis underlie the ciliopathies, a growing group of genetic disorders. We describe a whole-genome siRNA-based reverse genetics screen for defects in biogenesis and/or maintenance of the primary cilium, obtaining a global resource. We identify 112 candidate ciliogenesis and ciliopathy genes, including 44 components of the ubiquitin-proteasome system, 12 G-protein-coupled receptors, and 3 pre-mRNA processing factors (PRPF6, PRPF8 and PRPF31) mutated in autosomal dominant retinitis pigmentosa. The PRPFs localize to the connecting cilium, and PRPF8- and PRPF31-mutated cells have ciliary defects. Combining the screen with exome sequencing data identified recessive mutations in PIBF1, also known as CEP90, and C21orf2, also known as LRRC76, as causes of the ciliopathies Joubert and Jeune syndromes. Biochemical approaches place C21orf2 within key ciliopathy-associated protein modules, offering an explanation for the skeletal and retinal involvement observed in individuals with C21orf2 variants. Our global, unbiased approaches provide insights into ciliogenesis complexity and identify roles for unanticipated pathways in human genetic disease.
Keywords: Abnormalities, Multiple; Animals; Caenorhabditis elegans; Cerebellar Diseases; Cerebellum; Cilia; Ciliary Motility Disorders; Databases, Genetic; Ellis-Van Creveld Syndrome; Eye Abnormalities; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Genomics; HEK293 Cells; High-Throughput Nucleotide Sequencing; Humans; Kidney Diseases, Cystic; Membrane Proteins; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Photoreceptor Cells; Pregnancy Proteins; Proteins; Reproducibility of Results; Retina; RNA Interference; Suppressor Factors, Immunologic; Transfection; Zebrafish

TBX6 null variants and a common hypomorphic allele in congenital scoliosis. - Wu, N; Ming, X; Xiao, J; Wu, Z; Chen, X; Shinawi, M; Shen, Y; Yu, G; Liu, J; Xie, H; Gucev, Z S; Liu, S; et al. (N Engl J Med, 2015)
BACKGROUND: Congenital scoliosis is a common type of vertebral malformation. Genetic susceptibility has been implicated in congenital scoliosis. METHODS: We evaluated 161 Han Chinese persons with sporadic congenital scoliosis, 166 Han Chinese controls, and 2 pedigrees, family members of which had a 16p11.2 deletion, using comparative genomic hybridization, quantitative polymerase-chain-reaction analysis, and DNA sequencing. We carried out tests of replication using an additional series of 76 Han Chinese persons with congenital scoliosis and a multicenter series of 42 persons with 16p11.2 deletions. RESULTS: We identified a total of 17 heterozygous TBX6 null mutations in the 161 persons with sporadic congenital scoliosis (11%); we did not observe any null mutations in TBX6 in 166 controls (P<3.8×10(-6)). These null alleles include copy-number variants (12 instances of a 16p11.2 deletion affecting TBX6) and single-nucleotide variants (1 nonsense and 4 frame-shift mutations). However, the discordant intrafamilial phenotypes of 16p11.2 deletion carriers suggest that heterozygous TBX6 null mutation is insufficient to cause congenital scoliosis. We went on to identify a common TBX6 haplotype as the second risk allele in all 17 carriers of TBX6 null mutations (P<1.1×10(-6)). Replication studies involving additional persons with congenital scoliosis who carried a deletion affecting TBX6 confirmed this compound inheritance model. In vitro functional assays suggested that the risk haplotype is a hypomorphic allele. Hemivertebrae are characteristic of TBX6-associated congenital scoliosis. CONCLUSIONS: Compound inheritance of a rare null mutation and a hypomorphic allele of TBX6 accounted for up to 11% of congenital scoliosis cases in the series that we analyzed. (Funded by the National Basic Research Program of China and others.).
Keywords: Adolescent; Asian Continental Ancestry Group; Child; Child, Preschool; Chromosomes, Human, Pair 16; DNA Copy Number Variations; Female; Genetic Predisposition to Disease; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Radiography; Scoliosis; Sequence Deletion; Spine; T-Box Domain Proteins

Truncating mutations in the last exon of NOTCH3 cause lateral meningocele syndrome. - Gripp, Karen W; Robbins, Katherine M; Sobreira, Nara L; Witmer, P Dane; Bird, Lynne M; Avela, Kristiina; Mäkitie, Outi; Alves, Daniela; Hogue, Jacob S; Zackai, Elaine H; Doheny, Kimberly F; Stabley, Deborah L; et al. (Am J Med Genet A, 2015)
Lateral meningocele syndrome (LMS, OMIM%130720), also known as Lehman syndrome, is a very rare skeletal disorder with facial anomalies, hypotonia and meningocele-related neurologic dysfunction. The characteristic lateral meningoceles represent the severe end of the dural ectasia spectrum and are typically most severe in the lower spine. Facial features of LMS include hypertelorism and telecanthus, high arched eyebrows, ptosis, midfacial hypoplasia, micrognathia, high and narrow palate, low-set ears and a hypotonic appearance. Hyperextensibility, hernias and scoliosis reflect a connective tissue abnormality, and aortic dilation, a high-pitched nasal voice, wormian bones and osteolysis may be present. Lateral meningocele syndrome has phenotypic overlap with Hajdu-Cheney syndrome. We performed exome resequencing in five unrelated individuals with LMS and identified heterozygous truncating NOTCH3 mutations. In an additional unrelated individual Sanger sequencing revealed a deleterious variant in the same exon 33. In total, five novel de novo NOTCH3 mutations were identified in six unrelated patients. One had a 26 bp deletion (c.6461_6486del, p.G2154fsTer78), two carried the same single base pair insertion (c.6692_93insC, p.P2231fsTer11), and three individuals had a nonsense point mutation at c.6247A > T (pK2083*), c.6663C > G (p.Y2221*) or c.6732C > A, (p.Y2244*). All mutations cluster into the last coding exon, resulting in premature termination of the protein and truncation of the negative regulatory proline-glutamate-serine-threonine rich PEST domain. Our results suggest that mutant mRNA products escape nonsense mediated decay. The truncated NOTCH3 may cause gain-of-function through decreased clearance of the active intracellular product, resembling NOTCH2 mutations in the clinically related Hajdu-Cheney syndrome and contrasting the NOTCH3 missense mutations causing CADASIL.
Keywords: Abnormalities, Multiple; Child; Child, Preschool; DNA Mutational Analysis; Exome; Exons; Facies; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Meningocele; Mutation; Phenotype; Receptor, Notch3; Receptors, Notch; Young Adult

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Adenylate cyclase 1 (ADCY1) mutations cause recessive hearing impairment in humans and defects in hair cell function and hearing in zebrafish. - Santos-Cortez, Regie Lyn P; Lee, Kwanghyuk; Giese, Arnaud P; Ansar, Muhammad; Amin-ud-Din, Muhammad; Rehn, Kira; Wang, Xin; Aziz, Abdul; Chiu, Ilene; Hussain Ali, Raja; Smith, Joshua D; Shendure, Jay; et al. (Hum Mol Genet, 2014)
Cyclic AMP (cAMP) production, which is important for mechanotransduction within the inner ear, is catalyzed by adenylate cyclases (AC). However, knowledge of the role of ACs in hearing is limited. Previously, a novel autosomal recessive non-syndromic hearing impairment locus DFNB44 was mapped to chromosome 7p14.1-q11.22 in a consanguineous family from Pakistan. Through whole-exome sequencing of DNA samples from hearing-impaired family members, a nonsense mutation c.3112C>T (p.Arg1038*) within adenylate cyclase 1 (ADCY1) was identified. This stop-gained mutation segregated with hearing impairment within the family and was not identified in ethnically matched controls or within variant databases. This mutation is predicted to cause the loss of 82 amino acids from the carboxyl tail, including highly conserved residues within the catalytic domain, plus a calmodulin-stimulation defect, both of which are expected to decrease enzymatic efficiency. Individuals who are homozygous for this mutation had symmetric, mild-to-moderate mixed hearing impairment. Zebrafish adcy1b morphants had no FM1-43 dye uptake and lacked startle response, indicating hair cell dysfunction and gross hearing impairment. In the mouse, Adcy1 expression was observed throughout inner ear development and maturation. ADCY1 was localized to the cytoplasm of supporting cells and hair cells of the cochlea and vestibule and also to cochlear hair cell nuclei and stereocilia. Ex vivo studies in COS-7 cells suggest that the carboxyl tail of ADCY1 is essential for localization to actin-based microvilli. These results demonstrate that ADCY1 has an evolutionarily conserved role in hearing and that cAMP signaling is important to hair cell function within the inner ear.
Keywords: Adenylyl Cyclases; Animals; Cercopithecus aethiops; Codon, Nonsense; COS Cells; Cyclic AMP; Cytoplasm; Ear, Inner; Female; Hair Cells, Auditory; Hearing Loss; Humans; Labyrinth Supporting Cells; Male; Mice; Zebrafish

The Alu-rich genomic architecture of SPAST predisposes to diverse and functionally distinct disease-associated CNV alleles. - Boone, Philip M; Yuan, Bo; Campbell, Ian M; Scull, Jennifer C; Withers, Marjorie A; Baggett, Brett C; Beck, Christine R; Shaw, Christine J; Stankiewicz, Pawel; Moretti, Paolo; Goodwin, Wendy E; Hein, Nichole; et al. (Am J Hum Genet, 2014)
Intragenic copy-number variants (CNVs) contribute to the allelic spectrum of both Mendelian and complex disorders. Although pathogenic deletions and duplications in SPAST (mutations in which cause autosomal-dominant spastic paraplegia 4 [SPG4]) have been described, their origins and molecular consequences remain obscure. We mapped breakpoint junctions of 54 SPAST CNVs at nucleotide resolution. Diverse combinations of exons are deleted or duplicated, highlighting the importance of particular exons for spastin function. Of the 54 CNVs, 38 (70%) appear to be mediated by an Alu-based mechanism, suggesting that the Alu-rich genomic architecture of SPAST renders this locus susceptible to various genome rearrangements. Analysis of breakpoint Alus further informs a model of Alu-mediated CNV formation characterized by small CNV size and potential involvement of mechanisms other than homologous recombination. Twelve deletions (22%) overlap part of SPAST and a portion of a nearby, directly oriented gene, predicting novel chimeric genes in these subjects' genomes. cDNA from a subject with a SPAST final exon deletion contained multiple SPAST:SLC30A6 fusion transcripts, indicating that SPAST CNVs can have transcriptional effects beyond the gene itself. SLC30A6 has been implicated in Alzheimer disease, so these fusion gene data could explain a report of spastic paraplegia and dementia cosegregating in a family with deletion of the final exon of SPAST. Our findings provide evidence that the Alu genomic architecture of SPAST predisposes to diverse CNV alleles with distinct transcriptional--and possibly phenotypic--consequences. Moreover, we provide further mechanistic insights into Alu-mediated copy-number change that are extendable to other loci.
Keywords: Adenosine Triphosphatases; Alu Elements; Base Sequence; Cation Transport Proteins; Cell Line, Transformed; DNA Copy Number Variations; Genotype; Humans; Protein Isoforms; Recombinant Fusion Proteins; Sequence Analysis, DNA; Sequence Deletion; Spastic Paraplegia, Hereditary; Spastin

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration. - Schaffer, Ashleigh E; Eggens, Veerle R C; Çağlayan, Ahmet Okay; Reuter, Miriam S; Scott, Eric; Coufal, Nicole G; Silhavy, Jennifer L; Xue, Yuanchao; Kayserili, Hülya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
Keywords: Animals; Brain; Cerebellum; Cleavage And Polyadenylation Specificity Factor; Female; Humans; Male; Mice; Models, Molecular; Neurodegenerative Diseases; Nuclear Proteins; Pedigree; Phosphotransferases; RNA Splicing; RNA, Transfer; Saccharomyces cerevisiae; Transcription Factors; Zebrafish; Zebrafish Proteins

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Expanding the phenotypic spectrum of ARID1B-mediated disorders and identification of altered cell-cycle dynamics due to ARID1B haploinsufficiency. - Sim, Joe C H; White, Susan M; Fitzpatrick, Elizabeth; Wilson, Gabrielle R; Gillies, Greta; Pope, Kate; Mountford, Hayley S; Torring, Pernille M; McKee, Shane; Vulto-van Silfhout, Anneke T; Jhangiani, Shalini N; Muzny, Donna M; et al. (Orphanet J Rare Dis, 2014)
BACKGROUND: Mutations in genes encoding components of the Brahma-associated factor (BAF) chromatin remodeling complex have recently been shown to contribute to multiple syndromes characterised by developmental delay and intellectual disability. ARID1B mutations have been identified as the predominant cause of Coffin-Siris syndrome and have also been shown to be a frequent cause of nonsyndromic intellectual disability. Here, we investigate the molecular basis of a patient with an overlapping but distinctive phenotype of intellectual disability, plantar fat pads and facial dysmorphism. METHODS/RESULTS: High density microarray analysis of the patient demonstrated a heterozygous deletion at 6q25.3, which resulted in the loss of four genes including AT Rich Interactive Domain 1B (ARID1B). Subsequent quantitative real-time PCR analysis revealed ARID1B haploinsufficiency in the patient. Analysis of both patient-derived and ARID1B knockdown fibroblasts after serum starvation demonstrated delayed cell cycle re-entry associated with reduced cell number in the S1 phase. Based on the patient's distinctive phenotype, we ascertained four additional patients and identified heterozygous de novo ARID1B frameshift or nonsense mutations in all of them. CONCLUSIONS: This study broadens the spectrum of ARID1B associated phenotypes by describing a distinctive phenotype including plantar fat pads but lacking the hypertrichosis or fifth nail hypoplasia associated with Coffin-Siris syndrome. We present the first direct evidence in patient-derived cells that alterations in cell cycle contribute to the underlying pathogenesis of syndromes associated with ARID1B haploinsufficiency.
Keywords: Abnormalities, Multiple; Cell Cycle; Chromatin Assembly and Disassembly; DNA-Binding Proteins; Face; Female; Hand Deformities, Congenital; Haploinsufficiency; Humans; Intellectual Disability; Male; Micrognathism; Neck; Transcription Factors

A general framework for estimating the relative pathogenicity of human genetic variants. - Kircher, Martin; Witten, Daniela M; Jain, Preti; O'Roak, Brian J; Cooper, Gregory M; Shendure, Jay (Nat Genet, 2014)
Current methods for annotating and interpreting human genetic variation tend to exploit a single information type (for example, conservation) and/or are restricted in scope (for example, to missense changes). Here we describe Combined Annotation-Dependent Depletion (CADD), a method for objectively integrating many diverse annotations into a single measure (C score) for each variant. We implement CADD as a support vector machine trained to differentiate 14.7 million high-frequency human-derived alleles from 14.7 million simulated variants. We precompute C scores for all 8.6 billion possible human single-nucleotide variants and enable scoring of short insertions-deletions. C scores correlate with allelic diversity, annotations of functionality, pathogenicity, disease severity, experimentally measured regulatory effects and complex trait associations, and they highly rank known pathogenic variants within individual genomes. The ability of CADD to prioritize functional, deleterious and pathogenic variants across many functional categories, effect sizes and genetic architectures is unmatched by any current single-annotation method.
Keywords: Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; INDEL Mutation; Models, Genetic; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Selection, Genetic; Support Vector Machine

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hülya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Nails, Malformed; Phenotype; Sequence Analysis, DNA; Young Adult

Germ-line and somatic DICER1 mutations in pineoblastoma. - de Kock, Leanne; Sabbaghian, Nelly; Druker, Harriet; Weber, Evan; Hamel, Nancy; Miller, Suzanne; Choong, Catherine S; Gottardo, Nicholas G; Kees, Ursula R; Rednam, Surya P; van Hest, Liselotte P; Jongmans, Marjolijn C; et al. (Acta Neuropathol, 2014)
Germ-line RB-1 mutations predispose to pineoblastoma (PinB), but other predisposing genetic factors are not well established. We recently identified a germ-line DICER1 mutation in a child with a PinB. This was accompanied by loss of heterozygosity (LOH) of the wild-type allele within the tumour. We set out to establish the prevalence of DICER1 mutations in an opportunistically ascertained series of PinBs. Twenty-one PinB cases were studied: Eighteen cases had not undergone previous testing for DICER1 mutations; three patients were known carriers of germ-line DICER1 mutations. The eighteen PinBs were sequenced by Sanger and/or Fluidigm-based next-generation sequencing to identify DICER1 mutations in blood gDNA and/or tumour gDNA. Testing for somatic DICER1 mutations was also conducted on one case with a known germ-line DICER1 mutation. From the eighteen PinBs, we identified four deleterious DICER1 mutations, three of which were germ line in origin, and one for which a germ line versus somatic origin could not be determined; in all four, the second allele was also inactivated leading to complete loss of DICER1 protein. No somatic DICER1 RNase IIIb mutations were identified. One PinB arising in a germ-line DICER1 mutation carrier was found to have LOH. This study suggests that germ-line DICER1 mutations make a clinically significant contribution to PinB, establishing DICER1 as an important susceptibility gene for PinB and demonstrates PinB to be a manifestation of a germ-line DICER1 mutation. The means by which the second allele is inactivated may differ from other DICER1-related tumours.
Keywords: Adolescent; Brain Neoplasms; Child; Child, Preschool; DEAD-box RNA Helicases; DNA Mutational Analysis; Family Health; Female; Germ-Line Mutation; Humans; Infant; Male; Pineal Gland; Pinealoma; Ribonuclease III; Young Adult

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Yuan, Bo; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors

Increased frequency of de novo copy number variants in congenital heart disease by integrative analysis of single nucleotide polymorphism array and exome sequence data. - Glessner, Joseph T; Bick, Alexander G; Ito, Kaoru; Homsy, Jason; Rodriguez-Murillo, Laura; Fromer, Menachem; Mazaika, Erica; Vardarajan, Badri; Italia, Michael; Leipzig, Jeremy; DePalma, Steven R; Golhar, Ryan; et al. (Circ Res, 2014)
RATIONALE: Congenital heart disease (CHD) is among the most common birth defects. Most cases are of unknown pathogenesis. OBJECTIVE: To determine the contribution of de novo copy number variants (CNVs) in the pathogenesis of sporadic CHD. METHODS AND RESULTS: We studied 538 CHD trios using genome-wide dense single nucleotide polymorphism arrays and whole exome sequencing. Results were experimentally validated using digital droplet polymerase chain reaction. We compared validated CNVs in CHD cases with CNVs in 1301 healthy control trios. The 2 complementary high-resolution technologies identified 63 validated de novo CNVs in 51 CHD cases. A significant increase in CNV burden was observed when comparing CHD trios with healthy trios, using either single nucleotide polymorphism array (P=7×10(-5); odds ratio, 4.6) or whole exome sequencing data (P=6×10(-4); odds ratio, 3.5) and remained after removing 16% of de novo CNV loci previously reported as pathogenic (P=0.02; odds ratio, 2.7). We observed recurrent de novo CNVs on 15q11.2 encompassing CYFIP1, NIPA1, and NIPA2 and single de novo CNVs encompassing DUSP1, JUN, JUP, MED15, MED9, PTPRE SREBF1, TOP2A, and ZEB2, genes that interact with established CHD proteins NKX2-5 and GATA4. Integrating de novo variants in whole exome sequencing and CNV data suggests that ETS1 is the pathogenic gene altered by 11q24.2-q25 deletions in Jacobsen syndrome and that CTBP2 is the pathogenic gene in 10q subtelomeric deletions. CONCLUSIONS: We demonstrate a significantly increased frequency of rare de novo CNVs in CHD patients compared with healthy controls and suggest several novel genetic loci for CHD.
Keywords: Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Exome; Gene Frequency; Gene Regulatory Networks; Heart Defects, Congenital; Humans; Molecular Sequence Data; Polymorphism, Single Nucleotide

Laterality defects other than situs inversus totalis in primary ciliary dyskinesia: insights into situs ambiguus and heterotaxy. - Shapiro, Adam J; Davis, Stephanie D; Ferkol, Thomas; Dell, Sharon D; Rosenfeld, Margaret; Olivier, Kenneth N; Sagel, Scott D; Milla, Carlos; Zariwala, Maimoona A; Wolf, Whitney; Carson, Johnny L; Hazucha, Milan J; et al. (Chest, 2014)
BACKGROUND: Motile cilia dysfunction causes primary ciliary dyskinesia (PCD), situs inversus totalis (SI), and a spectrum of laterality defects, yet the prevalence of laterality defects other than SI in PCD has not been prospectively studied. METHODS: In this prospective study, participants with suspected PCD were referred to our multisite consortium. We measured nasal nitric oxide (nNO) level, examined cilia with electron microscopy, and analyzed PCD-causing gene mutations. Situs was classified as (1) situs solitus (SS), (2) SI, or (3) situs ambiguus (SA), including heterotaxy. Participants with hallmark electron microscopic defects, biallelic gene mutations, or both were considered to have classic PCD. RESULTS: Of 767 participants (median age, 8.1 years, range, 0.1-58 years), classic PCD was defined in 305, including 143 (46.9%), 125 (41.0%), and 37 (12.1%) with SS, SI, and SA, respectively. A spectrum of laterality defects was identified with classic PCD, including 2.6% and 2.3% with SA plus complex or simple cardiac defects, respectively; 4.6% with SA but no cardiac defect; and 2.6% with an isolated possible laterality defect. Participants with SA and classic PCD had a higher prevalence of PCD-associated respiratory symptoms vs SA control participants (year-round wet cough, P < .001; year-round nasal congestion, P = .015; neonatal respiratory distress, P = .009; digital clubbing, P = .021) and lower nNO levels (median, 12 nL/min vs 252 nL/min; P < .001). CONCLUSIONS: At least 12.1% of patients with classic PCD have SA and laterality defects ranging from classic heterotaxy to subtle laterality defects. Specific clinical features of PCD and low nNO levels help to identify PCD in patients with laterality defects. TRIAL REGISTRY: ClinicalTrials.gov; No.: NCT00323167; URL: www.clinicaltrials.gov.
Keywords: Adolescent; Adult; Biopsy; Child; Child, Preschool; Cilia; DNA; DNA Mutational Analysis; Female; Humans; Infant; Infant, Newborn; Kartagener Syndrome; Male; Microscopy, Electron, Transmission; Middle Aged; Mutation; Prevalence; Prospective Studies; Tomography, X-Ray Computed; United States; Young Adult

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Yu, Fuli; Muzny, Donna; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

Loss-of-function HDAC8 mutations cause a phenotypic spectrum of Cornelia de Lange syndrome-like features, ocular hypertelorism, large fontanelle and X-linked inheritance. - Kaiser, Frank J; Ansari, Morad; Braunholz, Diana; Concepción Gil-Rodríguez, María; Decroos, Christophe; Wilde, Jonathan J; Fincher, Christopher T; Kaur, Maninder; Bando, Masashige; Amor, David J; Atwal, Paldeep S; Bahlo, Melanie; et al. (Hum Mol Genet, 2014)
Cornelia de Lange syndrome (CdLS) is a multisystem genetic disorder with distinct facies, growth failure, intellectual disability, distal limb anomalies, gastrointestinal and neurological disease. Mutations in NIPBL, encoding a cohesin regulatory protein, account for >80% of cases with typical facies. Mutations in the core cohesin complex proteins, encoded by the SMC1A, SMC3 and RAD21 genes, together account for ∼5% of subjects, often with atypical CdLS features. Recently, we identified mutations in the X-linked gene HDAC8 as the cause of a small number of CdLS cases. Here, we report a cohort of 38 individuals with an emerging spectrum of features caused by HDAC8 mutations. For several individuals, the diagnosis of CdLS was not considered prior to genomic testing. Most mutations identified are missense and de novo. Many cases are heterozygous females, each with marked skewing of X-inactivation in peripheral blood DNA. We also identified eight hemizygous males who are more severely affected. The craniofacial appearance caused by HDAC8 mutations overlaps that of typical CdLS but often displays delayed anterior fontanelle closure, ocular hypertelorism, hooding of the eyelids, a broader nose and dental anomalies, which may be useful discriminating features. HDAC8 encodes the lysine deacetylase for the cohesin subunit SMC3 and analysis of the functional consequences of the missense mutations indicates that all cause a loss of enzymatic function. These data demonstrate that loss-of-function mutations in HDAC8 cause a range of overlapping human developmental phenotypes, including a phenotypically distinct subgroup of CdLS.
Keywords: Amino Acid Sequence; Child; Child, Preschool; Cohort Studies; Cranial Fontanelles; De Lange Syndrome; Eye Abnormalities; Female; Genes, X-Linked; Histone Deacetylases; Humans; Hypertelorism; Infant; Male; Molecular Sequence Data; Mutation, Missense; Phenotype; Repressor Proteins; Sequence Alignment

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Muzny, Donna M; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutation of NLRC4 causes a syndrome of enterocolitis and autoinflammation. - Romberg, Neil; Al Moussawi, Khatoun; Nelson-Williams, Carol; Stiegler, Amy L; Loring, Erin; Choi, Murim; Overton, John; Meffre, Eric; Khokha, Mustafa K; Huttner, Anita J; West, Brian; Podoltsev, Nikolai A; et al. (Nat Genet, 2014)
Upon detection of pathogen-associated molecular patterns, innate immune receptors initiate inflammatory responses. These receptors include cytoplasmic NOD-like receptors (NLRs) whose stimulation recruits and proteolytically activates caspase-1 within the inflammasome, a multiprotein complex. Caspase-1 mediates the production of interleukin-1 family cytokines (IL1FCs), leading to fever and inflammatory cell death (pyroptosis). Mutations that constitutively activate these pathways underlie several autoinflammatory diseases with diverse clinical features. We describe a family with a previously unreported syndrome featuring neonatal-onset enterocolitis, periodic fever, and fatal or near-fatal episodes of autoinflammation. We show that the disease is caused by a de novo gain-of-function mutation in NLRC4 encoding a p.Val341Ala substitution in the HD1 domain of the protein that cosegregates with disease. Mutant NLRC4 causes constitutive IL1FC production and macrophage cell death. Infected macrophages from affected individuals are polarized toward pyroptosis and exhibit abnormal staining for inflammasome components. These findings identify and describe the cause of a life-threatening but treatable autoinflammatory disease that underscores the divergent roles of the NLRC4 inflammasome.
Keywords: Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Enterocolitis; Exome; Family Health; Fatal Outcome; Female; Humans; Inflammation; Male; Mutation, Missense; Pedigree; Sequence Analysis, DNA; Syndrome

Mutations in PIEZO2 cause Gordon syndrome, Marden-Walker syndrome, and distal arthrogryposis type 5. - McMillin, Margaret J; Beck, Anita E; Chong, Jessica X; Shively, Kathryn M; Buckingham, Kati J; Gildersleeve, Heidi I S; Aracena, Mariana I; Aylsworth, Arthur S; Bitoun, Pierre; Carey, John C; Clericuzio, Carol L; Crow, Yanick J; et al. (Am J Hum Genet, 2014)
Gordon syndrome (GS), or distal arthrogryposis type 3, is a rare, autosomal-dominant disorder characterized by cleft palate and congenital contractures of the hands and feet. Exome sequencing of five GS-affected families identified mutations in piezo-type mechanosensitive ion channel component 2 (PIEZO2) in each family. Sanger sequencing revealed PIEZO2 mutations in five of seven additional families studied (for a total of 10/12 [83%] individuals), and nine families had an identical c.8057G>A (p.Arg2686His) mutation. The phenotype of GS overlaps with distal arthrogryposis type 5 (DA5) and Marden-Walker syndrome (MWS). Using molecular inversion probes for targeted sequencing to screen PIEZO2, we found mutations in 24/29 (82%) DA5-affected families and one of two MWS-affected families. The presence of cleft palate was significantly associated with c.8057G>A (Fisher's exact test, adjusted p value < 0.0001). Collectively, although GS, DA5, and MWS have traditionally been considered separate disorders, our findings indicate that they are etiologically related and perhaps represent variable expressivity of the same condition.
Keywords: Abnormalities, Multiple; Arachnodactyly; Arthrogryposis; Blepharophimosis; Child; Child, Preschool; Cleft Palate; Clubfoot; Connective Tissue Diseases; Contracture; Exome; Female; Hand Deformities, Congenital; Humans; Ion Channels; Male; Mutation; Ophthalmoplegia; Pedigree; Retinal Diseases

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult

Mutations in TBC1D24, a gene associated with epilepsy, also cause nonsyndromic deafness DFNB86. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Morell, Robert J; Drummond, Meghan C; Ito, Taku; Lee, Kwanghyuk; Khan, Asma A; Basra, Muhammad Asim R; Wasif, Naveed; Ayub, Muhammad; Ali, Rana A; Raza, Syed I; et al. (Am J Hum Genet, 2014)
Inherited deafness is clinically and genetically heterogeneous. We recently mapped DFNB86, a locus associated with nonsyndromic deafness, to chromosome 16p. In this study, whole-exome sequencing was performed with genomic DNA from affected individuals from three large consanguineous families in which markers linked to DFNB86 segregate with profound deafness. Analyses of these data revealed homozygous mutation c.208G>T (p.Asp70Tyr) or c.878G>C (p.Arg293Pro) in TBC1D24 as the underlying cause of deafness in the three families. Sanger sequence analysis of TBC1D24 in an additional large family in which deafness segregates with DFNB86 identified the c.208G>T (p.Asp70Tyr) substitution. These mutations affect TBC1D24 amino acid residues that are conserved in orthologs ranging from fruit fly to human. Neither variant was observed in databases of single-nucleotide variants or in 634 chromosomes from ethnically matched control subjects. TBC1D24 in the mouse inner ear was immunolocalized predominantly to spiral ganglion neurons, indicating that DFNB86 deafness might be an auditory neuropathy spectrum disorder. Previously, six recessive mutations in TBC1D24 were reported to cause seizures (hearing loss was not reported) ranging in severity from epilepsy with otherwise normal development to epileptic encephalopathy resulting in childhood death. Two of our four families in which deafness segregates with mutant alleles of TBC1D24 were available for neurological examination. Cosegregation of epilepsy and deafness was not observed in these two families. Although the causal relationship between genotype and phenotype is not presently understood, our findings, combined with published data, indicate that recessive alleles of TBC1D24 can cause either epilepsy or nonsyndromic deafness.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Chromosomes, Human, Pair 16; Consanguinity; Deafness; Epilepsy; Exome; Exons; Female; Genes, Recessive; Genetic Loci; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Male; Molecular Sequence Data; Mutation; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA, Messenger; Sequence Analysis, DNA

Mutations in TJP2 cause progressive cholestatic liver disease. - Sambrotta, Melissa; Strautnieks, Sandra; Papouli, Efterpi; Rushton, Peter; Clark, Barnaby E; Parry, David A; Logan, Clare V; Newbury, Lucy J; Kamath, Binita M; Ling, Simon; Grammatikopoulos, Tassos; Wagner, Bart E; et al. (Nat Genet, 2014)
Elucidating genetic causes of cholestasis has proved to be important in understanding the physiology and pathophysiology of the liver. Here we show that protein-truncating mutations in the tight junction protein 2 gene (TJP2) cause failure of protein localization and disruption of tight-junction structure, leading to severe cholestatic liver disease. These findings contrast with those in the embryonic-lethal knockout mouse, highlighting differences in redundancy in junctional complexes between organs and species.
Keywords: Animals; Base Sequence; Cholestasis, Intrahepatic; High-Throughput Nucleotide Sequencing; Humans; Immunoblotting; Immunohistochemistry; Mice; Mice, Knockout; Microscopy, Electron, Transmission; Models, Biological; Molecular Sequence Data; Mutation; Pedigree; Real-Time Polymerase Chain Reaction; Sequence Alignment; Species Specificity; Tight Junctions; Zonula Occludens-2 Protein

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Muzny, Donna M; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

Parental somatic mosaicism is underrecognized and influences recurrence risk of genomic disorders. - Campbell, Ian M; Yuan, Bo; Robberecht, Caroline; Pfundt, Rolph; Szafranski, Przemyslaw; McEntagart, Meriel E; Nagamani, Sandesh C S; Erez, Ayelet; Bartnik, Magdalena; Wiśniowiecka-Kowalnik, Barbara; Plunkett, Katie S; Pursley, Amber N; et al. (Am J Hum Genet, 2014)
New human mutations are thought to originate in germ cells, thus making a recurrence of the same mutation in a sibling exceedingly rare. However, increasing sensitivity of genomic technologies has anecdotally revealed mosaicism for mutations in somatic tissues of apparently healthy parents. Such somatically mosaic parents might also have germline mosaicism that can potentially cause unexpected intergenerational recurrences. Here, we show that somatic mosaicism for transmitted mutations among parents of children with simplex genetic disease is more common than currently appreciated. Using the sensitivity of individual-specific breakpoint PCR, we prospectively screened 100 families with children affected by genomic disorders due to rare deletion copy-number variants (CNVs) determined to be de novo by clinical analysis of parental DNA. Surprisingly, we identified four cases of low-level somatic mosaicism for the transmitted CNV in DNA isolated from parental blood. Integrated probabilistic modeling of gametogenesis developed in response to our observations predicts that mutations in parental blood increase recurrence risk substantially more than parental mutations confined to the germline. Moreover, despite the fact that maternally transmitted mutations are the minority of alleles, our model suggests that sexual dimorphisms in gametogenesis result in a greater proportion of somatically mosaic transmitting mothers who are thus at increased risk of recurrence. Therefore, somatic mosaicism together with sexual differences in gametogenesis might explain a considerable fraction of unexpected recurrences of X-linked recessive disease. Overall, our results underscore an important role for somatic mosaicism and mitotic replicative mutational mechanisms in transmission genetics.
Keywords: Cell Division; DNA Copy Number Variations; Female; Gametogenesis; Genetic Diseases, Inborn; Genomics; Germ Cells; Germ-Line Mutation; Humans; Male; Models, Genetic; Mosaicism; Mutation; Pedigree; Prospective Studies; Recurrence; Risk; Sex Characteristics; Smith-Magenis Syndrome

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Phenotypic expansion of DGKE-associated diseases. - Westland, Rik; Bodria, Monica; Carrea, Alba; Lata, Sneh; Scolari, Francesco; Fremeaux-Bacchi, Veronique; D'Agati, Vivette D; Lifton, Richard P; Gharavi, Ali G; Ghiggeri, Gian Marco; Sanna-Cherchi, Simone (J Am Soc Nephrol, 2014)
Atypical hemolytic uremic syndrome (aHUS) is usually characterized by uncontrolled complement activation. The recent discovery of loss-of-function mutations in DGKE in patients with aHUS and normal complement levels challenged this observation. DGKE, encoding diacylglycerol kinase-ε, has not been implicated in the complement cascade but hypothetically leads to a prothrombotic state. The discovery of this novel mechanism has potential implications for the treatment of infants with aHUS, who are increasingly treated with complement blocking agents. In this study, we used homozygosity mapping and whole-exome sequencing to identify a novel truncating mutation in DGKE (p.K101X) in a consanguineous family with patients affected by thrombotic microangiopathy characterized by significant serum complement activation and consumption of the complement fraction C3. Aggressive plasma infusion therapy controlled systemic symptoms and prevented renal failure, suggesting that this treatment can significantly affect the natural history of this aggressive disease. Our study expands the clinical phenotypes associated with mutations in DGKE and challenges the benefits of complement blockade treatment in such patients. Mechanistic studies of DGKE and aHUS are, therefore, essential to the design of appropriate therapeutic strategies in patients with DGKE mutations.
Keywords: Atypical Hemolytic Uremic Syndrome; Child, Preschool; Diacylglycerol Kinase; Female; Hemolytic-Uremic Syndrome; Humans; Male; Pedigree; Phenotype

Power analysis and sample size estimation for sequence-based association studies. - Wang, Gao T; Li, Biao; Santos-Cortez, Regie P Lyn; Peng, Bo; Leal, Suzanne M (Bioinformatics, 2014)
MOTIVATION: Statistical methods have been developed to test for complex trait rare variant (RV) associations, in which variants are aggregated across a region, which is typically a gene. Power analysis and sample size estimation for sequence-based RV association studies are challenging because of the necessity to realistically model the underlying allelic architecture of complex diseases within a suitable analytical framework to assess the performance of a variety of RV association methods in an unbiased manner. SUMMARY: We developed SEQPower, a software package to perform statistical power analysis for sequence-based association data under a variety of genetic variant and disease phenotype models. It aids epidemiologists in determining the best study design, sample size and statistical tests for sequence-based association studies. It also provides biostatisticians with a platform to fairly compare RV association methods and to validate and assess novel association tests. AVAILABILITY AND IMPLEMENTATION: The SEQPower program, source code, multi-platform executables, documentation, list of association tests, examples and tutorials are available at http://bioinformatics.org/spower.
Keywords: Alleles; Data Interpretation, Statistical; Disease; Genetic Association Studies; Genetic Variation; Humans; Phenotype; Sample Size; Sequence Analysis, DNA; Software

Rare-variant extensions of the transmission disequilibrium test: application to autism exome sequence data. - He, Zongxiao; O'Roak, Brian J; Smith, Joshua D; Wang, Gao; Hooker, Stanley; Santos-Cortez, Regie Lyn P; Li, Biao; Kan, Mengyuan; Krumm, Nik; Nickerson, Deborah A; Shendure, Jay; Eichler, Evan E; et al. (Am J Hum Genet, 2014)
Many population-based rare-variant (RV) association tests, which aggregate variants across a region, have been developed to analyze sequence data. A drawback of analyzing population-based data is that it is difficult to adequately control for population substructure and admixture, and spurious associations can occur. For RVs, this problem can be substantial, because the spectrum of rare variation can differ greatly between populations. A solution is to analyze parent-child trio data, by using the transmission disequilibrium test (TDT), which is robust to population substructure and admixture. We extended the TDT to test for RV associations using four commonly used methods. We demonstrate that for all RV-TDT methods, using proper analysis strategies, type I error is well-controlled even when there are high levels of population substructure or admixture. For trio data, unlike for population-based data, RV allele-counting association methods will lead to inflated type I errors. However type I errors can be properly controlled by obtaining p values empirically through haplotype permutation. The power of the RV-TDT methods was evaluated and compared to the analysis of case-control data with a number of genetic and disease models. The RV-TDT was also used to analyze exome data from 199 Simons Simplex Collection autism trios and an association was observed with variants in ABCA7. Given the problem of adequately controlling for population substructure and admixture in RV association studies and the growing number of sequence-based trio studies, the RV-TDT is extremely beneficial to elucidate the involvement of RVs in the etiology of complex traits.
Keywords: Alleles; Autistic Disorder; Computer Simulation; Exome; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Haplotypes; Humans; Linkage Disequilibrium; Models, Genetic; Phenotype; Sequence Analysis, DNA

Recurrent activating mutation in PRKACA in cortisol-producing adrenal tumors. - Goh, Gerald; Scholl, Ute I; Healy, James M; Choi, Murim; Prasad, Manju L; Nelson-Williams, Carol; Kunstman, John W; Kuntsman, John W; Korah, Reju; Suttorp, Anna-Carinna; Dietrich, Dimo; Haase, Matthias; et al. (Nat Genet, 2014)
Adrenal tumors autonomously producing cortisol cause Cushing's syndrome. We performed exome sequencing of 25 tumor-normal pairs and identified 2 subgroups. Eight tumors (including three carcinomas) had many somatic copy number variants (CNVs) with frequent deletion of CDC42 and CDKN2A, amplification of 5q31.2 and protein-altering mutations in TP53 and RB1. Seventeen tumors (all adenomas) had no somatic CNVs or TP53 or RB1 mutations. Six of these had known gain-of-function mutations in CTNNB1 (β-catenin) or GNAS (Gαs). Six others had somatic mutations in PRKACA (protein kinase A (PKA) catalytic subunit) resulting in a p.Leu206Arg substitution. Further sequencing identified this mutation in 13 of 63 tumors (35% of adenomas with overt Cushing's syndrome). PRKACA, GNAS and CTNNB1 mutations were mutually exclusive. Leu206 directly interacts with the regulatory subunit of PKA, PRKAR1A. Leu206Arg PRKACA loses PRKAR1A binding, increasing the phosphorylation of downstream targets. PKA activity induces cortisol production and cell proliferation, providing a mechanism for tumor development. These findings define distinct mechanisms underlying adrenal cortisol-producing tumors.
Keywords: Adolescent; Adrenal Gland Neoplasms; Adult; Aged; Amino Acid Sequence; Base Sequence; cdc42 GTP-Binding Protein; Cell Proliferation; Cyclic AMP-Dependent Protein Kinase Catalytic Subunits; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Exome; Female; Gene Deletion; Gene Dosage; HEK293 Cells; Humans; Hydrocortisone; Male; Middle Aged; Molecular Sequence Data; Mutation; Phosphorylation; Sequence Analysis, DNA; Sequence Homology, Amino Acid

RNF213 rare variants in an ethnically diverse population with Moyamoya disease. - Cecchi, Alana C; Guo, Dongchuan; Ren, Zhao; Flynn, Kelly; Santos-Cortez, Regie Lyn P; Leal, Suzanne M; Wang, Gao T; Regalado, Ellen S; Steinberg, Gary K; Shendure, Jay; Bamshad, Michael J; Grotta, James C; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there are a lack of data on the role of RNF213 in patients with MMD of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States. METHODS: We initially sequenced RNF213 exons 43, 44, and 45 (encoding the eponymous RING finger domain) and exon 60 (encoding p.R4810K) in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional patients with MMD was then analyzed to identify RNF213 variants globally. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of patients with MMD of Asian descent and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of patients with MMD who underwent exome sequencing. Segregation analysis supported an association with MMD for 2 variants and a lack of association with disease for 1 variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the United States to MMD.
Keywords: Adenosine Triphosphatases; Adolescent; Adult; Child; Cohort Studies; Ethnic Groups; Female; Genetic Variation; Humans; Male; Moyamoya Disease; Population Surveillance; Ubiquitin-Protein Ligases; Young Adult

Somatic mutations in cerebral cortical malformations. - Jamuar, Saumya S; Lam, Anh-Thu N; Kircher, Martin; D'Gama, Alissa M; Wang, Jian; Barry, Brenda J; Zhang, Xiaochang; Hill, Robert Sean; Partlow, Jennifer N; Rozzo, Aldo; Servattalab, Sarah; Mehta, Bhaven K; et al. (N Engl J Med, 2014)
BACKGROUND: Although there is increasing recognition of the role of somatic mutations in genetic disorders, the prevalence of somatic mutations in neurodevelopmental disease and the optimal techniques to detect somatic mosaicism have not been systematically evaluated. METHODS: Using a customized panel of known and candidate genes associated with brain malformations, we applied targeted high-coverage sequencing (depth, ≥200×) to leukocyte-derived DNA samples from 158 persons with brain malformations, including the double-cortex syndrome (subcortical band heterotopia, 30 persons), polymicrogyria with megalencephaly (20), periventricular nodular heterotopia (61), and pachygyria (47). We validated candidate mutations with the use of Sanger sequencing and, for variants present at unequal read depths, subcloning followed by colony sequencing. RESULTS: Validated, causal mutations were found in 27 persons (17%; range, 10 to 30% for each phenotype). Mutations were somatic in 8 of the 27 (30%), predominantly in persons with the double-cortex syndrome (in whom we found mutations in DCX and LIS1), persons with periventricular nodular heterotopia (FLNA), and persons with pachygyria (TUBB2B). Of the somatic mutations we detected, 5 (63%) were undetectable with the use of traditional Sanger sequencing but were validated through subcloning and subsequent sequencing of the subcloned DNA. We found potentially causal mutations in the candidate genes DYNC1H1, KIF5C, and other kinesin genes in persons with pachygyria. CONCLUSIONS: Targeted sequencing was found to be useful for detecting somatic mutations in patients with brain malformations. High-coverage sequencing panels provide an important complement to whole-exome and whole-genome sequencing in the evaluation of somatic mutations in neuropsychiatric disease. (Funded by the National Institute of Neurological Disorders and Stroke and others.).
Keywords: Cerebral Cortex; Classical Lissencephalies and Subcortical Band Heterotopias; DNA Mutational Analysis; Humans; Lissencephaly; Magnetic Resonance Imaging; Malformations of Cortical Development; Mutation; Periventricular Nodular Heterotopia

Structural variation and missense mutation in SBDS associated with Shwachman-Diamond syndrome. - Carvalho, Claudia M B; Zuccherato, Luciana W; Williams, Christopher L; Neill, Nicholas J; Murdock, David R; Bainbridge, Matthew; Jhangiani, Shalini N; Muzny, Donna M; Gibbs, Richard A; Ip, Wan; Guillerman, Robert Paul; Lupski, James R; et al. (BMC Med Genet, 2014)
BACKGROUND: Shwachman-Diamond syndrome (SDS) is an autosomal recessive ribosomopathy caused mainly by compound heterozygous mutations in SBDS. Structural variation (SV) involving the SBDS locus has been rarely reported in association with the disease. We aimed to determine whether an SV contributed to the pathogenesis of a case lacking biallelic SBDS point mutations. CASE PRESENTATION: Whole exome sequencing was performed in a patient with SDS lacking biallelic SBDS point mutations. Array comparative genomic hybridization and Southern blotting were used to seek SVs across the SBDS locus. Locus-specific polymerase chain reaction (PCR) encompassing flanking intronic sequence was also performed to investigate mutation within the locus. RNA expression and Western blotting were performed to analyze allele and protein expression. We found the child harbored a single missense mutation in SBDS (c.98A > C; p.K33T), inherited from the mother, and an SV in the SBDS locus, inherited from the father. The missense allele and SV segregated in accordance with Mendelian expectations for autosomal recessive SDS. Complementary DNA and western blotting analysis and locus specific PCR support the contention that the SV perturbed SBDS protein expression in the father and child. CONCLUSION: Our findings implicate genomic rearrangements in the pathogenesis of some cases of SDS and support patients lacking biallelic SBDS point mutations be tested for SV within the SBDS locus.
Keywords: Abdomen; Alleles; Bone Marrow Diseases; Cell Line, Transformed; Child, Preschool; Comparative Genomic Hybridization; DNA Mutational Analysis; Exocrine Pancreatic Insufficiency; Female; Gene Order; Humans; Lipomatosis; Mutagenesis, Insertional; Mutation; Mutation, Missense; Pedigree; Proteins; Radiography, Abdominal; Ultrasonography

TCIRG1-associated congenital neutropenia. - Makaryan, Vahagn; Rosenthal, Elisabeth A; Bolyard, Audrey Anna; Kelley, Merideth L; Below, Jennifer E; Bamshad, Michael J; Bofferding, Kathryn M; Smith, Joshua D; Buckingham, Kati; Boxer, Laurence A; Skokowa, Julia; Welte, Karl; et al. (Hum Mutat, 2014)
Severe congenital neutropenia (SCN) is a rare hematopoietic disorder, with estimated incidence of 1 in 200,000 individuals of European descent, many cases of which are inherited in an autosomal dominant pattern. Despite the fact that several causal genes have been identified, the genetic basis for >30% of cases remains unknown. We report a five-generation family segregating a novel single nucleotide variant (SNV) in TCIRG1. There is perfect cosegregation of the SNV with congenital neutropenia in this family; all 11 affected, but none of the unaffected, individuals carry this novel SNV. Western blot analysis show reduced levels of TCIRG1 protein in affected individuals, compared to healthy controls. Two unrelated patients with SCN, identified by independent investigators, are heterozygous for different, rare, highly conserved, coding variants in TCIRG1.
Keywords: DNA Mutational Analysis; Heterozygote; Humans; Mutation; Neutropenia; Pedigree; Vacuolar Proton-Translocating ATPases

Variant association tools for quality control and analysis of large-scale sequence and genotyping array data. - Wang, Gao T; Peng, Bo; Leal, Suzanne M (Am J Hum Genet, 2014)
Currently there is great interest in detecting associations between complex traits and rare variants. In this report, we describe Variant Association Tools (VAT) and the VAT pipeline, which implements best practices for rare-variant association studies. Highlights of VAT include variant-site and call-level quality control (QC), summary statistics, phenotype- and genotype-based sample selection, variant annotation, selection of variants for association analysis, and a collection of rare-variant association methods for analyzing qualitative and quantitative traits. The association testing framework for VAT is regression based, which readily allows for flexible construction of association models with multiple covariates and weighting themes based on allele frequencies or predicted functionality. Additionally, pathway analyses, conditional analyses, and analyses of gene-gene and gene-environment interactions can be performed. VAT is capable of rapidly scanning through data by using multi-process computation, adaptive permutation, and simultaneously conducting association analysis via multiple methods. Results are available in text or graphic file formats and additionally can be output to relational databases for further annotation and filtering. An interface to R language also facilitates user implementation of novel association methods. The VAT's data QC and association-analysis pipeline can be applied to sequence, imputed, and genotyping array, e.g., "exome chip," data, providing a reliable and reproducible computational environment in which to analyze small- to large-scale studies with data from the latest genotyping and sequencing technologies. Application of the VAT pipeline is demonstrated through analysis of data from the 1000 Genomes project.
Keywords: Genetic Association Studies; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Multifactorial Inheritance; Quality Control; Software

Whole exome sequencing identifies de novo mutations in GATA6 associated with congenital diaphragmatic hernia. - Yu, Lan; Bennett, James T; Wynn, Julia; Carvill, Gemma L; Cheung, Yee Him; Shen, Yufeng; Mychaliska, George B; Azarow, Kenneth S; Crombleholme, Timothy M; Chung, Dai H; Potoka, Douglas; Warner, Brad W; et al. (J Med Genet, 2014)
BACKGROUND: Congenital diaphragmatic hernia (CDH) is a common birth defect affecting 1 in 3000 births. It is characterised by herniation of abdominal viscera through an incompletely formed diaphragm. Although chromosomal anomalies and mutations in several genes have been implicated, the cause for most patients is unknown. METHODS: We used whole exome sequencing in two families with CDH and congenital heart disease, and identified mutations in GATA6 in both. RESULTS: In the first family, we identified a de novo missense mutation (c.1366C>T, p.R456C) in a sporadic CDH patient with tetralogy of Fallot. In the second, a nonsense mutation (c.712G>T, p.G238*) was identified in two siblings with CDH and a large ventricular septal defect. The G238* mutation was inherited from their mother, who was clinically affected with congenital absence of the pericardium, patent ductus arteriosus and intestinal malrotation. Deep sequencing of blood and saliva-derived DNA from the mother suggested somatic mosaicism as an explanation for her milder phenotype, with only approximately 15% mutant alleles. To determine the frequency of GATA6 mutations in CDH, we sequenced the gene in 378 patients with CDH. We identified one additional de novo mutation (c.1071delG, p.V358Cfs34*). CONCLUSIONS: Mutations in GATA6 have been previously associated with pancreatic agenesis and congenital heart disease. We conclude that, in addition to the heart and the pancreas, GATA6 is involved in development of two additional organs, the diaphragm and the pericardium. In addition, we have shown that de novo mutations can contribute to the development of CDH, a common birth defect.
Keywords: Amino Acid Sequence; DNA Mutational Analysis; Exome; Female; GATA6 Transcription Factor; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Male; Molecular Sequence Data; Mutation; Sequence Alignment; Sequence Analysis, DNA

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Muzny, Donna; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing reveals GPIHBP1 mutations in infantile colitis with severe hypertriglyceridemia. - Gonzaga-Jauregui, Claudia; Mir, Sabina; Penney, Samantha; Jhangiani, Shalini; Midgen, Craig; Finegold, Milton; Muzny, Donna M; Wang, Min; Bacino, Carlos A; Gibbs, Richard A; Lupski, James R; Kellermayer, Richard; et al. (J Pediatr Gastroenterol Nutr, 2014)
Severe congenital hypertriglyceridemia (HTG) is a rare disorder caused by mutations in genes affecting lipoprotein lipase (LPL) activity. Here we report a 5-week-old Hispanic girl with severe HTG (12,031 mg/dL, normal limit 150 mg/dL) who presented with the unusual combination of lower gastrointestinal bleeding and milky plasma. Initial colonoscopy was consistent with colitis, which resolved with reduction of triglycerides. After negative sequencing of the LPL gene, whole-exome sequencing revealed novel compound heterozygous mutations in GPIHBP1. Our study broadens the phenotype of GPIHBP1-associated HTG, reinforces the effectiveness of whole-exome sequencing in Mendelian diagnoses, and implicates triglycerides in gastrointestinal mucosal injury.
Keywords: Colitis; DNA Mutational Analysis; Exome; Female; Humans; Hypertriglyceridemia; Infant; Receptors, Lipoprotein

ADCK4 mutations promote steroid-resistant nephrotic syndrome through CoQ10 biosynthesis disruption. - Ashraf, Shazia; Gee, Heon Yung; Woerner, Stephanie; Xie, Letian X; Vega-Warner, Virginia; Lovric, Svjetlana; Fang, Humphrey; Song, Xuewen; Cattran, Daniel C; Avila-Casado, Carmen; Paterson, Andrew D; Nitschké, Patrick; et al. (J Clin Invest, 2013)
Identification of single-gene causes of steroid-resistant nephrotic syndrome (SRNS) has furthered the understanding of the pathogenesis of this disease. Here, using a combination of homozygosity mapping and whole human exome resequencing, we identified mutations in the aarF domain containing kinase 4 (ADCK4) gene in 15 individuals with SRNS from 8 unrelated families. ADCK4 was highly similar to ADCK3, which has been shown to participate in coenzyme Q10 (CoQ10) biosynthesis. Mutations in ADCK4 resulted in reduced CoQ10 levels and reduced mitochondrial respiratory enzyme activity in cells isolated from individuals with SRNS and transformed lymphoblasts. Knockdown of adck4 in zebrafish and Drosophila recapitulated nephrotic syndrome-associated phenotypes. Furthermore, ADCK4 was expressed in glomerular podocytes and partially localized to podocyte mitochondria and foot processes in rat kidneys and cultured human podocytes. In human podocytes, ADCK4 interacted with members of the CoQ10 biosynthesis pathway, including COQ6, which has been linked with SRNS and COQ7. Knockdown of ADCK4 in podocytes resulted in decreased migration, which was reversed by CoQ10 addition. Interestingly, a patient with SRNS with a homozygous ADCK4 frameshift mutation had partial remission following CoQ10 treatment. These data indicate that individuals with SRNS with mutations in ADCK4 or other genes that participate in CoQ10 biosynthesis may be treatable with CoQ10.
Keywords: Adolescent; Adrenal Cortex Hormones; Amino Acid Sequence; Animals; Cells, Cultured; Child; Consanguinity; Conserved Sequence; Disease Models, Animal; DNA Mutational Analysis; Drosophila Proteins; Drug Resistance; Exome; Fibroblasts; Gene Knockdown Techniques; Humans; Mitochondria; Molecular Sequence Data; Mutation; Nephrotic Syndrome; Podocytes; Protein Kinases; Rats; Sequence Alignment; Sequence Homology, Amino Acid; Ubiquinone; Young Adult; Zebrafish; Zebrafish Proteins

ARMC4 mutations cause primary ciliary dyskinesia with randomization of left/right body asymmetry. - Hjeij, Rim; Lindstrand, Anna; Francis, Richard; Zariwala, Maimoona A; Liu, Xiaoqin; Li, You; Damerla, Rama; Dougherty, Gerard W; Abouhamed, Marouan; Olbrich, Heike; Loges, Niki T; Pennekamp, Petra; et al. (Am J Hum Genet, 2013)
The motive forces for ciliary movement are generated by large multiprotein complexes referred to as outer dynein arms (ODAs), which are preassembled in the cytoplasm prior to transport to the ciliary axonemal compartment. In humans, defects in structural components, docking complexes, or cytoplasmic assembly factors can cause primary ciliary dyskinesia (PCD), a disorder characterized by chronic airway disease and defects in laterality. By using combined high resolution copy-number variant and mutation analysis, we identified ARMC4 mutations in twelve PCD individuals whose cells showed reduced numbers of ODAs and severely impaired ciliary beating. Transient suppression in zebrafish and analysis of an ENU mouse mutant confirmed in both model organisms that ARMC4 is critical for left-right patterning. We demonstrate that ARMC4 is an axonemal protein that is necessary for proper targeting and anchoring of ODAs.
Keywords: Amino Acid Sequence; Animals; Armadillo Domain Proteins; Axoneme; Body Patterning; Cilia; DNA Copy Number Variations; DNA Mutational Analysis; Dyneins; Gene Expression Regulation; Humans; Kartagener Syndrome; Mice; Microtubule-Associated Proteins; Molecular Sequence Data; Mutation; Respiratory System; Zebrafish

De novo mutations in histone-modifying genes in congenital heart disease. - Zaidi, Samir; Choi, Murim; Wakimoto, Hiroko; Ma, Lijiang; Jiang, Jianming; Overton, John D; Romano-Adesman, Angela; Bjornson, Robert D; Breitbart, Roger E; Brown, Kerry K; Carriero, Nicholas J; Cheung, Yee Him; et al. (Nature, 2013)
Congenital heart disease (CHD) is the most frequent birth defect, affecting 0.8% of live births. Many cases occur sporadically and impair reproductive fitness, suggesting a role for de novo mutations. Here we compare the incidence of de novo mutations in 362 severe CHD cases and 264 controls by analysing exome sequencing of parent-offspring trios. CHD cases show a significant excess of protein-altering de novo mutations in genes expressed in the developing heart, with an odds ratio of 7.5 for damaging (premature termination, frameshift, splice site) mutations. Similar odds ratios are seen across the main classes of severe CHD. We find a marked excess of de novo mutations in genes involved in the production, removal or reading of histone 3 lysine 4 (H3K4) methylation, or ubiquitination of H2BK120, which is required for H3K4 methylation. There are also two de novo mutations in SMAD2, which regulates H3K27 methylation in the embryonic left-right organizer. The combination of both activating (H3K4 methylation) and inactivating (H3K27 methylation) chromatin marks characterizes 'poised' promoters and enhancers, which regulate expression of key developmental genes. These findings implicate de novo point mutations in several hundreds of genes that collectively contribute to approximately 10% of severe CHD.
Keywords: Adult; Case-Control Studies; Child; Chromatin; DNA Mutational Analysis; Enhancer Elements, Genetic; Exome; Female; Genes, Developmental; Heart Diseases; Histones; Humans; Lysine; Male; Methylation; Mutation; Odds Ratio; Promoter Regions, Genetic

Evidence for replicative mechanism in a CHD7 rearrangement in a patient with CHARGE syndrome. - Vatta, Matteo; Niu, Zhiyv; Lupski, James R; Putnam, Philip; Spoonamore, Katherine G; Fang, Ping; Eng, Christine M; Willis, Alecia S (Am J Med Genet A, 2013)
Haploinsufficiency of CHD7 (OMIM# 608892) is known to cause CHARGE syndrome (OMIM# 214800). Molecular testing supports a definitive diagnosis in approximately 65-70% of cases. Most CHD7 mutations arise de novo, and no mutations affecting exon-7 have been reported to date. We report on an 8-year-old girl diagnosed with CHARGE syndrome that was referred to our laboratory for comprehensive CHD7 gene screening. Genomic DNA from the subject with a suspected diagnosis of CHARGE was isolated from peripheral blood lymphocytes and comprehensive Sanger sequencing, along with deletion/duplication analysis of the CHD7 gene using multiplex ligation-dependent probe amplification (MLPA), was performed. MLPA analysis identified a reduced single probe signal for exon-7 of the CHD7 gene consistent with potential heterozygous deletion. Long-range PCR breakpoint analysis identified a complex genomic rearrangement (CGR) leading to the deletion of exon-7 and breakpoints consistent with a replicative mechanism such as fork stalling and template switching (FoSTeS) or microhomology-mediated break-induced replication (MMBIR). Taken together this represents the first evidence for a CHD7 intragenic CGR in a patient with CHARGE syndrome leading to what appears to be also the first report of a mutation specifically disrupting exon-7. Although likely rare, CGR may represent an overlooked mechanism in subjects with CHARGE syndrome that can be missed by current sequencing and dosage assays.
Keywords: Abnormalities, Multiple; CHARGE Syndrome; Child; DNA Helicases; DNA Replication; DNA-Binding Proteins; Exons; Female; Gene Deletion; Haploinsufficiency; Humans; Mutation

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Muzny, Donna M; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Mutations in DSTYK and dominant urinary tract malformations. - Sanna-Cherchi, Simone; Sampogna, Rosemary V; Papeta, Natalia; Burgess, Katelyn E; Nees, Shannon N; Perry, Brittany J; Choi, Murim; Bodria, Monica; Liu, Yan; Weng, Patricia L; Lozanovski, Vladimir J; Verbitsky, Miguel; et al. (N Engl J Med, 2013)
BACKGROUND: Congenital abnormalities of the kidney and the urinary tract are the most common cause of pediatric kidney failure. These disorders are highly heterogeneous, and the etiologic factors are poorly understood. METHODS: We performed genomewide linkage analysis and whole-exome sequencing in a family with an autosomal dominant form of congenital abnormalities of the kidney or urinary tract (seven affected family members). We also performed a sequence analysis in 311 unrelated patients, as well as histologic and functional studies. RESULTS: Linkage analysis identified five regions of the genome that were shared among all affected family members. Exome sequencing identified a single, rare, deleterious variant within these linkage intervals, a heterozygous splice-site mutation in the dual serine-threonine and tyrosine protein kinase gene (DSTYK). This variant, which resulted in aberrant splicing of messenger RNA, was present in all affected family members. Additional, independent DSTYK mutations, including nonsense and splice-site mutations, were detected in 7 of 311 unrelated patients. DSTYK is highly expressed in the maturing epithelia of all major organs, localizing to cell membranes. Knockdown in zebrafish resulted in developmental defects in multiple organs, which suggested loss of fibroblast growth factor (FGF) signaling. Consistent with this finding is the observation that DSTYK colocalizes with FGF receptors in the ureteric bud and metanephric mesenchyme. DSTYK knockdown in human embryonic kidney cells inhibited FGF-stimulated phosphorylation of extracellular-signal-regulated kinase (ERK), the principal signal downstream of receptor tyrosine kinases. CONCLUSIONS: We detected independent DSTYK mutations in 2.3% of patients with congenital abnormalities of the kidney or urinary tract, a finding that suggests that DSTYK is a major determinant of human urinary tract development, downstream of FGF signaling. (Funded by the National Institutes of Health and others.).
Keywords: Adult; Animals; Base Sequence; Child; Exome; Female; Gene Knockdown Techniques; Genetic Linkage; Genome-Wide Association Study; Heterozygote; Humans; Infant; Kidney; Male; Mice; Molecular Sequence Data; Mutation; Pedigree; Receptor-Interacting Protein Serine-Threonine Kinases; RNA, Small Interfering; Urinary Tract; Urogenital Abnormalities; Young Adult

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases

Perrault syndrome is caused by recessive mutations in CLPP, encoding a mitochondrial ATP-dependent chambered protease. - Jenkinson, Emma M; Rehman, Atteeq U; Walsh, Tom; Clayton-Smith, Jill; Lee, Kwanghyuk; Morell, Robert J; Drummond, Meghan C; Khan, Shaheen N; Naeem, Muhammad Asif; Rauf, Bushra; Billington, Neil; Schultz, Julie M; et al. (Am J Hum Genet, 2013)
Perrault syndrome is a genetically and clinically heterogeneous autosomal-recessive condition characterized by sensorineural hearing loss and ovarian failure. By a combination of linkage analysis, homozygosity mapping, and exome sequencing in three families, we identified mutations in CLPP as the likely cause of this phenotype. In each family, affected individuals were homozygous for a different pathogenic CLPP allele: c.433A>C (p.Thr145Pro), c.440G>C (p.Cys147Ser), or an experimentally demonstrated splice-donor-site mutation, c.270+4A>G. CLPP, a component of a mitochondrial ATP-dependent proteolytic complex, is a highly conserved endopeptidase encoded by CLPP and forms an element of the evolutionarily ancient mitochondrial unfolded-protein response (UPR(mt)) stress signaling pathway. Crystal-structure modeling suggests that both substitutions would alter the structure of the CLPP barrel chamber that captures unfolded proteins and exposes them to proteolysis. Together with the previous identification of mutations in HARS2, encoding mitochondrial histidyl-tRNA synthetase, mutations in CLPP expose dysfunction of mitochondrial protein homeostasis as a cause of Perrault syndrome.
Keywords: Adenosine Triphosphate; Adolescent; Adult; ATP-Dependent Proteases; Endopeptidase Clp; Exome; Female; Genes, Recessive; Gonadal Dysgenesis, 46,XX; Hearing Loss, Sensorineural; Homozygote; Humans; In Situ Hybridization; Male; Mitochondria; Mutation; Pedigree; Phenotype; Young Adult

Somatic and germline CACNA1D calcium channel mutations in aldosterone-producing adenomas and primary aldosteronism. - Scholl, Ute I; Goh, Gerald; Stölting, Gabriel; de Oliveira, Regina Campos; Choi, Murim; Overton, John D; Fonseca, Annabelle L; Korah, Reju; Starker, Lee F; Kunstman, John W; Prasad, Manju L; Hartung, Erum A; et al. (Nat Genet, 2013)
Adrenal aldosterone-producing adenomas (APAs) constitutively produce the salt-retaining hormone aldosterone and are a common cause of severe hypertension. Recurrent mutations in the potassium channel gene KCNJ5 that result in cell depolarization and Ca(2+) influx cause ∼40% of these tumors. We identified 5 somatic mutations (4 altering Gly403 and 1 altering Ile770) in CACNA1D, encoding a voltage-gated calcium channel, among 43 APAs without mutated KCNJ5. The altered residues lie in the S6 segments that line the channel pore. Both alterations result in channel activation at less depolarized potentials; Gly403 alterations also impair channel inactivation. These effects are inferred to cause increased Ca(2+) influx, which is a sufficient stimulus for aldosterone production and cell proliferation in adrenal glomerulosa. We also identified de novo germline mutations at identical positions in two children with a previously undescribed syndrome featuring primary aldosteronism and neuromuscular abnormalities. These findings implicate gain-of-function Ca(2+) channel mutations in APAs and primary aldosteronism.
Keywords: Adrenal Cortex Neoplasms; Adrenocortical Adenoma; Aldosterone; Amino Acid Sequence; Calcium Channels, L-Type; Cell Line; Child; Child, Preschool; Female; Germ-Line Mutation; Humans; Hyperaldosteronism; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Sequence Alignment

TM4SF20 ancestral deletion and susceptibility to a pediatric disorder of early language delay and cerebral white matter hyperintensities. - Wiszniewski, Wojciech; Hunter, Jill V; Hanchard, Neil A; Willer, Jason R; Shaw, Chad; Tian, Qi; Illner, Anna; Wang, Xueqing; Cheung, Sau W; Patel, Ankita; Campbell, Ian M; Gelowani, Violet; et al. (Am J Hum Genet, 2013)
White matter hyperintensities (WMHs) of the brain are important markers of aging and small-vessel disease. WMHs are rare in healthy children and, when observed, often occur with comorbid neuroinflammatory or vasculitic processes. Here, we describe a complex 4 kb deletion in 2q36.3 that segregates with early childhood communication disorders and WMH in 15 unrelated families predominantly from Southeast Asia. The premature brain aging phenotype with punctate and multifocal WMHs was observed in ~70% of young carrier parents who underwent brain MRI. The complex deletion removes the penultimate exon 3 of TM4SF20, a gene encoding a transmembrane protein of unknown function. Minigene analysis showed that the resultant net loss of an exon introduces a premature stop codon, which, in turn, leads to the generation of a stable protein that fails to target to the plasma membrane and accumulates in the cytoplasm. Finally, we report this deletion to be enriched in individuals of Vietnamese Kinh descent, with an allele frequency of about 1%, embedded in an ancestral haplotype. Our data point to a constellation of early language delay and WMH phenotypes, driven by a likely toxic mechanism of TM4SF20 truncation, and highlight the importance of understanding and managing population-specific low-frequency pathogenic alleles.
Keywords: Age of Onset; Aging, Premature; Asian Continental Ancestry Group; Base Sequence; Brain; Child; Child, Preschool; Chromosomes, Human, Pair 2; Exons; Female; Genetic Predisposition to Disease; Humans; Language Development Disorders; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Pedigree; Sequence Analysis, DNA; Sequence Deletion; Tetraspanins

Whole-exome sequencing reveals somatic mutations in HRAS and KRAS, which cause nevus sebaceus. - Levinsohn, Jonathan L; Tian, Li C; Boyden, Lynn M; McNiff, Jennifer M; Narayan, Deepak; Loring, Erin S; Yun, Duri; Sugarman, Jeffrey L; Overton, John D; Mane, Shrikant M; Lifton, Richard P; Paller, Amy S; et al. (J Invest Dermatol, 2013)
Keywords: Adolescent; Adult; Amino Acid Sequence; Biopsy; Child; Child, Preschool; Cohort Studies; Epidermis; Exome; Humans; Infant; Middle Aged; Molecular Sequence Data; Mutation; Nevus, Sebaceous of Jadassohn; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA; Young Adult

A fast and noise-resilient approach to detect rare-variant associations with deep sequencing data for complex disorders. - Cheung, Yee Him; Wang, Gao; Leal, Suzanne M; Wang, Shuang (Genet Epidemiol, 2012)
Next generation sequencing technology has enabled the paradigm shift in genetic association studies from the common disease/common variant to common disease/rare-variant hypothesis. Analyzing individual rare variants is known to be underpowered; therefore association methods have been developed that aggregate variants across a genetic region, which for exome sequencing is usually a gene. The foreseeable widespread use of whole genome sequencing poses new challenges in statistical analysis. It calls for new rare-variant association methods that are statistically powerful, robust against high levels of noise due to inclusion of noncausal variants, and yet computationally efficient. We propose a simple and powerful statistic that combines the disease-associated P-values of individual variants using a weight that is the inverse of the expected standard deviation of the allele frequencies under the null. This approach, dubbed as Sigma-P method, is extremely robust to the inclusion of a high proportion of noncausal variants and is also powerful when both detrimental and protective variants are present within a genetic region. The performance of the Sigma-P method was tested using simulated data based on realistic population demographic and disease models and its power was compared to several previously published methods. The results demonstrate that this method generally outperforms other rare-variant association methods over a wide range of models. Additionally, sequence data on the ANGPTL family of genes from the Dallas Heart Study were tested for associations with nine metabolic traits and both known and novel putative associations were uncovered using the Sigma-P method.
Keywords: Angiopoietin-like 4 Protein; Angiopoietin-like Proteins; Angiopoietins; Case-Control Studies; Data Interpretation, Statistical; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; High-Throughput Nucleotide Sequencing; Humans; Metabolism; Sequence Analysis, DNA; Texas; Triglycerides

Next generation analytic tools for large scale genetic epidemiology studies of complex diseases. - Mechanic, Leah E; Chen, Huann-Sheng; Amos, Christopher I; Chatterjee, Nilanjan; Cox, Nancy J; Divi, Rao L; Fan, Ruzong; Harris, Emily L; Jacobs, Kevin; Kraft, Peter; Leal, Suzanne M; McAllister, Kimberly; et al. (Genet Epidemiol, 2012)
Over the past several years, genome-wide association studies (GWAS) have succeeded in identifying hundreds of genetic markers associated with common diseases. However, most of these markers confer relatively small increments of risk and explain only a small proportion of familial clustering. To identify obstacles to future progress in genetic epidemiology research and provide recommendations to NIH for overcoming these barriers, the National Cancer Institute sponsored a workshop entitled "Next Generation Analytic Tools for Large-Scale Genetic Epidemiology Studies of Complex Diseases" on September 15-16, 2010. The goal of the workshop was to facilitate discussions on (1) statistical strategies and methods to efficiently identify genetic and environmental factors contributing to the risk of complex disease; and (2) how to develop, apply, and evaluate these strategies for the design, analysis, and interpretation of large-scale complex disease association studies in order to guide NIH in setting the future agenda in this area of research. The workshop was organized as a series of short presentations covering scientific (gene-gene and gene-environment interaction, complex phenotypes, and rare variants and next generation sequencing) and methodological (simulation modeling and computational resources and data management) topic areas. Specific needs to advance the field were identified during each session and are summarized.
Keywords: Data Mining; Gene-Environment Interaction; Genetic Variation; Genome-Wide Association Study; Humans; Molecular Epidemiology; National Institutes of Health (U.S.); Neoplasms; Phenotype; United States

SimRare: a program to generate and analyze sequence-based data for association studies of quantitative and qualitative traits. - Li, Biao; Wang, Gao; Leal, Suzanne M (Bioinformatics, 2012)
MOTIVATION: Currently, there is great interest in detecting complex trait rare variant associations using next-generation sequence data. On a monthly basis, new rare variant association methods are published. It is difficult to evaluate these methods because there is no standard to generate data and often comparisons are biased. In order to fairly compare rare variant association methods, it is necessary to generate data using realistic population demographic and phenotypic models. RESULT: SimRare is an interactive program that integrates generation of rare variant genotype/phenotype data and evaluation of association methods using a unified platform. Variant data are generated for gene regions using forward-time simulation that incorporates realistic population demographic and evolutionary scenarios. Phenotype data can be obtained for both case-control and quantitative traits. SimRare has a user-friendly interface that allows for easy entry of genetic and phenotypic parameters. Novel rare variant association methods implemented in R can also be imported into SimRare, to evaluate their performance and compare results, e.g. power and Type I error, with other currently available methods both numerically and graphically.
Keywords: Genetic Association Studies; Genetic Variation; Humans; Phenotype; Quantitative Trait, Heritable; Software